Technoeconomic and life-cycle assessment of multi-product and single-product lignocellulosic biorefineries - Seyedamirreza Babaei; Lauren Philips; Juhee Lee; Eun Joong Oh; Ye Huang; Adriana C. Neves; Yinglei Han; Jikai Zhao (Bioresource Technology, 2026)

Temporal and spatial transferability in telemetry-based dynamic species distribution models: The effects of algorithms and pseudo-absence techniques - Joshua C Wilson; Philip N Trathan; Hugh J Venables; Horst Bornemann; Rochelle Constantine; Daniel P Costa; Luciano Dalla Rosa; Louise Emmerson; Ari S Friedlaender; Michael E Goebel; Simon Goldsworthy; Mark A Hindell; et al. (Ecological Modelling, 2026)

A juvenile specimen of Gorgosaurus libratus from the Wapiti Formation of northeastern British Columbia, Canada sheds light on the palaeoecology of Upper Campanian tyrannosaurids - Colton C. Coppock; Hans C.E. Larsson; Philip J. Currie (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Trophic ecology and niche segregation among coexisting Macrourus species at South Georgia, Southern Ocean - José Abreu; Richard A. Phillips; Philip R. Hollyman; José P. Queirós; Paco Bustamante; Mark Belchier; Martin A. Collins; José C. Xavier (Deep Sea Research Part I: Oceanographic Research Papers, 2026)

Spatial dynamics of three estuarine predatory fishes in a subtropical estuary - Paco Fontaine; Christine C. Jensen; Philip Matich; Jay R. Rooker; R. J. David Wells (Marine Biology, 2026)
Understanding movement and habitat use patterns of co-occurring predatory fishes is crucial for effective conservation and management of estuarine ecosystems, where dynamic seasonal shifts and species interactions play crucial roles in shaping community structure. Using acoustic telemetry and network analysis, we compared the movements of alligator gar ( Atractosteus spatula , n = 13), bull sharks ( Carcharhinus leucas , n = 12), and Atlantic stingrays ( Hypanus sabinus , n = 11) within and outside the boundaries of a large estuary (Galveston Bay Complex, GBC) in the northwestern Gulf of Mexico. Habitat use varied seasonally for all species, though these patterns have been affected by tagging locations and receiver deployment. Alligator gar were detected year-round in the GBC, with seasonal variation likely driven by environmental conditions and prey availability. Bull sharks displayed seasonal migrations, with increased estuarine use during warmer months and a notable shift out of the GBC to southern bays in the winter. Atlantic stingrays exhibited restricted movement within the GBC during the summer, with few detections in other seasons potentially attributable to receiver coverage, tag retention and predation. Interspecific overlap in habitat use was highest between alligator gar and bull sharks, and lower with Atlantic stingrays. Intraspecific overlap was observed across all three species but was most extensive for bull sharks, suggesting that increased overlap may intensify competition, possibly driving size-based habitat partitioning. Our findings highlight the importance of habitat connectivity and seasonal dynamics for co-occurring predatory fishes within an estuary.

Multiple Strains of Trichomonas gallinae are Widespread in Reservoir Hosts and Environmental Resources in UK Farmland - Rebecca C. Thomas; Jenny C. Dunn; Helen Hipperson; Antony J. Morris; Philip V. Grice; Keith C. Hamer; Simon J. Goodman (Molecular Ecology, 2026)
Understanding transmission routes of parasites and pathogens is critical for the development of control measures and mitigation of impacts on host populations. Trichomonas gallinae is a widespread parasite in columbids worldwide, and has emerged as a lethal disease in passerines, particularly finches. The postulated transmission route from columbids to passerines via spillover at shared resources has not yet been empirically tested. Here, we screen 363 birds (261 columbids and 102 non‐columbids) in the UK and France for the presence and strain identity of T. gallinae . To quantify potential environmental transmission, we also screened 51 food and water resources common in farmland, at 12 sites over a 2‐year period. We isolated T. gallinae parasites from 79% of columbids, 36% of non‐columbids, and 39% of environmental resources. Prevalence of the Type A strain was more than double in birds sampled at fed sites compared to those at unfed sites. Strain composition was mirrored in columbids, passerines, and shared food and water resources, providing compelling evidence that T. gallinae , especially the Type A strain, is transmitted via these shared resources. T. gallinae was isolated from high density feeding resources (where supplementary food was provided) nearly three times as often as low density resources (natural areas of seed‐providing vegetation), meaning that careful management of supplementary resources has the potential to reduce T. gallinae prevalence in wild bird populations. Further work needs to test practical means of achieving this, but ensuring any supplementary feeding is provided at low density is likely to be critical to reducing parasite transmission.

Remote Spectral Detection of Canopy Functional Dimensions Varying Within and Across Forest Types - Fengqi Wu; Shuwen Liu; Constantin M. Zohner; Philip A. Townsend; Thomas W. Crowther; Josep Peñuelas; Daryl Yang; Nan Yang; Tingting Dong; Weiying Xu; Zhihui Wang; Xiaojuan Liu; et al. (Ecology Letters, 2026)
Global trait axes reveal overarching dimensions of plant functional variation. However, how these dimensions are spatially organized within and across forest types remains unclear. We combined drone‐based full‐range imaging spectroscopy with crown‐level measurements of 16 physiological, morphological and biochemical traits across temperate, subtropical and tropical forests in China to enable spatially‐explicit trait mapping. Through site‐training scenario, leaf‐to‐canopy scaling and spectral‐domain modelling tests, we find that reliable canopy trait retrieval depends not only on trait and spectral coverage, but also on preserving trait‐spectral relationships across sites and scales. Spectral predictions recovered observed multivariate covariation, summarizing crown variation into a leaf‐economics dimension and two additional biochemical dimensions related to hydro‐thermal regulation and defence/metabolism. Mapping these dimensions revealed distinct community‐level trait organization alongside substantial species‐ and crown‐level variation within forests. These findings link remotely sensed trait retrieval to environmental filtering and plant functional differentiation, providing a scalable framework for monitoring forest functional diversity.

New genomic regions in dry bean (Phaseolus vulgaris L.) associated with stem diameter, plant height, and other plant architecture traits - Oscar Rodríguez; Jayanta Roy; Philip E. McClean; Didier Murillo; Kristin Simons; Nusrat Khan; Jose C. Figueroa-Cerna; Juan M. Osorno (Euphytica, 2026)
Growth habit is one of the most important domestication traits in dry bean ( Phaseolus vulgaris L.). In the U.S. for example, Type II indeterminate upright plant varieties have allowed farmers to switch from historic two-pass harvest to one-pass direct harvest. Previous work suggested a stem diameter of 5.6 mm as threshold to select Type II architecture genotypes suitable for direct combining. This study aimed to validate the correlation between stem diameter and other agronomic traits using lines comprising various market classes from a public breeding program. It also assesses if stem diameter could be used to select genotypes that combine high seed yield and upright architecture. GWAS was also used to identify genomic regions related to plant height and stem diameter. Mean stem diameter among breeding lines was 7.7 mm, higher than the proposed threshold. Stem diameter showed no significant G × E interactions, with the highest broad-sense heritabilities observed for regular-darkening pinto (pinto) and slow darkening (SD) pinto. Plant height was the most relevant trait for seed yield variation in black, great northern, and navy beans. In contrast, both plant height and stem diameter are required to explain part of seed yield variability and selecting upright plants for pinto, red/pink, and SD-pinto. GWAS revealed significant regions located on chromosomes Pv03, Pv07, and Pv11 depending on trait and race used. A region near 40.7 Mb on Pv07 was associated with both plant height and stem diameter, suggesting further studies on indeterminate upright dry bean plant architecture should focus on this region.

Multidimensional Experimental Characterization of Lumbar Spinal Deformity - Emma C. Coltoff; Alexander Hooke; Asghar Rezaei; Philip J. Brown (Annals of Biomedical Engineering, 2026)
Purpose Spinal deformities and motions of the spinal joints are rarely confined to a single anatomical plane. Yet diagnosis of such deformities and characterizations of their biomechanical behavior under load are often limited to two-dimensional methods of analysis. This study presented a testing methodology and visualization method to characterize the biomechanical responses of the intact and deformed lumbar spine under combined loading in multiple dimensions simultaneously. Methods Two L1–L5 lumbar spinal specimens underwent loading by five custom trajectories (rays, clockwise and counterclockwise petals and circles), each intended to perturb different responses of the spinal joints within the same range of motion. Results Multidimensional loading highlighted differing regions of spinal stiffness between intact and deformed specimens that do not fall along the sagittal and coronal planes. The rays trajectory crucially captured the non-linear, hysteretic behavior of planar loading and unloading patterns of the spine but also suggested a potentially misleading isotropy of spinal behavior relative to the craniocaudal axis. The petals and circles trajectories appropriately capture the anisotropy of spinal bending between the sagittal and coronal planes. The clockwise and counterclockwise versions of these trajectories emphasize how deformity impacts this anisotropy in both the neutral and elastic zones. Conclusion The insights from these trajectories highlight nuances of biomechanical behavior of the lumbar spine and disruptions due to deformity that would not be captured by pure moment loading alone. Introducing multidimensional characterization of biomechanical differences holds promise to supplement future clinical considerations for treatment of spinal deformity.

New water histories of Schistosomiasis in China: an introduction - Philip C. Brown; Qun Che; Nicholas B. Breyfogle (Water History, 2026)

Nutrient Enrichment Increases Grassland Biomass Sensitivity to Interannual Precipitation Variation - Ingrid J. Slette; Eric W. Seabloom; Carlos Alberto Arnillas; Jonathan D. Bakker; Dana Blumenthal; Jane A. Catford; Scott L. Collins; Nico Eisenhauer; Philip A. Fay; Magda Garbowski; Sylvia Haider; W. Stanley Harpole; et al. (Global Change Biology, 2026)
Primary production underpins much of ecosystem functioning and is often limited by nutrient and water availability. Ongoing global increases in nutrient inputs and interannual precipitation variability are thus likely to impact primary production, with unclear consequences for interannual variability in plant biomass. We used data from 35 grasslands in the Nutrient Network coordinated fertilization experiment to test if nutrient addition alters the response of plant biomass to year‐to‐year variation in growing season precipitation, and whether the effects of nutrient addition vary with factors such as site aridity or plant community composition. Nutrient addition increased biomass (by an average of 46% across sites), rain‐use efficiency (by 48%), and the sensitivity of biomass to interannual variation in precipitation (i.e., larger increase in biomass in wet years; by 13%), but did not change the strength of the interannual precipitation‐biomass correlation. Both sensitivity and correlation strength were higher in more arid sites, regardless of nutrient addition. These results suggest that grassland ecosystem functioning may become more variable from year to year as nutrient enrichment increases biomass sensitivity to precipitation and precipitation becomes more variable.

Variation in cocaine responses across genetically diverse mouse strains - Malia Pollock; AbdulRahman Abbas; Hien M. Bui; Jay-Ho Chung; Yanchao Dai; Jack DiCola; Levi Goldberg; Savanna Hale; Carter Joyce; Emily Rubio; M Schoales; Owen Snyder-Smith; et al. (Psychopharmacology, 2026)

Micronutrients and omega-3 PUFAs to promote healthy ageing: informing a physiology-based complementation strategy - Mette M. Berger; Renée Blaauw; Patrizia D’Amelio; Nicole Ehrhart; Adrian F. Gombart; Leah Gramlich; Reto W. Kressig; Philip C. Calder (GeroScience, 2026)
Global population ageing is increasing the burden of chronic disease, functional decline, and loss of independence. For most organs, decline in function starts during the 5th decade of life. Micronutrient (MN) insufficiencies/deficiencies are common and may accelerate biological ageing. MNs are required to support multiple physiologic processes, including mitochondrial homeostasis. Age-related declines in organ function are tightly linked to mitochondrial dysfunction, oxidative stress, inflammageing, and immunosenescence. Selected MNs (vitamins B, C, D, E, iron, selenium, zinc) are critical cofactors for mitochondrial function, antioxidant defence, immunity, and resolution of inflammation. Inadequate MN intakes require specific repletion strategies beyond diet for correction. Low intake, (patho)physiological changes, and common medications jointly contribute to compromised MN status. Emerging trials suggest that correcting MN deficiency may restore mitochondrial function and thereby promote healthy ageing. Optimizing intake over the lifespan represents another means to support healthy ageing. Nevertheless, MNs do not work individually but as a web, and may behave differently in different individuals. Further, low status of the n-3 polyunsaturated fatty acids eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) is common in older adults, which favours inflammation and functional decline. EPA+DHA work in combination with MNs on inflammation containment. Routine risk assessment, selected biomarker measurement from midlife onwards, and well-designed trials are needed to complement an insufficient status. MN and EPA+DHA optimization should be integral to healthy ageing strategies.

A sustainable seaweed win-win: dietary fortification with Irish Wakame (Alaria esculenta) enhances Atlantic salmon (Salmo salar) muscle growth and modulates gene expression - Courtney E. Gorman; Lewis D. Taylor; Fintan Egan; Francisco Javier Alarcón-López; Philip McGinnity; C. Darrin Hulsey (Frontiers in Marine Science, 2026)
Seaweeds are increasingly being incorporated into animal diets to address the challenge of intensifying food production while minimizing ecological impacts. Although seaweeds represent promising natural resources for developing economically and environmentally sustainable feeds, especially in aquaculture, the consequences of ingesting seaweed for the animals themselves are often unclear. Therefore, this study examined how the inclusion of the brown seaweed Alaria esculenta affects body condition, skeletal muscle growth, and gene expression across three tissues in Atlantic salmon ( Salmo salar ). Dietary inclusion of A. esculenta was found to significantly enhance juvenile S. salar body condition. Then, using a novel application of contrast-enhanced soft tissue computed tomography, it was demonstrated that seaweed positively influenced the muscle cross-sectional area of the commercially valuable filet muscle. Transcriptomic analysis further revealed that dietary seaweed altered the expression of hundreds of genes, including several involved in muscle and immune function across the three tissues. These integrative findings indicate that A. esculenta enhances salmon muscle growth and influences the molecular underpinnings of fish health, collectively supporting the utility of seaweed as a sustainable win-win functional food.

Harnessing quantum technology in food and nutrition sciences: a scoping review of innovations, challenges, and future directions - Karim Karbin; Vyom Patel; Mojtaba Shafiee; Adam Dominic George Baxter-Jones; Marta C. Erlandson; Ginny Lane; Philip D. Chilibeck; Steven Rayan; Hassan Vatanparast (Critical Reviews in Food Science and Nutrition, 2026)

Recent advances and opportunities for multi-robot systems in oceanography - Jessica C. Garwood; Xi Yu; Geoffrey A. Hollinger; Philip B. Lundrigan; Atsuhiro Muto; Nicholas R. Rypkema; Yu She (Frontiers in Marine Science, 2026)
Autonomous multi-robot missions are revolutionizing oceanographic data collection by increasing spatial coverage, mission durations, and allowing safe access to remote and dangerous environments at a fraction of the cost of ship-based missions. While terrestrial and aerial field robotics offer several approaches for multi-robot coordination, ocean applications present unique challenges — including navigation in a time-evolving, unknown, 3D fluid environment with significant drag, limited communications, and long-duration missions without opportunities to recharge — which require tailored solutions. To promote novel solutions arising from collaborations between field robotics and oceanography, we detail recent advances in terrestrial and aerial multi-robot coordination which we contextualize in relation to oceanographic needs, distinguishing applications at the ocean surface, at depth, and between the two domains. We conclude by highlighting future research opportunities, focusing on vehicle technology, underwater networking, and de-risking. We also emphasize that oceanographic and space missions share several similarities, making the ocean an excellent test bed for future developments.

Long-lived mammals contain more phosphorylation sites in the SIRT6 C-terminus that enhance PARP1 interaction and resistance to oxidative stress - Jonathan Gigas; Michael E. Meadow; Jing Guo; Catherine Lan; Eric Hillpot; John C. Martinez; Gregory Tombline; Philip Bellomio; Valeria Rivera-Almodóvar; Kevin A. Welle; Kyle Swovick; Jennifer R. Hryhorenko; et al. (GeroScience, 2026)

Mesoscale eddies in the Southern Ocean influence foraging trip behaviour of multiple penguin species - Joshua C. Wilson; Philip N. Trathan; Hugh J. Venables; David G. Ainley; Matthis Auger; Alistair M.M. Baylis; Charles-André Bost; Louise Emmerson; Kimberley T. Goetz; Mark A. Hindell; Jefferson T. Hinke; Catharine Horswill; et al. (Progress in Oceanography, 2026)

Demonstration of seismic monitoring of CO2 storage using a 3D acoustic laboratory - Kasper Aas Hunnestad; Robin André Rørstadbotnen; Tim-Cato Netland; Martin Landrø; Marijn Beugelsdijk; Jørgen Avdal; Børge Arntsen; Philip Ringrose; Guillaume Carraux; Anne C. Elster (International Journal of Greenhouse Gas Control, 2026)

E-cigarette Aerosol Containing Nicotine Increases Aortic Stiffness in Young Mice - Pireyatharsheny Mulorz; Joscha Mulorz; Agnesa Mazrekaj; Hsiang-Han Liu; Wiebke Ibing; Joshua M. Spin; Lasse Bach Steffensen; Hans C. Beck; Uwe Raaz; Kensuke Toyama; Hubert Schelzig; Philip S. Tsao; et al. (Cardiovascular Toxicology, 2026)

Climate Predicts Tree Dispersal Strategies Across Brazil's Ecosystems - Fernanda C. Souza; Vinícius Andrade Maia; Renata Françoso; Matheus Coutinho Freitas de Oliveira; Ana Beatriz Ligo; Bruno X. Pinho; Jesús Aguirre‐Gutiérrez; Martin Sullivan; Larissa Rocha‐Santos; Laura de Brito Évora; Leonardo de Sousa Miranda; María Natalia Umaña; et al. (Global Ecology and Biogeography, 2026)
Aim We investigate the distribution of dispersal modes — endozoochory (via animal ingestion), synzoochory (via animal seed accumulation) and anemochory (via wind)—and seed mass of woody plants across Brazilian ecosystems, testing whether their relative abundance in local plant communities could be predicted by climate, edaphic factors and dispersal agents (e.g., the main vectors moving seeds). We expected climate to be the main predictor of dispersal strategy abundance. Location Brazilian ecosystems (Amazon, Atlantic Forest, Cerrado and Caatinga). Time Period 2004–2020. Major Taxa Studied Woody angiosperms, trees and shrubs. Methods We assigned seed mass to 1984 species and dispersal mode to 2203 species within 300 old‐growth and non‐flooded plots. We employed Random Forest regressions to assess the influence of water availability, temperature seasonality, soil fertility, wind and frugivorous primates on the community‐weighted means of seed mass and dispersal modes. We mapped predictions and estimated the area of applicability to identify regions where predictions were reliable. Results Climate was the main factor predicting tree dispersal strategies, followed by dispersal agents or soil properties. Endozoochory was prevalent in wetter regions with high water availability and greater diurnal temperature range. Anemochory was more common in drier regions with low water availability, stronger winds and greater diurnal temperature range, whereas synzoochory was more abundant in areas with low temperature seasonality. Heavier seeds were more prevalent in regions with less seasonal temperatures, smaller diurnal temperature ranges and weaker winds. Main Conclusions Climate is a key predictor of the distribution and prevalence of plants with contrasting dispersal modes and seed masses. We thus expect functional responses to environmental change associated with shifts in the relative abundance of dispersal strategies, with implications for ecosystem services. Our results also highlight the critical role of plot‐based datasets in improving our understanding of how environmental factors influence seed dispersal strategies across tropical ecosystems.

Design and Validation of a Stiffness-Matched Cervical Spine Surrogate - Katie R. G. Zilevicius; Mary Kathryn Hederick; B. Wade von Kleeck; Emma C. Coltoff; Tyler J. Roy; Jed C. Wilbur; Brian S. Graybill; F. Scott Gayzik; Philip J. Brown (Annals of Biomedical Engineering, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Behavioral variation across multiple phases of intravenous cocaine self-administration among genetically diverse mouse populations - Price E. Dickson; Udita Datta; Troy D. Wilcox; Ashley A. Auth; Robyn L. Ball; Matt Dunn; Heidi S. Fisher; Alyssa Klein; Michael R. Leonardo; Tyler A. Roy; Michael C. Saul; Jason A. Bubier; et al. (Psychopharmacology, 2026)
Genetic and other predisposing factors can influence the progression from initiation of drug intake to compulsive substance use through distinct biobehavioral processes. Operant cocaine self-administration studies in laboratory mice offer a powerful method to dissect the biology of this progression from initiation, dose-response, extinction, and cued reinstatement in a controlled, tractable system. However, many such studies encompass limited genetic diversity and rarely examine self-administration behaviors beyond the acquisition stage. Here, we study three high-diversity mouse populations – 50 strains from the Collaborative Cross (CC) reference panel, a large sample of Diversity Outbred (J: DO) population and their eight founder strains – to characterize the varied phenotypic manifestation of behaviors across multiple phases of cocaine intravenous self-administration (IVSA) in both sexes. We observed distinct strain differences among the founders and CC strains in all phases of self-administration, with heritability estimates ranging from 0 to 0.585 and many CC and J: DO phenotypic values exceeding the range of founders including the C57BL/6J strain. Sex differences were common across behaviors, some manifesting as main effects, others as strain interactions. Finally, by adopting a multi-stage design, we identified extreme strains for various cocaine intake and response traits. Together, these findings demonstrate the utility of extended self-administration protocols in high-diversity mouse populations and establish feasibility for their use in the discovery and characterization of biological mechanisms of substance use traits and for preclinical studies in relevant, complex mouse models.

Oral phosphodiesterase-5 inhibitor does not augment red blood cell deformability at rest or during handgrip exercise - Andrew R. Steele; Liam A. Kightley-Kauser; Jacob McCormick; Nina K. Geerts; Brydie Lemkes; Jonah C. Dizon; Jay M. J. R. Carr; Philip N. Ainslie (European Journal of Applied Physiology, 2026)

The impact of mild hypohydration and sex on the cardiovascular responses to progressive lower-body negative pressure - Megan Hunt; Jenna C. McCrone; Christopher Pignanelli; Monica M. Grigore; Katrin Turetskiy; Gavin C. Lydiate; Alexa A. Robertson; Regan E. J. Parris; Ella M. Bisset-Cavallin; Connor Wideman; Philip J. Millar; Jamie F. Burr; et al. (European Journal of Applied Physiology, 2026)

A comparative analysis of specific surface area and molecular structure in CO2-microbubble-assisted starch hydrolysis for the effective binding of α-amylase to starch - Elahe Abedi; Philip C. Wietstock (Innovative Food Science & Emerging Technologies, 2026)

Effects of dietary fermented sugar kelp (Saccharina latissima) on intestinal histology, antioxidant capacity, and immune-related biomarkers of post-smolt Atlantic salmon (Salmo salar) - Sahar Sartipiyarahmadi; Ingvild Lunderød Øverbø; Benjamin Costas; Lourenço Ramos-Pinto; Nina S. Liland; Harald Sveier; Silje Steinsund; Tom Johnny Hansen; Øivind Strand; Jan Vidar Jakobsen; Antony J. Prabhu Philip; Sofie C. Remø (Fish & Shellfish Immunology, 2026)

Variable pH habitats could help prepare stone crabs for coastal acidification - Philip M. Gravinese; Hannah E. Craft; Alex Douwes; Gretchen S. Faraci; Morgan L. Jarrett; Shelby A. Perry; Chloe E. Potts; Emma C. Rosser; Abigail L. Smith; Alexis R. Trevillian; Christopher Moore; Kimberly K. Yates (Marine Biology, 2026)

Acoustic telemetry reveals high site fidelity of yellow‐phase American eels Anguilla rostrata in a large river - Felix Eissenhauer; Tommi Linnansaari; Thomas C. Pratt; R. Allen Curry; Philip M. Harrison (Journal of Fish Biology, 2026)
Movement patterns and habitat use of yellow‐phase American eels Anguilla rostrata in the Wolastoq/Saint John River were examined using acoustic telemetry. Tracking 72 tagged yellow‐phase eels from late summer 2021 to autumn 2023 revealed overall restricted longitudinal movements (mean linear range ± standard deviation [SD] 6.4 ± 10.9 km) and high site fidelity. However, two eels exhibited small‐scale (20–25 km) seasonal movements within freshwater habitats and one eel undertook large‐scale (~83 km) seasonal movements between estuarine habitats in winter and freshwater habitats in summer. Tracking 24 yellow‐phase eels equipped with depth sensors indicated that depth use correlated with diel period, season and fish length, with eels occupying shallower habitats at night, presumably for foraging, and deeper habitats during the day, likely for shelter. Sixteen tagged eels presumably matured to the silver phase and initiated out‐migration in late summer. These eels moved rapidly through freshwater (mean ± SD 11.9 ± 8.8 km/day) but slowed considerably on reaching estuarine habitats (1.3 ± 1.3 km/day). These findings highlight the diversity of movement strategies in yellow‐phase eels and provide new insights into the transition to the migratory silver phase.

Dry‐Season Water Deficits in the Southwestern Amazon Under High Emissions - Débora J. Dutra; Chris Jones; Richard A. Betts; Igor J. M. Ferreira; Luiz E. O. C. Aragão; Guilherme Mataveli; Henrique Leão; Breno I. Domingos; Beatriz F. Cabral; Philip M. Fearnside; Paulo M. L. A. Graça; Aurora M. Yanai; et al. (International Journal of Climatology, 2026)
Understanding future changes in cumulative water deficit (CWD) is essential for assessing the vulnerability of Amazonian ecosystems to climate change. This study evaluates the performance of CMIP6 models in simulating CWD in the southwestern Amazon from 1985 to 2024 and projects future changes through 2100 under three emission scenarios (SSP1‐2.6, SSP3‐7.0, SSP5‐8.5). CWD was calculated using a fixed evapotranspiration threshold of 100 mm/month, and the maximum cumulative water deficit (MCWD) was derived to quantify overall water stress over time. Model performance was assessed using statistical metrics (MAE, RMSE, bias and Pearson correlation), and the best‐performing models were selected for future projections. Additionally, time series decomposition with breakpoint detection (BFAST) was applied. Results show that most models reproduce the seasonal cycle but diverge during peak dry months. Under SSP5‐8.5, deficits intensify significantly, exceeding 150 mm between July and September. CAS‐ESM2‐0 and CESM2‐WACCM exhibit large negative biases, while BCC‐CSM2‐MR and IPSL‐CM6A‐LR perform best. SSP1‐2.6 shows minimal changes, whereas SSP3‐7.0 and SSP5‐8.5 exhibit significant negative trends, with depletion rates reaching −21 mm/month by 2100. Temporal decomposition reveals increased hydrological instability, structural breaks after 2040 (SSP3‐7.0) and 2050 (SSP5‐8.5), and amplified seasonality under high emissions. Residual variability also increases, indicating a higher frequency of non‐seasonal anomalies. These findings highlight growing water stress under higher warming scenarios and emphasise CWD as a key indicator of ecological risk. Reliable projections depend on careful model evaluation, underscoring the need for model selection to guide climate adaptation and forest conservation strategies.

Peripheral microRNA signature in genetic frontotemporal dementia—findings from the GENFI initiative - Chiara Fenoglio; Maria Serpente; Marina Arcaro; Tiziana Carandini; Luca Sacchi; Manuela Pintus; Vittoria Borracci; Giulia Giudici; Marta Rigoni; Paola Muti; Laura Ghezzi; Arabella Bouzigues; et al. (GeroScience, 2026)
Frontotemporal dementia (FTD) is a neurodegenerative disease characterized by significant clinical and genetic heterogeneity, with approximately 40% of cases linked to hereditary genetic mutations, including MAPT , GRN , and C9ORF72 . Recently, microRNAs (miRNAs) have emerged as key regulators of cellular processes related to neurodegeneration and as potential biomarkers for FTD. However, their relevance in presymptomatic stages remains poorly understood. We conducted a miRNA expression analysis using TaqMan OpenArray® panels on blood samples collected from 171 individuals, including symptomatic mutation carriers (SMC), presymptomatic carriers (PMC), and healthy non-carriers (NC). Dysregulated miRNAs were validated and bioinformatic tools were used to identify potential associated molecular pathways. In C9ORF72 , miR-20b-5p and miR-223-5p were significantly upregulated in SMC (fold regulation over NC: 2.418 p = 0.0336 and 7.829 p < 0.0264 respectively) and PMC (5.518, p < 0.0001 and 3.941, p < 0.0001 respectively). In GRN mutation carriers, miR-28-3p was altered in both SMC and PMC (fold regulation over NC: 1.484 p < 0.050 and 3.287, p < 0.050). In MAPT mutation carriers, miR-28-5p, miR-192-3p, miR-25-3p, and miR-532-3p were altered only in SMC (fold regulation over NC: 1.496 p < 0.050, 1.911 p = 0.006, 1.468 p < 0.05, and 0.728 p < 0.05). Bioinformatic analysis revealed enrichment of pathways related to neurodegeneration and synapse impairment. These results suggest that miRNA expression levels are deregulated in mutated SMC, in C9ORF72 and GRN PMC. Notably, miR-20b-5p, miR-223-5p, and miR-28-3p were increased in preclinical stages of the disease, supporting their role as early biomarkers for C9ORF72 -FTD and GRN -FTD. Conversely, alterations in MAPT carriers appeared only in symptomatic stages, suggesting a different involvement in disease progression.

Innovative methodologies for elucidating bushfire smoke-induced pathophysiological mechanism - Keshav R. Paudel; Karl J. Hegarty; Jesus Shrestha; Kurtis F. Budden; Nikhil T. Awatade; Tayyaba Sadaf; Vamshikrishna Malyla; Shafagh Waters; Paris C. Papagianis; Jane E. Bourke; Peter A. Wark; Philip M. Hansbro (Science of The Total Environment, 2026)

The impact of 75 years of climate change on Mediterranean glacier mass balance - Bingdian Wang; Philip D. Hughes; Christopher M. Darvill; Jamie C. Woodward (Global and Planetary Change, 2026)

Valuing mangrove ecosystem services along the Brazilian Amazon coast - Philip Otieno; Margaret Owuor; Carla F. Pacheco; Gabriel C. Coppo; Thuareag Monteiro Santos; Tiago O. Ferreira; Angelo F. Bernardino (Ecosystem Services, 2026)

Innovations in underground hydrogen storage with multiphysics simulations, optimization, and monitoring: A review - Yue Zhang; Zhenxue Dai; Hung Vo Thanh; Mingxu Cao; Lulu Xu; Xiaoying Zhang; Bicheng Yan; Philip H. Stauffer; Huichao Yin; Kenneth C. Carroll; Mohamad Reza Soltanian (Earth-Science Reviews, 2026)

Assessment of tick populations associated with capybaras in natural reserves and human-modified environments with or without invasive plants in the state of São Paulo, Brazil - Matheus Pasini-Martins; Rubia Diaz Taveiros Kuhne; Carolina Moura de Oliveira; Lina C. Binder; Igor S. Silito; Adriano Pinter; Fernanda B. Passos Nunes; Thiago F. Martins; José Henrique de Hildebrand e Grisi Filho; Wayne Dawson; Philip A. Stephens; Dalva Maria da Silva Matos; et al. (Experimental and Applied Acarology, 2026)
In southeastern Brazil, capybaras ( Hydrochoerus hydrochaeris ) are main hosts of the ticks Amblyomma dubitatum and Amblyomma sculptum ; the latter has great medical importance for being the main vector of Rickettsia rickettsii , the agent of Brazilian spotted fever (BSF). This study aimed to quantify ticks in areas invaded and not invaded by exotic plants ( Hedychium coronarium , Cenchrus purpureus or Megathyrsus maximus ) within capybaras’ living areas in São Paulo state. Tick populations were quantified in 24 capybara habitats, eight in natural reserves and 16 human-modified landscapes; the latter were composed of eight BSF-endemic areas and eight BSF-nonendemic areas. In the 24 areas, ticks were sampled in plots of natural forests and plots with at least one of the three invasive plants. Both presence and density of A. sculptum were higher in human-modified landscapes, while the presence and density of A. dubitatum tended to be similar among human-modified landscapes and natural reserve areas. The two tick species were collected both in areas colonized by invasive plants ( H. coronarium , M. maximus , and/or C. purpureus ) and in areas of non-invaded vegetation. However, a higher density of A. dubitatum was observed in areas of H. coronarium and a lower density of A. sculptum in this type of vegetation. Within human-modified landscapes, there was a higher density of A. sculptum in BSF-endemic areas when compared to non-endemic areas, unlike A. dubitatum , which remained at an almost constant density and presence among BSF-endemic and non-endemic areas. Plant invasions may have some role in the ecology of capybara-associated ticks.

High-latitude F2 peak density thickness: a long-term characterization using PFISR measurements - Mohamed O. Shammat; Bodo W. Reinisch; Ivan Galkin; Philip J. Erickson; Wyatt Johnson; Sophia Karpouzas; Jay A. Weitzen; William C. Rideout (Advances in Space Research, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Distribution and ecology of the four Macrourus species by‐caught in the longline fishery at South Georgia, Southern Ocean - José Abreu; Philip R. Hollyman; Jennifer J. Freer; M. L. Romero Martínez; José P. Queirós; Timothy Jones; Richard A. Phillips; José C. Xavier; Martin A. Collins (Journal of Fish Biology, 2026)
Although Macrourus species are the main by‐catch across Southern Ocean longline fisheries, including around South Georgia, the lack of species‐specific data has hindered effective management and ecological understanding. Aggregation of macrourids at genus level masks critical interspecific differences in life‐history strategies and vulnerabilities to fishing. Here, we provide the first comprehensive biological assessment of the four macrourid species caught in South Georgia waters: Macrourus caml , Macrourus carinatus , Macrourus holotrachys and Macrourus whitsoni . Using fishery and observer data collected in 2018–2022, we reveal pronounced female‐biased sex ratios in three species ( M. holotrachys , M. carinatus and M. caml ), strong depth‐based segregation by body length, distinct distributions and habitat preferences related to environmental features (bathymetric depth and slope, primary productivity and temperature). By‐catch rates were highest in the southern region of South Georgia and varied across species: M. holotrachys was the most frequently caught and had a wide spatial and bathymetric distribution (∼1000–1750 m); M. caml was the second most caught and appeared the most flexible in terms of habitat use; M. carinatus was mainly caught in the west, including at Shag Rocks; and M. whitsoni was caught less frequently and in deeper water (> 1500 m), mostly in the northeast and east, and had the most restricted distribution. These interspecific differences underscore the need for species‐level assessments of fisheries risk and improved data collection to fill knowledge gaps. Overall, this study provides a critical foundation for understanding the ecology of Macrourus species in sub‐Antarctic ecosystems and highlights that additional data are required for by‐caught species to aid species‐level management in toothfish longline fisheries in the CCAMLR area.

PTUPB improves cognitive function in Alzheimer’s disease associated with enhancing cerebral vascular myogenic response and attenuating vascular remodeling - Gilbert C. Morgan; Andrew Gregory; Chengyun Tang; Sung Hee Hwang; Jane J. Border; Jing Xu; Yedan Liu; Shan Bai; Tae Jin Lee; Cameron Cantwell; David Bunn; Karen M. Wagner; et al. (GeroScience, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Evaluating Local Calibration Methods for Improving Diameter Growth Predictions in the Southern Variant, Forest Vegetation Simulator (FVS-Sn) - Ergin C. Cankaya; Philip J. Radtke (Forest Science, 2026)
Local calibration methods were evaluated for diameter at breast height (dbh) growth predictions in 11 tree species in Virginia, USA, using a model form based on the Forest Vegetation Simulator Southern Variant (FVS-Sn) large tree dbh regression model. Data from 1090 remeasured forest inventory plots from the USDA Forest Service’s Forest Inventory and Analysis (FIA) database were used to calibrate FVS dbh growth predictions to local conditions and evaluate four calibration methods based on the following information: 1) median prediction errors calculated from locally observed dbh pairs before and after a five-year remeasurement period; 2) a random intercept estimated from locally observed dbh using mixed-effects regression; 3) a simple linear regression (SLR) model fitted to observed and predicted dbh at the local scale; and 4) an SLR model with regression through the origin. Calibration methods were assessed using leave-one-out cross-validation, comparing model predictions to observed dbh growth from withheld trees. Equivalence testing indicated median or regression-based local calibration methods achieved prediction-error tolerances over 5–7 year growth intervals as small as 0.11 cm (0.03 cm for two regression-based methods) for all species, whereas the random-intercept approach only achieved a minimum tolerance of 0.2 cm. Compared to uncalibrated models, local calibration substantially reduced prediction errors, demonstrating efficacy in increasing prediction accuracy, even with sparse FIA dbh growth data used for local-calibration.

A New Dayongaspid Galeaspid from the Silurian of the Lower Yangtze Region: Implications for Biogeography and the Evolution of Key Adaptations in Galeaspids - Yumeng Zhang; Xianren Shan; Xianghong Lin; Zhikun Gai; Philip C. J. Donoghue (Journal of Earth Science, 2026)

Impact of non-digestible carbohydrates and prebiotics on immunity, infections, inflammation and vaccine responses: a systematic review of evidence in healthy humans and a discussion of mechanistic proposals - Hediye Arioz Tunc; Philip C. Calder; Alissa Cait; Georgina F. Dodd; Naschla Y. I. Gasaly Retamal; Damien Guillemet; Daniel James; Konrad J. Korzeniowski; Anna Lubkowska; Alexandra Meynier; Weronika Ratajczak; Frédérique Respondek; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Mercury concentrations, habitat and trophic position of Antimora rostrata and Macrourus holotrachys from South Georgia (Southern Ocean) - Diana Vaz; José P. Queirós; José C. Xavier; Paco Bustamante; José Abreu; Eduarda Pereira; Philip R. Hollyman; João P. Coelho; José Seco (Marine Pollution Bulletin, 2026)

An in vitro-in silico workflow for predicting renal clearance of environmental chemicals and drugs - Courtney Sakolish; Hsing-Chieh Lin; Haley L. Moyer; Lucie C. Ford; Charles H. Christen; Barbara A. Wetmore; Michael J. DeVito; Philip Hewitt; Stephen S. Ferguson; Farah Raad; Ivan Rusyn; Weihsueh A. Chiu (Toxicology, 2026)

Pollen and sterol content differentially affect solitary bee development - Carlos Martel; Josef Kreidt; Jennifer Scott; Janine Griffiths-Lee; Ernesto Rázuri-Gonzales; Geraldine A. Wright; Philip C. Stevenson (Science of The Total Environment, 2026)

Runoff and soil erosion on woodland-encroached sagebrush rangeland under simulated rainfall and concentrated flow conditions - Viktor O. Polyakov; C. Jason Williams; Justin C. Johnson; Erin L. Phelps; Raven Chavez; Philip Heilman; William A. Rutherford; Osama Z. Al-Hamdan; Sayjro K. Nouwakpo; Jia Hu; Kenneth E. Spaeth; Samuel Anderson (CATENA, 2026)

Exogenous ketone monoester supplementation: a potential alternative strategy to mitigate altitude sickness? - Johan S. Thiessen; Natalie I. Miners; Devin G. McCarthy; Philip J. Millar; Julian C. Bommarito; Erik R. Swenson; Jeremy J. Walsh; Michael M. Tymko (European Journal of Applied Physiology, 2026)

Circum‐Island Line‐Transect Abundance Estimates of Spinner Dolphins Around Oʻahu, Hawaiʻi - Claire Lacey; Marie C. Hill; Amanda L. Bradford; Erin M. Oleson; Fabien Vivier; Aude F. Pacini; Philip S. Hammond; Lars Bejder (Marine Mammal Science, 2026)
Spinner dolphins ( Stenella longirostris subsp.) in Hawaiʻi face the highest documented human activity exposure rates of any dolphin species worldwide, raising concerns about long‐term impacts. Fundamental to any appropriate management action for a protected species is the availability of reliable information on their abundance and distribution. Currently, abundance estimates are only available for one of the six designated stocks of spinner dolphins in Hawaiʻi. To address this information gap, small‐boat line‐transect surveys for spinner dolphins were conducted around the island of Oʻahu between October 2020 and May 2022. A total of 73 survey days were achieved, resulting in 3098 km of transects surveyed around the Oʻahu coastline. We used a novel method utilizing opportunistically collected unoccupied aerial system data to assess dolphin availability at the surface. We also investigated the potential for responsive movement of animals, for which no evidence was found. Estimated abundance of spinner dolphins for Oʻahu was 594 animals (95% CI [360, 980], CV = 0.26). Our findings represent the first circum‐island abundance estimate of Oʻahu's spinner dolphins, allowing management to explore strategies aimed at minimizing human‐dolphin interactions in the region and assess long‐term impacts.

Electrospun fibrous membranes from waste thermocol-based PU-EPS/ZnO for oil-water separation - Nikhi Maria Raju; K. Manjima; Peter Philip; Sabadh; Soney C. George (Journal of Environmental Chemical Engineering, 2025)

Modelling nitrogen fertilization responses in temperate Eucalyptus plantations using APSIM - Philip J. Smethurst; John F. McGrath; Ian C. Dumbrell; Danielle Wiseman; Barrie May; Thomas G. Baker; Daniel S. Mendham (Forest Ecology and Management, 2025)

Enhancing carbon storage through proactively managing fire-prone coniferous mountain forests - Weichao Guo; Mohammad Safeeq; Guotao Cui; Philip C. Myint; Panmei Jiang; Han Guo; Michael L. Goulden; Kristen D. Emmett; Stephen C. Hart; Roger C. Bales (Ecological Modelling, 2025)

Exploring the potential of coconut coir fiber as a biodegradable mulch: Properties, uses, processing methods, and applications - Christian Lloyd Salva; Dinah Mae B. Ordista; Philip Donald C. Sanchez; Joan Jane J. Sanchez (Bioresource Technology Reports, 2025)

A subduction-modified source for the parental melts to MARID assemblages from the Kaapvaal craton lithosphere and their formation via hybridisation with wall-rock peridotite - Jason C. Hinde; Philip E. Janney; Hélène Legros; Yan Luo; Sarah Woodland; Graham D. Pearson (Mineralogy and Petrology, 2025)

Benthopelagic Deep-Sea Food Webs Along a Latitudinal Gradient in the Scotia Sea (Southern Ocean) - José P. Queirós; Mark Belchier; José Abreu; Paco Bustamante; Martin A. Collins; Ana M. M. Gonçalves; Irene Bermúdez-Gutiérrez; Gabriele Stowasser; Diana Vaz; Philip R. Hollyman; José C. Xavier (Ecosystems, 2025)
Understanding food-web structure is crucial to determine the functioning of ecosystems and sustainably manage resources. The Scotia Sea is an important area for Antarctic krill and toothfish fisheries, and one of the regions most impacted by climate change in the Southern Ocean. Whilst the pelagic Antarctic krill-centric food web has been investigated in reasonable detail, the structure of deep-sea food webs associated with toothfish fisheries remain largely unknown. Utilising stable isotopes and fatty acids as trophic proxies, we studied the deep-sea food-web structure in three locations of the Scotia Sea, from South Georgia (SG) to the South Sandwich Islands (SSI; divided into north and south). Our analyses indicate that all food webs were similar, presenting high trophic redundancy and similar vertical structure. All food webs had five trophic levels, with the 5th and 4th trophic levels mainly constituted of fish and the 3rd trophic level of cephalopods and crustaceans. However, some differences existed with the SG food web presenting larger diversity of producers and the bigeye grenadier Macrourus holotrachys in the highest trophic position, while Patagonian toothfish Dissostichus eleginoides and both Patagonian and Antarctic toothfish D. mawsoni were the top predators at SSI-North and SSI-South, respectively. Compared to coastal and pelagic food webs in the Southern Ocean, our results suggest that deep-sea food webs, including the benthic/demersal components, have a longer food-chain length. This study provides essential knowledge of the ecological variability of Southern Ocean deep-sea food webs while contributing to the management of resources within the SG and SSI Marine Protected Area.

Aotearoa New Zealand’s marine carbon cycle in a changing climate – Current understanding and future directions - Scott D. Nodder; Cliff S. Law; Erik Behrens; Sarah J. Bury; Antonia Cristi; Charine Collins; Kim I. Currie; Moira Décima; Alain De Verneil; Pablo C. Escobar‐Flores; Denise Fernandez; Mark P. Gall; et al. (New Zealand Journal of Marine and Freshwater Research, 2025)
The marine system plays a critical role in the global climate cycle, as a major control of atmospheric carbon dioxide (CO 2 ). Marine primary production (photosynthesis) and remineralisation of organic carbon (respiration, degradation) determine the amount of CO 2 sequestered in marine sediments and deep‐water environments on century to millennial timescales. The stocks and fluxes of the marine carbon cycle are susceptible to global climate change impacts and other anthropogenic activities that modify key processes. Oceanographic studies of the marine carbon cycle in Aotearoa New Zealand’s Exclusive Economic Zone (NZ EEZ) and Territorial Seas over past decades have provided broad knowledge across a complex and dynamic seascape, but there remain fundamental knowledge gaps that limit identification of and response to present and future anthropogenic threats. In particular, several areas of the EEZ have been under‐sampled and there are currently insufficient data to establish baselines and variability for the marine carbon cycle. We recommend that new observational technologies and ocean modelling applications be fully developed and utilised to enable development of robust predictive capability of our ocean’s response to human‐induced perturbations. Future focus on oceanic nature‐based solutions to accelerate CO 2 uptake will require improved knowledge of the marine carbon cycle in NZ’s EEZ.

SpiderATLAS : A Database of Spider Traits and Distributions in the Brazilian Atlantic Forest - Gabriel X. Boldorini; Paulo M. Martins; Antonio D. Brescovit; Adalberto J. Santos; Leonardo S. Carvalho; Ubirajara Oliveira; Philip Russo; Joyce C. B. Brito; Aparecida P. Barbosa; André Celso Bezerra Rodrigues; Aníbal Silva Cantalice; Arthur A. B. Rodrigues; et al. (Journal of Biogeography, 2025)
Aim Biodiversity shortfalls related to limited knowledge about geographic distribution (Wallacean) and species traits (Raunkiæran) are extremely common in many animal groups and perhaps more evident in invertebrate groups such as spiders. This lack of knowledge could present challenges for researchers investigating the response and effects of spiders along large spatial scales, particularly in the Global South. The aim of the SpiderATLAS is to facilitate research that links macroecology, biogeography, trait‐based ecology and global change biology. Location Brazilian Atlantic Forest, spanning virtually the entire eastern coastline of Brazil, encompassing 1,620,000 km 2 , 30 degrees of latitude (3° 42′ S to 33° 31′ S), and 22 degrees of longitude (34° 50′ W to 56° 45′ W). Taxon Spiders (Class Araneae), including 1648 species from 63 families. Methods We compiled the spatial distribution (i.e., occurrence data) and data on morphological characteristics and derived traits for spider species from species descriptions, taxonomic revisions and personal collection. Species occurrences were extracted from several data sources spanning from the 1880s to 2023. Data on the morphological traits of species were compiled from taxonomic and diversity inventory papers published between 1833 and 2024. Results We provide 9369 georeferenced point locations and six morphological traits (body length, prosoma length, prosoma width, prosoma height, femur I length, and patella I length) for 1648 spider species. Most data are available for females and males. The dataset and code are available to download from Dryad, World Spider Trait database, and the ZooTraits app. Main Conclusions The SpiderATLAS can be useful to access information on the distribution and traits of spiders, contributing to the development of macroecological, biogeographical and trait‐based ecology. This dataset can also facilitate the biodiversity conservation of one of the most abundant and important arthropod predators on the planet, in a biodiversity hotspot.

Position Spoofing Attacks on Unmanned Surface Vehicles - Jia Wang; Yang Xiao; Tieshan Li; Philip C. L. Chen (Journal of Marine Science and Engineering, 2025)
Unmanned surface vehicles (USVs) are equipped with numerous sensors, and data is transmitted through networks. Attackers may remotely compromise unmanned surface vehicle (USV) systems and commit criminal acts via networks, causing USVs to deviate from their intended course or pose a collision risk. Although significant research efforts have focused on developing attack detection and defense technologies for USVs, less attention has been paid to the offensive perspective—particularly the design and modeling of novel attack strategies. In this paper, we investigate the potential attack locations of USVs equipped with distributed navigation, guidance, and control modules. We propose a series of novel attack methods designed to compromise the navigation safety of USVs. These methods compromise the control system by blocking, modifying, and delaying navigation data to manipulate the navigation routes of USVs. Ultimately, the simulation results demonstrate the effectiveness of these attacks on the navigation of USVs.

Modeling barometric pumping of martian methane: Implications for Perseverance sample timing and gas loss from drilled cores - John P. Ortiz; Kevin W. Lewis; Roger C. Wiens; Philip H. Stauffer; Dylan R. Harp; Harihar Rajaram (Icarus, 2025)

Effects of fire severity and fire frequency on the abundance of hollows and hollow-bearing trees - Marlon Taylor; Ben C. Scheele; Renee Brawata; Matthew Gale; Philip Gibbons (Forest Ecology and Management, 2025)

Use of the APSIM process-based model to predict early genotype-by-environment interactions of temperate Eucalyptus - Rafael A. Rubilar; Philip J. Smethurst; Juan C. Valverde; Matías Pincheira; Veronica Emhart; Alex Medina; Daniel Bozo; Otavio Campoe (Forest Ecology and Management, 2025)

Unlocking the potential of cacao bean shell as a functional food additive: Composition, applications, optimization, and future directions – a review - Philip Donald C. Sanchez; Norhashila Hashim; Mohd Salahuddin Mohd Basri; Nazamid Bin Saari; Dimas Rahadian Aji Muhammad (Food Chemistry, 2025)

Temporal Changes to Migratory Fuel Load in Migratory Birds Across Europe - Jennifer Anne Border; Robert A. Robinson; James W. Pearce‐Higgins; Chris M. Hewson; Christine Howard; Philip A. Stephens; Stephen G. Willis; Jan A. C. von Rönn; Pierre‐Yves Henry; Romain Lorrilliere; Lorenzo Serra; Simona Imperio; et al. (Global Change Biology, 2025)
Climate change is a major threat to biodiversity, and migratory animals are particularly vulnerable, due partly to their reliance upon good resource availability across a network of sites at specific times. Migrants perform vital ecosystem functions, transferring significant resources across large spatial scales, but the impacts of climate change on the ability of individuals to complete these journeys are poorly studied. Collecting the large‐scale and long‐term data on the condition of individuals during migration to address this is challenging, but in migratory birds, we have a model system for which a large network of ringers (banders) collect individual data on body size and mass, enabling variation in body condition to be tracked. We used long‐term ringing data on 33 Afro–Palearctic migratory bird species at 286 sites across Europe to demonstrate a large‐scale decrease in migratory fuel loads during autumn over the last 40 years, but not in spring. Declines were strongest across southern Europe and linked to rising temperatures. The timing of autumn fuelling has also shifted, occurring earlier at northern sites and later at southern sites. These relationships varied depending on diet and breeding cycle length. Obligate insectivores were more constrained by temperature in the timing and magnitude of fuelling than frugivores. Species with short breeding cycles departed later at southern sites in warmer years, likely reflecting an extended breeding season. Altogether, these latitudinally varying findings suggest a trade‐off between maximising productivity or maximising adult survival as climate drives changing constraints on breeding season length and resource availability. Similar climate‐induced trade‐offs may be happening in other migratory taxa with the potential to influence population trends.

Local flow estimation at the top of the Earth’s core using Physics Informed Neural Networks - Naomi Shakespeare-Rees; Philip W. Livermore; Christopher J. Davies; Hannah F. Rogers; William J. Brown; Ciarán D. Beggan; Christopher C. Finlay (Physics of the Earth and Planetary Interiors, 2025)

Heterogeneous impacts of statewide policies across urban and rural markets: Evidence from liquor sales - Philip Watson; Jason A. Winfree; Ron C. Mittelhammer; Jill J. McCluskey (Journal of Rural Studies, 2025)

Geologic History Explains Freshwater Fish Species Richness Across the Conterminous USA - Brian K. Gallagher; Elizabeth C. Santos; Michael Dumelle; Philip R. Kaufmann; Joseph L. Ebersole (Global Ecology and Biogeography, 2025)
Aim Freshwater fishes comprise over 20% of vertebrate biodiversity despite occupying Time Period 2008–2019. Location Conterminous United States (USA). Major Taxa Freshwater fishes. Methods We analysed native species richness from a spatially representative survey of 5321 fish assemblages at 3609 sites. Geologic history was determined from surrogates of tectonic activity, glaciation, sea levels and river capture over the last 66 million years, which were paired with previously published evolutionary time estimates. Hypotheses were tested with spatial linear models. Results All hypotheses were at least partially supported. (1) Rank‐order richness matched hypothesized effects of geologic disturbances on evolutionary time and diversification rates. (2) Richness peaked in lowlands with high putative river capture rates. (3) Richness increased with evolutionary time at broad scales, but this relationship was weak and influenced by non‐teleost taxa. (4) Richness largely increased with stream size. Overall, the tectonically active western USA exhibited lower richness, weaker effects of stream size and a greater share of young lineages compared to the more geologically stable eastern USA, especially unglaciated lowlands within the Mississippi Basin. Main Conclusions We demonstrate that deep‐time processes leave a persistent mark on fish species richness. Thus, accounting for geologic history can improve assessments of freshwater biodiversity and biological condition in the USA and beyond.

The abundance, diversity, and assemblage structure of the macrobenthos at the South Georgia shelf methane seeps - Madeline P. B. C. Anderson; William D. K. Reid; Gerhard Bohrmann; Ingrid Dohrmann; Philip R. Hollyman; Sabine Kasten; Thomas Pape; Miriam Römer; Jason Newton; Ben D. Wigham; Katrin Linse (Frontiers in Marine Science, 2025)
A quarter of all marine methane, a potent greenhouse gas, is estimated to be hosted in Southern Ocean sediments. Climate change-induced ocean warming and ice shelf melting risk the stability of sedimentary gas hydrates, resulting in potential degassing and establishment of marine methane seeps. While methane seeps can originate from various sources, the destabilisation of gas hydrates may contribute to the formation and persistence of some active seeps. The impact of these seeps and their risks to the diverse sub-Antarctic and Antarctic benthic shelf fauna is uncertain. As a sentinel for change in the sub-Antarctic and wider Antarctic region, this study explores South Georgia’s continental shelf macrobenthic methane seep assemblages, for their diversity, richness, and abundance, and their environmental drivers influencing macrofaunal community composition. Seven of South Georgia’s shelf troughs hosting active methane seeps were investigated during RV METEOR’s M134 expedition in 2017. Species richness at 11 stations ranged from 19–51 species from a total of 103 species discovered across all sites. Station abundance ranged from 3,303–30,326 m². Diversity was higher at stations with greater methane- and sulfate-flux, and hydrogen sulfide at 25 cm depth. Abundance and richness were lower where surface sediment had high hydrogen sulfide concentrations. Abundance and species richness were lower at stations dominated by iron-reduction in the sediment. Assemblages were characterized by the presence of Southern Ocean species and by the absence of megafaunal chemosynthetic taxa. Arthropods, mostly crustacean, and annelid species made up three quarters of overall species richness, while molluscan and echinoderm species were depauperate with only 15 species. Compared with Southern Ocean macrobenthic assemblages, the South Georgia seep assemblages from sediments with gas hydrates present in the near-surface showed a lower species richness and change in taxon composition, also accompanied by lower numbers of calcium-carbonate shell bearing taxa. The current diverse benthic Antarctic biodiversity, especially the diversity of calcifiers, is likely at risk when methane seeps become established on Southern Ocean continental shelves as the reduction in habitat diversity leads to the decline in taxonomic diversity and species richness.

Modelling the spatial bound of an eDNA signal in the marine environment – the effect of local conditions - Tiago A. M. Silva; Claire P. C. Beraud; Philip D. Lamb; Wayne Rostant; Hannah J. Tidbury (Frontiers in Marine Science, 2025)
Environmental DNA (eDNA) is a powerful technique for biological assessments and monitoring in aquatic environments. The accurate interpretation of the source of eDNA detected requires understanding of its spatial and temporal bound. Studies which estimate eDNA dispersal in the aquatic environment, in particular the marine environment, are scarce and seldom represent the effect of hydrodynamics and eDNA decay. This study modelled eDNA dispersal in a coastal environment under diverse environmental conditions to assess how these conditions influence dispersal patterns. A modelling experiment shows that under thermally stratified conditions sampling eDNA across this gradient reduces detectability. Statistical analysis shows that both median and extreme eDNA dispersal distances simulated by the model were primarily controlled by local tidal conditions (tidal excursion), followed by month (influencing the water temperature and thus eDNA decay rate). The median distance varies between 2.27 and 14.14 km which falls within the range of previously published model results, and is up to 10x greater than observed values. However this gap has been narrowing, and the present statistical model helps set limits on the distance to source as a function of regional oceanography and water temperature. The present method can also be used post-survey to help interpret the location and number of sources. This study constitutes an advance in modelling eDNA dispersal in coastal areas and crucially provides much needed evidence to underpin robust interpretation of eDNA monitoring data and to inform the design of eDNA monitoring programmes that account for variable environmental conditions.

Establishment, current status and possible origin of the greater white-toothed shrew Crocidura russula in Great Britain - Graham C. Smith; Ian F. Bond; Terry Coult; Dan Henderson; Courtney Graham; Emma Brand; Allan D. McDevitt; Philip A. Stephens; Sophie Webb; Matt Larsen-Daw (Biological Invasions, 2025)
Great Britain has three native shrews, while the greater white-toothed shrew (GWT: Crocidura russula ) is native to the European continent and some Channel islands. The GWT shrew was first reported in northern England in 2022. We detail its immediate investigation through national authorities, non-government bodies and individuals. Sixteen GWT were among 595 small mammals live-trapped. Barn owl pellet analysis revealed 56 GWT skulls in two areas. Genetic analysis of the cytochrome b gene suggests these population were derived from one or more continental European introductions, but not from the nearby island of Ireland where this non-native species has been present since at least 2007. The overall government response from the Department for Environment, Food and Rural Affairs and Natural England concluded that the species is too widespread to have any reasonable chance of eradication, but there remain ongoing efforts to determine the extent of invasion and its effect on native species.

Assessing the Effectiveness of 3D-Printed Ceramic Structures for Coral Restoration: Growth, Survivorship, and Biodiversity Using Visual Surveys and eDNA - Vriko Yu; Alison D. Corley; Horace Lau; Philip D. Thompson; Zhongyue Wilson Wan; Jane C. Y. Wong; Zoe Kwan Ting Wong; Louise Wai Hung Li; Shelby E. McIlroy; David M. Baker (Journal of Marine Science and Engineering, 2025)
Coral reef degradation has spurred the development of artificial structures to mitigate losses in coral cover. These structures serve as substrates for coral transplantation, with the expectation that growing corals will attract reef-associated taxa—while the substrate’s ability to directly support biodiversity is often neglected. We evaluated a novel 3D-printed modular tile made of porous terra cotta, designed with complex surface structures to enhance micro- and cryptic biodiversity, through a restoration project in Hong Kong. Over four years, we monitored 378 outplanted coral fragments using diver assessments and photography, while biodiversity changes were assessed through visual surveys and eDNA metabarcoding. Coral survivorship was high, with 88% survival after four years. Visual surveys recorded seven times more fish and almost 60% more invertebrates at the restoration site compared to a nearby unrestored area. eDNA analyses revealed a 23.5% higher eukaryote ASV richness at the restoration site than the unrestored site and 13.3% greater richness relative to a natural reference coral community. This study highlights the tiles’ dual functionality: (1) supporting coral growth and (2) enhancing cryptic biodiversity, an aspect often neglected in traditional reef restoration efforts. Our findings underscore the potential of 3D-printed ceramic structures to improve both coral restoration outcomes and broader reef ecosystem recovery.

Gravitational instability of thickened yet compositionally buoyant Tibetan mantle lithosphere - Gregory A. Houseman; Philip C. England; Lynn A. Evans (Tectonophysics, 2025)

Corrigendum to “Toxicity and absorption of polystyrene micro-nanoplastics in healthy and Crohn’s disease human duodenum-chip models” [J Hazard Mater 490 (2025) 137714] - Davood Kharaghani; Glen M. DeLoid; Ping He; Ben Swenor; Trung Huu Bui; Nubia Zuverza-Mena; Carlos Tamez; Craig Musante; Michael Verzi; Jason C. White; Philip Demokritou (Journal of Hazardous Materials, 2025)

Deep learning and machine learning enable broad-scale woodland height, cover, and biomass mapping - Michael J. Campbell; Jessie F. Eastburn; Simon C. Brewer; Philip E. Dennison (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Enhancement of dry-hopped cider aroma through selection of apple cultivar, hop variety and yeast strain - Natalia Svedlund; Anton Kiepert; José Rodríguez Pérez; Frederico Magalhães; Philip C. Wietstock; Brian Gibson (Food Microbiology, 2025)

Synthetic cytotoxicity profiling of cohesin mutants highlights recombination-based dependencies - Rafaela Horbach Marodin; Ecaterina Cozma; Sivan Reytan-Miron; Nigel J. O’Neil; Peter C. Stirling; Philip Hieter (DNA Repair, 2025)

Thermal diodes, transistors and logic: Review of unconventional computing methods - Philip Tabor; Matei C. Ignuta-Ciuncanu; Ricardo F. Martinez-Botas (BioSystems, 2025)

Global Study of Plant‐Herbivore Interactions Reveals Similar Patterns of Herbivory Across Native and Non‐Native Plants - Andrea Galmán; Philip G. Hahn; Brian D. Inouye; Nora Underwood; Yanjie Liu; Susan R. Whitehead; William C. Wetzel (Ecology Letters, 2025)
A core hypothesis in invasion and community ecology is that species interaction patterns should differ between native and non‐native species due to non‐native species lacking a long evolutionary history in their resident communities. Numerous studies testing this hypothesis yield conflicting results, often focusing on mean interaction rates and overlooking the substantial within‐population variability in species interactions. We explored plant‐herbivore interactions in populations of native and established non‐native plant species by quantifying differences in mean herbivory and added a novel approach by comparing within‐population variability in herbivory. We include as covariates latitude, plant richness, plant growth form and cover. Using leaf herbivory data from the Herbivory Variability Network for 788 plant populations spanning 504 species globally distributed, we found no overall differences in mean herbivory or variability between native and non‐native plants. These results suggest native and established non‐native plants interact similarly with herbivores, indicating non‐native status is not a strong predictor of ecological roles.

Optimizing automated photo identification for population assessments - Philip T. Patton; Krishna Pacifici; Robin W. Baird; Erin M. Oleson; Jason B. Allen; Erin Ashe; Aline Athayde; Charla J. Basran; Elsa Cabrera; John Calambokidis; Júlio Cardoso; Emma L. Carroll; et al. (Conservation Biology, 2025)
Several legal acts mandate that management agencies regularly assess biological populations. For species with distinct markings, these assessments can be conducted noninvasively via capture‐recapture and photographic identification (photo‐ID), which involves processing considerable quantities of photographic data. To ease this burden, agencies increasingly rely on automated identification (ID) algorithms. Identification algorithms present agencies with an opportunity—reducing the cost of population assessments—and a challenge—propagating misidentifications into abundance estimates at a large scale. We explored several strategies for generating capture histories with an ID algorithm, evaluating trade‐offs between labor costs and estimation error in a hypothetical population assessment. To that end, we conducted a simulation study informed by 39 photo‐ID datasets representing 24 cetacean species. We fed the results into a custom optimization tool to discern the optimal strategy for each dataset. Our strategies included choosing between truly and partially automated photo‐ID and, in the case of the latter, choosing the number of suggested matches to inspect. True automation was optimal for datasets for which the algorithm identified individuals well. As identification performance declined, the optimization recommended that users inspect more suggested matches from the ID algorithm, particularly for small datasets. False negatives (i.e., individual was resighted but erroneously marked as a first capture) strongly predicted estimation error. A 2% increase in the false negative rate translated to a 5% increase in the relative bias in abundance estimates. Our framework can be used to estimate expected error of the abundance estimate, project labor effort, and find the optimal strategy for a dataset and algorithm. We recommend estimating a strategy's false negative rate before implementing the strategy in a population assessment. Our framework provides organizations with insights into the conservation benefits and consequences of automation as conservation enters a new era of artificial intelligence for population assessments.

Fish consumption advice is depriving children of neurolipids and other nutrients essential to brain and eye development - Philip Spiller; J. Thomas Brenna; Susan E. Carlson; Jean Golding; Michael A. Crawford; Joseph R. Hibbeln; Berthold V. Koletzko; John Columbo; Penny Kris-Etherton; Sonja L. Connor; Clark Carrington; P. Michael Bolger; et al. (NeuroToxicology, 2025)

Impacts of straw addition on ryegrass (Lolium perenne L.) heavy metal absorption and microbial community structure - Jiuwei Song; Yunxiu Zhao; Yuhan Cai; Boping Tang; Fenghua Ding; Philip C. Brookes; Xingmei Liu (Plant and Soil, 2025)

Effects of calcareous marine algae on performance, rumen fermentation and methane emissions of high-yielding dairy cows - Philip C. Garnsworthy; Neil Saunders; Jennifer R. Goodman; Shane O’Connell (Animal Feed Science and Technology, 2025)

Spectral biology across scales in changing environments - Jeannine Cavender‐Bares; Jose Eduardo Meireles; Jesús Pinto‐Ledezma; Peter B. Reich; Meredith C. Schuman; Philip A. Townsend; Amy Trowbridge (Ecology, 2025)
Understanding ecosystem processes on our rapidly changing planet requires integration across spatial, temporal, and biological scales. We propose that spectral biology, using tools that enable near‐ to far‐range sensing by capturing the interaction of energy with matter across domains of the electromagnetic spectrum, will increasingly enable ecological insights across scales from cells to continents. Here, we focus on advances using spectroscopy in the visible to short‐wave infrared, chlorophyll fluorescence‐detecting systems, and optical laser scanning (light detection and ranging, LiDAR) to introduce the topic and special feature. Remote sensing using these tools, in conjunction with in situ measurements, can powerfully capture ecological and evolutionary processes in changing environments. These tools are amenable to capturing variation in life processes across biological scales that span physiological, evolutionary, and macroecological hierarchies. We point out key areas of spectral biology with high potential to advance understanding and monitoring of ecological processes across scales—particularly at large spatial extents—in the face of rapid global change. These include: the detection of plant and ecosystem composition, diversity, structure, and function as well as their relationships; detection of the causes and consequences of environmental stress, including disease and drought, for ecosystems; and detection of change through time in ecosystems over large spatial extents to discern variation in and mechanisms underlying their resistance, recovery, and resilience in the face of disturbance. We discuss opportunities for spectral biology to discover previously unseen variation and novel processes and to prepare the field of ecology for novel computational tools on the horizon with vast new capabilities for monitoring the ecology of our changing planet.

Toxicity and absorption of polystyrene micro-nanoplastics in healthy and Crohn’s disease human duodenum-chip models - Davood Kharaghani; Glen M. DeLoid; Ping He; Ben Swenor; Trung Huu Bui; Nubia Zuverza-Mena; Carlos Tamez; Craig Musante; Michael Verzi; Jason C. White; Philip Demokritou (Journal of Hazardous Materials, 2025)

Do Pinus radiata hybrids represent a solution to forestry’s wilding conifer problem? - Sarah V. Wyse; Robert D. Gibson; Daniel C. Raikes; Philip E. Hulme (Forest Ecology and Management, 2025)

Rapid and significant lithium isotope response to afforestation in Icelandic topsoils - Xianyi Liu; David J. Wilson; Kevin W. Burton; Bjarni Diðrik Sigurdsson; Julia C. Bos; Wesley T. Fraser; Philip A.E. Pogge von Strandmann (CATENA, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Development and characterization of reference environmentally relevant micro-nano-plastics for risk assessment studies - Milton Das; Leonardo Calderon; Dilpreet Singh; Satwik Majumder; Lila Bazina; Nachiket Vaze; Una Trivanovic; Glen DeLoid; Nubia Zuverza-Mena; Mandeep Kaur; Jakub Konkol; Nassifatou Koko Tittikpina; et al. (NanoImpact, 2025)

Acute exercise impacts heart rate variability but not cognitive flexibility during subsequent simulated firefighter occupational tasks - Philip J. Agostinelli; Nicholas C. Bordonie; Braxton A. Linder; Ann M. Robbins; Parker L. Jones; Lee F. Reagan; C. Brooks Mobley; Matthew W. Miller; William M. Murrah; JoEllen M. Sefton (European Journal of Applied Physiology, 2025)
Purpose Acute exercise can transiently enhance cognitive flexibility. The cognitive demand of firefighters makes it relevant to understand if on-shift exercise could produce similar improvements in cognitive performance during subsequent occupational tasks. Metrics of heart rate variability (HRV), such as time- and frequency-domain outcomes, may shed light upon the influence exercise has on cognition, as they discern information related to cardiac autonomic (sympathetic/parasympathetic) function. We aimed to determine if acute resistance and aerobic exercise impact cognitive flexibility during occupational tasks and its relation to HRV. Methods 32 participants completed a baseline Wisconsin Card Sorting Task (WCST) and three experimental trials: resistance exercise (RE), aerobic exercise (AE), or a rested control (CON). An occupational task assessment (OTA) including four rounds of 10 deadlifts and a 0.15-mile sandbag carry in an environmental chamber (35 °C/50% humidity) was completed after each trial. The second round was followed by the WCST. Repeated measures ANOVAs were used to analyze differences by condition. Results For the WCST, total, perseverative, and non-perseverative errors did not differ (ps > 0.39). Time-domain HRV metrics were not different (ps > 0.05). All frequency-domain metrics, other than low-frequency power, were not different (ps > 0.24). Low-frequency power was lower based on condition (p = 0.03). Post hoc analysis showed low-frequency power was lower following AE compared to RE and CON. Conclusion Results suggest an acute bout of on-shift aerobic or resistance exercise may not impact cognitive flexibility during subsequent simulated occupational tasks, despite depressed metrics of heart rate variability following aerobic exercise.

Consilience in practice: social–ecological dynamics of the Lake Volvi region (Greece) during the last two millennia - Lucrezia Masci; Georgios C. Liakopoulos; Raphael Gromig; Elias Kolovos; Katerina Kouli; Matthias Moros; Laura Sadori; Alexander Sarantis; Philip Slavin; Jakub Sypiański; Georgios Vidras; Cristiano Vignola; et al. (Journal of Quaternary Science, 2025)
The Lake Volvi area, part of the region of Macedonia (northern Greece), is a biodiversity hotspot, located in the central part of a major communication corridor connecting the western and eastern parts of the Balkans. The sediment succession from Lake Volvi is investigated here to provide a unique high‐resolution pollen and geochemical record for the last 2000 years combining palaeoecological and historical methods, implementing the concept of consilience. The palaeoecological data document the environmental dynamics since the occupation of the area by the Romans. The vegetation changes reveal the development of wetland habitats and the variations of the mixed deciduous oak and thermophilous–mesophilous forests, as well as cereal cultivation, grazing and arboriculture, whose intensity varied over time. Archaeological data are available for the 1st millennium ce , but detailed historical evidence becomes accessible from the 13th century ce onwards through Byzantine and Ottoman documents. Both historical and palaeoecological data indicate that the 16th century was the period of strongest population pressure on the environment of the Volvi region. However, for other periods, it is possible to observe disagreements between the proxies. We demonstrate that these contradictions can be resolved with a more complex understanding of the region's social–ecological dynamics.

Tree diversity shapes the spectral signature of light transmittance in developing forests - Laura J. Williams; Kyle R. Kovach; J. Antonio Guzmán Q.; Artur Stefanski; Raimundo Bermudez; Ethan E. Butler; Domitille Coq‐‐Etchegaray; Catherine Glenn‐Stone; Peter Hajek; Johanna Klama; Belinda E. Medlyn; Christian Messier; et al. (Ecology, 2025)
Greater tree diversity often increases forest productivity by increasing the fraction of light captured and the effectiveness of light use at the community scale. However, light may shape forest function not only as a source of energy or a cause of stress but also as a context cue: Plant photoreceptors can detect specific wavelengths of light, and plants use this information to assess their neighborhoods and adjust their patterns of growth and allocation. These cues have been well documented in laboratory studies, but little studied in diverse forests. Here, we examined how the spectral profile of light (350–2200 nm) transmitted through canopies differs among tree communities within three diversity experiments on two continents (200 plots each planted with one to 12 tree species, amounting to roughly 10,000 trees in total), laying the groundwork for expectations about how diversity in forests may shape light quality with consequences for forest function. We hypothesized—and found—that the species composition and diversity of tree canopies influenced transmittance in predictable ways. Canopy transmittance—in total and in spectral regions with known biological importance—principally declined with increasing leaf area per ground area (LAI) and, in turn, LAI was influenced by the species composition and diversity of communities. For a given LAI, broadleaved angiosperm canopies tended to transmit less light with lower red‐to‐far‐red ratios than canopies of needle‐leaved gymnosperms or angiosperm‐gymnosperm mixtures. Variation among communities in the transmittance of individual leaves had a minor effect on canopy transmittance in the visible portion of the spectrum but contributed beyond this range along with differences in foliage arrangement. Transmittance through mixed species canopies often deviated from expectations based on monocultures, and this was only partly explained by diversity effects on LAI, suggesting that diversity effects on transmittance also arose through shifts in the arrangement and optical properties of foliage. We posit that differences in the spectral profile of light transmitted through diverse canopies serve as a pathway by which tree diversity affects some forest ecosystem functions.

Toward an integrated pantropical ocean observing system - Gregory R. Foltz; Yassir A. Eddebbar; Janet Sprintall; Antonietta Capotondi; Sophie Cravatte; Peter Brandt; Adrienne J. Sutton; Tamaryn Morris; Juliet Hermes; Clive R. McMahon; Michael J. McPhaden; Lev B. Looney; et al. (Frontiers in Marine Science, 2025)
Global climate is regulated by the ocean, which stores, releases, and transports large amounts of mass, heat, carbon, and oxygen. Understanding, monitoring, and predicting the exchanges of these quantities across the ocean’s surface, their interactions with the atmosphere, and their horizontal and vertical pathways through the global oceans, are key for advancing fundamental knowledge and improving forecasts and longer-term projections of climate, weather, and ocean ecosystems. The existing global observing system provides immense value for science and society in this regard by supplying the data essential for these advancements. The tropical ocean observing system in particular has been developed over decades, motivated in large part by the far-reaching and complex global impacts of tropical climate variability and change. However, changes in observing needs and priorities, new challenges associated with climate change, and advances in observing technologies demand periodic evaluations to ensure that stakeholders’ needs are met. Previous reviews and assessments of the tropical observing system have focused separately on individual basins and their associated observing needs. Here we provide a broader perspective covering the tropical observing system as a whole. Common gaps, needs, and recommendations are identified, and interbasin differences driven by socioeconomic disparities are discussed, building on the concept of an integrated pantropical observing system. Finally, recommendations for improved observations of tropical basin interactions, through oceanic and atmospheric pathways, are presented, emphasizing the benefits that can be achieved through closer interbasin coordination and international partnerships.

Inhibition of soluble epoxide hydrolase ameliorates cerebral blood flow autoregulation and cognition in alzheimer's disease and diabetes-related dementia rat models - Chengyun Tang; Jane J. Border; Huawei Zhang; Andrew Gregory; Shan Bai; Xing Fang; Yedan Liu; Shaoxun Wang; Sung Hee Hwang; Wenjun Gao; Gilbert C. Morgan; Jhania Smith; et al. (GeroScience, 2025)

Quaternary rivers, tufas and mires of southern England: Description of Geological Conservation Review sites - Rebecca M. Briant; Colin A. Whiteman; B. Andrew Haggart; David R. Bridgland; Ella Egberts; Michael J. Grant; Marcus Hatch; Peter G. Knowles; Danielle C. Schreve; Philip S. Toms; Francis F. Wenban-Smith; Mark J. White (Proceedings of the Geologists' Association, 2025)

Squid beaks as a proxy for mercury concentrations in muscle of the giant warty squid Moroteuthopsis longimana - Sara Lopes-Santos; José C. Xavier; José Seco; João P. Coelho; Philip R. Hollyman; Eduarda Pereira; Richard A. Phillips; José P. Queirós (Marine Environmental Research, 2025)

Development and application of a genetic baseline to inform bull trout (Salvelinus confluentus) passage and conservation in the Snake River - John S. Hargrove; Thomas A. Delomas; Matthew R. Campbell; Philip J. Howell; Audrey C. Harris; Richard Wilkison (Conservation Genetics, 2025)

Leaving the niche: Recommendations for mainstreaming Low Trophic Aquaculture in countries around the Atlantic basin - Paul Tett; George Charalambides; Sofia C. Franco; Adam D. Hughes; Eirik Mikkelsen; Kåre Nolde Nielsen; Eric Arthur Bastos Routledge; Pernille Nielsen; Philip James (Marine Policy, 2025)

Micro-nanoscale polystyrene co-exposure impacts the uptake and translocation of arsenic and boscalid by lettuce (Lactuca sativa) - Trung Huu Bui; Nubia Zuverza-Mena; Emilie Kendrick; Carlos Tamez; Manavi Yadav; Sarah Alotaibi; Christian Dimkpa; Glen DeLoid; Omowunmi Sadik; Philip Demokritou; Jason C. White (NanoImpact, 2025)

Demonstrating a biobased concept for the production of sustainable bacterial cellulose from mixed textile, agricultural and municipal wastes - Alexandra Lanot; Shivam Tiwari; Philip Purnell; Abdalla M. Omar; Miriam Ribul; Daniel J. Upton; Heather Eastmond; Ishrat J. Badruddin; Hannah F. Walker; Angharad Gatenby; Sharon Baurley; Paulo J.D.S. Bartolo; et al. (Journal of Cleaner Production, 2025)

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Very fine roots differ among switchgrass (Panicum virgatum L.) cultivars and differentially affect soil pores and carbon processes - Jin Ho Lee; Tayler C. Ulbrich; Maik Geers-Lucas; G. Philip Robertson; Andrey K. Guber; Alexandra N. Kravchenko (Soil Biology and Biochemistry, 2024)

Architecture, light, and circadian biology: A scoping review - Philip Lewis; Rania Christoforou; Peiman Pilehchi Ha; Ursula Wild; Marcel Schweiker; Thomas C. Erren (Science of The Total Environment, 2024)

A model for transcription-dependent R-loop formation at double-stranded DNA breaks: Implications for their detection and biological effects - Boris P. Belotserkovskii; Philip C. Hanawalt (Journal of Theoretical Biology, 2024)

Applying trace element geochemistry of archaeological bone to study the coevolution of environmental change and human health in the Roman Empire - Sean R. Scott; Martin M. Shafer; Joel T. Overdier; Maria E. Teschler-Nicola; Peter C. Ramsl; Barry Cunliffe; Philip M. Farrell (Environmental Research, 2024)

Trends in population structure of Patagonian toothfish over 25 years of fishery exploitation at South Georgia - José Abreu; Philip R. Hollyman; José C. Xavier; Connor C.G. Bamford; Richard A. Phillips; Martin A. Collins (Fisheries Research, 2024)

Orthophosphate uptake onto woodchips in denitrifying bioreactors is enhanced by anoxic-(anaerobic-)oxic cycling - Zihao Zhang; Philip M. McGuire; Ruth E. Richardson; April Z. Gu; James P. Shapleigh; Matthew C. Reid (Science of The Total Environment, 2024)

Properties of outer solar system pebbles during planetesimal formation from meteor observations - Peter Jenniskens; Paul R. Estrada; Stuart Pilorz; Peter S. Gural; Dave Samuels; Steve Rau; Timothy M.C. Abbott; Jim Albers; Scott Austin; Dan Avner; Jack W. Baggaley; Tim Beck; et al. (Icarus, 2024)

Sheeppox virus genome sequences from the European outbreaks in Spain, Bulgaria, and Greece in 2022–2024 - Floris C. Breman; Andy Haegeman; Wannes Philips; Nina Krešić; Stefan Hoffman; Sigrid C. J. De Keersmaecker; Nancy H. C. Roosens; Montserrat Agüero; Ruben Villalba; Aleksandra Miteva; Emiliya Ivanova; Konstantia E. Tasioudi; et al. (Archives of Virology, 2024)

Melting of Totten Glacier, East Antarctica since the Last Glacial Maximum Revealed by Beryllium Isotope Ratios of Marine Sediment - Zihan Huang; Bethany C. Behrens; Yosuke Miyairi; Takahiro Aze; Stephen Obrochta; Takato Takemura; Reisuke Kondo; Alexandra Post; Leanne K. Armand; Philip O'Brien; Amy Leventer; Yusuke Yokoyama (Global and Planetary Change, 2024)

Tuning the composition of highly stable mixed-metal MOFs by microwave-assisted hydrothermal method for ultra-high selective and simultaneous capture of CO2 and H2S - Manh B. Nguyen; Linh Ho Thuy Nguyen; Hoa Thi Lai; Huan V. Doan; Ngoc Quang Tran; Ngoc Xuan Dat Mai; Lam Dai Tran; Philip Anggo Krisbiantoro; Kevin C.-W. Wu; Tan Le Hoang Doan (Chemical Engineering Journal, 2024)

Mercury concentrations in Seaside Sparrows and Marsh Rice Rats differ across the Mississippi River Estuary - Andrea Bonisoli-Alquati; Allyson K. Jackson; Collin A. Eagles-Smith; Sydney Moyo; Anna A. Pérez-Umphrey; Michael J. Polito; Allison M. Snider; S. Tyler Williams; Stefan Woltmann; Philip C. Stouffer; Sabrina S. Taylor (Ecotoxicology, 2024)
Mercury (Hg) concentrations and their associated toxicological effects in terrestrial ecosystems of the Gulf of Mexico are largely unknown. Compounding this uncertainty, a large input of organic matter from the 2010 Deepwater Horizon oil spill may have altered Hg cycling and bioaccumulation dynamics. To test this idea, we quantified blood concentrations of total mercury (THg) in Seaside Sparrows ( Ammospiza maritima ) and Marsh Rice Rats ( Oryzomys palustris ) in marshes west and east of the Mississippi River in 2015 and 2016. We also tested for a difference in THg concentrations between oiled and non-oiled sites. To address the potential confounding effect of diet variation on Hg transfer, we used stable nitrogen (δ 15 N) and carbon (δ 13 C) isotope values as proxies of trophic position and the source of primary production, respectively. Our results revealed that five to six years after the spill, THg concentrations were not higher in sites oiled by the spill compared to non-oiled sites. In both species, THg was higher at sites east of the Mississippi River compared to control and oiled sites, located west. In Seaside Sparrows but not in Marsh Rice Rats, THg increased with δ 15 N values, suggesting Hg trophic biomagnification. Overall, even in sites with the most elevated THg, concentrations were generally low. In Seaside Sparrows, THg concentrations were also lower than previously reported in this and other closely related passerines, with only 7% of tested birds exceeding the lowest observed effect concentration associated with toxic effects across bird species (0.2 µg/g ww ) . The factors associated with geographic heterogeneity in Hg exposure remain uncertain. Clarification could inform risk assessment and future restoration and management actions in a region facing vast anthropogenic changes.

Using pollen in turbidites for vegetation reconstructions - Laura S. McDonald; Lorna J. Strachan; Katherine Holt; Adam D. McArthur; Philip M. Barnes; Katherine L. Maier; Alan R. Orpin; Mark Horrocks; Aratrika Ganguly; Jenni L. Hopkins; Helen C. Bostock (Journal of Quaternary Science, 2024)
Turbidites, deposited by sub‐aqueous gravity flows, are common in sedimentary archives worldwide and present a unique challenge and opportunity when reconstructing past vegetation through pollen analysis. When sampling pollen from a sediment core for palaeovegetation records, it is common practice to target background sediments (i.e. pelagic sediment) and avoid sampling turbidites, as they are presumed to portray a misleading picture of past vegetation. This assumption stems from our limited understanding of pollen abundance and distribution through turbidites, meaning that palynologists overlook deposits that could potentially be used to reconstruct past vegetation and climate. We present pollen assemblage and sedimentological data from four recent (

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Omics biomarkers and an approach for their practical implementation to delineate health status for personalized nutrition strategies - Jaap Keijer; Xavier Escoté; Sebastià Galmés; Andreu Palou-March; Francisca Serra; Mona Adnan Aldubayan; Kristina Pigsborg; Faidon Magkos; Ella J. Baker; Philip C. Calder; Joanna Góralska; Urszula Razny; et al. (Critical Reviews in Food Science and Nutrition, 2024)

Independent effects of volume and energy density manipulation on energy intake and appetite in healthy adults: A randomized, controlled, crossover study - Adrienne Hatch-McChesney; Claire C. Whitney; Michelle Richardson; Ann Barrett; J. Philip Karl (Appetite, 2024)

Cadmium exposure induced light/dark- and time-dependent redox changes at subcellular level in Arabidopsis plants - Aurelio M. Collado-Arenal; Marino Exposito-Rodriguez; Philip M. Mullineaux; Adela Olmedilla; María C. Romero-Puertas; Luisa M. Sandalio (Journal of Hazardous Materials, 2024)

Post-fire Recovery Dynamics and Resilience of Ecosystem Services Capacity in Mediterranean-Type Ecosystems - Philip K. Roche; C. Sylvie Campagne; Anne Ganteaume (Ecosystems, 2024)

Adaptation to climate change and limits in food production systems: Physics, the chemistry of biology, and human behavior - Gerald C. Nelson; William W. L. Cheung; Rachel Bezner Kerr; James Franke; Francisco Meza; Muhammed A. Oyinlola; Philip Thornton; Florian Zabel (Global Change Biology, 2024)
Are there limits to our ability to adapt food systems to climate change? This overview paper for the special issue highlights results of research on potential limits and responses by food system actors. Responses are shaped by the critical interactions among the physical, chemical, biological, and social impacts in food systems arising from climate change. Food grains, temperate perennials, livestock, and oceanic capture fisheries and farming are covered. Climate change impacts on the biology of plants, animals, and humans, as well as the options for societal responses are explored. The results show where and how possible adaptations will be limited.

Determining evolutionary origin and phylogenetic relationships of mallard-like ducks of Oceania, greater Indonesia, and the Philippines with ddRAD-seq data - Marissa Kaminski; Joshua I. Brown; Sara R. Seibert; Flor Hernández; Melizar V. Duya; Ian Kendrich C. Fontanilla; David Roshier; Adam Miles; Leo Joseph; Jeffrey L. Peters; Philip Lavretsky (Molecular Phylogenetics and Evolution, 2024)

Decoding paleomire conditions of paleogene superhigh-organic-sulfur coals - Tushar Adsul; Molly D. O'Beirne; David A. Fike; Santanu Ghosh; Josef P. Werne; William P. Gilhooly; Paul C. Hackley; Javin J. Hatcherian; Bright Philip; Bodhisatwa Hazra; Sudip Bhattacharyya; Ritam Konar; et al. (International Journal of Coal Geology, 2024)

Planet’s Biomass Proxy for monitoring aboveground agricultural biomass and estimating crop yield - Pierre C. Guillevic; Benjamin Aouizerats; Rogier Burger; Nadja Den Besten; Daniel Jackson; Margot Ridderikhoff; Ariel Zajdband; Rasmus Houborg; Trenton E. Franz; G. Philip Robertson; Richard De Jeu (Field Crops Research, 2024)

Two pathways to understanding electron transfer in reaction centers from photosynthetic bacteria: A comparison of Rhodobacter sphaeroides and Rhodobacter capsulatus mutants - Kaitlyn M. Faries; Deborah K. Hanson; James C. Buhrmaster; Stephen Hippleheuser; Gregory A. Tira; Ryan M. Wyllie; Claire E. Kohout; Nikki Cecil M. Magdaong; Dewey Holten; Philip D. Laible; Christine Kirmaier (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

Evaluation of a novel palm-free fat supplement to reduce the carbon footprint of diets for dairy cows - Philip C. Garnsworthy; Neil Saunders; Jennifer R. Goodman (Animal Feed Science and Technology, 2024)

Evaluating the performance of airborne and spaceborne lidar for mapping biomass in the United States' largest dry woodland ecosystem - Michael J. Campbell; Jessie F. Eastburn; Philip E. Dennison; Jody C. Vogeler; Atticus E.L. Stovall (Remote Sensing of Environment, 2024)

Challenges in assessing and managing multi-hazard risks: A European stakeholders perspective - Robert Šakić Trogrlić; Karina Reiter; Roxana L. Ciurean; Stefania Gottardo; Silvia Torresan; Anne Sophie Daloz; Lin Ma; Noemi Padrón Fumero; Sharon Tatman; Stefan Hochrainer-Stigler; Marleen C. de Ruiter; Julius Schlumberger; et al. (Environmental Science & Policy, 2024)

Characteristics of the Tropical Tropopause over Chennai (13.0° N, 80.06° E) in the Northeast Monsoon Region - Purushotham Pooja; Sanjay Kumar Mehta; Sachin Philip Kakkanattu; K. B. Betsy; C. J. Seetha; P. P. Musaid (Pure and Applied Geophysics, 2024)

Floral scent changes in response to pollen removal are rare in buzz-pollinated Solanum - C. Douglas Moore; Dudley I. Farman; Tiina Särkinen; Philip C. Stevenson; Mario Vallejo-Marín (Planta, 2024)
Main conclusion One of seven Solanum taxa studied displayed associations between pollen presence and floral scent composition and volume, suggesting buzz-pollinated plants rarely use scent as an honest cue for foraging pollinators. Abstract Floral scent influences the recruitment, learning, and behaviour of floral visitors. Variation in floral scent can provide information on the amount of reward available or whether a flower has been visited recently and may be particularly important in species with visually concealed rewards. In many buzz-pollinated flowers, tubular anthers opening via small apical pores (poricidal anthers) visually conceal pollen and appear similar regardless of pollen quantity within the anther. We investigated whether pollen removal changes floral scent composition and emission rate in seven taxa of buzz-pollinated Solanum (Solanaceae). We found that pollen removal reduced both the overall emission of floral scent and the emission of specific compounds (linalool and farnesol) in S. lumholtzianum . Our findings suggest that in six out of seven buzz-pollinated taxa studied here, floral scent could not be used as a signal by visitors as it does not contain information on pollen availability.

Blue mussel (Mytilus edulis) silage, a possible low trophic marine protein source for Atlantic salmon (Salmo salar L.) - Sahar Sartipiyarahmadi; Antony J. Prabhu Philip; Aksel N. Forshei; Harald Sveier; Silje Steinsund; Malin Kleppe; Erik-Jan Lock; Angelico Madaro; Tom Johnny Hansen; Øivind Strand; Martin Wiech; Jan Vidar Jakobsen; et al. (Aquaculture, 2024)

Concomitant urea stabilization and phosphorus recovery from source-separated fresh urine in magnesium anode-based peroxide-producing electrochemical cells - Philip H. Arve; Marc Mason; Dyllon G. Randall; Prithvi Simha; Sudeep C. Popat (Water Research, 2024)

Lifetime of cm-sized zodiacal dust from the physical and dynamical evolution of meteoroid streams - Peter Jenniskens; Stuart Pilorz; Peter S. Gural; Dave Samuels; Steve Rau; Timothy M.C. Abbott; Jim Albers; Scott Austin; Dan Avner; Jack W. Baggaley; Tim Beck; Solvay Blomquist; et al. (Icarus, 2024)

Molecular docking and simulation studies of some pyrazolone-based bioactive ligands targeting the NF-$$κ$$B signaling pathways - Surya Philip; D. R. Sherin; T. K. Manoj Kumar; T. C. Badisha Banu; Reny Mary Roy (Molecular Diversity, 2024)

Missing phosphorus legacy of the Anthropocene: Quantifying residual phosphorus in the biosphere - Andrew J. Margenot; Shengnan Zhou; Suwei Xu; Leo M. Condron; Geneviève S. Metson; Philip M. Haygarth; Jordon Wade; Prince C. Agyeman (Global Change Biology, 2024)
A defining feature of the Anthropocene is the distortion of the biosphere phosphorus (P) cycle. A relatively sudden acceleration of input fluxes without a concomitant increase in output fluxes has led to net accumulation of P in the terrestrial‐aquatic continuum. Over the past century, P has been mined from geological deposits to produce crop fertilizers. When P inputs are not fully removed with harvest of crop biomass, the remaining P accumulates in soils. This residual P is a uniquely anthropogenic pool of P, and its management is critical for agronomic and environmental sustainability. Managing residual P first requires its quantification—but measuring residual P is challenging. In this review, we synthesize approaches to quantifying residual P, with emphasis on advantages, disadvantages, and complementarity. Common approaches to estimate residual P are mass balances, long‐term experiments, soil test P trends and chronosequences, with varying suitability or even limitations to distinct spatiotemporal scales. We demonstrate that individual quantification approaches are (i) constrained, (ii) often complementary, and (iii) may be feasible at only certain time–space scales. While some of these challenges are inherent to the quantification approach, in many cases there are surmountable challenges that can be addressed by unifying existing P pool and flux datasets, standardizing and synchronizing data collection on pools and fluxes, and quantifying uncertainty. Though defined as a magnitude, the distribution and speciation of residual P is relatively less understood but shapes its utilization and environmental impacts. The form of residual P will vary by agroecosystem context due to edaphoclimatic‐specific transformation of the accumulated P, which has implications for management (e.g., crop usage) and future policies (e.g., lag times in P loading from non‐point sources). Quantifying the uncertainty in measuring residual P holds value beyond scientific understanding, as it supports prioritization of monitoring and management resources and inform policy.

Studying interactions among anthropogenic stressors in freshwater ecosystems: A systematic review of 2396 multiple‐stressor experiments - James A. Orr; Samuel J. Macaulay; Adriana Mordente; Benjamin Burgess; Dania Albini; Julia G. Hunn; Katherin Restrepo‐Sulez; Ramesh Wilson; Anne Schechner; Aoife M. Robertson; Bethany Lee; Blake R. Stuparyk; et al. (Ecology Letters, 2024)
Understanding the interactions among anthropogenic stressors is critical for effective conservation and management of ecosystems. Freshwater scientists have invested considerable resources in conducting factorial experiments to disentangle stressor interactions by testing their individual and combined effects. However, the diversity of stressors and systems studied has hindered previous syntheses of this body of research. To overcome this challenge, we used a novel machine learning framework to identify relevant studies from over 235,000 publications. Our synthesis resulted in a new dataset of 2396 multiple‐stressor experiments in freshwater systems. By summarizing the methods used in these studies, quantifying trends in the popularity of the investigated stressors, and performing co‐occurrence analysis, we produce the most comprehensive overview of this diverse field of research to date. We provide both a taxonomy grouping the 909 investigated stressors into 31 classes and an open‐source and interactive version of the dataset ( https://jamesaorr.shinyapps.io/freshwater‐multiple‐stressors/ ). Inspired by our results, we provide a framework to help clarify whether statistical interactions detected by factorial experiments align with stressor interactions of interest, and we outline general guidelines for the design of multiple‐stressor experiments relevant to any system. We conclude by highlighting the research directions required to better understand freshwater ecosystems facing multiple stressors.

Integral Sliding Mode Output Feedback Control for Unmanned Marine Vehicles Using T–S Fuzzy Model with Unknown Premise Variables and Actuator Faults - Yang Wang; Xin Yang; Liying Hao; Tieshan Li; C. L. (Philip) Chen (Journal of Marine Science and Engineering, 2024)
This paper addresses integral sliding mode output feedback fault-tolerant control (FTC) of unmanned marine vessels (UMVs) with unknown premise variables and actuator faults. Due to the complexity of the marine environment, the presence of uncertainties in the yaw angle renders the premise variables in the Takagi–Sugeno (T–S) fuzzy model of UMVs unknown. Consequently, traditional integral sliding mode techniques become infeasible. To address this issue, a control strategy combining integral sliding mode based on output feedback with a compensator utilizing switching mechanisms is proposed. First, a radial basis function neural network is used to approximate the nonlinear terms in the UMV T–S fuzzy model. In addition, an integral sliding mode surface is constructed based on fault estimation information and membership function estimation. On this basis, an FTC scheme based on integral sliding mode output feedback is developed to ensure that the UMV system is asymptotically stable and satisfies the prescribed H∞ performance index. Finally, simulation results are provided to demonstrate the effectiveness of the presented control strategy.

Low- and high-load resistance training exercise to volitional fatigue generate exercise-induced appetite suppression - Seth F. McCarthy; Derek P.D. Bornath; Daniel Grisebach; Jessica A.L. Tucker; Claudia Jarosz; Sion C. Ormond; Philip J. Medeiros; Tom J. Hazell (Appetite, 2024)

Corrigendum to “Four-dimensional electrical resistivity imaging for monitoring pumping-induced saltwater intrusion in a coastal aquifer” [Sci. Total Environ. Volume 867 (2023) 161442] - Mark C. McDonnell; Raymond Flynn; Jesús Fernández Águila; Gerard A. Hamill; Shane Donohue; Eric M. Benner; Christopher Thomson; Georgios Etsias; Thomas S.L. Rowan; Paul B. Wilkinson; Philip I. Meldrum; Jonathan E. Chambers (Science of The Total Environment, 2024)

Antibiotic use in the Northern Irish sheep flock: What lessons can be learnt from medicine records and farmer attitudes to improve stewardship of these essential medicines? - Paul E. Crawford; Kim Hamer; Fiona Lovatt; Malgorzata C. Behnke; Philip A. Robinson (Preventive Veterinary Medicine, 2024)

SVEPM 2023, the annual conference of the Society for Veterinary Epidemiology and Preventive Medicine: Toulouse finally welcomes us in person - Fernanda C. Dórea; Timothée Vergne; Carla Correia-Gomes; Luís Pedro Carmo; Egil A.J. Fischer; Locksley L. McV. Messam; Dave C. Brodbelt; Philip A. Robinson (Preventive Veterinary Medicine, 2024)

What can we learn about fish neutrophil and macrophage response to immune challenge from studies in zebrafish - Zoë C. Speirs; Catherine A. Loynes; Heidi Mathiessen; Philip M. Elks; Stephen A. Renshaw; Louise von Gersdorff Jørgensen (Fish & Shellfish Immunology, 2024)

When is it safe to go home? Post-predation assessment of risk and safety when personal information conflicts with social cues - Brian D. Wisenden; Cat M. Adkins; Seth A. Campbell; Shree Chakraborty; Madelyn E. Cloutier; Alex D. Doebler; Kathryn A. Hanson; Lou Hoff; Molly I. M. Johnson; Philip S. Larson; Claire M. Lukasik; Zoe R. Michaelson; et al. (Behavioral Ecology and Sociobiology, 2024)

Meta‐analysis reveals that the effects of precipitation change on soil and litter fauna in forests depend on body size - Philip A. Martin; Leonora Fisher; Leticia Pérez‐Izquierdo; Charlotte Biryol; Bertrand Guenet; Sebastiaan Luyssaert; Stefano Manzoni; Claire Menival; Mathieu Santonja; Rebecca Spake; Jan C. Axmacher; Jorge Curiel Yuste (Global Change Biology, 2024)
Anthropogenic climate change is altering precipitation regimes at a global scale. While precipitation changes have been linked to changes in the abundance and diversity of soil and litter invertebrate fauna in forests, general trends have remained elusive due to mixed results from primary studies. We used a meta‐analysis based on 430 comparisons from 38 primary studies to address associated knowledge gaps, (i) quantifying impacts of precipitation change on forest soil and litter fauna abundance and diversity, (ii) exploring reasons for variation in impacts and (iii) examining biases affecting the realism and accuracy of experimental studies. Precipitation reductions led to a decrease of 39% in soil and litter fauna abundance, with a 35% increase in abundance under precipitation increases, while diversity impacts were smaller. A statistical model containing an interaction between body size and the magnitude of precipitation change showed that mesofauna (e.g. mites, collembola) responded most to changes in precipitation. Changes in taxonomic richness were related solely to the magnitude of precipitation change. Our results suggest that body size is related to the ability of a taxon to survive under drought conditions, or to benefit from high precipitation. We also found that most experiments manipulated precipitation in a way that aligns better with predicted extreme climatic events than with predicted average annual changes in precipitation and that the experimental plots used in experiments were likely too small to accurately capture changes for mobile taxa. The relationship between body size and response to precipitation found here has far‐reaching implications for our ability to predict future responses of soil biodiversity to climate change and will help to produce more realistic mechanistic soil models which aim to simulate the responses of soils to global change.

Long term trends in source apportioned particle number concentrations in Rochester NY - Philip K. Hopke; Yunle Chen; David C. Chalupa; David Q. Rich (Environmental Pollution, 2024)

Zerumbone liquid crystalline nanoparticles protect against oxidative stress, inflammation and senescence induced by cigarette smoke extract in vitro - Keshav Raj Paudel; Dvya Delilaa Clarence; Nisha Panth; Bikash Manandhar; Gabriele De Rubis; Hari Prasad Devkota; Gaurav Gupta; Flavia C. Zacconi; Kylie A. Williams; Lisa G. Pont; Sachin Kumar Singh; Majid Ebrahimi Warkiani; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
The purpose of this study was to evaluate the potential of zerumbone-loaded liquid crystalline nanoparticles (ZER-LCNs) in the protection of broncho-epithelial cells and alveolar macrophages against oxidative stress, inflammation and senescence induced by cigarette smoke extract in vitro . The effect of the treatment of ZER-LCNs on in vitro cell models of cigarette smoke extract (CSE)-treated mouse RAW264.7 and human BCi-NS1.1 basal epithelial cell lines was evaluated for their anti-inflammatory, antioxidant and anti-senescence activities using colorimetric and fluorescence-based assays, fluorescence imaging, RT-qPCR and proteome profiler kit. The ZER-LCNs successfully reduced the expression of pro-inflammatory markers including Il-6 , Il-1β and Tnf-α , as well as the production of nitric oxide in RAW 264.7 cells. Additionally, ZER-LCNs successfully inhibited oxidative stress through reduction of reactive oxygen species (ROS) levels and regulation of genes, namely GPX2 and GCLC in BCi-NS1.1 cells. Anti-senescence activity of ZER-LCNs was also observed in BCi-NS1.1 cells, with significant reductions in the expression of SIRT1 , CDKN1A and CDKN2A . This study demonstrates strong in vitro anti-inflammatory, antioxidative and anti-senescence activities of ZER-LCNs paving the path for this formulation to be translated into a promising therapeutic agent for chronic respiratory inflammatory conditions including COPD and asthma.

Evaluating the Educational Value of Cancer Registries — a Systematic Review and Thematic Analysis - James Lin; Hugo C. Temperley; Kirsten Larkins; Caitlin Waters; Kit Loong Chong; Jack Maida; David Proud; Adele Burgess; Alexander Heriot; Philip Smart; Helen Mohan (Journal of Cancer Education, 2024)

In vitro screening of per- and polyfluorinated substances (PFAS) for interference with seven thyroid hormone system targets across nine assays - Sigmund J. Degitz; Jennifer H. Olker; Jeffery S. Denny; Philip P. Degoey; Phillip C. Hartig; Mary C. Cardon; Stephanie A. Eytcheson; Jonathan T. Haselman; Sally A. Mayasich; Michael W. Hornung (Toxicology in Vitro, 2024)

What inhabits the South Sandwich Islands deep-sea? Biodiversity and biogeography of bathyal communities using predators as biological samplers - José P. Queirós; José C. Xavier; José Abreu; Martin A. Collins; Mark Belchier; Philip R. Hollyman (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Straw digestibility in rice: Novel insights from pyrolysis GC-MS and biomass phenotyping - Mariana P. Silva; Caragh Whitehead; Reynante L. Ordonio; Trinidad C. Fernando; Mark Philip B. Castillo; Jeremias L. Ordonio; Tony Larson; Daniel J. Upton; Susan E. Hartley; Leonardo D. Gomez (Biomass and Bioenergy, 2024)

A new winter wheat genetic resource harbors untapped diversity from synthetic hexaploid wheat - Tally I. C. Wright; Richard Horsnell; Bethany Love; Amanda J. Burridge; Keith A. Gardner; Robert Jackson; Fiona J. Leigh; Aleksander Ligeza; Sigrid Heuer; Alison R. Bentley; Philip Howell (Theoretical and Applied Genetics, 2024)
Key message The NIAB_WW_SHW_NAM population, a large nested association mapping panel, is a useful resource for mapping QTL from synthetic hexaploid wheat that can improve modern elite wheat cultivars. Abstract The allelic richness harbored in progenitors of hexaploid bread wheat ( Triticum aestivum L.) is a useful resource for addressing the genetic diversity bottleneck in modern cultivars. Synthetic hexaploid wheat (SHW) is created through resynthesis of the hybridisation events between the tetraploid ( Triticum turgidum subsp. durum Desf.) and diploid ( Aegilops tauschii Coss.) bread wheat progenitors. We developed a large and diverse winter wheat nested association mapping (NAM) population (termed the NIAB_WW_SHW_NAM) consisting of 3241 genotypes derived from 54 nested back-cross 1 (BC 1 ) populations, each formed via back-crossing a different primary SHW into the UK winter wheat cultivar ‘Robigus’. The primary SHW lines were created using 15 T. durum donors and 47 Ae. tauschii accessions that spanned the lineages and geographical range of the species. Primary SHW parents were typically earlier flowering, taller and showed better resistance to yellow rust infection ( Yr ) than ‘Robigus’. The NIAB_WW_SHW_NAM population was genotyped using a single nucleotide polymorphism (SNP) array and 27 quantitative trait loci (QTLs) were detected for flowering time, plant height and Yr resistance. Across multiple field trials, a QTL for Yr resistance was found on chromosome 4D that corresponded to the Yr28 resistance gene previously reported in other SHW lines. These results demonstrate the value of the NIAB_WW_SHW_NAM population for genetic mapping and provide the first evidence of Yr28 working in current UK environments and genetic backgrounds. These examples, coupled with the evidence of commercial wheat breeders selecting promising genotypes, highlight the potential value of the NIAB_WW_SHW_NAM to variety improvement.

A Histone H2A Derived Antimicrobial Peptide from the Blue Swimmer Crab, Portunus pelagicus Linnaeus 1758: In silico Characterization and Phylogenetic Analysis - V. V. Anooja; P. P. Athira; Kesavan Dhanya; S. Neelima; M. V. Anju; K. Archana; S. Muhammed Musthafa; C. K. Radhakrishnan; Rosamma Philip (Thalassas: An International Journal of Marine Sciences, 2024)

Effects of testosterone enanthate on aggression, risk-taking, competition, mood, and other cognitive domains during 28 days of severe energy deprivation - Harris R. Lieberman; John A. Caldwell; Oshin Vartanian; Owen T. Carmichael; J. Philip Karl; Claire E. Berryman; Kishore M. Gadde; Philip J. Niro; Melissa N. Harris; Jennifer C. Rood; Stefan M. Pasiakos (Psychopharmacology, 2024)
Rationale Behavioral effects of testosterone depend on dose, acute versus sustained formulation, duration of administration, personality, genetics, and endogenous levels of testosterone. There are also considerable differences between effects of endogenous and exogenous testosterone. Objectives This study was the secondary behavioral arm of a registered clinical trial designed to determine if testosterone protects against loss of lean body mass and lower-body muscle function induced by a severe energy deficit typical of sustained military operations. Methods Behavioral effects of repeated doses of testosterone on healthy young men whose testosterone was reduced by severe energy deficit were examined. This was a double-blind, placebo-controlled, between-group study. Effects of four weekly intramuscular injections of testosterone enanthate (200 mg/week, N = 24) or matching placebo ( N = 26) were evaluated. Determination of sample size was based on changes in lean body mass. Tasks assessing aggression, risk-taking, competition, social cognition, vigilance, memory, executive function, and mood were repeatedly administered. Results During a period of artificially induced, low testosterone levels, consistent behavioral effects of administration of exogenous testosterone were not observed. Conclusions Exogeneous testosterone enanthate (200 mg/week) during severe energy restriction did not reliably alter the measures of cognition. Study limitations include the relatively small sample size compared to many studies of acute testosterone administration. The findings are specific to healthy males experiencing severe energy deficit and should not be generalized to effects of other doses, formulations, or acute administration of endogenous testosterone or studies conducted with larger samples using tests of cognitive function designed to detect specific effects of testosterone.

Molecular identification of Crimean-Congo haemorrhagic fever virus in Hyalomma rufipes and Amblyomma variegatum in the Upper East Region of Ghana - Seth Offei Addo; Ronald Essah Bentil; Charlotte Adwoa Addae; Bernice Olivia Ama Baako; Kevin Nii Yartey; Jane Ansah‑Owusu; Christopher Nii Laryea Tawiah-Mensah; Bright Agbodzi; Selassie Kumordjie; Clara Yeboah; Victor Asoala; James C. Dunford; et al. (Archives of Virology, 2024)

Protecting and restoring freshwater biodiversity across urban areas in Aotearoa New Zealand: Citizens’ reporting of pollution in stormwater drains and waterways - Lynette J. McLeod; Donald W. Hine; Taciano L. Milfont; Zack Dorner; Natasha A. Tassell-Matamua; Robbie D.C. Maris; Jane C. Kitson; Philip Stahlmann-Brown (Journal of Environmental Management, 2024)

Biochar amendments to tropical paddy soil increase rice yields and decrease N2O emissions by modifying the genes involved in nitrogen cycling - Qunli Shen; Honghao Wang; Cristina Lazcano; Paul Voroney; Ahmed Elrys; Guanglin Gou; Houfu Li; Qilin Zhu; Yunzhong Chen; Yanzheng Wu; Lei Meng; Philip C. Brookes (Soil and Tillage Research, 2024)

Climate change and collapsing thermal niches of desert reptiles and amphibians: Assisted migration and acclimation rescue from extirpation - Barry Sinervo; Rafael A. Lara Reséndiz; Donald B. Miles; Jeffrey E. Lovich; Philip C. Rosen; Héctor Gadsden; Gamaliel Casteñada Gaytán; Patricia Galina Tessaro; Víctor H. Luja; Raymond B. Huey; Amy Whipple; Víctor Sánchez Cordero; et al. (Science of The Total Environment, 2024)

Risk assessment of nutrients: There must be a threshold for their effects - Michiel RH. Löwik; Arne Astrup; Alan R. Boobis; Philip C. Calder; Hannelore Daniel; Ivonne MCM. Rietjens; John L. Sievenpiper; Hans Verhagen (Regulatory Toxicology and Pharmacology, 2024)

Holocene climate and catchment change inferred from the geochemistry of Lashmars Lagoon, Kangaroo Island (Karti/Karta), southern Australia - Lucinda Cameron Duxbury; Lluka Yohanni Johns-Mead; Haidee Cadd; Alexander Francke; Stefan C. Löhr; Wallace Boone Law; Linda Armbrecht; Philip Anthony Hall; Atun Zawadzki; Geraldine E. Jacobsen; Patricia S. Gadd; David P. Child; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Less is more: Less herbicide does more when biological control is present in Pontederia crassipes - Linhao Xu; Ashley B.C. Goode; Philip W. Tipping; Melissa C. Smith; Lyn A. Gettys; Brittany K. Knowles; Eileen Pokorny; Luz Salinas; Donald L. DeAngelis (Ecological Modelling, 2024)

Zerumbone-incorporated liquid crystalline nanoparticles inhibit proliferation and migration of non-small-cell lung cancer in vitro - Bikash Manandhar; Keshav Raj Paudel; Dvya Delilaa Clarence; Gabriele De Rubis; Thiagarajan Madheswaran; Jithendra Panneerselvam; Flavia C. Zacconi; Kylie A. Williams; Lisa G. Pont; Majid Ebrahimi Warkiani; Ronan MacLoughlin; Brian Gregory Oliver; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
Lung cancer is the second most prevalent type of cancer and is responsible for the highest number of cancer-related deaths worldwide. Non-small-cell lung cancer (NSCLC) makes up the majority of lung cancer cases. Zerumbone (ZER) is natural compound commonly found in the roots of Zingiber zerumbet which has recently demonstrated anti-cancer activity in both in vitro and in vivo studies. Despite their medical benefits, ZER has low aqueous solubility, poor GI absorption and oral bioavailability that hinders its effectiveness. Liquid crystalline nanoparticles (LCNs) are novel drug delivery carrier that have tuneable characteristics to enhance and ease the delivery of bioactive compounds. This study aimed to formulate ZER-loaded LCNs and investigate their effectiveness against NSCLC in vitro using A549 lung cancer cells. ZER-LCNs, prepared in the study, inhibited the proliferation and migration of A549 cells. These inhibitory effects were superior to the effects of ZER alone at a concentration 10 times lower than that of free ZER, demonstrating a potent anti-cancer activity of ZER-LCNs. The underlying mechanisms of the anti-cancer effects by ZER-LCNs were associated with the transcriptional regulation of tumor suppressor genes P53 and PTEN , and metastasis-associated gene KRT18 . The protein array data showed downregulation of several proliferation associated proteins such as AXL, HER1, PGRN, and BIRC5 and metastasis-associated proteins such as DKK1, CAPG, CTSS, CTSB, CTSD, and PLAU. This study provides evidence of potential for increasing the potency and effectiveness of ZER with LCN formulation and developing ZER-LCNs as a treatment strategy for mitigation and treatment of NSCLC.

Assessing spatial patterns and density of a dolphin population through signature whistles - Bianca Romeu; Fábio G. Daura‐Jorge; Philip S. Hammond; Pedro V. Castilho; Paulo C. Simões‐Lopes (Marine Mammal Science, 2024)
Some dolphin species produce signature whistles, which may allow the identification of individual dolphins using passive acoustic monitoring (PAM). Identifying individuals by their sounds may enhance the opportunities for monitoring and addressing biological and ecological questions about these species. Here, we explored the potential of signature whistles to investigate ecological aspects of a resident bottlenose dolphin population. Using a limited data set, with few individuals recognized by signature whistles, combined with spatial capture‐recapture (SCR) methods, we investigated how effective such approach is describing spatial use patterns and estimating density for this population. The data were collected using 4–6 stationary bottom‐moored recorders. Since only eight signature whistles were identified, our density estimate may represent a subset of the entire population. However, even with only a few signature whistles identified, our results confirmed the center of the core area used by these dolphins as the area with the highest encounter probability. In addition, our results provided evidence that these dolphins have the same spatial use pattern at night as during the day. This study shows that SCR analysis of signature whistle data can improve our ecological knowledge and understanding of dolphin populations.

What factors influence the rediscovery of lost tetrapod species? - Tim Lindken; Christopher V. Anderson; Daniel Ariano‐Sánchez; Goni Barki; Christina Biggs; Philip Bowles; Ramamoorthi Chaitanya; Drew T. Cronin; Sonja C. Jähnig; Jonathan M. Jeschke; Rosalind J. Kennerley; Thomas E. Lacher; et al. (Global Change Biology, 2024)
We created a database of lost and rediscovered tetrapod species, identified patterns in their distribution and factors influencing rediscovery. Tetrapod species are being lost at a faster rate than they are being rediscovered, due to slowing rates of rediscovery for amphibians, birds and mammals, and rapid rates of loss for reptiles. Finding lost species and preventing future losses should therefore be a conservation priority. By comparing the taxonomic and spatial distribution of lost and rediscovered tetrapod species, we have identified regions and taxa with many lost species in comparison to those that have been rediscovered—our results may help to prioritise search effort to find them. By identifying factors that influence rediscovery, we have improved our ability to broadly distinguish the types of species that are likely to be found from those that are not (because they are likely to be extinct). Some lost species, particularly those that are small and perceived to be uncharismatic, may have been neglected in terms of conservation effort, and other lost species may be hard to find due to their intrinsic characteristics and the characteristics of the environments they occupy (e.g. nocturnal species, fossorial species and species occupying habitats that are more difficult to survey such as wetlands). These lost species may genuinely await rediscovery. However, other lost species that possess characteristics associated with rediscovery (e.g. large species) and that are also associated with factors that negatively influence rediscovery (e.g. those occupying small islands) are more likely to be extinct. Our results may foster pragmatic search protocols that prioritise lost species likely to still exist.

Range of the perfluorooctanoate (PFOA) safe dose for human health: An international collaboration - Lyle D. Burgoon; Harvey J. Clewell; Tony Cox; Wolfgang Dekant; Linda D. Dell; James A. Deyo; Michael L. Dourson; Bernard K. Gadagbui; Philip Goodrum; Laura C. Green; K. Vijayavel; Travis R. Kline; et al. (Regulatory Toxicology and Pharmacology, 2023)

Net effects explains the benefits to children from maternal fish consumption despite methylmercury in fish - Philip Spiller; Edwin van Wijngaarden; Heather R. Adams; J.J. Strain; Emeir M. McSorley; Maria S. Mulhern; Marie C. Conway; Allison J. Yeates; Clark Carrington; P. Michael Bolger; Kara M. Morgan; Caroline M. Taylor; et al. (NeuroToxicology, 2023)

Arsenic speciation and arsenic feed-to-fish transfer in Atlantic salmon fed marine low trophic feeds based blue mussel and kelp - Marta S. Silva; Jojo Tibon; Sahar Sartipiyarahmadi; Sofie C. Remø; Veronika Sele; Liv Søfteland; Harald Sveier; Martin Wiech; Antony J. Prabhu Philip; Marc Berntssen (Journal of Trace Elements in Medicine and Biology, 2023)

Ultimate strength and fatigue of stiffened welded tubular joints in floating energy production structures - Theocharis Papatheocharis; George T. Plakias; Anna D. Zervaki; Philip C. Perdikaris; Spyros A. Karamanos (Engineering Structures, 2023)

Long-term impacts of urban floodplain management and habitat restoration on lizard communities in a Sonoran Desert city - Jules T. Wyman; Aaron D. Flesch; Jennifer L. Becker; Philip C. Rosen (Ecological Engineering, 2023)

Harnessing indigenous knowledge and practices for effective adaptation in the Sahel - Robert Zougmoré; Alcade C Segnon; Philip Thornton (Current Opinion in Environmental Sustainability, 2023)

Mouse phenome database: curated data repository with interactive multi-population and multi-trait analyses - Molly A. Bogue; Robyn L. Ball; David O. Walton; Matthew H. Dunn; Georgi Kolishovski; Alexander Berger; Anna Lamoureux; Stephen C. Grubb; Matthew Gerring; Matthew Kim; Hongping Liang; Jake Emerson; et al. (Mammalian Genome, 2023)
The Mouse Phenome Database continues to serve as a curated repository and analysis suite for measured attributes of members of diverse mouse populations. The repository includes annotation to community standard ontologies and guidelines, a database of allelic states for 657 mouse strains, a collection of protocols, and analysis tools for flexible, interactive, user directed analyses that increasingly integrates data across traits and populations. The database has grown from its initial focus on a standard set of inbred strains to include heterogeneous mouse populations such as the Diversity Outbred and mapping crosses and well as Collaborative Cross, Hybrid Mouse Diversity Panel, and recombinant inbred strains. Most recently the system has expanded to include data from the International Mouse Phenotyping Consortium. Collectively these data are accessible by API and provided with an interactive tool suite that enables users’ persistent selection, storage, and operation on collections of measures. The tool suite allows basic analyses, advanced functions with dynamic visualization including multi-population meta-analysis, multivariate outlier detection, trait pattern matching, correlation analyses and other functions. The data resources and analysis suite provide users a flexible environment in which to explore the basis of phenotypic variation in health and disease across the lifespan.

Integrating machine learning and multi-linear regression modeling approaches in groundwater quality assessment around Obosi, SE Nigeria - Obinna Chigoziem Akakuru; Casmir C Zanders Akaolisa; Godwin Okumagbe Aigbadon; Moses Oghenenyoreme Eyankware; Alexander Iheanyichukwu Opara; Philip Njoku Obasi; Ifeyinwa Juliana Ofoh; Adaora Olivia Njoku; Bernard E. B Akudinobi (Environment, Development and Sustainability, 2023)

Exceptionally Preserved Conodont Natural Assemblages from the Middle Triassic Luoping Biota, Yunnan Province, China: Implications for Architecture of Conodont Feeding Apparatus - Jinyuan Huang; Carlos Martínez-Pérez; Qiyue Zhang; Kexin Zhang; Mao Luo; Wen Wen; Changyong Zhou; Xiao Min; Zhixin Ma; Tao Xie; Michael J. Benton; Philip C. J. Donoghue (Journal of Earth Science, 2023)

Review of Solar Energetic Particle Prediction Models - Kathryn Whitman; Ricky Egeland; Ian G. Richardson; Clayton Allison; Philip Quinn; Janet Barzilla; Irina Kitiashvili; Viacheslav Sadykov; Hazel M. Bain; Mark Dierckxsens; M. Leila Mays; Tilaye Tadesse; et al. (Advances in Space Research, 2023)

A review of methods for detecting rats at low densities, with implications for surveillance - Robert A. Davis; Philip J. Seddon; Michael D. Craig; James C. Russell (Biological Invasions, 2023)
Invasive rats are the biggest threat to island biodiversity world-wide. Though the ecological impacts of rats on insular biota are well documented, introduced rats present a difficult problem for detection and management. In recent decades, improved approaches have allowed for island-wide eradications of invasive rats on small-medium sized islands and suppression on large islands, although both these still represent a formidable logistical and financial challenge. A key aspect of eradication or suppression and ongoing management is the ability to detect the presence of rats, especially at low densities. Here we review recent developments in the field of rat surveillance and summarise current published literature to recommend practices and the factors to consider when developing a surveillance program for either eradication or suppression plans. Of 51 empirical studies covering 17 countries, 58% were from New Zealand. Although detecting rats at low density is extremely challenging, advances over the past 15 years, have significantly improved our ability to detect rats. Motion-sensored cameras and rodent detection dogs have greatly improved our ability to detect rats at low densities, with cameras consistently showing an ability to detect rats at lower densities than other techniques. Rodent detection dogs are also able to reliably detect even an individual rat, although there are challenges to their widespread adoption, particularly in developing countries, due to the cost and skills required for their training and maintenance. New monitoring devices, the use of eDNA and drones represent current and future innovations to improve detection.

Observing the full ocean volume using Deep Argo floats - Nathalie V. Zilberman; Virginie Thierry; Brian King; Matthew Alford; Xavier André; Kevin Balem; Nathan Briggs; Zhaohui Chen; Cécile Cabanes; Laurent Coppola; Giorgio Dall’Olmo; Damien Desbruyères; et al. (Frontiers in Marine Science, 2023)
The ocean is the main heat reservoir in Earth’s climate system, absorbing most of the top-of-the-atmosphere excess radiation. As the climate warms, anomalously warm and fresh ocean waters in the densest layers formed near Antarctica spread northward through the abyssal ocean, while successions of warming and cooling events are seen in the deep-ocean layers formed near Greenland. The abyssal warming and freshening expands the ocean volume and raises sea level. While temperature and salinity characteristics and large-scale circulation of upper 2000 m ocean waters are well monitored, the present ocean observing network is limited by sparse sampling of the deep ocean below 2000 m. Recently developed autonomous robotic platforms, Deep Argo floats, collect profiles from the surface to the seafloor. These instruments supplement satellite, Core Argo float, and ship-based observations to measure heat and freshwater content in the full ocean volume and close the sea level budget. Here, the value of Deep Argo and planned strategy to implement the global array are described. Additional objectives of Deep Argo may include dissolved oxygen measurements, and testing of ocean mixing and optical scattering sensors. The development of an emerging ocean bathymetry dataset using Deep Argo measurements is also described.

Ambient air particulate total lung deposited surface area (LDSA) levels in urban Europe - Xiansheng Liu; Hadiatullah Hadiatullah; Xun Zhang; Pedro Trechera; Marjan Savadkoohi; Meritxell Garcia-Marlès; Cristina Reche; Noemí Pérez; David C.S. Beddows; Imre Salma; Wanda Thén; Panayiotis Kalkavouras; et al. (Science of The Total Environment, 2023)

The influence of river-derived particles on estuarine and marine elemental cycles: Evidence from lithium isotopes - Chun-Yao Liu; David J. Wilson; Ed C. Hathorne; Antao Xu; Philip A.E. Pogge von Strandmann (Geochimica et Cosmochimica Acta, 2023)

An adaptable integrated modelling platform to support rapidly evolving agricultural and environmental policy - Paula A. Harrison; Kate Beauchamp; Joe Cooper; Ian Dickie; Alice Fitch; Richard Gooday; Michael Hollaway; Ian P. Holman; Merryn Hunt; Laurence Jones; Thomas Mondain-Monval; Daniel Sandars; et al. (Environmental Modelling & Software, 2023)

The combined effects of treated sewage discharge and land use on rivers - Dania Albini; Lauren Lester; Philip Sanders; Jocelyne Hughes; Michelle C. Jackson (Global Change Biology, 2023)
Freshwater ecosystems are increasingly threatened by multiple anthropogenic stressors. Release of treated sewage effluent and pollution from agricultural or urban sources can independently reduce water quality with implications for ecological communities. However, our knowledge of the combined effects of these stressors is limited. We performed a field study to quantify the combined effect of treated sewage discharge and land use on nutrient concentrations, sewage fungus presence and communities of macroinvertebrates and benthic algae. Over three seasons in four rivers we found that a model which included an interaction between sewage pollution and time of the year (i.e. months) was the best predictor of nutrient concentrations and the abundance of algae and sewage fungus. Both macroinvertebrate and algae communities shifted downstream of sewage input. Specifically, more tolerant groups, such as cyanobacteria and oligochaetes, were more abundant. The EPT (Ephemeroptera, Plecoptera and Tricoptera) water quality score was best explained by an interaction between month and agriculture in the surrounding landscape. Overall, our results show that sewage discharge has a significant impact on water quality and benthic riverine communities, regardless of the surrounding land uses. Agricultural inputs, however, could be more important than treated sewage discharge in reducing the abundance of sensitive invertebrate taxa. We need both improvements to wastewater treatment processes and reductions in agricultural pollution to reduce threats to vulnerable freshwater communities.

Globalization and its environmental effects: assessing the role of de facto and de jure conditions in trade, financial and information (ICT) developments in West Africa - Philip C. Omoke; Chinazaekpere Nwani; Ekpeno L. Effiong (Climate and Development, 2023)

25 Years of thermomorphogenesis research: milestones and perspectives - Marcel Quint; Carolin Delker; Sureshkumar Balasubramanian; Martin Balcerowicz; Jorge J. Casal; Christian Danve M. Castroverde; Meng Chen; Xuemei Chen; Ive De Smet; Christian Fankhauser; Keara A. Franklin; Karen J. Halliday; et al. (Trends in Plant Science, 2023)

Global variability and controls on the accumulation of fallout radionuclides in cryoconite - Caroline C. Clason; Giovanni Baccolo; Edyta Łokas; Philip N. Owens; Przemyslaw Wachniew; Geoff E. Millward; Alex Taylor; Will H. Blake; Dylan B. Beard; Ewa Poniecka; Nick Selmes; Elizabeth A. Bagshaw; et al. (Science of The Total Environment, 2023)

Long-term glacial and fluvial system coupling in southern Greece and evidence for glaciation during Marine Isotope Stage 16 - Richard J.J. Pope; Philip D. Hughes; Jamie C. Woodward; Stephen Noble; Diana Sahy; Emmanuel Skourtsos (Quaternary Science Reviews, 2023)

Sterol composition in plants is specific to pollen, leaf, pollination and pollinator - Samuel Furse; Carlos Martel; Abdikarim Yusuf; Gemma C. Shearman; Hauke Koch; Philip C. Stevenson (Phytochemistry, 2023)

Cryptic crustal growth identified through Variscan post-collisional lamprophyre-granite composite dykes, French Massif Central - Mariana Werle; Gary Stevens; Jean-François Moyen; Oscar Laurent; Chris Harris; Cristiano C. Lana; Philip E. Janney (Lithos, 2023)

Quantifying the impacts of an invasive weed on habitat quality and prey availability for tiger snakes (Notechis scutatus) in urban wetlands - Jari Cornelis; Brenton von Takach; Christine E. Cooper; Jordan Vos; Philip W. Bateman; Damian C. Lettoof (Wetlands Ecology and Management, 2023)
Invasive plants are a threat to natural ecosystems worldwide, with urban wetlands being some of the most susceptible and highly modified environments of all. The tiger snake ( Notechis scutatus ) is a top predator that persists in urban wetlands of south-western Australia, many of which have been degraded by introduced kikuyu grass ( Cenchrus clandestinus ). To evaluate the potential impact of kikuyu grass on habitat quality for tiger snakes we quantified the structural features of habitats within wetlands degraded by kikuyu grass and compared them to wetlands with native vegetation. We also examined tiger snake prey availability, assessed predation risk for juvenile snakes using clay models, and measured the thermal quality of the vegetation. Proliferation of kikuyu grass has reduced habitat structural heterogeneity by reducing available bare ground and increasing vegetation density. This homogenisation of habitat structure had little effect on the predation risk for juveniles or the thermal properties of tiger snake shelter sites; however, one key prey species, the motorbike frog, had significantly lower abundance in the most impacted habitat. Habitat types with more structural complexity also offered tiger snakes more stable thermal regimes and lower predation risk. These findings indicate that the current extent of kikuyu grass invasion offers overall similar habitat quality for tiger snakes to native vegetation and may contribute to their persistence in urban wetlands; however, both tiger snakes and their anuran prey may benefit from increased habitat structural complexity.

Characteristics of the atmospheric boundary layer during transient conditions of the Indian summer monsoon - C. J. Seetha; Sanjay Kumar Mehta; Sachin Philip Kakkanattu; Pooja Purushotham; K. B. Betsy; P. P. Musaid (Theoretical and Applied Climatology, 2023)

Genomic approaches to mitigating genetic diversity loss in declining populations - Christen M. Bossu; Marina Rodriguez; Christine Rayne; Debra A. Chromczak; Philip G. Higgins; Lynne A. Trulio; Kristen C. Ruegg (Molecular Ecology, 2023)
The accelerating pace of global biodiversity loss is exacerbated by habitat fragmentation and subsequent inbreeding in small populations. To address this problem, conservation practitioners often turn to assisted breeding programmes with the aim of enhancing genetic diversity in declining populations. Although genomic information is infrequently included in these efforts, it has the potential to significantly enhance the success of such programmes. In this study, we showcase the value of genomic approaches for increasing genetic diversity in assisted breeding efforts, specifically focusing on a highly inbred population of Western burrowing owls. To maximize genetic diversity in the resulting offspring, we begin by creating an optimal pairing decision tree based on sex, kinship and patterns of homozygosity across the genome. To evaluate the effectiveness of our strategy, we compare genetic diversity, brood size and nestling success rates between optimized and non‐optimized pairs. Additionally, we leverage recently discovered correlations between telomere length and fitness across species to investigate whether genomic optimization could have long‐term fitness benefits. Our results indicate that pairing individuals with contrasting patterns of homozygosity across the genome is an effective way to increase genetic diversity in offspring. Although short‐term field‐based metrics of success did not differ significantly between optimized and non‐optimized pairs, offspring from optimized pairs had significantly longer telomeres, suggesting that genetic optimization can help reduce the risk of inbreeding depression. These findings underscore the importance of genomic tools for informing efforts to preserve the adaptive potential of small, inbred populations at risk of further decline.

Impacts of coral bleaching on reef fish abundance, biomass and assemblage structure at remote Aldabra Atoll, Seychelles: insights from two survey methods - Anna Koester; Cesc Gordó−Vilaseca; Nancy Bunbury; Sebastian C. A. Ferse; Amanda Ford; Philip Haupt; Luke A’Bear; Maria Bielsa; April Jasmine Burt; Jake Letori; Emma Mederic; Ella Nancy; et al. (Frontiers in Marine Science, 2023)
Introduction Coral bleaching immediately impacts the reef benthos, but effects on fish communities are less well understood because they are often delayed and confounded by anthropogenic interactions. Methods We assessed changes in fish abundance, biomass and community composition before and after the 2015/16 coral bleaching event at Aldabra Atoll, Seychelles, where local human impacts are minimal, but reefs suffered 50% bleaching-induced coral mortality. We monitored 12 shallow (2–5 m water depth) and nine deep (15 m water depth) permanent survey sites using two survey methods: indicator surveys recording 84 taxa over six years (pre-: 2014; post-bleaching: 2016–2019, 2021), sizing fish based on six size-class categories, and extended fish surveys recording 198 taxa over two years (pre-: 2015; post-bleaching: 2020) with size estimates to the nearest cm (excluding fish < 8 cm). Results During indicator surveys, mean fish abundance did not change on deep reefs. However, abundance increased by 77% on shallow reefs between 2014 and 2016, which was mainly driven by increases in herbivores and omnivores, likely as a response to elevated turf algae cover following coral mortality. Overall (and functional group-specific) indicator fish biomass did not differ between 2014 and 2016 and remained at or above pre-bleaching levels throughout 2016–2021. In contrast, extended fish surveys in 2015 and 2020 showed a 55–60% reduction in overall abundance on shallow and deep reefs, and a 69% reduction in biomass on shallow reefs, with decreases in biomass occurring in all functional groups. Biomass on deep reefs did not differ between 2015 and 2020. Multivariate analysis of both data sets revealed immediate and long-lasting differences between pre- and post-bleaching fish community compositions, driven largely by herbivorous, omnivorous and piscivorous taxa. Discussion Results from the indicator surveys suggest that the bleaching event had limited impact on fish abundance and biomass, while the extended surveys recorded changes in abundance and biomass which would otherwise have gone undetected. Our findings improve understanding of the shift a broad community of fish undergoes following a mass coral bleaching event and highlights the value of survey methods that include the full suite of species to detect ecological responses to environmental drivers.

Global change scenarios in coastal river deltas and their sustainable development implications - Murray W. Scown; Frances E. Dunn; Stefan C. Dekker; Detlef P. van Vuuren; Sitar Karabil; Edwin H. Sutanudjaja; Maria J. Santos; Philip S.J. Minderhoud; Ahjond S. Garmestani; Hans Middelkoop (Global Environmental Change, 2023)

Giants of the Amazon: How does environmental variation drive the diversity patterns of large trees? - Robson Borges de Lima; Eric Bastos Görgens; Diego Armando S. da Silva; Cinthia Pereira de Oliveira; Anderson Pedro B. Batista; Rinaldo L. Caraciolo Ferreira; Flavia R. C. Costa; Renato A. Ferreira de Lima; Perseu da Silva Aparício; Jadson Coelho de Abreu; José Antônio Aleixo da Silva; Aretha Franklin Guimaraes; et al. (Global Change Biology, 2023)
For more than three decades, major efforts in sampling and analyzing tree diversity in South America have focused almost exclusively on trees with stems of at least 10 and 2.5 cm diameter, showing highest species diversity in the wetter western and northern Amazon forests. By contrast, little attention has been paid to patterns and drivers of diversity in the largest canopy and emergent trees, which is surprising given these have dominant ecological functions. Here, we use a machine learning approach to quantify the importance of environmental factors and apply it to generate spatial predictions of the species diversity of all trees (dbh ≥ 10 cm) and for very large trees (dbh ≥ 70 cm) using data from 243 forest plots (108,450 trees and 2832 species) distributed across different forest types and biogeographic regions of the Brazilian Amazon. The diversity of large trees and of all trees was significantly associated with three environmental factors, but in contrasting ways across regions and forest types. Environmental variables associated with disturbances, for example, the lightning flash rate and wind speed, as well as the fraction of photosynthetically active radiation, tend to govern the diversity of large trees. Upland rainforests in the Guiana Shield and Roraima regions had a high diversity of large trees. By contrast, variables associated with resources tend to govern tree diversity in general. Places such as the province of Imeri and the northern portion of the province of Madeira stand out for their high diversity of species in general. Climatic and topographic stability and functional adaptation mechanisms promote ideal conditions for species diversity. Finally, we mapped general patterns of tree species diversity in the Brazilian Amazon, which differ substantially depending on size class.

Oxic–anoxic cycling promotes coupling between complex carbon metabolism and denitrification in woodchip bioreactors - Philip M. McGuire; Natalie Butkevich; Aryaman V. Saksena; M. Todd Walter; James P. Shapleigh; Matthew C. Reid (Environmental Microbiology, 2023)
Denitrifying woodchip bioreactors (WBRs) are increasingly used to manage the release of non‐point source nitrogen (N) by stimulating microbial denitrification. Woodchips serve as a renewable organic carbon (C) source, yet the recalcitrance of organic C in lignocellulosic biomass causes many WBRs to be C‐limited. Prior studies have observed that oxic–anoxic cycling increased the mobilization of organic C, increased nitrate (NO 3 − ) removal rates, and attenuated production of nitrous oxide (N 2 O). Here, we use multi‐omics approaches and amplicon sequencing of fungal 5.8S‐ITS2 and prokaryotic 16S rRNA genes to elucidate the microbial drivers for enhanced NO 3 − removal and attenuated N 2 O production under redox‐dynamic conditions. Transient oxic periods stimulated the expression of fungal ligninolytic enzymes, increasing the bioavailability of woodchip‐derived C and stimulating the expression of denitrification genes. Nitrous oxide reductase ( nosZ ) genes were primarily clade II, and the ratio of clade II/clade I nosZ transcripts during the oxic–anoxic transition was strongly correlated with the N 2 O yield. Analysis of metagenome‐assembled genomes revealed that many of the denitrifying microorganisms also have a genotypic ability to degrade complex polysaccharides like cellulose and hemicellulose, highlighting the adaptation of the WBR microbiome to the ecophysiological niche of the woodchip matrix.

Climate change effects on denitrification performance of woodchip bioreactors treating agricultural tile drainage - Jenna K. Israel; Zihao Zhang; Yi Sang; Philip M. McGuire; Scott Steinschneider; Matthew C. Reid (Water Research, 2023)

Landscape fires disproportionally affect high conservation value temperate peatlands, meadows, and deciduous forests, but only under low moisture conditions - Máire Kirkland; Philip W. Atkinson; James W. Pearce-Higgins; Mark C. de Jong; Thomas P.F. Dowling; Dmitri Grummo; Megan Critchley; Adham Ashton-Butt (Science of The Total Environment, 2023)

Grayanotoxin I variation across tissues and species of Rhododendron suggests pollinator-herbivore defence trade-offs - Róisín Fattorini; Paul A. Egan; James Rosindell; Iain W. Farrell; Philip C. Stevenson (Phytochemistry, 2023)

Hot crabs with bold choices: Temperature has little impact on behavioural repeatability in Caribbean hermit crabs - Nicholas B. Sakich; Philip C. Bartel; Miriam H. Richards; Glenn J. Tattersall (Behavioural Processes, 2023)

The longitudinal relation between executive functioning and multilayer network topology in glioma patients - Marike R. van Lingen; Lucas C. Breedt; Jeroen J.G. Geurts; Arjan Hillebrand; Martin Klein; Mathilde C.M. Kouwenhoven; Shanna D. Kulik; Jaap C. Reijneveld; Cornelis J. Stam; Philip C. De Witt Hamer; Mona L.M. Zimmermann; Fernando A.N. Santos; et al. (Brain Imaging and Behavior, 2023)
Many patients with glioma, primary brain tumors, suffer from poorly understood executive functioning deficits before and/or after tumor resection. We aimed to test whether frontoparietal network centrality of multilayer networks, allowing for integration across multiple frequencies, relates to and predicts executive functioning in glioma. Patients with glioma (n = 37) underwent resting-state magnetoencephalography and neuropsychological tests assessing word fluency, inhibition, and set shifting before (T1) and one year after tumor resection (T2). We constructed binary multilayer networks comprising six layers, with each layer representing frequency-specific functional connectivity between source-localized time series of 78 cortical regions. Average frontoparietal network multilayer eigenvector centrality, a measure for network integration, was calculated at both time points. Regression analyses were used to investigate associations with executive functioning. At T1, lower multilayer integration ( p = 0.017) and epilepsy ( p = 0.006) associated with poorer set shifting (adj. R 2 = 0.269). Decreasing multilayer integration ( p = 0.022) and not undergoing chemotherapy at T2 ( p = 0.004) related to deteriorating set shifting over time (adj. R 2 = 0.283). No significant associations were found for word fluency or inhibition, nor did T1 multilayer integration predict changes in executive functioning. As expected, our results establish multilayer integration of the frontoparietal network as a cross-sectional and longitudinal correlate of executive functioning in glioma patients. However, multilayer integration did not predict postoperative changes in executive functioning, which together with the fact that this correlate is also found in health and other diseases, limits its specific clinical relevance in glioma.

The prevalence and outcomes of depression in older HIV-positive adults in Northern Tanzania: a longitudinal study - Damneek Dua; Oliver Stubbs; Sarah Urasa; Jane Rogathe; Ashanti Duijinmaijer; William Howlett; Marieke Dekker; Aloyce Kisoli; Elizabeta B. Mukaetova-Ladinska; William K. Gray; Thomas Lewis; Richard W. Walker; et al. (Journal of NeuroVirology, 2023)
Studies of depression and its outcomes in older people living with HIV (PLWH) are currently lacking in sub-Saharan Africa. This study aims to investigate the prevalence of psychiatric disorders in PLWH aged ≥ 50 years in Tanzania focussing on prevalence and 2-year outcomes of depression. PLWH aged ≥ 50 were systematically recruited from an outpatient clinic and assessed using the Mini-International Neuropsychiatric Interview (MINI). Neurological and functional impairment was assessed at year 2 follow-up. At baseline, 253 PLWH were recruited (72.3% female, median age 57, 95.5% on cART). DSM-IV depression was highly prevalent (20.9%), whereas other DSM-IV psychiatric disorders were uncommon. At follow-up ( n = 162), incident cases of DSM-IV depression decreased from14.2 to 11.1% (χ 2 : 2.48, p = 0.29); this decline was not significant. Baseline depression was associated with increased functional and neurological impairment. At follow-up, depression was associated with negative life events ( p = 0.001), neurological impairment ( p < 0.001), and increased functional impairment ( p = 0.018), but not with HIV and sociodemographic factors. In this setting, depression appears highly prevalent and associated with poorer neurological and functional outcomes and negative life events. Depression may be a future intervention target.

Bilateral fornix infarction as a cause of acute amnesia - Kshitij Thapa; Stella Setyapranata; Philip M. C. Choi; Ian Clare (Acta Neurologica Belgica, 2023)

Variation in gut microbial contribution of essential amino acids to host protein metabolism in a wild small mammal community - Alexi C. Besser; Philip J. Manlick; Christina M. Blevins; Cristina D. Takacs‐Vesbach; Seth D. Newsome (Ecology Letters, 2023)
Herbivory is a dominant feeding strategy among animals, yet herbivores are often protein limited. The gut microbiome is hypothesized to help maintain host protein balance by provisioning essential macromolecules, but this has never been tested in wild consumers. Using amino acid carbon (δ 13 C) and nitrogen (δ 15 N) isotope analysis, we estimated the proportional contributions of essential amino acids (AA ESS ) synthesized by gut microbes to five co‐occurring desert rodents representing herbivorous, omnivorous and insectivorous functional groups. We found that herbivorous rodents occupying lower trophic positions ( Dipodomys spp.) routed a substantial proportion (~40%–50%) of their AA ESS from gut microbes, while higher trophic level omnivores ( Peromyscus spp.) and insectivores ( Onychomys arenicola ) obtained most of their AA ESS (~58%) from plant‐based energy channels but still received ~20% of their AA ESS from gut microbes. These findings empirically demonstrate that gut microbes play a key functional role in host protein metabolism in wild animals.

Application of an Encoder–Decoder Model with Attention Mechanism for Trajectory Prediction Based on AIS Data: Case Studies from the Yangtze River of China and the Eastern Coast of the U.S - Licheng Zhao; Yi Zuo; Tieshan Li; C. L. Philip Chen (Journal of Marine Science and Engineering, 2023)
With the rapid growth of shipping volumes, ship navigation and path planning have attracted increased attention. To design navigation routes and avoid ship collisions, accurate ship trajectory prediction based on automatic identification system data is required. Therefore, this study developed an encoder–decoder learning model for ship trajectory prediction, to avoid ship collisions. The proposed model includes long short-term memory units and an attention mechanism. Long short-term memory can extract relationships between the historical trajectory of a ship and the current state of encountered ships. Simultaneously, the global attention mechanism in the proposed model can identify interactions between the output and input trajectory sequences, and a multi-head self-attention mechanism in the proposed model is used to learn the feature fusion representation between the input trajectory sequences. Six case studies of trajectory prediction for ship collision avoidance from the Yangtze River of China and the eastern coast of the U.S. were investigated and compared. The results showed that the average mean absolute errors of our model were much lower than those of the classical neural networks and other state-of-the-art models that included attention mechanisms.

A framework for establishing a rapid ‘Ōhi‘a death resistance program - Blaine C. Luiz; Christian P. Giardina; Lisa M. Keith; Douglass F. Jacobs; Richard A. Sniezko; Marc A. Hughes; James B. Friday; Philip Cannon; Robert Hauff; Kainana Francisco; Marian M. Chau; Nicklos Dudley; et al. (New Forests, 2023)
Metrosideros polymorpha Gaud. (‘ōhi‘a) is the most abundant native forest tree in Hawai‘i and a keystone species of cultural, ecological, and economic importance. ‘Ōhi‘a forests, particularly on Hawaiʻi Island, are being severely impacted by Rapid ‘Ōhi‘a Death (ROD), which is caused by the fungal pathogens Ceratocystis lukuohia and C. huliohia . ROD is characterized by branch dieback, crown wilting, and mortality. Initial disease resistance screening of four varieties of M. polymorpha with C. lukuohia demonstrated that varieties may differ in susceptibility. Several survivors of field or screening-based infections still exist, providing strong impetus for the establishment of the ‘Ōhiʻa Disease Resistance Program (ʻŌDRP). Here, we outline a framework for guiding the ʻŌDRP throughout the process of identifying and developing ROD resistance in M. polymorpha and, possibly, all Hawaiian Metrosideros species. Core ʻŌDRP projects include: (1) evaluating and operationalizing methods for greenhouse-based production and screening of test plants; (2) greenhouse screening of seedlings and rooted cuttings sampled from native Metrosideros throughout Hawaiʻi; (3) establishing field trials to validate results from greenhouse assays; (4) understanding environmental and genetic drivers of resistance to characterize the durability of resistance to ROD; (5) developing remote sensing and molecular methods to rapidly detect ROD-resistant individuals; and (6) conducting breeding trials to improve the degree and durability of ROD resistance. Ultimately, the ʻŌDRP seeks to produce ROD-resistant material for the perpetuation of M. polymorpha across Hawai‘i, with the goal of preserving the ecology, culture, and communities that are dependent on this tree species.

Attribution of the heavy rainfall events leading to severe flooding in Western Europe during July 2021 - Jordis S. Tradowsky; Sjoukje Y. Philip; Frank Kreienkamp; Sarah F. Kew; Philip Lorenz; Julie Arrighi; Thomas Bettmann; Steven Caluwaerts; Steven C. Chan; Lesley De Cruz; Hylke de Vries; Norbert Demuth; et al. (Climatic Change, 2023)
In July 2021 extreme rainfall across Western Europe caused severe flooding and substantial impacts, including over 200 fatalities and extensive infrastructure damage within Germany and the Benelux countries. After the event, a hydrological assessment and a probabilistic event attribution analysis of rainfall data were initiated and complemented by discussing the vulnerability and exposure context. The global mean surface temperature (GMST) served as a covariate in a generalised extreme value distribution fitted to observational and model data, exploiting the dependence on GMST to estimate how anthropogenic climate change affects the likelihood and severity of extreme events. Rainfall accumulations in Ahr/Erft and the Belgian Meuse catchment vastly exceeded previous observed records. In regions of that limited size the robust estimation of return values and the detection and attribution of rainfall trends are challenging. However, for the larger Western European region it was found that, under current climate conditions, on average one rainfall event of this magnitude can be expected every 400 years at any given location. Consequently, within the entire region, events of similar magnitude are expected to occur more frequently than once in 400 years. Anthropogenic climate change has already increased the intensity of the maximum 1-day rainfall event in the summer season by 3–19 %. The likelihood of such an event to occur today compared to a 1.2 $$^{° }$$ ∘ C cooler climate has increased by a factor of 1.2–9. Models indicate that intensity and frequency of such events will further increase with future global warming. While attribution of small-scale events remains challenging, this study shows that there is a robust increase in the likelihood and severity of rainfall events such as the ones causing extreme impacts in July 2021 when considering a larger region.

Can blood proteome diversity among fish species help explain perfluoroalkyl acid trophodynamics in aquatic food webs? - Adam D. Point; Bernard S. Crimmins; Thomas M. Holsen; Sujan Fernando; Philip K. Hopke; Costel C. Darie (Science of The Total Environment, 2023)

SVEPM 2022, the annual conference of the Society for Veterinary Epidemiology and Preventive Medicine: A joyful hybrid meeting after two years online - Fernanda C. Dórea; Timothée Vergne; Carla Correia-Gomes; Luís Pedro Carmo; Egil A.J. Fischer; Dave C. Brodbelt; Philip A. Robinson; Gerdien van Schaik (Preventive Veterinary Medicine, 2023)

Quantifying stream-loss recovery in a spring using dual-tracer injections in the Snake Creek drainage, Great Basin National Park, Nevada, USA - C. Eric Humphrey; Philip M. Gardner; Lawrence E. Spangler; Nora C. Nelson; Laura Toran; D. Kip Solomon (Hydrogeology Journal, 2023)
Simultaneous short-pulse injections of two tracers (sodium bromide [Br – ] and fluorescein dye) were made in a losing reach of Snake Creek in Great Basin National Park, Nevada, USA, to evaluate the quantity of stream loss through permeable carbonates that resurfaces at a spring approximately 10 km down drainage. A revised hydrogeologic cross section for a possible flow path of the infiltrated Snake Creek water is presented, and the results may inform water management in the region. First arrival and peak concentration of the two tracers occurred at 9.5 and 12.7 days after injection, respectively. Fracture transport simulations indicate that Br – preferentially diffuses into immobile regions of the aquifer, and this diffusive flux is likely responsible for the major differences in the breakthrough curves. When considering the diffusive tracer flux, total apparent Br – and fluorescein dye recoveries were 16.9–22.1% and 21.7–24.3%, respectively. These findings imply that consideration of diffusive flux and long-term monitoring in fracture-dominated flow may support accurate quantification of tracer recovery. In addition, the apparent power law slopes of the breakthrough tails for both tracers were steeper at early times than have been attributed to heterogeneous advection or channeling in meter-scale tests, but the late-time Br – power law slope becomes less steep than has been attributed to diffusive exchange. These deviations may reflect fracture transport patterns that occur at larger scales.

Occurrence of Rickettsia spp. and Coxiella burnetii in ixodid ticks in Kassena-Nankana, Ghana - Seth Offei Addo; Ronald Essah Bentil; Bernice Olivia Ama Baako; Kevin Nii Yartey; Eric Behene; Benjamin Asiamah; Abena Akyeamaa Nyarko; Victor Asoala; Mohamed Sallam; Suzanne Mate; James C. Dunford; John Asiedu Larbi; et al. (Experimental and Applied Acarology, 2023)

Best practices in the use and exchange of microorganism biological control genetic resources - Peter G. Mason; Martin Hill; David Smith; Luciana C. Silvestri; Philip Weyl; Jacques Brodeur; Marcello Diniz Vitorino (BioControl, 2023)
The Nagoya Protocol actions the third objective of the Convention on Biological Diversity and provides a framework to effectively implement the fair and equitable sharing of benefits arising out of the use of genetic resources. This includes microorganisms used as biological control agents. Thus biological control practitioners must comply with access and benefit-sharing regulations that are implemented by countries providing microbial biological control agents. A review of best practices and guidance for the use and exchange of microorganisms used for biological control has been prepared by the IOBC Global Commission on Biological Control and Access and Benefit-Sharing to demonstrate commitment to comply with access and benefit-sharing requirements, and to reassure the international community that biological control is a very successful and environmentally safe pest management strategy that uses biological resources responsibly and sustainably. We propose that best practices include the following elements: collaboration to facilitate information exchange about the availability of microbial biological control agents and where they may be sourced; freely sharing available knowledge in databases about successes and failures; collaborative research with provider countries to develop capacity; and production technology transfer to provide economic opportunities. We recommend the use of model concept agreements for accessing microorganisms for scientific research and non-commercial release into nature where access and benefit-sharing regulations exist and where regulations are not restrictive or do not exist. We also recommend a model agreement for deposition of microbial biological control agents into culture collections.

Impact of Access and Benefit Sharing implementation on biological control genetic resources - Peter G. Mason; Barbara I. P. Barratt; Fernando Mc Kay; Johannette N. Klapwijk; Luciana C. Silvestri; Martin Hill; Hariet L. Hinz; Andy Sheppard; Jacques Brodeur; Marcello Diniz Vitorino; Philip Weyl; Kim A. Hoelmer (BioControl, 2023)
The third objective of the Convention on Biological Diversity, the fair and equitable sharing of benefits arising out of the use of genetic resources was further developed when the Nagoya Protocol on Access and Benefit Sharing came into effect in 2014. Interpretation of how this agreement is being implemented is wide-ranging and there are implications for biological control. A survey of biological control workers indicated that while some countries have facilitated access to biological control genetic resources, requirements in other countries have impeded biological control implementation. There was consensus that benefits to provider countries should be in the form of supporting local research communities. There was also agreement that the free use and exchange of biological control genetic resources has provided benefits to the global community, including to both providers and recipients of the agents. It is recommended that consideration of the free use and exchange principal should be a key element of Access and Benefit Sharing measures for the future.

International agreement for the use and exchange of classical biological control genetic resources: a practical proposal - Peter G. Mason; Fernando Mc Kay; Luciana C. Silvestri; Martin Hill; Philip Weyl; Hariet L. Hinz; Jacques Brodeur; Marcelo Diniz Vitorino; Barbara I. P. Barratt (BioControl, 2023)
The Nagoya Protocol on Access and Benefit Sharing (ABS) was implemented to further develop the third objective of the Convention on Biological Diversity, the fair and equitable sharing of benefits arising out of the utilization of genetic resources. Interpretation of this agreement is wide-ranging and there is concern that if ABS measures are poorly implemented biological control and the resultant public good will be greatly impeded. The ethos of multilateral use and exchange of genetic resources used in classical biological control will be particularly affected. In the spirit of the fair and equitable sharing of benefits arising out of the utilization of genetic resources, we propose a simple practical solution in the form of an international agreement on the use and exchange of classical biological control genetic resources.

Mission Tara Microplastics: a holistic set of protocols and data resources for the field investigation of plastic pollution along the land-sea continuum in Europe - Jean-François Ghiglione; Valérie Barbe; Stéphane Bruzaud; Gaëtan Burgaud; Jérôme Cachot; Boris Eyheraguibel; Franck Lartaud; Wolfgang Ludwig; Anne-Leila Meistertzheim; Ika Paul-Pont; Stéphane Pesant; Alexandra ter Halle; et al. (Environmental Science and Pollution Research, 2023)
The Tara Microplastics mission was conducted for 7 months to investigate plastic pollution along nine major rivers in Europe—Thames, Elbe, Rhine, Seine, Loire, Garonne, Ebro, Rhone, and Tiber. An extensive suite of sampling protocols was applied at four to five sites on each river along a salinity gradient from the sea and the outer estuary to downstream and upstream of the first heavily populated city. Biophysicochemical parameters including salinity, temperature, irradiance, particulate matter, large and small microplastics (MPs) concentration and composition, prokaryote and microeukaryote richness, and diversity on MPs and in the surrounding waters were routinely measured onboard the French research vessel Tara or from a semi-rigid boat in shallow waters. In addition, macroplastic and microplastic concentrations and composition were determined on river banks and beaches. Finally, cages containing either pristine pieces of plastics in the form of films or granules, and others containing mussels were immersed at each sampling site, 1 month prior to sampling in order to study the metabolic activity of the plastisphere by meta-OMICS and to run toxicity tests and pollutants analyses. Here, we fully described the holistic set of protocols designed for the Mission Tara Microplastics and promoted standard procedures to achieve its ambitious goals: (1) compare traits of plastic pollution among European rivers, (2) provide a baseline of the state of plastic pollution in the Anthropocene, (3) predict their evolution in the frame of the current European initiatives, (4) shed light on the toxicological effects of plastic on aquatic life, (5) model the transport of microplastics from land towards the sea, and (6) investigate the potential impact of pathogen or invasive species rafting on drifting plastics from the land to the sea through riverine systems.

Corrigendum to “The exercise-induced suppression of acylated ghrelin is blunted in the luteal phase of the menstrual cycle compared to the follicular phase following vigorous-intensity exercise” [Appetite 182 (2023) 106425] - Sara C. Moniz; Seth F. McCarthy; Abigail A. Broad; Philip J. Medeiros; Tom J. Hazell (Appetite, 2023)

Uranus ring occultation observations: 1977–2006 - Richard G. French; Colleen A. McGhee-French; Mitchell Gordon; Richard L. Baron; Amanda S. Bosh; Marc W. Buie; Nancy Chanover; Mary Ann Clark; Edward W. Dunham; Linda M. French; Ian S. Glass; Jay D. Goguen; et al. (Icarus, 2023)

The effects of habitat heterogeneity, as measured by satellite image texture, on tropical forest bird distributions - Naparat Suttidate; Anna M. Pidgeon; Martina L. Hobi; Philip D. Round; Maxim Dubinin; Volker C. Radeloff (Biological Conservation, 2023)

A review of formulations and preclinical studies of inhaled rifampicin for its clinical translation - Prakash Khadka; Jack Dummer; Philip C. Hill; Rajesh Katare; Shyamal C. Das (Drug Delivery and Translational Research, 2023)
Inhaled drug delivery is a promising approach to achieving high lung drug concentrations to facilitate efficient treatment of tuberculosis (TB) and to reduce the overall duration of treatment. Rifampicin is a good candidate for delivery via the pulmonary route. There have been no clinical studies yet at relevant inhaled doses despite the numerous studies investigating its formulation and preclinical properties for pulmonary delivery. This review discusses the clinical implications of pulmonary drug delivery in TB treatment, the drug delivery systems reported for pulmonary delivery of rifampicin, animal models, and the animal studies on inhaled rifampicin formulations, and the research gaps hindering the transition from preclinical development to clinical investigation. A review of reports in the literature suggested there have been minimal attempts to test inhaled formulations of rifampicin in laboratory animals at relevant high doses and there is a lack of appropriate studies in animal models. Published studies have reported testing only low doses (≤ 20 mg/kg) of rifampicin, and none of the studies has investigated the safety of inhaled rifampicin after repeated administration. Preclinical evaluations of inhaled anti-TB drugs, such as rifampicin, should include high-dose formulations in preclinical models, determined based on allometric conversions, for relevant high-dose anti-TB therapy in humans. Graphical abstract

The Humanities are invited to the Anthropocene Event but not to the Anthropocene Series/Epoch: a response to Chvostek (2023) - Stanley C. Finney; Philip L. Gibbard (Journal of Quaternary Science, 2023)

Degradation rates influence the ability of composite samples to represent 24-hourly means of SARS-CoV-2 and other microbiological target measures in wastewater - Kristina M. Babler; Mark E. Sharkey; Samantha Abelson; Ayaaz Amirali; Aymara Benitez; Gabriella A. Cosculluela; George S. Grills; Naresh Kumar; Jennifer Laine; Walter Lamar; Erik D. Lamm; Jiangnan Lyu; et al. (Science of The Total Environment, 2023)

Four-dimensional electrical resistivity imaging for monitoring pumping-induced saltwater intrusion in a coastal aquifer - Mark C. McDonnell; Raymond Flynn; Jesús Fernández Águila; Gerard A. Hamill; Shane Donohue; Eric M. Benner; Christopher Thomson; Georgios Etsias; Thomas S.L. Rowan; Paul B. Wilkinson; Philip I. Meldrum (Science of The Total Environment, 2023)

Regional variability in peatland burning at mid-to high-latitudes during the Holocene - Thomas G. Sim; Graeme T. Swindles; Paul J. Morris; Andy J. Baird; Angela V. Gallego-Sala; Yuwan Wang; Maarten Blaauw; Philip Camill; Michelle Garneau; Mark Hardiman; Julie Loisel; Minna Vӓliranta; et al. (Quaternary Science Reviews, 2023)

Graphene oxide exposure alters gut microbial community composition and metabolism in an in vitro human model - Sneha P. Couvillion; Robert E. Danczak; Xiaoqiong Cao; Qin Yang; Tharushi P. Keerthisinghe; Ryan S. McClure; Dimitrios Bitounis; Meagan C. Burnet; Sarah J. Fansler; Rachel E. Richardson; Mingliang Fang; Wei-Jun Qian; et al. (NanoImpact, 2023)

Industrial output, services and carbon emissions: the role of information and communication technologies and economic freedom in Africa - Chinazaekpere Nwani; Festus Victor Bekun; Phillips O. Agboola; Philip C. Omoke; Ekpeno L. Effiong (Environment, Development and Sustainability, 2023)

Genetic diversity goals and targets have improved, but remain insufficient for clear implementation of the post-2020 global biodiversity framework - Sean Hoban; Michael W. Bruford; Jessica M. da Silva; W. Chris Funk; Richard Frankham; Michael J. Gill; Catherine E. Grueber; Myriam Heuertz; Margaret E. Hunter; Francine Kershaw; Robert C. Lacy; Caroline Lees; et al. (Conservation Genetics, 2023)
Genetic diversity among and within populations of all species is necessary for people and nature to survive and thrive in a changing world. Over the past three years, commitments for conserving genetic diversity have become more ambitious and specific under the Convention on Biological Diversity’s (CBD) draft post-2020 global biodiversity framework (GBF). This Perspective article comments on how goals and targets of the GBF have evolved, the improvements that are still needed, lessons learned from this process, and connections between goals and targets and the actions and reporting that will be needed to maintain, protect, manage and monitor genetic diversity. It is possible and necessary that the GBF strives to maintain genetic diversity within and among populations of all species, to restore genetic connectivity, and to develop national genetic conservation strategies, and to report on these using proposed, feasible indicators.

Correction to: Plasma extracellular vesicles and cell-free mitochondrial DNA are associated with cognitive dysfunction in treated older adults with HIV - Carrie D. Johnston; Erika G. Marques de Menezes; Scott Bowler; Eugenia L. Siegler; Courtney Friday; Philip J. Norris; Michelle C. Rice; Mary E. Choi; Marshall J. Glesby; Lishomwa C. Ndhlovu (Journal of NeuroVirology, 2023)

Plasma extracellular vesicles and cell-free mitochondrial DNA are associated with cognitive dysfunction in treated older adults with HIV - Carrie D. Johnston; Erika G. Marques de Menezes; Scott Bowler; Eugenia L. Siegler; Courtney Friday; Philip J. Norris; Michelle C. Rice; Mary E. Choi; Marshall J. Glesby; Lishomwa C. Ndhlovu (Journal of NeuroVirology, 2023)

Laboratory‐based measures of temperature preference and metabolic thermal sensitivity provide insight into the habitat utilisation of juvenile California horn shark ( Heterodontus francisci ) and leopard shark ( Triakis semifasciata ) - Zachary R. Skelton; Tanya S. Prinzing; Philip A. Hastings; Nicholas C. Wegner (Journal of Fish Biology, 2023)
Laboratory‐based studies examining fish physiological and behavioural responses to temperature can provide important insight into species‐specific habitat preferences and utilisation, and are especially useful in examining vulnerable life stages that are difficult to study in the wild. This study couples shuttle box behavioural experiments with respirometry trials to determine the temperature preferences and metabolic thermal sensitivity of juvenile California horn shark ( Heterodontus francisci ) and leopard shark ( Triakis semifasciata ). As juveniles, these two species often occupy similar estuarine habitats but display contrasting behaviours and activity levels – H. francisci are relatively sedentary, whereas T. semifasciata are more active and mobile. This study shows that juvenile H. francisci and T. semifasciata have comparable thermal preferences and occupy similar temperature ranges, but H. francisci metabolism is more sensitive to acute changes in temperature as expressed through a higher Q 10 ( H. francisci = 2.58; T. semifasciata = 1.97; temperature range: 12–24°C). Underlying chronic temperature acclimation to both warm (21°C) and cool (15°C) representative seasonal temperatures did not appear to significantly affect these parameters . These results are discussed in the context of field studies examining known distributions, habitat and movement patterns of H. francisci and T. semifasciata to better understand the role of temperature in species‐specific behaviour. Juvenile H. francisci likely target thermally stable environments, such as estuaries that are close to their preferred temperature, whereas juvenile T. semifasciata metabolism and behaviour appear less dependent on temperature.

The exercise-induced suppression of acylated ghrelin is blunted in the luteal phase of the menstrual cycle compared to the follicular phase following vigorous-intensity exercise - Sara C. Moniz; Seth F. McCarthy; Abigail A. Broad; Philip J. Medeiros; Tom J. Hazell (Appetite, 2023)

The association of auditory function measures with low-level methylmercury from oceanic fish consumption and mercury vapor from amalgam: The Seychelles Child Development Study Nutrition 1 Cohort - Mark S. Orlando; Tanzy Love; Donald Harrington; Adam C. Dziorny; Conrad F. Shamlaye; Gene E. Watson; Edwin van Wijngaarden; Philip W. Davidson; Gary J. Myers (NeuroToxicology, 2023)

Absolute quantification of cellular levels of photosynthesis-related proteins in Synechocystis sp. PCC 6803 - Philip J. Jackson; Andrew Hitchcock; Amanda A. Brindley; Mark J. Dickman; C. Neil Hunter (Photosynthesis Research, 2023)
Quantifying cellular components is a basic and important step for understanding how a cell works, how it responds to environmental changes, and for re-engineering cells to produce valuable metabolites and increased biomass. We quantified proteins in the model cyanobacterium Synechocystis sp. PCC 6803 given the general importance of cyanobacteria for global photosynthesis, for synthetic biology and biotechnology research, and their ancestral relationship to the chloroplasts of plants. Four mass spectrometry methods were used to quantify cellular components involved in the biosynthesis of chlorophyll, carotenoid and bilin pigments, membrane assembly, the light reactions of photosynthesis, fixation of carbon dioxide and nitrogen, and hydrogen and sulfur metabolism. Components of biosynthetic pathways, such as those for chlorophyll or for photosystem II assembly, range between 1000 and 10,000 copies per cell, but can be tenfold higher for CO 2 fixation enzymes. The most abundant subunits are those for photosystem I, with around 100,000 copies per cell, approximately 2 to fivefold higher than for photosystem II and ATP synthase, and 5–20 fold more than for the cytochrome b 6 f complex. Disparities between numbers of pathway enzymes, between components of electron transfer chains, and between subunits within complexes indicate possible control points for biosynthetic processes, bioenergetic reactions and for the assembly of multisubunit complexes.

Molecular survey of Anaplasma and Ehrlichia species in livestock ticks from Kassena-Nankana, Ghana; with a first report of Anaplasma capra and Ehrlichia minasensis - Seth Offei Addo; Bernice Olivia Ama Baako; Ronald Essah Bentil; Charlotte Adwoa Addae; Eric Behene; Victor Asoala; Mohamed Sallam; Suzanne Mate; James C. Dunford; John Asiedu Larbi; Philip Kweku Baidoo; Michael David Wilson; et al. (Archives of Microbiology, 2023)

Pan‐Arctic soil moisture control on tundra carbon sequestration and plant productivity - Donatella Zona; Peter M. Lafleur; Koen Hufkens; Beniamino Gioli; Barbara Bailey; George Burba; Eugénie S. Euskirchen; Jennifer D. Watts; Kyle A. Arndt; Mary Farina; John S. Kimball; Martin Heimann; et al. (Global Change Biology, 2023)
Long‐term atmospheric CO 2 concentration records have suggested a reduction in the positive effect of warming on high‐latitude carbon uptake since the 1990s. A variety of mechanisms have been proposed to explain the reduced net carbon sink of northern ecosystems with increased air temperature, including water stress on vegetation and increased respiration over recent decades. However, the lack of consistent long‐term carbon flux and in situ soil moisture data has severely limited our ability to identify the mechanisms responsible for the recent reduced carbon sink strength. In this study, we used a record of nearly 100 site‐years of eddy covariance data from 11 continuous permafrost tundra sites distributed across the circumpolar Arctic to test the temperature (expressed as growing degree days, GDD) responses of gross primary production (GPP), net ecosystem exchange (NEE), and ecosystem respiration (ER) at different periods of the summer (early, peak, and late summer) including dominant tundra vegetation classes (graminoids and mosses, and shrubs). We further tested GPP, NEE, and ER relationships with soil moisture and vapor pressure deficit to identify potential moisture limitations on plant productivity and net carbon exchange. Our results show a decrease in GPP with rising GDD during the peak summer (July) for both vegetation classes, and a significant relationship between the peak summer GPP and soil moisture after statistically controlling for GDD in a partial correlation analysis. These results suggest that tundra ecosystems might not benefit from increased temperature as much as suggested by several terrestrial biosphere models, if decreased soil moisture limits the peak summer plant productivity, reducing the ability of these ecosystems to sequester carbon during the summer.

Integral Sliding Mode-Based Fault-Tolerant Control for Dynamic Positioning of Unmanned Marine Vehicles Based on a T-S Fuzzy Model - Yang Wang; Li-Ying Hao; Tieshan Li; C. L. Philip Chen (Journal of Marine Science and Engineering, 2023)
This paper investigates a fault-tolerant control problem for the dynamic positioning of unmanned marine vehicles based on a Takagi–Sugeno (T-S) fuzzy model using an integral sliding mode scheme. First, the T-S fuzzy model of an unmanned marine vehicle is established by taking the yaw angle variable range into account. An integral sliding mode control scheme combined with the H∞ performance index is then developed to attenuate the initial influence of thruster faults and ocean disturbances. The unknown nonlinear function is approximated using a fuzzy logic system based on a representation of marine data, which provides a good tradeoff between resolution of the unknown nonlinear term approximation and computational complexity for marine engineering by adjusting the number of fuzzy logic system rules. In addition, the fault estimation information is utilized to design the sliding mode surface on the basis of an adaptive mechanism and a matrix full rank decomposition technique, which reduces conservatism. The validity of the proposed approach is finally demonstrated by an analysis of simulation results using a typical floating production vessel model.

Planktic foraminifera iodine/calcium ratios from plankton tows - Helge A. Winkelbauer; Babette A. A. Hoogakker; Rosie J. Chance; Catherine V. Davis; Christopher J. Anthony; Juliane Bischoff; Lucy J. Carpenter; Simon R. N. Chenery; Elliott M. Hamilton; Philip Holdship; Victoria L. Peck; Alex J. Poulton; et al. (Frontiers in Marine Science, 2023)
Planktic foraminifera test iodine to calcium ratios represent an emerging proxy method to assess subsurface seawater oxygenation states. Several core-top studies show lower planktic foraminifera I/Ca in locations with oxygen depleted subsurface waters compared to well oxygenated environments. The reasoning behind this trend is that only the oxidized species of iodine, iodate, is incorporated in foraminiferal calcite. The I/Ca of foraminiferal calcite is thought to reflect iodate contents in seawater. To test this hypothesis, we compare planktic foraminifera I/Ca ratios, obtained from plankton tows, with published and new seawater iodate concentrations from 1) the Eastern North Pacific with extensive oxygen depletion, 2) the Benguela Current System with moderately depleted oxygen concentrations, and 3) the well oxygenated North and South Atlantic. We find the lowest I/Ca ratios (0.07 µmol/mol) in planktic foraminifera retrieved from the Eastern North Pacific, and higher values for samples (up to 0.72 µmol/mol) obtained from the Benguela Current System and North and South Atlantic. The I/Ca ratios of plankton tow foraminifera from environments with well oxygenated subsurface waters, however, are an order of magnitude lower compared to core-tops from similarly well-oxygenated regions. This would suggest that planktic foraminifera gain iodine post-mortem, either when sinking through the water column, or during burial.

When is green nudging ethically permissible? - C Tyler DesRoches; Daniel Fischer; Julia Silver; Philip Arthur; Rebecca Livernois; Timara Crichlow; Gil Hersch; Michiru Nagatsu; Joshua K Abbott (Current Opinion in Environmental Sustainability, 2023)

Continuous monitoring of the atmospheric boundary layer (ABL) height from micro pulse lidar over a tropical coastal station, Kattankulathur (12.82° N, 80.04° E) - Sachin Philip Kakkanattu; Sanjay Kumar Mehta; Pooja Purushotham; K. B. Betsy; C. J. Seetha; P. P. Musaid (Meteorology and Atmospheric Physics, 2023)

Identification of fish habitat hotspots for use in prioritizing conservation and restoration projects in coastal rivers - Philip W. Stevens; Richard Paperno; Jeff L. Beal; Timothy C. MacDonald; H. Nathan Miller; Phyllis A. Klarmann; Christopher R. Malinowski (Environmental Biology of Fishes, 2023)

Drivers of migration intentions in coastal Vietnam under increased flood risk from sea level rise - Sem J. Duijndam; W. J. Wouter Botzen; Liselotte C. Hagedoorn; Philip Bubeck; Toon Haer; My Pham; Jeroen C. J. H. Aerts (Climatic Change, 2023)
Elevated flood risk due to sea level rise is expected to increase migration from coastal areas. This presents an enormous policy challenge given the hundreds of millions of people living in low-lying coastal areas globally. Despite its relevance, little empirical research has been done on what drives coastal residents to migrate or stay under increased flood risk. This study aims to improve the knowledge base on this topic by collecting and analyzing unique survey data of flood-prone coastal residents in Central Vietnam. To explain permanent migration intentions under increased flood risk, we present respondents with realistic scenarios of more frequent severe flooding and utilize a theoretical framework that incorporates flood risk indicators as well as key indicators of sustainable livelihoods. Results indicate that flood risk could play a major role in future migration behavior; permanent migration intentions strongly increase under the scenarios of increased flood risk. Several individual characteristics also play an important role in the migration decision. Regression analyses reveal that respondents who implemented in situ flood adaptation, and thereby reduced their flood risk, are less inclined to migrate. Past experiences during flooding such as evacuation or the reception of help from community members or the government are also strong predictors of migration intentions. Of the sustainable livelihood indicators, social capital plays the most important role, where a larger social network inside (outside) the place of residence is negatively (positively) related to migration intentions. We draw lessons from these insights for policymakers aiming to anticipate the challenge of sea level rise-induced migration.

Stronger fertilization effects on aboveground versus belowground plant properties across nine U.S. grasslands - Adrienne B. Keller; Christopher A. Walter; Dana M. Blumenthal; Elizabeth T. Borer; Scott L. Collins; Lang C. DeLancey; Philip A. Fay; Kirsten S. Hofmockel; Johannes M. H. Knops; Andrew D. B. Leakey; Melanie A. Mayes; Eric W. Seabloom; et al. (Ecology, 2023)
Increased nutrient inputs due to anthropogenic activity are expected to increase primary productivity across terrestrial ecosystems, but changes in allocation aboveground versus belowground with nutrient addition have different implications for soil carbon (C) storage. Thus, given that roots are major contributors to soil C storage, understanding belowground net primary productivity (BNPP) and biomass responses to changes in nutrient availability is essential to predicting carbon–climate feedbacks in the context of interacting global environmental changes. To address this knowledge gap, we tested whether a decade of nitrogen (N) and phosphorus (P) fertilization consistently influenced aboveground and belowground biomass and productivity at nine grassland sites spanning a wide range of climatic and edaphic conditions in the continental United States. Fertilization effects were strong aboveground, with both N and P addition stimulating aboveground biomass at nearly all sites (by 30% and 36%, respectively, on average). P addition consistently increased root production (by 15% on average), whereas other belowground responses to fertilization were more variable, ranging from positive to negative across sites. Site‐specific responses to P were not predicted by the measured covariates. Atmospheric N deposition mediated the effect of N fertilization on root biomass and turnover. Specifically, atmospheric N deposition was positively correlated with root turnover rates, and this relationship was amplified with N addition. Nitrogen addition increased root biomass at sites with low N deposition but decreased it at sites with high N deposition. Overall, these results suggest that the effects of nutrient supply on belowground plant properties are context dependent, particularly with regard to background N supply rates, demonstrating that site conditions must be considered when predicting how grassland ecosystems will respond to increased nutrient loading from anthropogenic activity.

Quantifying and mapping species threat abatement opportunities to support national target setting - Louise Mair; Eduardo Amorim; Monira Bicalho; Thomas M. Brooks; Vincente Calfo; Renata de T. Capellão; Colin Clubbe; Marianne Evju; Eduardo P. Fernandez; Gláucia C. Ferreira; Frank Hawkins; Randall R. Jiménez; et al. (Conservation Biology, 2023)
The successful implementation of the Convention on Biological Diversity's post‐2020 Global Biodiversity Framework will rely on effective translation of targets from global to national level and increased engagement across diverse sectors of society. Species conservation targets require policy support measures that can be applied to a diversity of taxonomic groups, that link action targets to outcome goals, and that can be applied to both global and national data sets to account for national context, which the species threat abatement and restoration (STAR) metric does. To test the flexibility of STAR, we applied the metric to vascular plants listed on national red lists of Brazil, Norway, and South Africa. The STAR metric uses data on species’ extinction risk, distributions, and threats, which we obtained from national red lists to quantify the contribution that threat abatement and habitat restoration activities could make to reducing species’ extinction risk. Across all 3 countries, the greatest opportunity for reducing plant species’ extinction risk was from abating threats from agricultural activities, which could reduce species’ extinction risk by 54% in Norway, 36% in South Africa, and 29% in Brazil. Species extinction risk could be reduced by a further 21% in South Africa by abating threats from invasive species and by 21% in Brazil by abating threats from urban expansion. Even with different approaches to red‐listing among countries, the STAR metric yielded informative results that identified where the greatest conservation gains could be made for species through threat‐abatement and restoration activities. Quantifiably linking local taxonomic coverage and data collection to global processes with STAR would allow national target setting to align with global targets and enable state and nonstate actors to measure and report on their potential contributions to species conservation.

Long-term N-addition alters the community structure of functionally important N-cycling soil microorganisms across global grasslands - Beat Frey; Barbara Moser; Bjorn Tytgat; Stephan Zimmermann; Juan Alberti; Lori A. Biederman; Elizabeth T. Borer; Arthur A.D. Broadbent; Maria C. Caldeira; Kendi F. Davies; Nico Eisenhauer; Anu Eskelinen; et al. (Soil Biology and Biochemistry, 2023)

Toward resilient organizations after COVID-19: An analysis of circular and less circular companies - Lize Borms; Jan Brusselaers; Karl C. Vrancken; Sam Deckmyn; Philip Marynissen (Resources, Conservation and Recycling, 2023)

Gold and tail risks - Afees A. Salisu; Idris Adediran; Philip C. Omoke; Jean Paul Tchankam (Resources Policy, 2023)

Integrating knowledge on green infrastructure, health and well-being in ageing populations: Principles for research and practice - Matthew Dennis; Adam Barker; Jamie Anderson; Jenna C. Ashton; Gina Cavan; Penny A. Cook; David French; Anna Gilchrist; Philip James; Christopher Phillipson; Konstantinos Tzoulas; C. Philip Wheater; et al. (Ambio, 2023)
Ageing and urbanisation pose significant challenges for public health and urban planning. Ageing populations are at particular risk from hazards arising from urbanisation processes, some of which are in turn exacerbated by climate change. One approach for mitigating the negative effects of urbanisation on ageing populations is the leveraging of the beneficial effects of urban green infrastructure as a public health intervention in the planning process. We assessed the potential of available theoretical frameworks to provide the context for such leverage. This involved active engagement with academics and practitioners specialising in ageing, green infrastructure and health and well-being through a knowledge-brokering approach. We concluded that an integrated and comprehensive framework on the socio-cultural-ecological determinants of health is lacking. To address this, we present a set of principles for overcoming challenges to knowledge integration when working at the intersection of green infrastructure, ageing, health and well-being. Our findings—and the co-production process used to generate them—have wider significance for trans-disciplinary research into the benefits of the natural environment to human health and well-being as well as other complex and interconnected topics associated with global grand challenges.

Genomic prediction in the wild: A case study in Soay sheep - Bilal Ashraf; Darren C. Hunter; Camillo Bérénos; Philip A. Ellis; Susan E. Johnston; Jill G. Pilkington; Josephine M. Pemberton; Jon Slate (Molecular Ecology, 2022)
Genomic prediction, the technique whereby an individual's genetic component of their phenotype is estimated from its genome, has revolutionised animal and plant breeding and medical genetics. However, despite being first introduced nearly two decades ago, it has hardly been adopted by the evolutionary genetics community studying wild organisms. Here, genomic prediction is performed on eight traits in a wild population of Soay sheep. The population has been the focus of a >30 year evolutionary ecology study and there is already considerable understanding of the genetic architecture of the focal Mendelian and quantitative traits. We show that the accuracy of genomic prediction is high for all traits, but especially those with loci of large effect segregating. Five different methods are compared, and the two methods that can accommodate zero‐effect and large‐effect loci in the same model tend to perform best. If the accuracy of genomic prediction is similar in other wild populations, then there is a real opportunity for pedigree‐free molecular quantitative genetics research to be enabled in many more wild populations; currently the literature is dominated by studies that have required decades of field data collection to generate sufficiently deep pedigrees. Finally, some of the potential applications of genomic prediction in wild populations are discussed.

Linking changes in species composition and biomass in a globally distributed grassland experiment - Emma Ladouceur; Shane A. Blowes; Jonathan M. Chase; Adam T. Clark; Magda Garbowski; Juan Alberti; Carlos Alberto Arnillas; Jonathan D. Bakker; Isabel C. Barrio; Siddharth Bharath; Elizabeth T. Borer; Lars A. Brudvig; et al. (Ecology Letters, 2022)
Global change drivers, such as anthropogenic nutrient inputs, are increasing globally. Nutrient deposition simultaneously alters plant biodiversity, species composition and ecosystem processes like aboveground biomass production. These changes are underpinned by species extinction, colonisation and shifting relative abundance. Here, we use the Price equation to quantify and link the contributions of species that are lost, gained or that persist to change in aboveground biomass in 59 experimental grassland sites. Under ambient (control) conditions, compositional and biomass turnover was high, and losses (i.e. local extinctions) were balanced by gains (i.e. colonisation). Under fertilisation, the decline in species richness resulted from increased species loss and decreases in species gained. Biomass increase under fertilisation resulted mostly from species that persist and to a lesser extent from species gained. Drivers of ecological change can interact relatively independently with diversity, composition and ecosystem processes and functions such as aboveground biomass due to the individual contributions of species lost, gained or persisting.

Assessment of surface water quality and mercury levels from Artisanal and small-scale gold mining (ASGM) along Acupan River, Benguet, Philippines - Emilyn Q. Espiritu; Rene Juna R. Claveria; Philip Joshua C. Bernadas (Environmental Geochemistry and Health, 2022)

Life‐history constraints, short adult life span and reproductive strategies in coral reef gobies of the genus Trimma - Nisha C. Goldsworthy; Maya Srinivasan; Patrick Smallhorn‐West; Lit‐Chien Cheah; Philip L. Munday; Geoffrey P. Jones (Journal of Fish Biology, 2022)
Body size influences many life‐history traits, with small‐bodied animals tending to have short life spans, high mortality and greater reproductive effort early in life. In this study, the authors investigated the life‐history traits and reproductive strategies of three small‐bodied coral reef gobies of the genus Trimma : Trimma benjamini , Trimma capostriatum and Trimma yanoi . The authors found all Trimma species studied attained a small body size of T. benjamini individual and one T. yanoi individual had ovarian and testicular tissue active simultaneously. The results of this study highlight the life‐history challenges small CRFs face on their path to reproduction and reproductive strategies that could be beneficial in fishes with high and unpredictable mortality and short reproductive life spans.

Resource selection and species interactions between native and non‐native fishes in a simulated stream system - Philip R. Branigan; Michael C. Quist; Bradley B. Shepard; Susan C. Ireland (Fisheries Management and Ecology, 2022)
Effective fishery management necessitates understanding of resource partitioning by fishes that inhabit complex systems composed of biotic and abiotic features. Evaluations of non‐native species introductions have continually demonstrated adverse effects associated with abundance and distribution of native fishes. Therefore, understanding resource selection and interactions between native and non‐native species is important for recovery efforts. Habitat use by two native fish species (largescale sucker Catostomus macrocheilus [Girard] and mountain whitefish Prosopium williamsoni [Girard]) and one non‐native fish species (pumpkinseed Lepomis gibbosus [Linnaeus]) of the Kootenai River, Idaho, were evaluated in a laboratory stream system. Trials were conducted in allopatry and in sympatry with and without the presence of wood to describe habitat selection in the context of on‐going habitat rehabilitation efforts. Interactions were evident between native largescale sucker and non‐native pumpkinseed concerning use of a woody structure and current velocity. Mountain whitefish used low‐velocity habitats and selected locations that were further from wood when in sympatry with pumpkinseed. Our research suggests that habitat use of native, large‐river fishes may be influenced by the presence of a non‐native species, and that considering such interactions is critical when designing and implementing habitat rehabilitation efforts in river ecosystems.

Sinusoidal Organic Anion-Transporting Polypeptide 1B1/1B3 and Bile Canalicular Multidrug Resistance-Associated Protein 2 Play an Essential Role in the Hepatobiliary Disposition of a Synthetic Cyclic Dinucleotide (STING Agonist) - Philip Sandoval; Bei-Ching Chuang; John K. Fallon; Philip C. Smith; Swapan K. Chowdhury; Robert J. Griffin; Cindy Q. Xia; Shinji Iwasaki; Paresh P. Chothe (The AAPS Journal, 2022)
The liver is central to the elimination of many drugs from the body involving multiple processes and understanding of these processes is important to quantitively assess hepatic clearance of drugs. The synthetic STING (STimulator of INterferon Genes protein) agonist is a new class of drugs currently being evaluated in clinical trials as a potential anticancer therapy. In this study, we used ML00960317 (synthetic STING agonist) to investigate the hepatobiliary disposition of this novel molecular entity. A bile-duct cannulated (BDC) rat study indicated that biliary excretion is the major route of elimination for ML00960317 (84% of parent dose in bile). The human biliary clearance using in vitro sandwich cultured human hepatocyte model predicted significant biliary excretion of ML00960317 (biliary excretion index (BEI) of 47%). Moreover, the transport studies using transporter expressing cell lines, hepatocytes, and membrane vesicles indicated that ML00960317 is a robust substrate of OATP1B1, OATP1B3, and MRP2. Using relative expression factor approach, the combined contribution of OATP1B1 (fraction transported ( f t ) = 0.62) and OATP1B3 ( f t = 0.31) was found to be 93% of the active uptake clearance of ML00960317 into the liver. Furthermore, OATP1B1 and OATP1B3-mediated uptake of ML00960317 was inhibited by rifampicin with IC 50 of 6.5 and 2.3 μM, respectively indicating an in vivo DDI risk (R value of 1.5 and 2.5 for OATP1B1 and OATP1B3, respectively). These results highlighted an important role of OATP1B1, OATP1B3, and MRP2 in the hepatobiliary disposition of ML00960317. These pathways may act as rate-determining steps in the hepatic clearance of ML00960317 thus presenting clinical DDI risk. Graphical Abstract

Nitrogen but not phosphorus addition affects symbiotic N2 fixation by legumes in natural and semi-natural grasslands located on four continents - Eduardo Vázquez; Per-Marten Schleuss; Elizabeth T. Borer; Miguel N. Bugalho; Maria C. Caldeira; Nico Eisenhauer; Anu Eskelinen; Philip A. Fay; Sylvia Haider; Anke Jentsch; Kevin P. Kirkman; Rebecca L. McCulley; et al. (Plant and Soil, 2022)
Background and aims The amount of nitrogen (N) derived from symbiotic N 2 fixation by legumes in grasslands might be affected by anthropogenic N and phosphorus (P) inputs, but the underlying mechanisms are not known. Methods We evaluated symbiotic N 2 fixation in 17 natural and semi-natural grasslands on four continents that are subjected to the same full-factorial N and P addition experiment, using the 15 N natural abundance method. Results N as well as combined N and P (NP) addition reduced aboveground legume biomass by 65% and 45%, respectively, compared to the control, whereas P addition had no significant impact. Addition of N and/or P had no significant effect on the symbiotic N 2 fixation per unit legume biomass. In consequence, the amount of N fixed annually per grassland area was less than half in the N addition treatments compared to control and P addition, irrespective of whether the dominant legumes were annuals or perennials. Conclusion Our results reveal that N addition mainly impacts symbiotic N 2 fixation via reduced biomass of legumes rather than changes in N 2 fixation per unit legume biomass. The results show that soil N enrichment by anthropogenic activities significantly reduces N 2 fixation in grasslands, and these effects cannot be reversed by additional P amendment.

Native and non-native fish predators differ in their consumptive and non-consumptive impacts on a native freshwater snail - Tabitha R. Siegfried; Silvia M. M. Gutierre; Susan E. Piacenza; Philip C. Darby (Aquatic Ecology, 2022)

Transitioning global change experiments on Southern Ocean phytoplankton from lab to field settings: Insights and challenges - Philip W. Boyd; Scott C. Doney; Sam Eggins; Michael J. Ellwood; Marion Fourquez; Brook L. Nunn; Robert Strzepek; Emma Timmins‐Schiffman (Limnology and Oceanography, 2022)
The influence of global change on Southern Ocean productivity will have major ramifications for future management of polar life. A prior laboratory study investigated the response of a batch‐cultured subantarctic diatom to projected change simulating conditions for 2100 (increased temperature/CO 2 /irradiance/iron; decreased macronutrients), showed a twofold higher chlorophyll‐derived growth rate driven mainly by temperature and iron. We translated this design to the field to understand the phytoplankton community response, within a subantarctic foodweb, to 2100 conditions. A 7‐d shipboard study utilizing 250‐liter mesocosms was conducted in March 2016. The outcome mirrors lab‐culture experiments, yielding twofold higher chlorophyll in the 2100 treatment relative to the control. This trend was also evident for intrinsic metrics including nutrient depletion. Unlike the lab‐culture study, photosynthetic competence revealed a transient effect in the 2100 mesocosm, peaking on day 3 then declining. Metaproteomics revealed significant differences in protein profiles between treatments by day 7. The control proteome was enriched for photosynthetic processes (c.f. 2100) and exhibited iron‐limitation signatures; the 2100 proteome exposed a shift in cellular energy production. Our findings of enhanced phytoplankton growth are comparable to model simulations, but underlying mechanisms (temperature, iron, and/or light) differ between experiments and models. Batch‐culture approaches hinder cross‐comparison of mesocosm findings to model simulations (the latter are akin to “continuous‐culture chemostats”). However, chemostat techniques are problematic to use with mesocosms, as mesozooplankton will evade seawater flow‐through, thereby accumulating. Thus, laboratory, field, and modeling approaches reveal challenges to be addressed to better understand how global change will alter Southern Ocean productivity.

Persistence and resistance: survival mechanisms of Candidatus Dormibacterota from nutrient‐poor Antarctic soils - Kate Montgomery; Timothy J. Williams; Merryn Brettle; Jonathan F. Berengut; Eden Zhang; Julian Zaugg; Philip Hugenholtz; Belinda C. Ferrari (Environmental Microbiology, 2022)

Whole-crown 13C-pulse labelling in a sub-arctic woodland to target canopy-specific carbon fluxes - Nina L. Friggens; Iain P. Hartley; Helen K. Grant; Thomas C. Parker; Jens-Arne Subke; Philip A. Wookey (Trees, 2022)
Key message Whole-crown 13 C-pulse labelling can target tree canopy C fluxes in regions with dense understorey cover and investigate how increased photosynthetic C inputs may affect whole-ecosystem C fluxes. Abstract Climate change-driven increases in plant productivity have been observed at high northern latitudes. These trends are driven, in part, by the increasing abundance of tall shrub and tree species in arctic ecosystems, and the advance of treelines. Higher plant productivity may alter carbon (C) allocation and, hence, ecosystem C cycling and soil C sequestration. It is important to understand the contributions that the newly established canopy forming overstorey species makes to C cycling in these ecosystems. However, the presence of a dense understorey cover makes this challenging, with established partitioning approaches causing disturbance and potentially introducing measurement artefacts. Here, we develop an in situ whole-crown 13 C-pulse labelling technique to isolate canopy C fluxes in areas of dense understorey cover. The crowns of five mountain birch ( Betula pubescens ssp. czerepanovii ) trees were provided with a 13 CO 2 pulse using portable field equipment, and leaf samples were collected from neighbouring con-specific trees and hetero-specific understorey shrubs on days 1–10 and 377 post-crown labelling. We found effective and long-term enrichment of foliage in labelled trees, but no evidence of the 13 C-signal in con- or hetero-specific neighbouring trees or woody shrubs. This method is promising and provides a valuable tool to isolate the role of canopy tree species in ecosystems with dense understorey cover.

Test–retest reliability of arterial spin labelling for cerebral blood flow in older adults with small vessel disease - Lauren R. Binnie; Mathilde M. H. Pauls; Philip Benjamin; Mohani-Preet K. Dhillon; Shai Betteridge; Brian Clarke; Rita Ghatala; Fearghal A. H. Hainsworth; Franklyn A. Howe; Usman Khan; Christina Kruuse; Jeremy B. Madigan; et al. (Translational Stroke Research, 2022)
Cerebral small vessel disease (SVD) is common in older people and is associated with lacunar stroke, white matter hyperintensities (WMH) and vascular cognitive impairment. Cerebral blood flow (CBF) is reduced in SVD, particularly within white matter. Here we quantified test–retest reliability in CBF measurements using pseudo-continuous arterial spin labelling (pCASL) in older adults with clinical and radiological evidence of SVD (N=54, mean (SD): 66.9 (8.7) years, 15 females/39 males). We generated whole-brain CBF maps on two visits at least 7 days apart (mean (SD): 20 (19), range 7-117 days). Test–retest reliability for CBF was high in all tissue types, with intra-class correlation coefficient [95%CI]: 0.758 [0.616, 0.852] for whole brain, 0.842 [0.743, 0.905] for total grey matter, 0.771 [0.636, 0.861] for deep grey matter (caudate-putamen and thalamus), 0.872 [0.790, 0.923] for normal-appearing white matter (NAWM) and 0.780 [0.650, 0.866] for WMH (all p<0.001). ANCOVA models indicated significant decline in CBF in total grey matter, deep grey matter and NAWM with increasing age and diastolic blood pressure (all p<0.001). CBF was lower in males relative to females (p=0.013 for total grey matter, p=0.004 for NAWM). We conclude that pCASL has high test–retest reliability as a quantitative measure of CBF in older adults with SVD. These findings support the use of pCASL in routine clinical imaging and as a clinical trial endpoint. All data come from the PASTIS trial, prospectively registered at: https://eudract.ema.europa.eu (2015-001235-20, registered 13/05/2015), http://www.clinicaltrials.gov (NCT02450253, registered 21/05/2015).

Healthcare Professionals’ Views of Working with Medical Interpreters in a Cancer Setting: an Exploratory Study - Felicity C. Martin; Jennifer Philip; Sue-Anne McLachlan (Journal of Cancer Education, 2022)

Hydrogeology of an urban weathered basement aquifer in Kampala, Uganda - Philip M. Nyenje; Denis Ocoromac; Stephen Tumwesige; Matt J. Ascott; James P. R. Sorensen; Andrew J. Newell; David M. J. Macdonald; Daren C. Gooddy; Callist Tindimugaya; Robinah N. Kulabako; Dan J. Lapworth; Jan Willem Foppen (Hydrogeology Journal, 2022)
Weathered basement aquifers are vital sources of drinking water in Africa. In order to better understand their role in the urban water balance, in a weathered basement aquifer in Kampala, Uganda, this study installed a transect of monitoring piezometers, carried out spring flow and high-frequency groundwater level monitoring, slug tests and hydrochemical analyses, including stable isotopes and groundwater residence time indicators. Findings showed a typical weathered basement aquifer with a 20–50-m thickness. Groundwater recharge was 3–50 mm/year, occurring during sustained rainfall. Recharge to a deep groundwater system within the saprock was slow and prolonged, while recharge to the springs on the valley slopes was quick and episodic, responding rapidly to precipitation. Springs discharged shallow groundwater, mixed with wastewater infiltrating from onsite sanitation practices and contributions from the deeper aquifer and were characterised by low flow rates (< 0.001 m 3 /s), low pH (<5), high nitrate values (61–190 mg/L as NO 3 ), and residence times of <30 years. The deeper groundwater system occurred in the saprolite/saprock, had low transmissivity (< 1 × 10 −5 m 2 /s), lower nitrate values (<20 mg/L as NO 3 ), pH 6–6.5 and longer residence times (40–60 years). Confined groundwater conditions in the valleys were created by the presence of clay-rich alluvium and gave rise to artesian conditions where groundwater had lower nitrate concentrations. The findings provide new insights into weathered basement aquifers in the urban tropics and show that small-scale abstractions are more sustainable in the deeper groundwater system in the valleys, where confined conditions are present.

Association of cerebral microvascular dysfunction and white matter injury in Alzheimer’s disease - Zsolt Bagi; Christopher D. Kroenke; Katie Anne Fopiano; Yanna Tian; Jessica A. Filosa; Larry S. Sherman; Eric B. Larson; C. Dirk Keene; Kiera Degener O’Brien; Philip A. Adeniyi; Stephen A. Back (GeroScience, 2022)

Senolytic treatment rescues blunted muscle hypertrophy in old mice - Cory M. Dungan; Vandre C. Figueiredo; Yuan Wen; Georgia L. VonLehmden; Christopher J. Zdunek; Nicholas T. Thomas; C. Brooks Mobley; Kevin A. Murach; Camille R. Brightwell; Douglas E. Long; Christopher S. Fry; Philip A. Kern; et al. (GeroScience, 2022)
With aging, skeletal muscle plasticity is attenuated in response to exercise. Here, we report that senescent cells, identified using senescence-associated β-galactosidase (SA β-Gal) activity and p21 immunohistochemistry, are very infrequent in resting muscle, but emerge approximately 2 weeks after a bout of resistance exercise in humans. We hypothesized that these cells contribute to blunted hypertrophic potential in old age. Using synergist ablation-induced mechanical overload (MOV) of the plantaris muscle to model resistance training in adult (5–6-month) and old (23–24-month) male C57BL/6 J mice, we found increased senescent cells in both age groups during hypertrophy. Consistent with the human data, there were negligible senescent cells in plantaris muscle from adult and old sham controls, but old mice had significantly more senescent cells 7 and 14 days following MOV relative to young. Old mice had blunted whole-muscle hypertrophy when compared to adult mice, along with smaller muscle fibers, specifically glycolytic type 2x + 2b fibers. To ablate senescent cells using a hit-and-run approach, old mice were treated with vehicle or a senolytic cocktail consisting of 5 mg/kg dasatinib and 50 mg/kg quercetin (D + Q) on days 7 and 10 during 14 days of MOV; control mice underwent sham surgery with or without senolytic treatment. Old mice given D + Q had larger muscles and muscle fibers after 14 days of MOV, fewer senescent cells when compared to vehicle-treated old mice, and changes in the expression of genes (i.e., Igf1 , Ddit4 , Mmp14 ) that are associated with hypertrophic growth. Our data collectively show that senescent cells emerge in human and mouse skeletal muscle following a hypertrophic stimulus and that D + Q improves muscle growth in old mice.

Sublethal exposure to pyriproxyfen does not impair the abilities of the backswimmer Buenoa amnigenus to prey upon Aedes aegypti larvae - Wilson Valbon; Sabrina Helena C. Araújo; Ritanne S. Nery; Julianna F. Barbosa; Philip L. Newland; Eugênio E. Oliveira (Ecotoxicology, 2022)

Mismatches in scale between highly mobile marine megafauna and marine protected areas - Melinda G. Conners; Nicholas B. Sisson; Pierre D. Agamboue; Philip W. Atkinson; Alastair M. M. Baylis; Scott R. Benson; Barbara A. Block; Steven J. Bograd; Pablo Bordino; W. D. Bowen; Paul Brickle; Ignacio M. Bruno; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs), particularly large MPAs, are increasing in number and size around the globe in part to facilitate the conservation of marine megafauna under the assumption that large-scale MPAs better align with vagile life histories; however, this alignment is not well established. Using a global tracking dataset from 36 species across five taxa, chosen to reflect the span of home range size in highly mobile marine megafauna, we show most MPAs are too small to encompass complete home ranges of most species. Based on size alone, 40% of existing MPAs could encompass the home ranges of the smallest ranged species, while only < 1% of existing MPAs could encompass those of the largest ranged species. Further, where home ranges and MPAs overlapped in real geographic space, MPAs encompassed < 5% of core areas used by all species. Despite most home ranges of mobile marine megafauna being much larger than existing MPAs, we demonstrate how benefits from MPAs are still likely to accrue by targeting seasonal aggregations and critical life history stages and through other management techniques.

Predicting Seabird Foraging Habitat for Conservation Planning in Atlantic Canada: Integrating Telemetry and Survey Data Across Thousands of Colonies - Robert A. Ronconi; David J. Lieske; Laura A. McFarlane Tranquilla; Sue Abbott; Karel A. Allard; Brad Allen; Amie L. Black; François Bolduc; Gail K. Davoren; Antony W. Diamond; David A. Fifield; Stefan Garthe; et al. (Frontiers in Marine Science, 2022)
Conservation of mobile organisms is difficult in the absence of detailed information about movement and habitat use. While the miniaturization of tracking devices has eased the collection of such information, it remains logistically and financially difficult to track a wide range of species across a large geographic scale. Predictive distribution models can be used to fill this gap by integrating both telemetry and census data to construct distribution maps and inform conservation goals and planning. We used tracking data from 520 individuals of 14 seabird species in Atlantic Canada to first compare foraging range and distance to shorelines among species across colonies, and then developed tree-based machine-learning models to predict foraging distributions for more than 5000 breeding sites distributed along more than 5000 km of shoreline. Despite large variability in foraging ranges among species, tracking data revealed clusters of species using similar foraging habitats (e.g., nearshore vs. offshore foragers), and within species, foraging range was highly colony-specific. Even with this variability, distance from the nesting colony was an important predictor of distribution for nearly all species, while distance from coastlines and bathymetry (slope and ruggedness) were additional important predictors for some species. Overall, we demonstrated the utility of tree-based machine-learning approach when modeling tracking data to predict distributions at un-sampled colonies. Although tracking and colony data have some shortcomings (e.g., fewer data for some species), where results need to be interpreted with care in some cases, applying methods for modeling breeding season distributions of seabirds allows for broader-scale conservation assessment. The modeled distributions can be used in decisions about planning for offshore recreation and commercial activities and to inform conservation planning at regional scales.

Brain Reactions to Opening and Closing the Eyes: Salivary Cortisol and Functional Connectivity - Shen-Da Chang; Po-Chih Kuo; Karl Zilles; Tim Q. Duong; Simon B. Eickhoff; Andrew C. W. Huang; Arthur C. Tsai; Philip E. Cheng; Michelle Liou (Brain Topography, 2022)
This study empirically assessed the strength and duration of short-term effects induced by brain reactions to closing/opening the eyes on a few well-known resting-state networks. We also examined the association between these reactions and subjects’ cortisol levels. A total of 55 young adults underwent 8-min resting-state fMRI (rs-fMRI) scans under 4-min eyes-closed and 4-min eyes-open conditions. Saliva samples were collected from 25 of the 55 subjects before and after the fMRI sessions and assayed for cortisol levels. Our empirical results indicate that when the subjects were relaxed with their eyes closed, the effect of opening the eyes on conventional resting-state networks (e.g., default-mode, frontal-parietal, and saliency networks) lasted for roughly 60-s, during which we observed a short-term increase in activity in rs-fMRI time courses. Moreover, brain reactions to opening the eyes had a pronounced effect on time courses in the temporo-parietal lobes and limbic structures, both of which presented a prolonged decrease in activity. After controlling for demographic factors, we observed a significantly positive correlation between pre-scan cortisol levels and connectivity in the limbic structures under both conditions. Under the eyes-closed condition, the temporo-parietal lobes presented significant connectivity to limbic structures and a significantly positive correlation with pre-scan cortisol levels. Future research on rs-fMRI could consider the eyes-closed condition when probing resting-state connectivity and its neuroendocrine correlates, such as cortisol levels. It also appears that abrupt instructions to open the eyes while the subject is resting quietly with eyes closed could be used to probe brain reactivity to aversive stimuli in the ventral hippocampus and other limbic structures.

Natural and anthropogenic controls on lake water‐level decline and evaporation‐to‐inflow ratio in the conterminous United States - C. Emi Fergus; J. Renée Brooks; Philip R. Kaufmann; Amina I. Pollard; Richard Mitchell; G. John Geldhof; Ryan A. Hill; Steven G. Paulsen; Paul Ringold; Marc Weber (Limnology and Oceanography, 2022)
Lake water levels are integral to lake function, but hydrologic changes from land and water management may alter lake fluctuations beyond natural ranges. We constructed a conceptual model of multifaceted drivers of lake water levels and evaporation‐to‐inflow ratio (Evap : Inflow). Using a structural equation modeling framework, we tested our model on (1) a national subset of lakes in the conterminous United States with minimal water management to describe natural drivers of lake hydrology and (2) five ecoregional subsets of lakes to explore regional variation in water management effects. Our model fits the national and ecoregional datasets and explained up to 47% of variation in Evap : Inflow, 38% of vertical water level decline, and 79% of horizontal water level decline (littoral exposure). For lakes with minimal water management, Evap : Inflow was related to lake depth ( β = −0.31) and surface inflow ( β = −0.44); vertical decline was related to annual climate (e.g., precipitation β = −0.18) and water management ( β = −0.21); and horizontal decline was largely related to vertical decline ( β = 0.73) and lake morphometry (e.g., depth β = −0.18). Anthropogenic effects varied by ecoregion and likely reflect differences in regional water management and climate. In the West, water management indicators were related to greater vertical decline ( β = 0.38), whereas in the Midwest, these indicators were related to more stable and full lake levels ( β = −0.22) even during drought conditions. National analyses show how human water use interacts with regional climate resulting in contrasting impacts to lake hydrologic variation in the United States.

Delineation of blacktip shark ( Carcharhinus limbatus ) nursery habitats in the north‐western Gulf of Mexico - Philip Matich; Camryn L. Bigelow; Barrett Chambers; Jillian J. Dodds; Jessica A. Hebert; Alexis Lemieux; Christy M. Pittman; Julianna Trapp; Brooke Bianco; Carolina P. Cadena; Emily I. Castillo; Gabriela I. Castillo; et al. (Journal of Fish Biology, 2022)
Coevolution with predators leads to the use of low‐risk habitats by many prey species, which promotes survival during early developmental phases. These nurseries are valued by conservation and management agencies because of their contributions to adult populations. However, the physical and geographic characteristics, like shallow depths and isolation from other marine habitats, that restrict access to predators and thereby reduce risk to juvenile animals can also limit scientific research. Consequently, many nursery habitats are still unidentified and understudied. Here we used gillnet monitoring from 1982 to 2018 to delineate blacktip shark ( Carcharhinus limbatus ) nurseries in the north‐western Gulf of Mexico and elucidated their physical, environmental and biological characteristics. Nursery habitats within estuaries (

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Successful storage of Trichomonas gallinae on Whatman FTA cards following culture - Rebecca C. Thomas; Jenny C. Dunn; Chris J. Orsman; Antony J. Morris; Helen Hipperson; Philip V. Grice; Keith C. Hamer; Simon J. Goodman (Conservation Genetics Resources, 2022)
Logistical constraints concerning parasite sample storage can hinder progress with the discovery of genetic variation on a global scale. New storage methods are being developed to address this, but require testing in order to understand how widely applicable these methods are. Whatman FTA cards have been tested previously under laboratory conditions for storing low-concentration Trichomonas gallinae isolates with the conclusion that they are not suitable, but have not been tested under field conditions. Here, we conducted a field-test, comparing FTA cards with storage in ethanol for T. gallinae samples collected and cultured from wild Columbiformes in Africa using standard field methods, before transportation to the UK. After 6 months storage, both methods resulted in an overall prevalence of 100% following PCR amplification (n = 59), suggesting that FTA cards are suitable for estimation of T. gallinae prevalence. However, samples stored in ethanol produced more, and longer, sequences than those stored on FTA cards. These data suggest storage in ethanol is preferable for the acquisition of high quality genetic strain data, but that FTA cards can be used successfully to ascertain infection prevalence and identify parasite strains under field conditions.

Caribbean king crab larvae and juveniles show tolerance to ocean acidification and ocean warming - Philip M. Gravinese; Shelby A. Perry; Angelo Jason Spadaro; Albert E. Boyd; Ian C. Enochs (Marine Biology, 2022)
Coastal habitats are experiencing decreases in seawater pH and increases in temperature due to anthropogenic climate change. The Caribbean king crab, Maguimithrax spinosissimus , plays a vital role on Western Atlantic reefs by grazing macroalgae that competes for space with coral recruits. Therefore, identifying its tolerance to anthropogenic stressors is critically needed if this species is to be considered as a potential restoration management strategy in coral reef environments. We examined the effects of temperature (control: 28 °C and elevated: 31 °C) and pH (control: 8.0 and reduced pH: 7.7) on the king crab’s larval and early juvenile survival, molt-stage duration, and morphology in a fully crossed laboratory experiment. Survival to the megalopal stage was reduced (13.5% lower) in the combined reduced pH and elevated temperature treatment relative to the control. First-stage (J1) juveniles delayed molting by 1.5 days in the reduced pH treatment, while second-stage (J2) crabs molted 3 days earlier when exposed to elevated temperature. Juvenile morphology did not differ among treatments. These results suggests that juvenile king crabs are tolerant to changes associated with climate change. Given the important role of the king crab as a grazer of macroalgae, its tolerance to climate stressors suggests that it could benefit restoration efforts aimed at making coral reefs more resilient to increasingly warm and acidic oceans into the future.

Estimated life-history traits and movements of the Caribbean reef shark (Carcharhinus perezi) in The Bahamas based on tag-recapture data - Brendan S. Talwar; Darcy Bradley; Christopher Berry; Mark E. Bond; Ian A. Bouyoucos; Annabelle M. L. Brooks; Candace Y. A. Fields; Austin J. Gallagher; Tristan L. Guttridge; Annie E. Guttridge; Neil Hammerschlag; Ian Hamilton; et al. (Marine Biology, 2022)

Assessing rates of parasite coinfection and spatiotemporal strain variation via metabarcoding: Insights for the conservation of European turtle doves Streptopelia turtur - Rebecca C. Thomas; Jenny C. Dunn; Deborah A. Dawson; Helen Hipperson; Gavin J. Horsburgh; Antony J. Morris; Chris Orsman; John Mallord; Philip V. Grice; Keith C. Hamer; Cyril Eraud; Lormée Hervé; et al. (Molecular Ecology, 2022)
Understanding the frequency, spatiotemporal dynamics and impacts of parasite coinfections is fundamental to developing control measures and predicting disease impacts. The European turtle dove ( Streptopelia turtur ) is one of Europe's most threatened bird species. High prevalence of infection by the protozoan parasite Trichomonas gallinae has previously been identified, but the role of this and other coinfecting parasites in turtle dove declines remains unclear. Using a high‐throughput sequencing approach, we identified seven strains of T . gallinae , including two novel strains, from ITS1/5.8S/ITS2 ribosomal sequences in turtle doves on breeding and wintering grounds, with further intrastrain variation and four novel subtypes revealed by the iron‐hydrogenase gene. High spatiotemporal turnover was observed in T . gallinae strain composition, and infection was prevalent in all populations (89%–100%). Coinfection by multiple Trichomonas strains was rarer than expected (1% observed compared to 38.6% expected), suggesting either within‐host competition, or high mortality of coinfected individuals. In contrast, coinfection by multiple haemosporidians was common (43%), as was coinfection by haemosporidians and T . gallinae (90%), with positive associations between strains of T . gallinae and Leucocytozoon suggesting a mechanism such as parasite‐induced immune modulation. We found no evidence for negative associations between coinfections and host body condition. We suggest that longitudinal studies involving the recapture and investigation of infection status of individuals over their lifespan are crucial to understand the epidemiology of coinfections in natural populations.

The impacts of mangrove range expansion on wetland ecosystem services in the southeastern United States: Current understanding, knowledge gaps, and emerging research needs - Michael J. Osland; A. Randall Hughes; Anna R. Armitage; Steven B. Scyphers; Just Cebrian; Savannah H. Swinea; Christine C. Shepard; Micheal S. Allen; Laura C. Feher; James A. Nelson; Cherie L. O’Brien; Colt R. Sanspree; et al. (Global Change Biology, 2022)
Climate change is transforming ecosystems and affecting ecosystem goods and services. Along the Gulf of Mexico and Atlantic coasts of the southeastern United States, the frequency and intensity of extreme freeze events greatly influence whether coastal wetlands are dominated by freeze‐sensitive woody plants (mangrove forests) or freeze‐tolerant grass‐like plants (salt marshes). In response to warming winters, mangroves have been expanding and displacing salt marshes at varying degrees of severity in parts of north Florida, Louisiana, and Texas. As winter warming accelerates, mangrove range expansion is expected to increasingly modify wetland ecosystem structure and function. Because there are differences in the ecological and societal benefits that salt marshes and mangroves provide, coastal environmental managers are challenged to anticipate the effects of mangrove expansion on critical wetland ecosystem services, including those related to carbon sequestration, wildlife habitat, storm protection, erosion reduction, water purification, fisheries support, and recreation. Mangrove range expansion may also affect wetland stability in the face of extreme climatic events and rising sea levels. Here, we review the current understanding of the effects of mangrove range expansion and displacement of salt marshes on wetland ecosystem services in the southeastern United States. We also identify critical knowledge gaps and emerging research needs regarding the ecological and societal implications of salt marsh displacement by expanding mangrove forests. One consistent theme throughout our review is that there are ecological trade‐offs for consideration by coastal managers. Mangrove expansion and marsh displacement can produce beneficial changes in some ecosystem services, while simultaneously producing detrimental changes in other services. Thus, there can be local‐scale differences in perceptions of the impacts of mangrove expansion into salt marshes. For very specific local reasons, some individuals may see mangrove expansion as a positive change to be embraced, while others may see mangrove expansion as a negative change to be constrained.

Biogeography of Southern Ocean prokaryotes: a comparison of the Indian and Pacific sectors - Swan L. S. Sow; Mark V. Brown; Laurence J. Clarke; Andrew Bissett; Jodie van de Kamp; Thomas W. Trull; Eric J. Raes; Justin R. Seymour; Anna R. Bramucci; Martin Ostrowski; Philip W. Boyd; Bruce E. Deagle; et al. (Environmental Microbiology, 2022)
Summary We investigated the Southern Ocean (SO) prokaryote community structure via zero‐radius operational taxonomic unit (zOTU) libraries generated from 16S rRNA gene sequencing of 223 full water column profiles. Samples reveal the prokaryote diversity trend between discrete water masses across multiple depths and latitudes in Indian (71–99°E, summer) and Pacific (170–174°W, autumn‐winter) sectors of the SO. At higher taxonomic levels (phylum‐family) we observed water masses to harbour distinct communities across both sectors, but observed sectorial variations at lower taxonomic levels (genus‐zOTU) and relative abundance shifts for key taxa such as Flavobacteria, SAR324/Marinimicrobia, Nitrosopumilus and Nitrosopelagicus at both epi‐ and bathy‐abyssopelagic water masses. Common surface bacteria were abundant in several deep‐water masses and vice‐versa suggesting connectivity between surface and deep‐water microbial assemblages. Bacteria from same‐sector Antarctic Bottom Water samples showed patchy, high beta‐diversity which did not correlate well with measured environmental parameters or geographical distance. Unconventional depth distribution patterns were observed for key archaeal groups: Crenarchaeota was found across all depths in the water column and persistent high relative abundances of common epipelagic archaeon Nitrosopelagicus was observed in deep‐water masses. Our findings reveal substantial regional variability of SO prokaryote assemblages that we argue should be considered in wide‐scale SO ecosystem microbial modelling.

Lessons From the Western Atlantic Lionfish Invasion to Inform Management in the Mediterranean - Aylin Ulman; Fadilah Z. Ali; Holden E. Harris; Mohammad Adel; Sara A. A. Al Mabruk; Michel Bariche; Allison C. Candelmo; Jennifer K. Chapman; Burak Ali Çiçek; Kaylin R. Clements; Alexander Q. Fogg; Stacy Frank; et al. (Frontiers in Marine Science, 2022)
Major invasions of Indo-Pacific lionfish ( Pterois volitans and P. miles ) are underway in the Western Atlantic Ocean and the Mediterranean Sea. While the establishment of lionfish in the Western Atlantic is perhaps the most well-studied marine fish invasion to date, the rapidly expanding invasion in the Mediterranean is more recent and has received less attention. Here we review and synthesize successes and failures from two decades of lionfish management in the Western Atlantic to give policy recommendations for their management in the Mediterranean. Two failed approaches that were attempted multiple times in the Western Atlantic and that we advise against are (1) feeding lionfish to native fish to promote predation and (2) implementing bounty programs to incentivize lionfish harvest. Broadly, the most important management lessons that we recommend include (1) conducting routine removals by spearfishing with scuba, which can effectively suppress local abundances of lionfish; (2) encouraging the development of recreational and commercial lionfish fisheries, which can promote long-term, sustainable lionfish population control; and, (3) engaging local communities and resource users (e.g., with lionfish removal tournaments), which can concurrently achieve multiple objectives of promoting lionfish removals, market-development, research, and public education. Managers in the Western Atlantic often needed to adapt current conservation policies to enable lionfish removals in areas where spearfishing with scuba was otherwise prohibited for conservation purposes. The risk of abusing these policies was mitigated through the use of gear restrictions, diver trainings, and through participatory approaches that integrated scuba divers and stakeholder organizations in lionfish research and management. Our review of policies and practices in the Mediterranean Sea found that many of our recommended lionfish management approaches are not being done and indicate potential opportunities to implement these. We expect and fully recommend that work continues towards multinational cooperation to facilitate regional coordination of research, control, and management efforts with respect to the Mediterranean lionfish invasion. As with other major biological invasions, lionfish are unconstrained by political borders and their control will require rapid and strategic management approaches with broad cooperation among and between governments and stakeholders.

Genomic analysis of a parasite invasion: Colonization of the Americas by the blood fluke Schistosoma mansoni - Roy N. Platt; Winka Le Clec'h; Frédéric D. Chevalier; Marina McDew‐White; Philip T. LoVerde; Rafael Ramiro de Assis; Guilherme Oliveira; Safari Kinung'hi; Amadou Garba Djirmay; Michelle L. Steinauer; Anouk Gouvras; Muriel Rabone; et al. (Molecular Ecology, 2022)
Schistosoma mansoni , a snail‐borne, blood fluke that infects humans, was introduced into the Americas from Africa during the Trans‐Atlantic slave trade. As this parasite shows strong specificity to the snail intermediate host, we expected that adaptation to South American Biomphalaria spp. snails would result in population bottlenecks and strong signatures of selection. We scored 475,081 single nucleotide variants in 143 S. mansoni from the Americas (Brazil, Guadeloupe and Puerto Rico) and Africa (Cameroon, Niger, Senegal, Tanzania, and Uganda), and used these data to ask: (i) Was there a population bottleneck during colonization? (ii) Can we identify signatures of selection associated with colonization? (iii) What were the source populations for colonizing parasites? We found a 2.4‐ to 2.9‐fold reduction in diversity and much slower decay in linkage disequilibrium (LD) in parasites from East to West Africa. However, we observed similar nuclear diversity and LD in West Africa and Brazil, suggesting no strong bottlenecks and limited barriers to colonization. We identified five genome regions showing selection in the Americas, compared with three in West Africa and none in East Africa, which we speculate may reflect adaptation during colonization. Finally, we infer that unsampled populations from central African regions between Benin and Angola, with contributions from Niger, are probably the major source(s) for Brazilian S. mansoni . The absence of a bottleneck suggests that this is a rare case of a serendipitous invasion, where S. mansoni parasites were pre‐adapted to the Americas and able to establish with relative ease.

Nutrient identity modifies the destabilising effects of eutrophication in grasslands - Oliver Carroll; Evan Batzer; Siddharth Bharath; Elizabeth T. Borer; Sofía Campana; Ellen Esch; Yann Hautier; Timothy Ohlert; Eric W. Seabloom; Peter B. Adler; Jonathan D. Bakker; Lori Biederman; et al. (Ecology Letters, 2022)
Nutrient enrichment can simultaneously increase and destabilise plant biomass production, with co‐limitation by multiple nutrients potentially intensifying these effects. Here, we test how factorial additions of nitrogen (N), phosphorus (P) and potassium with essential nutrients (K+) affect the stability (mean/standard deviation) of aboveground biomass in 34 grasslands over 7 years. Destabilisation with fertilisation was prevalent but was driven by single nutrients, not synergistic nutrient interactions. On average, N‐based treatments increased mean biomass production by 21–51% but increased its standard deviation by 40–68% and so consistently reduced stability. Adding P increased interannual variability and reduced stability without altering mean biomass, while K+ had no general effects. Declines in stability were largest in the most nutrient‐limited grasslands, or where nutrients reduced species richness or intensified species synchrony. We show that nutrients can differentially impact the stability of biomass production, with N and P in particular disproportionately increasing its interannual variability.

Light and thermal niches of ground‐foraging A mazonian insectivorous birds - Vitek Jirinec; Patricia F. Rodrigues; Bruna R. Amaral; Philip C Stouffer (Ecology, 2022)
Insectivores of the tropical rainforest floor are consistently among the most vulnerable birds to forest clearing and fragmentation. Several hypotheses attempt to explain this pattern, including sensitivity to extreme microclimates found near forest borders, particularly brighter and warmer conditions. Importantly, this “microclimate hypothesis” has additional implications for intact forest under global climate change that could be evaluated through direct assessment of the light and temperature environment of terrestrial insectivores. In this study, we harness novel technology to directly quantify the light and thermal niches of 10 species of terrestrial insectivores in undisturbed Amazonian rainforest. Loggers placed on birds ( N = 33) and their environment ( N = 9) recorded nearly continuous microclimate data from 2017 to 2019, amassing >5 million measurements. We found that midday light intensity in tree fall gaps (~39,000 lux) was >40 times higher than at the ground level of forest interior (950 lux). Light intensity registered by sensors placed on birds averaged 17.4 (range 3.9–41.5) lux, with species using only 4.3% (0.9%–10.4%) of available light on the forest floor. Birds therefore selected very dark microhabitats—the light environment was >2200 times brighter in tree fall gaps. Bird thermal niche was a function of ambient temperature as well as body temperature, which averaged >40.5°C but varied among species. Forest floor temperature peaked daily at 27.0°C, whereas bird loggers averaged 35.1°C (34.5–35.7°C) at midday. The antpitta Myrmothera campanisona and the antthrush Formicarius colma used thermal conditions closest to their body temperatures, whereas leaftossers ( Sclerurus spp.) and Myrmornis torquata occupied relatively cool microclimates. We found no general link between abundance trends and variation in species‐specific light and thermal niches. However, all species occupied markedly dim and cool microclimates. Because such conditions are rare outside the interior of primary forest, these results support the microclimate hypothesis in disturbed landscapes. Moreover, strong avoidance of conditions that are becoming more common under climate change highlights the vulnerability of terrestrial insectivores even in the absence of disturbance and may be the reason for enigmatic declines in Amazonia and elsewhere.

Connectivity in the Urban Landscape (2015–2020): Who? Where? What? When? Why? and How? - Todd R. Lookingbill; Emily S. Minor; Charles S. Mullis; Gabriela C. Nunez-Mir; Philip Johnson (Current Landscape Ecology Reports, 2022)

Effects of continuous cycling training on motor unit firing rates, input excitation, and myosin heavy chain of the vastus lateralis in sedentary females - Michael A. Trevino; Hannah L. Dimmick; Mandy E. Parra; Adam J. Sterczala; Jonathan D. Miller; Jake A. Deckert; Philip M. Gallagher; Andrew C. Fry; Joseph P. Weir; Trent J. Herda (Experimental Brain Research, 2022)

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Soil carbon stocks in temperate grasslands differ strongly across sites but are insensitive to decade‐long fertilization - Adrienne B. Keller; Elizabeth T. Borer; Scott L. Collins; Lang C. DeLancey; Philip A. Fay; Kirsten S. Hofmockel; Andrew D.B. Leakey; Melanie A. Mayes; Eric W. Seabloom; Christopher A. Walter; Yong Wang; Qian Zhao; et al. (Global Change Biology, 2022)
Enhancing soil carbon (C) storage has the potential to offset human‐caused increases in atmospheric CO 2 . Rising CO 2 has occurred concurrently with increasing supply rates of biologically limiting nutrients such as nitrogen (N) and phosphorus (P). However, it is unclear how increased supplies of N and P will alter soil C sequestration, particularly in grasslands, which make up nearly a third of non‐agricultural land worldwide. Here, we leverage a globally distributed nutrient addition experiment (the Nutrient Network) to examine how a decade of N and P fertilization (alone and in combination) influenced soil C and N stocks at nine grassland sites spanning the continental United States. We measured changes in bulk soil C and N stocks and in three soil C fractions (light and heavy particulate organic matter, and mineral‐associated organic matter fractions). Nutrient amendment had variable effects on soil C and N pools that ranged from strongly positive to strongly negative, while soil C and N pool sizes varied by more than an order of magnitude across sites. Piecewise SEM clarified that small increases in plant C inputs with fertilization did not translate to greater soil C storage. Nevertheless, peak season aboveground plant biomass (but not root biomass or production) was strongly positively related to soil C storage at seven of the nine sites, and across all nine sites, soil C covaried with moisture index and soil mineralogy, regardless of fertilization. Overall, we show that site factors such as moisture index, plant productivity, soil texture, and mineralogy were key predictors of cross‐site soil C, while nutrient amendment had weaker and site‐specific effects on C sequestration. This suggests that prioritizing the protection of highly productive temperate grasslands is critical for reducing future greenhouse gas losses arising from land use change.

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Promoting FAIR Data Through Community-driven Agile Design: the Open Data Commons for Spinal Cord Injury (odc-sci.org) - Abel Torres-Espín; Carlos A. Almeida; Austin Chou; J. Russell Huie; Michael Chiu; Romana Vavrek; Jeff Sacramento; Michael B. Orr; John C. Gensel; Jeffery S. Grethe; Maryann E. Martone; Karim Fouad; et al. (Neuroinformatics, 2022)
The past decade has seen accelerating movement from data protectionism in publishing toward open data sharing to improve reproducibility and translation of biomedical research. Developing data sharing infrastructures to meet these new demands remains a challenge. One model for data sharing involves simply attaching data, irrespective of its type, to publisher websites or general use repositories. However, some argue this creates a ‘data dump’ that does not promote the goals of making data Findable, Accessible, Interoperable and Reusable (FAIR). Specialized data sharing communities offer an alternative model where data are curated by domain experts to make it both open and FAIR. We report on our experiences developing one such data-sharing ecosystem focusing on ‘long-tail’ preclinical data, the Open Data Commons for Spinal Cord Injury (odc-sci.org). ODC-SCI was developed with community-based agile design requirements directly pulled from a series of workshops with multiple stakeholders (researchers, consumers, non-profit funders, governmental agencies, journals, and industry members). ODC-SCI focuses on heterogeneous tabular data collected by preclinical researchers including bio-behaviour, histopathology findings and molecular endpoints. This has led to an example of a specialized neurocommons that is well-embraced by the community it aims to serve. In the present paper, we provide a review of the community-based design template and describe the adoption by the community including a high-level review of current data assets, publicly released datasets, and web analytics. Although odc-sci.org is in its late beta stage of development, it represents a successful example of a specialized data commons that may serve as a model for other fields.

Estimating Bycatch Mortality for Marine Mammals: Concepts and Best Practices - Jeffrey E. Moore; Dennis Heinemann; Tessa B. Francis; Philip S. Hammond; Kristy J. Long; André E. Punt; Randall R. Reeves; Maritza Sepúlveda; Guðjón Már Sigurðsson; Margaret C. Siple; Gísli A. Víkingsson; Paul R. Wade; et al. (Frontiers in Marine Science, 2021)
Fisheries bycatch is the greatest current source of human-caused deaths of marine mammals worldwide, with severe impacts on the health and viability of many populations. Recent regulations enacted in the United States under the Fish and Fish Product Import Provisions of its Marine Mammal Protection Act require nations with fisheries exporting fish and fish products to the United States (hereafter, “export fisheries”) to have or establish marine mammal protection standards that are comparable in effectiveness to the standards for United States commercial fisheries. In many cases, this will require estimating marine mammal bycatch in those fisheries. Bycatch estimation is conceptually straightforward but can be difficult in practice, especially if resources (funding) are limiting or for fisheries consisting of many, small vessels with geographically-dispersed landing sites. This paper describes best practices for estimating bycatch mortality, which is an important ingredient of bycatch assessment and mitigation. We discuss a general bycatch estimator and how to obtain its requisite bycatch-rate and fisheries-effort data. Scientific observer programs provide the most robust bycatch estimates and consequently are discussed at length, including characteristics such as study design, data collection, statistical analysis, and common sources of estimation bias. We also discuss alternative approaches and data types, such as those based on self-reporting and electronic vessel-monitoring systems. This guide is intended to be useful to managers and scientists in countries having or establishing programs aimed at managing marine mammal bycatch, especially those conducting first-time assessments of fisheries impacts on marine mammal populations.

Ultrastructure and in-situ chemical characterization of intracellular granules of embryo-like fossils from the early Ediacaran Weng’an biota - Weichen Sun; Zongjun Yin; Pengju Liu; Philip C. J. Donoghue; Jinhua Li; Maoyan Zhu (PalZ, 2021)

Soil properties as key predictors of global grassland production: Have we overlooked micronutrients? - Dajana Radujković; Erik Verbruggen; Eric W. Seabloom; Michael Bahn; Lori A. Biederman; Elizabeth T. Borer; Elizabeth H. Boughton; Jane A. Catford; Matteo Campioli; Ian Donohue; Anne Ebeling; Anu Eskelinen; et al. (Ecology Letters, 2021)
Fertilisation experiments have demonstrated that nutrient availability is a key determinant of biomass production and carbon sequestration in grasslands. However, the influence of nutrients in explaining spatial variation in grassland biomass production has rarely been assessed. Using a global dataset comprising 72 sites on six continents, we investigated which of 16 soil factors that shape nutrient availability associate most strongly with variation in grassland aboveground biomass. Climate and N deposition were also considered. Based on theory‐driven structural equation modelling, we found that soil micronutrients (particularly Zn and Fe) were important predictors of biomass and, together with soil physicochemical properties and C:N, they explained more unique variation (32%) than climate and N deposition (24%). However, the association between micronutrients and biomass was absent in grasslands limited by NP. These results highlight soil properties as key predictors of global grassland biomass production and point to serial co‐limitation by NP and micronutrients.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Best Practices for Assessing and Managing Bycatch of Marine Mammals - Paul R. Wade; Kristy J. Long; Tessa B. Francis; André E. Punt; Philip S. Hammond; Dennis Heinemann; Jeffrey E. Moore; Randall R. Reeves; Maritza Sepúlveda; Genoa Sullaway; Guðjón Már Sigurðsson; Margaret C. Siple; et al. (Frontiers in Marine Science, 2021)
Bycatch in marine fisheries is the leading source of human-caused mortality for marine mammals, has contributed to substantial declines of many marine mammal populations and species, and the extinction of at least one. Schemes for evaluating marine mammal bycatch largely rely on estimates of abundance and bycatch, which are needed for calculating biological reference points and for determining conservation status. However, obtaining these estimates is resource intensive and takes careful long-term planning. The need for assessments of marine mammal bycatch in fisheries is expected to increase worldwide due to the recently implemented Import Provisions of the United States Marine Mammal Protection Act. Managers and other stakeholders need reliable, standardized methods for collecting data to estimate abundance and bycatch rates. In some cases, managers will be starting with little or no data and no system in place to collect data. We outline a comprehensive framework for managing bycatch of marine mammals. We describe and provide guidance on (1) planning for an assessment of bycatch, (2) collecting appropriate data (e.g., abundance and bycatch estimates), (3) assessing bycatch and calculating reference points, and (4) using the results of the assessment to guide marine mammal bycatch reduction. We also provide a brief overview of available mitigation techniques to reduce marine mammal bycatch in various fisheries. This paper provides information for scientists and resource managers in the hope that it will lead to new or improved programs for assessing marine mammal bycatch, establishing best practices, and enhancing marine mammal conservation globally.

Animal Borne Ocean Sensors – AniBOS – An Essential Component of the Global Ocean Observing System - Clive R. McMahon; Fabien Roquet; Sophie Baudel; Mathieu Belbeoch; Sophie Bestley; Clint Blight; Lars Boehme; Fiona Carse; Daniel P. Costa; Michael A. Fedak; Christophe Guinet; Robert Harcourt; et al. (Frontiers in Marine Science, 2021)
Marine animals equipped with biological and physical electronic sensors have produced long-term data streams on key marine environmental variables, hydrography, animal behavior and ecology. These data are an essential component of the Global Ocean Observing System (GOOS). The Animal Borne Ocean Sensors (AniBOS) network aims to coordinate the long-term collection and delivery of marine data streams, providing a complementary capability to other GOOS networks that monitor Essential Ocean Variables (EOVs), essential climate variables (ECVs) and essential biodiversity variables (EBVs). AniBOS augments observations of temperature and salinity within the upper ocean, in areas that are under-sampled, providing information that is urgently needed for an improved understanding of climate and ocean variability and for forecasting. Additionally, measurements of chlorophyll fluorescence and dissolved oxygen concentrations are emerging. The observations AniBOS provides are used widely across the research, modeling and operational oceanographic communities. High latitude, shallow coastal shelves and tropical seas have historically been sampled poorly with traditional observing platforms for many reasons including sea ice presence, limited satellite coverage and logistical costs. Animal-borne sensors are helping to fill that gap by collecting and transmitting in near real time an average of 500 temperature-salinity-depth profiles per animal annually and, when instruments are recovered (∼30% of instruments deployed annually, n = 103 ± 34), up to 1,000 profiles per month in these regions. Increased observations from under-sampled regions greatly improve the accuracy and confidence in estimates of ocean state and improve studies of climate variability by delivering data that refine climate prediction estimates at regional and global scales. The GOOS Observations Coordination Group (OCG) reviews, advises on and coordinates activities across the global ocean observing networks to strengthen the effective implementation of the system. AniBOS was formally recognized in 2020 as a GOOS network. This improves our ability to observe the ocean’s structure and animals that live in them more comprehensively, concomitantly improving our understanding of global ocean and climate processes for societal benefit consistent with the UN Sustainability Goals 13 and 14: Climate and Life below Water. Working within the GOOS OCG framework ensures that AniBOS is an essential component of an integrated Global Ocean Observing System.

Acute alcohol intoxication and the cocktail party problem: do “mocktails” help or hinder? - Alistair J. Harvey; C. Philip Beaman (Psychopharmacology, 2021)
Rationale To test the notion that alcohol impairs auditory attentional control by reducing the listener’s cognitive capacity. Objectives We examined the effect of alcohol consumption and working memory span on dichotic speech shadowing and the cocktail party effect—the ability to focus on one of many simultaneous speakers yet still detect mention of one’s name amidst the background speech. Alcohol was expected either to increase name detection, by weakening the inhibition of irrelevant speech, or reduce name detection, by restricting auditory attention on to the primary input channel. Low-span participants were expected to show larger drug impairments than high-span counterparts. Methods On completion of the working memory span task, participants ( n = 81) were randomly assigned to an alcohol or placebo beverage treatment. After alcohol absorption, they shadowed speech presented to one ear while ignoring the synchronised speech of a different speaker presented to the other. Each participant’s first name was covertly embedded in to-be-ignored speech. Results The “cocktail party effect” was not affected by alcohol or working memory span, though low-span participants made more shadowing errors and recalled fewer words from the primary channel than high-span counterparts. Bayes factors support a null effect of alcohol on the cocktail party phenomenon, on shadowing errors and on memory for either shadowed or ignored speech. Conclusion Findings suggest that an alcoholic beverage producing a moderate level of intoxication ( M BAC ≈ 0.08%) neither enhances nor impairs the cocktail party effect.

Untangling local and remote influences in two major petrel habitats in the oligotrophic Southern Ocean - Daniel C. Jones; Filipe R. Ceia; Eugene Murphy; Karine Delord; Robert W. Furness; Ariane Verdy; Matthew Mazloff; Richard A. Phillips; Paul M. Sagar; Jean‐Baptiste Sallée; Ben Schreiber; David R. Thompson; et al. (Global Change Biology, 2021)
Ocean circulation connects geographically distinct ecosystems across a wide range of spatial and temporal scales via exchanges of physical and biogeochemical properties. Remote oceanographic processes can be especially important for ecosystems in the Southern Ocean, where the Antarctic Circumpolar Current transports properties across ocean basins through both advection and mixing. Recent tracking studies have indicated the existence of two large‐scale, open ocean habitats in the Southern Ocean used by grey petrels ( Procellaria cinerea ) from two populations (i.e., Kerguelen and Antipodes islands) during their nonbreeding season for extended periods during austral summer (i.e., October to February). In this work, we use a novel combination of large‐scale oceanographic observations, surface drifter data, satellite‐derived primary productivity, numerical adjoint sensitivity experiments, and output from a biogeochemical state estimate to examine local and remote influences on these grey petrel habitats. Our aim is to understand the oceanographic features that control these isolated foraging areas and to evaluate their ecological value as oligotrophic open ocean habitats. We estimate the minimum local primary productivity required to support these populations to be much

Local Treatment of Non-small Cell Lung Cancer with a Spray-Dried Bevacizumab Formulation - Kimberly B. Shepard; David T. Vodak; Philip J. Kuehl; David Revelli; Yue Zhou; Amanda M. Pluntze; Molly S. Adam; Julia C. Oddo; Lauren Switala; Jonathan L. Cape; John M. Baumann; Michael Banks (AAPS PharmSciTech, 2021)
Local delivery of biotherapeutics to the lung holds great promise for treatment of lung diseases, but development of physically stable, biologically active dry powder formulations of large molecules for inhalation has remained a challenge. Here, spray drying was used to manufacture a dry powder pulmonary formulation of bevacizumab, a monoclonal antibody approved to treat non-small cell lung cancer (NSCLC) by intravenous infusion. By reformulating bevacizumab for local delivery, reduced side effects, lower doses, and improved patient compliance are possible. The formulation had aerosol properties suitable for delivery to the deep lung, as well as good physical stability at ambient temperature for at least 6 months. Bevacizumab’s anti-VEGF bioactivity was not impacted by the manufacturing process. The formulation was efficacious in an in vivo rat model for NSCLC at a 10-fold decrease in dose relative to the intravenous control.

Long‐term, low incidence of web‐decorating by spiders in the Mariana Islands, Micronesia - Alexander M. Kerr; Joanne D. Sablan; Michelle K. Williams; Ferdinand Galsim; Philip C. Guerrero; Abram L. Townsend; J. Kawika Davis; Gregorio C. Borja; Ryszard Z. Oleksy; John F. Furey; David L. Benavente; Erin M. Derrington; et al. (Ecology, 2021)

Threats of illegal, unregulated, and unreported fishing to biodiversity and food security in the Republic of the Congo - Philip D. Doherty; Benoit C. Atsango; Gaston Ngassiki; Appolinaire Ngouembe; Nathalie Bréheret; Eva Chauvet; Brendan J. Godley; Lucie Machin; Baudelaire Dissondet Moundzoho; Richard J. Parnell; Kristian Metcalfe (Conservation Biology, 2021)
Illegal, unregulated, and unreported (IUU) fishing poses a major threat to effective management of marine resources, affecting biodiversity and communities dependent on these coastal resources. Spatiotemporal patterns of industrial fisheries in developing countries are often poorly understood, and global efforts to describe spatial patterns of fishing vessel activity are currently based on automatic identification system (AIS) data. However, AIS is often not a legal requirement on fishing vessels, likely resulting in underestimates of the scale and distribution of legal and illegal fishing activity, which could have significant ramifications for targeted enforcement efforts and the management of fisheries resources. To help address this knowledge gap, we analyzed 3 years of vessel monitoring system (VMS) data in partnership with the national fisheries department in the Republic of the Congo to describe the behavior of national and distant‐water industrial fleets operating in these waters. We found that the spatial footprint of the industrial fisheries fleet encompassed over one‐quarter of the Exclusive Economic Zone. On average, 73% of fishing activity took place on the continental shelf (waters shallower than 200 m). Our findings highlight that VMS is not acting as a deterrent or being effectively used as a proactive management tool. As much as 33% (13% on average) of fishing effort occurred in prohibited areas set aside to protect biodiversity, including artisanal fisheries resources, and the distant‐water fleet responsible for as much as 84% of this illegal activity. Given the growth in industrial and distant‐water fleets across the region, as well as low levels of management and enforcement, these findings highlight that there is an urgent need for the global community to help strengthen regional and national capacity to analyze national scale data sets if efforts to combat IUU fishing are to be effective.

Estimating the Abundance of Marine Mammal Populations - Philip S. Hammond; Tessa B. Francis; Dennis Heinemann; Kristy J. Long; Jeffrey E. Moore; André E. Punt; Randall R. Reeves; Maritza Sepúlveda; Guðjón Már Sigurðsson; Margaret C. Siple; Gísli Víkingsson; Paul R. Wade; et al. (Frontiers in Marine Science, 2021)
Motivated by the need to estimate the abundance of marine mammal populations to inform conservation assessments, especially relating to fishery bycatch, this paper provides background on abundance estimation and reviews the various methods available for pinnipeds, cetaceans and sirenians. We first give an “entry-level” introduction to abundance estimation, including fundamental concepts and the importance of recognizing sources of bias and obtaining a measure of precision. Each of the primary methods available to estimate abundance of marine mammals is then described, including data collection and analysis, common challenges in implementation, and the assumptions made, violation of which can lead to bias. The main method for estimating pinniped abundance is extrapolation of counts of animals (pups or all-ages) on land or ice to the whole population. Cetacean and sirenian abundance is primarily estimated from transect surveys conducted from ships, small boats or aircraft. If individuals of a species can be recognized from natural markings, mark-recapture analysis of photo-identification data can be used to estimate the number of animals using the study area. Throughout, we cite example studies that illustrate the methods described. To estimate the abundance of a marine mammal population, key issues include: defining the population to be estimated, considering candidate methods based on strengths and weaknesses in relation to a range of logistical and practical issues, being aware of the resources required to collect and analyze the data, and understanding the assumptions made. We conclude with a discussion of some practical issues, given the various challenges that arise during implementation.

Dosimetric evaluation of a patient-specific 3D-printed oral positioning stent for head-and-neck radiotherapy - Susannah Cleland; Philip Chan; Benjamin Chua; Scott B. Crowe; Jodi Dawes; Lizbeth Kenny; Charles Lin; Elise Obereigner; Samuel C. Peet; Jamie V. Trapp; Tania Poroa; Tanya Kairn (Physical and Engineering Sciences in Medicine, 2021)

Using Forecasting Methods to Incorporate Social, Economic, and Political Considerations Into Marine Protected Area Planning - Seth T. Sykora-Bodie; Jorge G. Álvarez-Romero; Javier A. Arata; Alistair Dunn; Jefferson T. Hinke; Grant Humphries; Christopher Jones; Pål Skogrand; Katharina Teschke; Philip N. Trathan; Dirk Welsford; Natalie C. Ban; et al. (Frontiers in Marine Science, 2021)
As the global environmental crisis grows in scale and complexity, conservation professionals and policymakers are increasingly called upon to make decisions despite high levels of uncertainty, limited resources, and insufficient data. Global efforts to protect biodiversity in areas beyond national jurisdiction require substantial international cooperation and negotiation, both of which are characterized by unpredictability and high levels of uncertainty. Here we build on recent studies to adapt forecasting techniques from the fields of hazard prediction, risk assessment, and intelligence analysis to forecast the likelihood of marine protected area (MPA) designation in the Southern Ocean. We used two questionnaires, feedback, and a discussion round in a Delphi-style format expert elicitation to obtain forecasts, and collected data on specific biophysical, socioeconomic, geopolitical, and scientific factors to assess how they shape and influence these forecasts. We found that areas further north along the Western Antarctic Peninsula were considered to be less likely to be designated than areas further south, and that geopolitical factors, such as global politics or events, and socioeconomic factors, such as the presence of fisheries, were the key determinants of whether an area was predicted to be more or less likely to be designated as an MPA. Forecasting techniques can be used to inform protected area design, negotiation, and implementation in highly politicized situations where data is lacking by aiding with spatial prioritization, targeting scarce resources, and predicting the success of various spatial arrangements, interventions, or courses of action.

The effects of soil incorporation depth of Biodiesel Co-Product (BCP) additions on N leaching losses and on genes involved in soil nitrogen cycling in an acidic Chinese tea soil - Qunli Shen; Jiuwei Song; Kaile Zhang; Paul Voroney; Jiangye Li; Jianming Xu; Philip C. Brookes (Biology and Fertility of Soils, 2021)

Persistence and resistance: survival mechanisms of Candidatus Dormibacterota from nutrient‐poor Antarctic soils - Kate Montgomery; Timothy J. Williams; Merryn Brettle; Jonathan F. Berengut; Angelique E. Ray; Eden Zhang; Julian Zaugg; Philip Hugenholtz; Belinda C. Ferrari (Environmental Microbiology, 2021)
Summary Candidatus Dormibacterota is an uncultured bacterial phylum found predominantly in soil that is present in high abundances within cold desert soils. Here, we interrogate nine metagenome‐assembled genomes ( MAGs ), including six new MAGs derived from soil metagenomes obtained from two eastern Antarctic sites. Phylogenomic and taxonomic analyses revealed these MAGs represent four genera and five species, representing two order‐level clades within Ca . Dormibacterota. Metabolic reconstructions of these MAGs revealed the potential for aerobic metabolism, and versatile adaptations enabling persistence in the ‘extreme’ Antarctic environment. Primary amongst these adaptations were abilities to scavenge atmospheric H 2 and CO as energy sources, as well as using the energy derived from H 2 oxidation to fix atmospheric CO 2 via the Calvin–Bassham–Benson cycle, using a RuBisCO type IE . We propose that these allow Ca . Dormibacterota to persist using H 2 oxidation and grow using atmospheric chemosynthesis in terrestrial Antarctica. Fluorescence in situ hybridization revealed Ca . Dormibacterota to be coccoid cells, 0.3–1.4 μm in diameter, with some cells exhibiting the potential for a symbiotic or syntrophic lifestyle.

Movements, Habitat Use, and Diving Behavior of Shortfin Mako in the Atlantic Ocean - Catarina C. Santos; Andrés Domingo; John Carlson; Lisa J. Natanson; Paulo Travassos; David Macías; Enric Cortés; Philip Miller; Fábio Hazin; Federico Mas; Josetxu Ortiz de Urbina; Pedro G. Lino; et al. (Frontiers in Marine Science, 2021)
The shortfin mako is one of the most important shark species caught in Atlantic Ocean pelagic fisheries. Given increasing concerns for the stock status of the species, the present study was designed to fill gaps in the knowledge of habitat use and movement patterns of shortfin mako in the Atlantic Ocean. From 2015 to 2019, 53 shortfin makos were tagged with pop-up satellite archival tags within the North, Central, and Southwest Atlantic Ocean, with successful transmissions received from 34 tags. Generally, sharks tagged in the Northwest and Central Atlantic moved away from tagging sites showing low to no apparent residency patterns, whereas sharks tagged in the Northeast and Southwest Atlantic spent large periods of time near the Canary Archipelago and Northwest Africa, and over shelf and oceanic waters off southern Brazil and Uruguay, respectively. These areas showed evidence of site fidelity and were identified as possible key areas for shortfin mako. Sharks spent most of their time in temperate waters (18–22°C) above 90 m; however, data indicated the depth range extended from the surface down to 979 m, in water temperatures ranging between 7.4 and 29.9°C. Vertical behavior of sharks seemed to be influenced by oceanographic features, and ranged from marked diel vertical movements, characterized by shallower mean depths during the night, to yo-yo diving behavior with no clear diel pattern observed. These results may aid in the development of more informed and efficient management measures for this species.

High Genetic Addiction Risk Score (GARS) in Chronically Prescribed Severe Chronic Opioid Probands Attending Multi-pain Clinics: an Open Clinical Pilot Trial - Mark Moran; Kenneth Blum; Jessica Valdez Ponce; Lisa Lott; Marjorie C. Gondré–Lewis; Sampada Badgaiyan; Raymond Brewer; B. William Downs; Philip Fynman; Alexander Weingarten; Jean Lud Cadet; David E. Smith; et al. (Molecular Neurobiology, 2021)
Millions of Americans experience pain daily. In 2017, opioid overdose claimed 64,000 lives increasing to 84,000 lives in 2020, resulting in a decrease in national life expectancy. Chronic opioid use results in dependency, drug tolerance, neuroadaptation, hyperalgesia, potential addictive behaviors, or Reward Deficiency Syndrome (RDS) caused by a hypodopaminergia. Evaluation of pain clinic patients with the Genetic Addiction Risk Score (GARS) test and the Addiction Severity Index (ASI- Media Version V) revealed that GARS scores equal to or greater than 4 and 7 alleles significantly predicted drug and alcohol severity, respectively. We utilized RT-PCR for SNP genotyping and multiplex PCR/capillary electrophoresis for fragment analysis of the role of eleven alleles in a ten-reward gene panel, reflecting the activity of brain reward circuitry in 121 chronic opioid users. The study consisted of 55 males and 66 females averaging ages 54 and 53 years of age, respectively. The patients included Caucasians, African Americans, Hispanics, and Asians. Inclusion criteria mandated that the Morphine Milligram Equivalent (MME) was 30–600 mg/day (males) and 20 to 180 mg/day (females) for treatment of chronic pain over 12 months. Ninety-six percent carried four or more risk alleles, and 73% carried seven or more risk alleles, suggesting a high predictive risk for opioid and alcohol dependence, respectively. These data indicate that chronic, legally prescribed opioid users attending a pain clinic possess high genetic risk for drug and alcohol addiction. Early identification of genetic risk, using the GARS test upon entry to treatment, may prevent iatrogenic induced opioid dependence.

Quantifying spatial variation in isotopic baselines reveals size-based feeding in a model estuarine predator: implications for trophic studies in dynamic ecotones - Philip Matich; Oliver N. Shipley; Ornella C. Weideli (Marine Biology, 2021)

Amendment with biodiesel co-product modifies genes for N cycling (nirK, nirS, nosZ) and greenhouse gas emissions (N2O, CH4, CO2) from an acid soil - Qunli Shen; Marc Redmile-Gordon; Jiuwei Song; Jiangye Li; Kaile Zhang; Paul Voroney; Jianming Xu; Philip C. Brookes (Biology and Fertility of Soils, 2021)

Tropicalization of temperate ecosystems in North America: The northward range expansion of tropical organisms in response to warming winter temperatures - Michael J. Osland; Philip W. Stevens; Margaret M. Lamont; Richard C. Brusca; Kristen M. Hart; J. Hardin Waddle; Catherine A. Langtimm; Caroline M. Williams; Barry D. Keim; Adam J. Terando; Eric A. Reyier; Katie E. Marshall; et al. (Global Change Biology, 2021)
Tropicalization is a term used to describe the transformation of temperate ecosystems by poleward‐moving tropical organisms in response to warming temperatures. In North America, decreases in the frequency and intensity of extreme winter cold events are expected to allow the poleward range expansion of many cold‐sensitive tropical organisms, sometimes at the expense of temperate organisms. Although ecologists have long noted the critical ecological role of winter cold temperature extremes in tropical–temperate transition zones, the ecological effects of extreme cold events have been understudied, and the influence of warming winter temperatures has too often been left out of climate change vulnerability assessments. Here, we examine the influence of extreme cold events on the northward range limits of a diverse group of tropical organisms, including terrestrial plants, coastal wetland plants, coastal fishes, sea turtles, terrestrial reptiles, amphibians, manatees, and insects. For these organisms, extreme cold events can lead to major physiological damage or landscape‐scale mass mortality. Conversely, the absence of extreme cold events can foster population growth, range expansion, and ecological regime shifts. We discuss the effects of warming winters on species and ecosystems in tropical–temperate transition zones. In the 21st century, climate change‐induced decreases in the frequency and intensity of extreme cold events are expected to facilitate the poleward range expansion of many tropical species. Our review highlights critical knowledge gaps for advancing understanding of the ecological implications of the tropicalization of temperate ecosystems in North America.

Shrub expansion in the Arctic may induce large‐scale carbon losses due to changes in plant‐soil interactions - Thomas C. Parker; Alana M. Thurston; Katrine Raundrup; Jens-Arne Subke; Philip A. Wookey; Iain P. Hartley (Plant and Soil, 2021)
Background Tall deciduous shrubs are increasing in range, size and cover across much of the Arctic, a process commonly assumed to increase carbon (C) storage. Major advances in remote sensing have increased our ability to monitor changes aboveground, improving quantification and understanding of arctic greening. However, the vast majority of C in the Arctic is stored in soils, where changes are more uncertain. Scope We present pilot data to argue that shrub expansion will cause changes in rhizosphere processes, including the development of new mycorrhizal associations that have the potential to promote soil C losses that substantially exceed C gains in plant biomass. However, current observations are limited in their spatial extent, and mechanistic understanding is still developing. Extending measurements across different regions and tundra types would greatly increase our ability to predict the biogeochemical consequences of arctic vegetation change, and we present a simple method that would allow such data to be collected. Conclusions Shrub expansion in the Arctic could promote substantial soil C losses that are unlikely to be offset by increases in plant biomass. However, confidence in this prediction is limited by a lack of information on how soil C stocks vary between contrasting Arctic vegetation communities; this needs to be addressed urgently.

A methodological framework for determining an optimal coastal protection strategy against storm surges and sea level rise - Yuki Miura; Huda Qureshi; Chanyang Ryoo; Philip C. Dinenis; Jiao Li; Kyle T. Mandli; George Deodatis; Daniel Bienstock; Heather Lazrus; Rebecca Morss (Natural Hazards, 2021)
Interdependent critical infrastructures in coastal regions, including transportation, electrical grid, and emergency services, are continually threatened by storm-induced flooding. This has been demonstrated a number of times, most recently by hurricanes such as Harvey and Maria, as well as Sandy and Katrina. The need to protect these infrastructures with robust protection mechanisms is critical for our continued existence along the world’s coastlines. Planning these protections is non-trivial given the rare-event nature of strong storms and climate change manifested through sea level rise. This article proposes a framework for a methodology that combines multiple computational models, stakeholder interviews, and optimization to find an optimal protective strategy over time for critical coastal infrastructure while being constrained by budgetary considerations.

Effects of hydroxycinnamic acid esters on sweetpotato weevil feeding and oviposition and interactions with Bacillus thuringiensis proteins - Milton O. Anyanga; Dudley I. Farman; Gorrettie N. Ssemakula; Robert O. M. Mwanga; Philip C. Stevenson (Journal of Pest Science, 2021)
Sweetpotato weevil (SPW) pest management is challenging because the pest target is sub-terranean, so the application of pesticides is impractical and usually ineffective. Host plant resistance and the genetic transformation of sweetpotatoes to produce entomotoxic Bt proteins offer potential for environmentally benign pest control. Resistance can be conferred by naturally occurring hydroxycinnamic acids which protect against oviposition by adults, but these compounds are restricted to the root surface so do not protect against the cortex bound larvae where the greatest damage occurs. Resistance could be enhanced if combined with expression of Bt proteins in transformed plants, but interactions between hydroxycinnamic acids and Bt proteins remain unknown. Here the bioactivity of Cry7Aa1 protein and hydroxycinnamic acid esters was evaluated individually and in combination against SPW larvae and mortality determined. Low and high concentrations of hydroxycinnamic acid esters alone caused significantly higher mortality of both weevil species in all experiments compared to the control. SPW larval mortality was greater when tested as a combination of hydroxycinnamic acid esters and Bt protein, but this effect was additive not synergistic. Although we report no evidence of antagonistic interactions, the antifeedant effects of the plant compounds conferring host plant resistance could have reduced consumption of the Bt protein in our assays leading to a lower efficacy when combined. Further work is required to determine whether the toxic effects of Bt proteins function alongside host plant resistance in sweetpotato under field conditions.

Role of miRNAs in the host–pathogen interaction between sugarcane and Colletotrichum falcatum, the red rot pathogen - M. Nandakumar; P. Malathi; A. R. Sundar; C. P. Rajadurai; Manuel Philip; R. Viswanathan (Plant Cell Reports, 2021)

The drifting dinoflagellate Ceratium furcoides (Levander) Langhans 1925: fundamental niche shift during global invasion - Rafael Lacerda Macêdo; Philip Russo; Raphael F. Corrêa; Odete Rocha; Luciano Neves dos Santos; Christina W. C. Branco (Hydrobiologia, 2021)

Comparison of Hepatic Transporter Tissue Expression in Rodents and Interspecies Hepatic OCT1 Activity - Bridget L. Morse; John K. Fallon; Anil Kolur; Andrew T. Hogan; Philip C. Smith; Kathleen M. Hillgren (The AAPS Journal, 2021)

Associations of muscle lipid content with physical function and resistance training outcomes in older adults: altered responses with metformin - Douglas E. Long; Bailey D. Peck; Steven C. Tuggle; Alejandro G. Villasante Tezanos; Samuel T. Windham; Marcas M. Bamman; Philip A. Kern; Charlotte A. Peterson; Rosicka G. Walton (GeroScience, 2021)

G protein-coupled receptor kinase 2 modifies the cellular reaction to cisplatin through interactions with NADPH oxidase 4 - Jane C. Ammon; Danielle Valls; Mohamed Eldemerdash; Jigisha R. Patel; Philip D. Tran; Lifeng Feng; Michael Gi; Trang T. Gonzalez; Chuc Phan; Ashley E. Zendejas; Christopher H. So (Molecular and Cellular Biochemistry, 2021)

Systemic criticality—a new assessment concept improving the evidence basis for CI protection - Philip M. Kruse; Hanna C. Schmitt; Stefan Greiving (Climatic Change, 2021)
With high certainty, extreme weather events will intensify in their impact within the next 10 years due to climate change-induced increases in hazard probability of occurrence and simultaneous increases in socio-economic vulnerability. Data from previous mega-disasters show that losses from disruptions of critical services surpass the value of direct damages in the exposed areas because critical infrastructures [CI] are increasingly (inter-) dependent. Local events may have global impacts. Systemic criticality, which describes the relevance of a critical infrastructure due to its positioning within the system, needs to be addressed to reduce the likelihood of cascading effects. This paper presents novel approaches to operationalise and assess systemic criticality. Firstly, the paper introduces systemic cascade potential as a measurement of systemic criticality. It takes the relevance of a sector and the relevance of its interdependencies into account to generate a relative value of systemic importance for a CI sector. Secondly, an exemplary sectoral assessment of the road network allows reflecting the spatial manifestation of the first level of cascading effects. It analyses the impact of traffic interruptions on the accessibility of critical facilities to point out the systemically most critical segments of the municipal road network. To further operationalise the spatial dimension of criticality, a normative assertion determining the worthiness of protection of system components is required. A nationwide spatial flood protection plan incorporates this aspect in Germany for the first time. Its formal approval process was initiated in February 2020.

Minding the Data-Gap Trap: Exploring Dynamics of Abundant Dolphin Populations Under Uncertainty - Erin Ashe; Rob Williams; Christopher Clark; Christine Erbe; Leah R. Gerber; Ailsa J. Hall; Philip S. Hammond; Robert C. Lacy; Randall Reeves; Nicole L. Vollmer (Frontiers in Marine Science, 2021)
Preventing declines in common species is key to sustaining the structure and function of marine ecosystems. Yet for many common marine mammals, including oceanic dolphins, statistical power to detect declines remains low due to patchy distribution and large variability in group sizes. In this study, population viability analyses (PVA) were used to model the dynamics of four oceanic dolphin populations off the United States West Coast: eastern North Pacific long-beaked common dolphins ( Delphinus delphis capensis ), short-beaked common dolphins ( D. delphis delphis ), Pacific white-sided dolphins ( Lagenorhynchus obliquidens ), and “offshore” common bottlenose dolphins ( Tursiops truncatus ). We calibrated the PVA with life-history tables, studies on proxy species, and stock assessment reports. We explored the sensitivity of populations to demographic variation and projected how they may respond to changes in three sublethal threats (prey limitation, ocean noise, and chemical pollution) and one lethal threat (fisheries bycatch). We found the most serious projected declines in long-beaked common dolphins, which showed the lowest birth rate. Most threat scenarios resulted in declines that would not be detected by existing monitoring programs in the United States, which are among the most data-rich surveys of their kind. The cumulative effects of the three sublethal stressors exceeded the effect of the one lethal stressor (fisheries bycatch). To implement pro-active management and monitoring programs, anticipating which cetaceans are more at risk and which anthropogenic threats could cause declines is paramount. Our study highlights the value of model testing with PVA when monitoring data are poor, thereby identifying priorities for future research, monitoring, and management.

Habitat type and altitude work in tandem to drive the community structure of dung beetles in Afromontane forest - Roisin Stanbrook; C. Philip Wheater; W. Edwin Harris; Martin Jones (Journal of Insect Conservation, 2021)

Finding incident cancer cases through outpatient oncology clinic claims data and integration into a state cancer registry - Christopher R. Cogle; Gary Levin; David J. Lee; Steven Peace; Megsys C. Herna; Jill MacKinnon; Clement K. Gwede; Celeste Philip; Tara Hylton (Cancer Causes & Control, 2021)

New insights into the trophic ecology of blacktip sharks ( Carcharhinus limbatus ) from a subtropical estuary in the western Gulf of Mexico - Philip Matich; Jeffrey D. Plumlee; Ornella C. Weideli; Mark Fisher (Journal of Fish Biology, 2021)
As environmental change persists, understanding resource use patterns is of value to predict the consequences of shifting trophic structures. While many sharks are opportunistic predators, some exhibit prey selectivity, putting them at higher risk compared to species with greater trophic plasticity. In the Gulf of Mexico (GOM), Clupeids and Sciaenids comprise 69% of blacktip shark ( Carcharhinus limbatus ) diets, which is consequential considering potential responses of these prey groups to disturbance and over harvesting. We assessed if blacktips exhibit selectivity for Clupeids and Sciaenids in the western GOM based on stomach contents from sharks in coastal Texas. Clupeids comprised Mugil cephalus ) and red drum ( Sciaenops ocellatus ) comprised >70% of identifiable prey. Ontogenetic shifts from smaller (Clupeids, small Sciaenids) to larger, higher trophic level (Ariidae, Elasmobranchii) prey fits our understanding of foraging among coastal sharks, and suggests our regional understanding of blacktip trophic ecology may be limited by the sizes of sampled sharks. Observed increases in blacktip densities coupled with declines in prey (Mugilids, Sciaenids) is concerning if blacktips have limited diet plasticity. Yet GOM blacktips may be more generalized than previously thought, which is promising for conservation and management.

Implications of scale dependence for cross‐study syntheses of biodiversity differences - Rebecca Spake; Akira S. Mori; Michael Beckmann; Philip A. Martin; Alec P. Christie; Marlyse C. Duguid; C. Patrick Doncaster (Ecology Letters, 2021)
Biodiversity studies are sensitive to well‐recognised temporal and spatial scale dependencies. Cross‐study syntheses may inflate these influences by collating studies that vary widely in the numbers and sizes of sampling plots. Here we evaluate sources of inaccuracy and imprecision in study‐level and cross‐study estimates of biodiversity differences, caused by within‐study grain and sample sizes, biodiversity measure, and choice of effect‐size metric. Samples from simulated communities of old‐growth and secondary forests demonstrated influences of all these parameters on the accuracy and precision of cross‐study effect sizes. In cross‐study synthesis by formal meta‐analysis, the metric of log response ratio applied to measures of species richness yielded better accuracy than the commonly used Hedges' g metric on species density, which dangerously combined higher precision with persistent bias. Full‐data analyses of the raw plot‐scale data using multilevel models were also susceptible to scale‐dependent bias. We demonstrate the challenge of detecting scale dependence in cross‐study synthesis, due to ubiquitous covariation between replication, variance and plot size. We propose solutions for diagnosing and minimising bias. We urge that empirical studies publish raw data to allow evaluation of covariation in cross‐study syntheses, and we recommend against using Hedges' g in biodiversity meta‐analyses.

Long‐term change in the avifauna of undisturbed Amazonian rainforest: ground‐foraging birds disappear and the baseline shifts - Philip C Stouffer; Vitek Jirinec; Cameron L. Rutt; Richard O. Bierregaard; Angélica Hernández‐Palma; Erik I. Johnson; Stephen R. Midway; Luke L. Powell; Jared D. Wolfe; Thomas E. Lovejoy (Ecology Letters, 2021)
How are rainforest birds faring in the Anthropocene? We use bird captures spanning > 35 years from 55 sites within a vast area of intact Amazonian rainforest to reveal reduced abundance of terrestrial and near‐ground insectivores in the absence of deforestation, edge effects or other direct anthropogenic landscape change. Because undisturbed forest includes far fewer terrestrial and near‐ground insectivores than it did historically, today’s fragments and second growth are more impoverished than shown by comparisons with modern ‘control’ sites. Any goals for bird community recovery in Amazonian second growth should recognise that a modern bird community will inevitably differ from a baseline from > 35 years ago. Abundance patterns driven by landscape change may be the most conspicuous manifestation of human activity, but biodiversity declines in undisturbed forest represent hidden losses, possibly driven by climate change, that may be pervasive in intact Amazonian forests and other systems considered to be undisturbed.

Increasing effects of chronic nutrient enrichment on plant diversity loss and ecosystem productivity over time - Eric W. Seabloom; Peter B. Adler; Juan Alberti; Lori Biederman; Yvonne M. Buckley; Marc W. Cadotte; Scott L. Collins; Laura Dee; Philip A. Fay; Jennifer Firn; Nicole Hagenah; W. Stanley Harpole; et al. (Ecology, 2021)
Human activities are enriching many of Earth’s ecosystems with biologically limiting mineral nutrients such as nitrogen (N) and phosphorus (P). In grasslands, this enrichment generally reduces plant diversity and increases productivity. The widely demonstrated positive effect of diversity on productivity suggests a potential negative feedback, whereby nutrient‐induced declines in diversity reduce the initial gains in productivity arising from nutrient enrichment. In addition, plant productivity and diversity can be inhibited by accumulations of dead biomass, which may be altered by nutrient enrichment. Over longer time frames, nutrient addition may increase soil fertility by increasing soil organic matter and nutrient pools. We examined the effects of 5–11 yr of nutrient addition at 47 grasslands in 12 countries. Nutrient enrichment increased aboveground live biomass and reduced plant diversity at nearly all sites, and these effects became stronger over time. We did not find evidence that nutrient‐induced losses of diversity reduced the positive effects of nutrients on biomass; however, nutrient effects on live biomass increased more slowly at sites where litter was also increasing, regardless of plant diversity. This work suggests that short‐term experiments may underestimate the long‐term nutrient enrichment effects on global grassland ecosystems.

Methyl-CpG-binding protein 2 gene mutations and its association with epilepsy: a single centre study from the Indian subcontinent - Payal Kamdar; Maya Thomas; Sangeetha Yoganathan; Karthik Muthusamy; Beena Koshy; Samuel Philip Oommen; Rekha Aaron; Anitha Barney; Suneetha Susan C. Abraham; Sumita Danda (Journal of Genetics, 2020)

Global impacts of fertilization and herbivore removal on soil net nitrogen mineralization are modulated by local climate and soil properties - Anita C. Risch; Stefan Zimmermann; Barbara Moser; Martin Schütz; Frank Hagedorn; Jennifer Firn; Philip A. Fay; Peter B. Adler; Lori A. Biederman; John M. Blair; Elizabeth T. Borer; Arthur A. D. Broadbent; et al. (Global Change Biology, 2020)
Soil nitrogen (N) availability is critical for grassland functioning. However, human activities have increased the supply of biologically limiting nutrients, and changed the density and identity of mammalian herbivores. These anthropogenic changes may alter net soil N mineralization (soil net N min ), that is, the net balance between N mineralization and immobilization, which could severely impact grassland structure and functioning. Yet, to date, little is known about how fertilization and herbivore removal individually, or jointly, affect soil net N min across a wide range of grasslands that vary in soil and climatic properties. Here we collected data from 22 grasslands on five continents, all part of a globally replicated experiment, to assess how fertilization and herbivore removal affected potential (laboratory‐based) and realized (field‐based) soil net N min . Herbivore removal in the absence of fertilization did not alter potential and realized soil net N min . However, fertilization alone and in combination with herbivore removal consistently increased potential soil net N min. Realized soil net N min , in contrast, significantly decreased in fertilized plots where herbivores were removed. Treatment effects on potential and realized soil net N min were contingent on site‐specific soil and climatic properties. Fertilization effects on potential soil net N min were larger at sites with higher mean annual precipitation (MAP) and temperature of the wettest quarter (T.q.wet). Reciprocally, realized soil net N min declined most strongly with fertilization and herbivore removal at sites with lower MAP and higher T.q.wet. In summary, our findings show that anthropogenic nutrient enrichment, herbivore exclusion and alterations in future climatic conditions can negatively impact soil net N min across global grasslands under realistic field conditions. This is an important context‐dependent knowledge for grassland management worldwide.

Microplastics in the soil environment: Occurrence, risks, interactions and fate – A review - Baile Xu; Fei Liu; Zachary Cryder; Dan Huang; Zhijiang Lu; Yan He; Haizhen Wang; Zhenmei Lu; Philip C. Brookes; Caixian Tang; Jay Gan; Jianming Xu (Critical Reviews in Environmental Science and Technology, 2020)

Hyperphosphorylation Renders Tau Prone to Aggregate and to Cause Cell Death - Mengyu Liu; Dexin Sui; Thomas Dexheimer; Stacy Hovde; Xiexiong Deng; Kuang-Wei Wang; Hsin Lian Lin; Hsiao-Tien Chien; Hye Kyong Kweon; Nora Sheen Kuo; Christopher A. Ayoub; Daniela Jimenez-Harrison; et al. (Molecular Neurobiology, 2020)

Four-dimensional thermal evolution of the East African Orogen: accessory phase petrochronology of crustal profiles through the Tanzanian Craton and Mozambique Belt, northeastern Tanzania - Francisco E. Apen; Roberta L. Rudnick; John M. Cottle; Andrew R. C. Kylander-Clark; Madalyn S. Blondes; Philip M. Piccoli; Gareth Seward (Contributions to Mineralogy and Petrology, 2020)

Herbivory and Time Since Flowering Shape Floral Rewards and Pollinator-Pathogen Interactions - Luis A. Aguirre; Julie K. Davis; Philip C. Stevenson; Lynn S. Adler (Journal of Chemical Ecology, 2020)

Effects of multiple drivers of ocean global change on the physiology and functional gene expression of the coccolithophore Emiliania huxleyi - Yuanyuan Feng; Michael Y. Roleda; Evelyn Armstrong; Tina C. Summerfield; Cliff S. Law; Catriona L. Hurd; Philip W. Boyd (Global Change Biology, 2020)
Ongoing ocean global change due to anthropogenic activities is causing multiple chemical and physical seawater properties to change simultaneously, which may affect the physiology of marine phytoplankton. The coccolithophore Emiliania huxleyi is a model species often employed in the study of the marine carbon cycle. The effect of ocean acidification (OA) on coccolithophore calcification has been extensively studied; however, physiological responses to multiple environmental drivers are still largely unknown. Here we examined two‐way and multiple driver effects of OA and other key environmental drivers—nitrate, phosphate, irradiance, and temperature—on the growth, photosynthetic, and calcification rates, and the elemental composition of E. huxleyi . In addition, changes in functional gene expression were examined to understand the molecular mechanisms underpinning the physiological responses. The single driver manipulation experiments suggest decreased nitrate supply being the most important driver regulating E. huxleyi physiology, by significantly reducing the growth, photosynthetic, and calcification rates. In addition, the interaction of OA and decreased nitrate supply (projected for year 2100) had more negative synergistic effects on E. huxleyi physiology than all other two‐way factorial manipulations, suggesting a linkage between the single dominant driver (nitrate) effects and interactive effects with other drivers. Simultaneous manipulation of all five environmental drivers to the conditions of the projected year 2100 had the largest negative effects on most of the physiological metrics. Furthermore, functional genes associated with inorganic carbon acquisition ( RubisCO , AEL1 , and δCA ) and calcification ( CAX3 , AEL1 , PATP , and NhaA2 ) were most downregulated by the multiple driver manipulation, revealing linkages between responses of functional gene expression and associated physiological metrics. These findings together indicate that for more holistic projections of coccolithophore responses to future ocean global change, it is necessary to understand the relative importance of environmental drivers both individually (i.e., mechanistic understanding) and interactively (i.e., cumulative effect) on coccolithophore physiology.

Argo Data 1999–2019: Two Million Temperature-Salinity Profiles and Subsurface Velocity Observations From a Global Array of Profiling Floats - Annie P. S. Wong; Susan E. Wijffels; Stephen C. Riser; Sylvie Pouliquen; Shigeki Hosoda; Dean Roemmich; John Gilson; Gregory C. Johnson; Kim Martini; David J. Murphy; Megan Scanderbeg; T. V. S. Udaya Bhaskar; et al. (Frontiers in Marine Science, 2020)

Does bank credit to the private sector promote low-carbon development in Brazil? An extended STIRPAT analysis using dynamic ARDL simulations - Chinazaekpere Nwani; Philip C. Omoke (Environmental Science and Pollution Research, 2020)

Tree planting in organic soils does not result in net carbon sequestration on decadal timescales - Nina L. Friggens; Alison J. Hester; Ruth J. Mitchell; Thomas C. Parker; Jens‐Arne Subke; Philip A. Wookey (Global Change Biology, 2020)
Tree planting is increasingly being proposed as a strategy to combat climate change through carbon (C) sequestration in tree biomass. However, total ecosystem C storage that includes soil organic C (SOC) must be considered to determine whether planting trees for climate change mitigation results in increased C storage. We show that planting two native tree species ( Betula pubescens and Pinus sylvestris ), of widespread Eurasian distribution, onto heather ( Calluna vulgaris ) moorland with podzolic and peaty podzolic soils in Scotland, did not lead to an increase in net ecosystem C stock 12 or 39 years after planting. Plots with trees had greater soil respiration and lower SOC in organic soil horizons than heather control plots. The decline in SOC cancelled out the increment in C stocks in tree biomass on decadal timescales. At all four experimental sites sampled, there was no net gain in ecosystem C stocks 12–39 years after afforestation—indeed we found a net ecosystem C loss in one of four sites with deciduous B. pubescens stands; no net gain in ecosystem C at three sites planted with B. pubescens ; and no net gain at additional stands of P. sylvestris . We hypothesize that altered mycorrhizal communities and autotrophic C inputs have led to positive ‘priming’ of soil organic matter, resulting in SOC loss, constraining the benefits of tree planting for ecosystem C sequestration. The results are of direct relevance to current policies, which promote tree planting on the assumption that this will increase net ecosystem C storage and contribute to climate change mitigation. Ecosystem‐level biogeochemistry and C fluxes must be better quantified and understood before we can be assured that large‐scale tree planting in regions with considerable pre‐existing SOC stocks will have the intended policy and climate change mitigation outcomes.

Elevated temperature shifts soil N cycling from microbial immobilization to enhanced mineralization, nitrification and denitrification across global terrestrial ecosystems - Zhongmin Dai; Mengjie Yu; Huaihai Chen; Haochun Zhao; Yanlan Huang; Weiqin Su; Fang Xia; Scott X. Chang; Philip C. Brookes; Randy A. Dahlgren; Jianming Xu (Global Change Biology, 2020)
We assessed the response of soil microbial nitrogen (N) cycling and associated functional genes to elevated temperature at the global scale. A meta‐analysis of 1,270 observations from 134 publications indicated that elevated temperature decreased soil microbial biomass N and increased N mineralization rates, both in the presence and absence of plants. These findings infer that elevated temperature drives microbially mediated N cycling processes from dominance by anabolic to catabolic reaction processes. Elevated temperature increased soil nitrification and denitrification rates, leading to an increase in N 2 O emissions of up to 227%, whether plants were present or not. Rates of N mineralization, denitrification and N 2 O emission demonstrated significant positive relationships with rates of CO 2 emissions under elevated temperatures, suggesting that microbial N cycling processes were associated with enhanced microbial carbon (C) metabolism due to soil warming. The response in the abundance of relevant genes to elevated temperature was not always consistent with changes in N cycling processes. While elevated temperature increased the abundances of the nirS gene with plants and nosZ genes without plants, there was no effect on the abundances of the ammonia‐oxidizing archaea amoA gene, ammonia‐oxidizing bacteria amoA and nirK genes. This study provides the first global‐scale assessment demonstrating that elevated temperature shifts N cycling from microbial immobilization to enhanced mineralization, nitrification and denitrification in terrestrial ecosystems. These findings infer that elevated temperatures have a profound impact on global N cycling processes with implications of a positive feedback to global climate and emphasize the close linkage between soil microbial C and N cycling.

Drivers of future alien species impacts: An expert‐based assessment - Franz Essl; Bernd Lenzner; Sven Bacher; Sarah Bailey; Cesar Capinha; Curtis Daehler; Stefan Dullinger; Piero Genovesi; Cang Hui; Philip E. Hulme; Jonathan M. Jeschke; Stelios Katsanevakis; et al. (Global Change Biology, 2020)
Understanding the likely future impacts of biological invasions is crucial yet highly challenging given the multiple relevant environmental, socio‐economic and societal contexts and drivers. In the absence of quantitative models, methods based on expert knowledge are the best option for assessing future invasion trajectories. Here, we present an expert assessment of the drivers of potential alien species impacts under contrasting scenarios and socioecological contexts through the mid‐21st century. Based on responses from 36 experts in biological invasions, moderate (20%–30%) increases in invasions, compared to the current conditions, are expected to cause major impacts on biodiversity in most socioecological contexts. Three main drivers of biological invasions—transport, climate change and socio‐economic change—were predicted to significantly affect future impacts of alien species on biodiversity even under a best‐case scenario. Other drivers (e.g. human demography and migration in tropical and subtropical regions) were also of high importance in specific global contexts (e.g. for individual taxonomic groups or biomes). We show that some best‐case scenarios can substantially reduce potential future impacts of biological invasions. However, rapid and comprehensive actions are necessary to use this potential and achieve the goals of the Post‐2020 Framework of the Convention on Biological Diversity.

Correction to: Soil biochemical properties and bacteria community in a repeatedly fumigated-incubated soil - Xiaoyu Zhou; Lin Chen; Jianming Xu; Philip C. Brookes (Biology and Fertility of Soils, 2020)

Assessing Chemical Mechanisms Underlying the Effects of Sunflower Pollen on a Gut Pathogen in Bumble Bees - Lynn S. Adler; Alison E. Fowler; Rosemary L. Malfi; Patrick R. Anderson; Lily M. Coppinger; Pheobe M. Deneen; Stephanie Lopez; Rebecca E. Irwin; Iain W. Farrell; Philip C. Stevenson (Journal of Chemical Ecology, 2020)

Ensuring tests of conservation interventions build on existing literature - William J. Sutherland; Sergio Ticul Alvarez‐Castañeda; Tatsuya Amano; Roberto Ambrosini; Philip Atkinson; John M. Baxter; Alexander L. Bond; Philip J. Boon; Katherine L. Buchanan; Jos Barlow; Giuseppe Bogliani; Olivia M. Bragg; et al. (Conservation Biology, 2020)

Soil biochemical properties and bacteria community in a repeatedly fumigated-incubated soil - Xiaoyu Zhou; Lin Chen; Jianming Xu; Philip C. Brookes (Biology and Fertility of Soils, 2020)

Yellowstone Lake Ecosystem Restoration: A Case Study for Invasive Fish Management - Todd M. Koel; Jeffery L. Arnold; Patricia E. Bigelow; Travis O. Brenden; Jeffery D. Davis; Colleen R. Detjens; Philip D. Doepke; Brian D. Ertel; Hayley C. Glassic; Robert E. Gresswell; Christopher S. Guy; Drew J. MacDonald; et al. (Fishes, 2020)
Invasive predatory lake trout Salvelinus namaycush were discovered in Yellowstone Lake in 1994 and caused a precipitous decrease in abundance of native Yellowstone cutthroat trout Oncorhynchus clarkii bouvieri. Suppression efforts (primarily gillnetting) initiated in 1995 did not curtail lake trout population growth or lakewide expansion. An adaptive management strategy was developed in 2010 that specified desired conditions indicative of ecosystem recovery. Population modeling was used to estimate effects of suppression efforts on the lake trout and establish effort benchmarks to achieve negative population growth (λ 46,800 100-m net nights; this effort level was achieved in 2012 and led to a reduction in lake trout biomass. Total lake trout biomass declined from 432,017 kg in 2012 to 196,675 kg in 2019, primarily because of a 79% reduction in adults. Total abundance declined from 925,208 in 2012 to 673,983 in 2019 but was highly variable because of recruitment of age-2 fish. Overall, 3.35 million lake trout were killed by suppression efforts from 1995 to 2019. Cutthroat trout abundance remained below target levels, but relative condition increased, large individuals (> 400 mm) became more abundant, and individual weights doubled, probably because of reduced density. Continued actions to suppress lake trout will facilitate further recovery of the cutthroat trout population and integrity of the Yellowstone Lake ecosystem.

For antagonists and mutualists: the paradox of insect toxic secondary metabolites in nectar and pollen - Philip C. Stevenson (Phytochemistry Reviews, 2020)

The impact of financial development on carbon, non-carbon, and total ecological footprint in Nigeria: new evidence from asymmetric dynamic analysis - Philip C. Omoke; Chinazaekpere Nwani; Ekpeno L. Effiong; Osaretin Omorodion Evbuomwan; Chukwuemeka Chinonso Emenekwe (Environmental Science and Pollution Research, 2020)

Assessing the Effects of Banana Pingers as a Bycatch Mitigation Device for Harbour Porpoises (Phocoena phocoena) - Lucy C. M. Omeyer; Philip D. Doherty; Sarah Dolman; Robert Enever; Allan Reese; Nicholas Tregenza; Ruth Williams; Brendan J. Godley (Frontiers in Marine Science, 2020)

Anticoccidial effects of Khaya senegalensis aqueous stem bark extract on broiler chickens experimentally infected with Eimeria species - Issa A. Muraina; Jurbe G. Gotep; James T. Tanko; ThankGod E. Onyiche; Oladimeji B. Aladelokun; Christiana C. Dapuliga; Gilead E. Forcados; Nonyelim Ozele; Ann L. Samuel; Olusola O. Oladipo; Olatunde B. Akanbi; Philip A. Okewole; et al. (Tropical Animal Health and Production, 2020)

Food and temperature stressors have opposing effects in determining flexible migration decisions in brown trout ( Salmo trutta ) - Louise C. Archer; Stephen A. Hutton; Luke Harman; Stephen D. McCormick; Michael N. O’Grady; Joseph P. Kerry; W. Russell Poole; Patrick Gargan; Philip McGinnity; Thomas E. Reed (Global Change Biology, 2020)
With rapid global change, organisms in natural systems are exposed to a multitude of stressors that likely co‐occur, with uncertain impacts. We explored individual and cumulative effects of co‐occurring environmental stressors on the striking, yet poorly understood, phenomenon of facultative migration. We reared offspring of a brown trout population that naturally demonstrates facultative anadromy (sea migration), under different environmental stressor treatments and measured life history responses in terms of migratory tactics and freshwater maturation rates. Juvenile fish were exposed to reduced food availability, temperatures elevated to 1.8°C above natural conditions or both treatments in combination over 18 months of experimental tank rearing. When considered in isolation, reduced food had negative effects on the size, mass and condition of fish across the experiment. We detected variable effects of warm temperatures (negative effects on size and mass, but positive effect on lipids). When combined with food restriction, temperature effects on these traits were less pronounced, implying antagonistic stressor effects on morphological traits. Stressors combined additively, but had opposing effects on life history tactics: migration increased and maturation rates decreased under low food conditions, whereas the opposite occurred in the warm temperature treatment. Not all fish had expressed maturation or migration tactics by the end of the study, and the frequency of these ‘unassigned’ fish was higher in food deprivation treatments, but lower in warm treatments. Fish showing migration tactics were smaller and in poorer condition than fish showing maturation tactics, but were similar in size to unassigned fish. We further detected effects of food restriction on hypo‐osmoregulatory function of migrants that may influence the fitness benefits of the migratory tactic at sea. We also highlight that responses to multiple stressors may vary depending on the response considered. Collectively, our results indicate contrasting effects of environmental stressors on life history trajectories in a facultatively migratory species.

A combined-method approach to trace submarine groundwater discharge from a coastal karst aquifer in Ireland - Philip Schuler; L. Stoeckl; P.-A. Schnegg; C. Bunce; L. Gill (Hydrogeology Journal, 2020)
Knowledge about the hydraulic connections between submarine groundwater discharge (SGD) and its terrestrial coastal catchment is relevant with regard to the management of marine and coastal waters in karst areas. This study applies different methods and monitoring approaches to trace SGD between the Burren Limestone Plateau and Galway Bay in western Ireland, via an excavated sinkhole shaft and deep conduit. Areas of potential SGD were first delineated based on sea surface temperature anomalies using Landsat satellite images. Two fluorescent dyes and solid wood chips were then used as tracers. Solid wood chips were tested as potential means to circumvent the problem of high dispersion in the sea, impacting on the fluorescent dyes to yield readings below the detection limits. Sampling was conducted at 10 different terrestrial locations and in the sea at Galway Bay. Offshore sampling was conducted in transects over a period of four successive days onboard of a vessel using an automated field fluorometer and a conductivity-temperature-depth sensor. No wood chips were recovered in the sea but both fluorescent dyes were successfully sampled. The estimated travel times are in the order of 100 to 354 m/h, and localised tracer readings correlate well in space and time with low conductivity readings. By confirming hydraulic connections between the two karst features and Galway Bay, the study substantiates the hypothesised importance of Variscan veins with regard to regional groundwater flow in the region.

UBC-Nepal expedition: dynamic cerebral autoregulation is attenuated in lowlanders upon ascent to 5050 m - Michael M. Tymko; Alexander B. Hansen; Joshua C. Tremblay; Alexander Patrician; Ryan L. Hoiland; Connor A. Howe; Matthew G. Rieger; Philip N. Ainslie (European Journal of Applied Physiology, 2020)

Bridging the Gap Between Salmon Spawner Abundance and Marine Nutrient Assimilation by Juvenile Salmon: Seasonal Cycles and Landscape Effects at the Watershed Scale - Philip J. Joy; Craig A. Stricker; Renae Ivanoff; Mark S. Wipfli; Andrew C. Seitz; Matthew Tyers (Ecosystems, 2020)

Spatial patterns in soil organic matter dynamics are shaped by mycorrhizosphere interactions in a treeline forest - Nina L. Friggens; Thomas J. Aspray; Thomas C. Parker; Jens-Arne Subke; Philip A. Wookey (Plant and Soil, 2020)
Aims In the Swedish sub-Arctic, mountain birch ( Betula pubescens ssp. czerepanovii ) forests mediate rapid soil C cycling relative to adjacent tundra heaths, but little is known about the role of individual trees within forests. Here we investigate the spatial extent over which trees influence soil processes. Methods We measured respiration, soil C stocks, root and mycorrhizal productivity and fungi:bacteria ratios at fine spatial scales along 3 m transects extending radially from mountain birch trees in a sub-Arctic ecotone forest. Root and mycorrhizal productivity was quantified using in-growth techniques and fungi:bacteria ratios were determined by qPCR. Results Neither respiration, nor root and mycorrhizal production, varied along transects. Fungi:bacteria ratios, soil organic C stocks and standing litter declined with increasing distance from trees. Conclusions As 3 m is half the average size of forest gaps, these findings suggest that forest soil environments are efficiently explored by roots and associated mycorrhizal networks of B. pubescens . Individual trees exert influence substantially away from their base, creating more uniform distributions of root, mycorrhizal and bacterial activity than expected. However, overall rates of soil C accumulation do vary with distance from trees, with potential implications for spatio-temporal soil organic matter dynamics and net ecosystem C sequestration.

Population projections of an endangered cactus suggest little impact of climate change - Eugenio Larios; Edgar J. González; Philip C. Rosen; Ami Pate; Peter Holm (Oecologia, 2020)

Changes in abundance and composition of nitrifying communities in barley (Hordeum vulgare L.) rhizosphere and bulk soils over the growth period following combined biochar and urea amendment - Lu Yu; Peter M. Homyak; Xiaoxi Kang; Philip C. Brookes; Yikai Ye; Yeneng Lin; Afzal Muhammad; Jianming Xu (Biology and Fertility of Soils, 2020)

Assessing changes in genomic divergence following a century of human‐mediated secondary contact among wild and captive‐bred ducks - Philip Lavretsky; Nancy Rotzel McInerney; Jonathon E. Mohl; Joshua I. Brown; Helen F. James; Kevin G. McCracken; Robert C. Fleischer (Molecular Ecology, 2020)
Along with manipulating habitat, the direct release of domesticated individuals into the wild is a practice used worldwide to augment wildlife populations. We test between possible outcomes of human‐mediated secondary contact using genomic techniques at both historical and contemporary timescales for two iconic duck species. First, we sequence several thousand ddRAD‐seq loci for contemporary mallards ( Anas platyrhynchos ) throughout North America and two domestic mallard types (i.e., known game‐farm mallards and feral Khaki Campbell's). We show that North American mallards may well be becoming a hybrid swarm due to interbreeding with domesticated game‐farm mallards released for hunting. Next, to attain a historical perspective, we applied a bait‐capture array targeting thousands of loci in century‐old (1842–1915) and contemporary (2009–2010) mallard and American black duck ( Anas rubripes ) specimens. We conclude that American black ducks and mallards have always been closely related, with a divergence time of ~600,000 years before present, and likely evolved through prolonged isolation followed by limited bouts of gene flow (i.e., secondary contact). They continue to maintain genetic separation, a finding that overturns decades of prior research and speculation suggesting the genetic extinction of the American black duck due to contemporary interbreeding with mallards. Thus, despite having high rates of hybridization, actual gene flow is limited between mallards and American black ducks. Conversely, our historical and contemporary data confirm that the intensive stocking of game‐farm mallards during the last ~100 years has fundamentally changed the genetic integrity of North America's wild mallard population, especially in the east. It thus becomes of great interest to ask whether the iconic North American mallard is declining in the wild due to introgression of maladaptive traits from domesticated forms. Moreover, we hypothesize that differential gene flow from domestic game‐farm mallards into the wild mallard population may explain the overall temporal increase in differentiation between wild black ducks and mallards, as well as the uncoupling of genetic diversity and effective population size estimates across time in our results. Finally, our findings highlight how genomic methods can recover complex population histories by capturing DNA preserved in traditional museum specimens.

Increased high‐latitude photosynthetic carbon gain offset by respiration carbon loss during an anomalous warm winter to spring transition - Zhihua Liu; John S. Kimball; Nicholas C. Parazoo; Ashley P. Ballantyne; Wen J. Wang; Nima Madani; Caleb G. Pan; Jennifer D. Watts; Rolf H. Reichle; Oliver Sonnentag; Philip Marsh; Miriam Hurkuck; et al. (Global Change Biology, 2020)
Arctic and boreal ecosystems play an important role in the global carbon (C) budget, and whether they act as a future net C sink or source depends on climate and environmental change. Here, we used complementary in situ measurements, model simulations, and satellite observations to investigate the net carbon dioxide (CO 2 ) seasonal cycle and its climatic and environmental controls across Alaska and northwestern Canada during the anomalously warm winter to spring conditions of 2015 and 2016 (relative to 2010–2014). In the warm spring, we found that photosynthesis was enhanced more than respiration, leading to greater CO 2 uptake. However, photosynthetic enhancement from spring warming was partially offset by greater ecosystem respiration during the preceding anomalously warm winter, resulting in nearly neutral effects on the annual net CO 2 balance. Eddy covariance CO 2 flux measurements showed that air temperature has a primary influence on net CO 2 exchange in winter and spring, while soil moisture has a primary control on net CO 2 exchange in the fall. The net CO 2 exchange was generally more moisture limited in the boreal region than in the Arctic tundra. Our analysis indicates complex seasonal interactions of underlying C cycle processes in response to changing climate and hydrology that may not manifest in changes in net annual CO 2 exchange. Therefore, a better understanding of the seasonal response of C cycle processes may provide important insights for predicting future carbon–climate feedbacks and their consequences on atmospheric CO 2 dynamics in the northern high latitudes.

Evaluating approaches for scaling‐up community‐based marine‐protected areas into socially equitable and ecologically representative networks - Alessia Kockel; Natalie C. Ban; Maycira Costa; Philip Dearden (Conservation Biology, 2020)
Marine‐protected areas (MPAs) are vital to marine conservation, but their coverage and distribution is insufficient to address declines in global biodiversity and fisheries. In response, many countries have committed through the Aichi Target 11 of the Convention on Biological Diversity to conserve 10% of the marine environment through ecologically representative and equitably managed MPAs by 2020. The rush to fulfill this commitment has raised concerns on how increasing MPA coverage will affect other elements of Target 11, including representation and equity. We examined a Philippines case study to assess and compare 3 MPA planning approaches for biodiversity representation and equitable distribution of costs to small‐scale fishers. In the opportunistic approach, MPAs were identified and supported by coastal communities. The donor‐assisted approach used local knowledge to select MPAs through a national‐scale and donor‐assisted conservation project. The systematic conservation planning approach identified MPA locations with the spatial prioritization software Marxan with Zones to achieve biodiversity objectives with minimal costs to fishers. We collected spatial data on biodiversity and fisheries features and performed a gap analysis to evaluate MPAs derived from different approaches. We assessed representation based on the proportion of biodiversity features conserved in MPAs and distribution equity by the distribution of opportunity costs (fishing areas lost in MPAs) among fisher stakeholder groups. The opportunistic approach did not ineffectively represent biodiversity and resulted in inequitable costs to fishers. The donor‐assisted approach affected fishers disproportionately but provided near‐optimal regional representation. Only the systematic approach achieved all representation targets with minimal and equitable costs to fishers. Our results demonstrate the utility of systematic conservation planning to address key elements of Target 11 and highlight opportunities (e.g., integration of local and scientific knowledge can address representation and equity concerns) and pitfalls (e.g., insufficient stakeholder considerations can exacerbate social inequalities) for planning MPAs in similar contexts.

Water diversion in Brazil threatens biodiversity - Vanessa S. Daga; Valter M. Azevedo-Santos; Fernando M. Pelicice; Philip M. Fearnside; Gilmar Perbiche-Neves; Lucas R. P. Paschoal; Daniel C. Cavallari; José Erickson; Ana M. C. Ruocco; Igor Oliveira; André A. Padial; Jean R. S. Vitule (Ambio, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Elevated temperature increased nitrification activity by stimulating AOB growth and activity in an acidic paddy soil - Qian Zhang; Yong Li; Yan He; Philip C. Brookes; Jianming Xu (Plant and Soil, 2019)

The role of WNK in modulation of KCl cotransport activity in red cells from normal individuals and patients with sickle cell anaemia - David C.-Y. Lu; Anke Hannemann; Rasiqh Wadud; David C. Rees; John N. Brewin; Philip S. Low; John S. Gibson (Pflügers Archiv - European Journal of Physiology, 2019)
Abnormal activity of red cell KCl cotransport (KCC) is involved in pathogenesis of sickle cell anaemia (SCA). KCC-mediated solute loss causes shrinkage, concentrates HbS, and promotes HbS polymerisation. Red cell KCC also responds to various stimuli including pH, volume, urea, and oxygen tension, and regulation involves protein phosphorylation. The main aim of this study was to investigate the role of the WNK/SPAK/OSR1 pathway in sickle cells. The pan WNK inhibitor WNK463 stimulated KCC with an EC 50 of 10.9 ± 1.1 nM and 7.9 ± 1.2 nM in sickle and normal red cells, respectively. SPAK/OSR1 inhibitors had little effect. The action of WNK463 was not additive with other kinase inhibitors (staurosporine and N -ethylmaleimide). Its effects were largely abrogated by pre-treatment with the phosphatase inhibitor calyculin A. WNK463 also reduced the effects of physiological KCC stimuli (pH, volume, urea) and abolished any response of KCC to changes in oxygen tension. Finally, although protein kinases have been implicated in regulation of phosphatidylserine exposure, WNK463 had no effect. Findings indicate a predominant role for WNKs in control of KCC in sickle cells but an apparent absence of downstream involvement of SPAK/OSR1. A more complete understanding of the mechanisms will inform pathogenesis whilst manipulation of WNK activity represents a potential therapeutic approach.

Age and Sex Influence the Hippocampal Response and Recovery Following Sepsis - Jolie Barter; Ashok Kumar; Julie A. Stortz; McKenzie Hollen; Dina Nacionales; Philip A. Efron; Lyle L. Moldawer; Thomas C. Foster (Molecular Neurobiology, 2019)

Changes of Serum IgG Dimer Levels after Treatment with IVIg in Guillain-Barré Syndrome - Martin K. R. Svačina; Philip Röth; Ilja Bobylev; Alina Sprenger; Gang Zhang; Kazim A. Sheikh; Helmar C. Lehmann (Journal of Neuroimmune Pharmacology, 2019)

Dynamic changes in soil chemical properties and microbial community structure in response to different nitrogen fertilizers in an acidified celery soil - Yuping Wu; Jiangxing Wu; Yongjun Ma; Ying Lian; Hui Sun; Danchao Xie; Yaying Li; Philip C. Brookes; Huaiying Yao (Soil Ecology Letters, 2019)

Improved rhizoremediation for decabromodiphenyl ether (BDE-209) in E-waste contaminated soils - Jiayin Feng; Xinquan Shen; Jian Chen; Jiachun Shi; Jianming Xu; Caixian Tang; Philip C. Brookes; Yan He (Soil Ecology Letters, 2019)

Effects of anticoagulants on stable‐isotope values (δ 13 C and δ 15 N) of shark blood components - Ornella C. Weideli; Jeremy J. Kiszka; Philip Matich; Michael R. Heithaus (Journal of Fish Biology, 2019)
The effects of anticoagulant EDTA and sodium heparin (SH) on stable carbon δ 13 C and nitrogen δ 15 N isotopic values of red blood cells (RBC) and blood plasma in juvenile blacktip reef sharks Carcharhinus melanopterus were analysed. Plasma preserved with anticoagulants was not isotopically distinct from plasma stored in no‐additive control tubes but RBC δ 15 N values exhibited small enrichments when preserved with EDTA and SH. Results suggest EDTA and SH are viable anticoagulants for stable isotopic analyses of blood fractions but further studies are advised to validate results.

Floral Odors and the Interaction between Pollinating Ceratopogonid Midges and Cacao - Sarah E. J. Arnold; Samantha J. Forbes; David R. Hall; Dudley I. Farman; Puran Bridgemohan; Gustavo R. Spinelli; Daniel P. Bray; Garvin B. Perry; Leroy Grey; Steven R. Belmain; Philip C. Stevenson (Journal of Chemical Ecology, 2019)
Most plant species depend upon insect pollination services, including many cash and subsistence crops. Plants compete to attract those insects using visual cues and floral odor which pollinators associate with a reward. The cacao tree, Theobroma cacao , has a highly specialized floral morphology permitting pollination primarily by Ceratopogonid midges. However, these insects do not depend upon cacao flowers for their life cycle, and can use other sugar sources. To understand how floral cues mediate pollination in cacao we developed a method for rearing Ceratopogonidae through several complete lifecycles to provide material for bioassays. We carried out collection and analysis of cacao floral volatiles, and identified a bouquet made up exclusively of saturated and unsaturated, straight-chain hydrocarbons, which is unusual among floral odors. The most abundant components were tridecane, pentadecane, ( Z )-7-pentadecene and ( Z )-8-heptadecene with a heptadecadiene and heptadecatriene as minor components. We presented adult midges, Forcipomyia sp. (subgen . Forcipomyia ) , Culicoides paraensis and Dasyhelea borgmeieri, with natural and synthetic cacao flower odors in choice assays. Midges showed weak attraction to the complete natural floral odor in the assay, with no significant evidence of interspecific differences. This suggests that cacao floral volatiles play a role in pollinator behavior. Midges were not attracted to a synthetic blend of the above four major components of cacao flower odor, indicating that a more complete blend is required for attraction. Our findings indicate that cacao pollination is likely facilitated by the volatile blend released by flowers, and that the system involves a generalized odor response common to different species of Ceratopogonidae.

Lack of genetic structuring, low effective population sizes and major bottlenecks characterise common and German wasps in New Zealand - Julia M. Schmack; Evan C. Brenton-Rule; Ruan Veldtman; Tom Wenseleers; Jacqueline R. Beggs; Philip J. Lester; Mariana Bulgarella (Biological Invasions, 2019)

Comparative toxicoproteogenomics of mouse and rat liver identifies TCDD-resistance genes - Stephenie D. Prokopec; Aileen Lu; Sandy Che-Eun S. Lee; Cindy Q. Yao; Ren X. Sun; John D. Watson; Rabah Soliymani; Richard de Borja; Ada Wong; Michelle Sam; Philip Zuzarte; John D. McPherson; et al. (Archives of Toxicology, 2019)

From plant fungi to bee parasites: mycorrhizae and soil nutrients shape floral chemistry and bee pathogens - Julie K. Davis; Luis A. Aguirre; Nicholas A. Barber; Philip C. Stevenson; Lynn S. Adler (Ecology, 2019)
Bee populations have experienced declines in recent years, due in part to increased disease incidence. Multiple factors influence bee–pathogen interactions, including nectar and pollen quality and secondary metabolites. However, we lack an understanding of how plant interactions with their environment shape bee diet quality. We examined how plant interactions with the belowground environment alter floral rewards and, in turn, bee–pathogen interactions. Soil‐dwelling mycorrhizal fungi are considered plant mutualists, although the outcome of the relationship depends on environmental conditions such as nutrients. In a 2 × 2 factorial design, we asked whether mycorrhizal fungi and nutrients affect concentrations of nectar and pollen alkaloids (anabasine and nicotine) previously shown to reduce infection by the gut pathogen Crithidia in the native bumble bee Bombus impatiens . To ask how plant interactions affect this common bee pathogen, we fed pollen and nectar from our treatment plants, and from a wildflower pollen control with artificial nectar, to bees infected with Crithidia . Mycorrhizal fungi and fertilizer both influenced flowering phenology and floral chemistry. While we found no anabasine or nicotine in nectar, high fertilizer increased anabasine and nicotine in pollen. Arbuscular mycorrhizal fungi ( AMF ) decreased nicotine concentrations, but the reduction due to AMF was stronger in high than low‐nutrient conditions. AMF and nutrients also had interactive effects on bee pathogens via changes in nectar and pollen. High fertilizer reduced Crithidia cell counts relative to low fertilizer in AMF plants, but increased Crithidia in non‐ AMF plants. These results did not correspond with effects of fertilizer and AMF on pollen alkaloid concentrations, suggesting that other components of pollen or nectar were affected by treatments and shaped pathogen counts. Our results indicate that soil biotic and abiotic environment can alter bee–pathogen interactions via changes in floral rewards, and underscore the importance of integrative studies to predict disease dynamics and ecological outcomes.

Utility of High Resolution NMR Methods to Probe the Impact of Chemical Modifications on Higher Order Structure of Monoclonal Antibodies in Relation to Antigen Binding - Subhabrata Majumder; Andrew Saati; Shibu Philip; Lucy L. Liu; Elaine Stephens; Jason C. Rouse; Arun Alphonse Ignatius (Pharmaceutical Research, 2019)

Quantitative proteomic analysis of tomato genotypes with differential cadmium tolerance - Karina Lima Reis Borges; Fernanda Salvato; Philip L. Loziuk; David C. Muddiman; Ricardo Antunes Azevedo (Environmental Science and Pollution Research, 2019)

SMART Cables for Observing the Global Ocean: Science and Implementation - Bruce M. Howe; Brian K. Arbic; Jérome Aucan; Christopher R. Barnes; Nigel Bayliff; Nathan Becker; Rhett Butler; Laurie Doyle; Shane Elipot; Gregory C. Johnson; Felix Landerer; Stephen Lentz; et al. (Frontiers in Marine Science, 2019)

On the Future of Argo: A Global, Full-Depth, Multi-Disciplinary Array - Dean Roemmich; Matthew H. Alford; Hervé Claustre; Kenneth Johnson; Brian King; James Moum; Peter Oke; W. Brechner Owens; Sylvie Pouliquen; Sarah Purkey; Megan Scanderbeg; Toshio Suga; et al. (Frontiers in Marine Science, 2019)

Quantification of aerobic determinants of performance in post-pubertal adolescent middle-distance runners - Richard C. Blagrove; Glyn Howatson; Charles R. Pedlar; Philip R. Hayes (European Journal of Applied Physiology, 2019)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

The International Comprehensive Ocean-Atmosphere Data Set – Meeting Users Needs and Future Priorities - Eric Freeman; Elizabeth C. Kent; Philip Brohan; Thomas Cram; Lydia Gates; Boyin Huang; Chunying Liu; Shawn R. Smith; Steven J. Worley; Huai-Min Zhang (Frontiers in Marine Science, 2019)

Observational Needs for Improving Ocean and Coupled Reanalysis, S2S Prediction, and Decadal Prediction - Stephen G. Penny; Santha Akella; Magdalena A. Balmaseda; Philip Browne; James A. Carton; Matthieu Chevallier; Francois Counillon; Catia Domingues; Sergey Frolov; Patrick Heimbach; Patrick Hogan; Ibrahim Hoteit; et al. (Frontiers in Marine Science, 2019)

Mechanisms in mutualisms: a chemically mediated thrips pollination strategy in common elder - Alison S. Scott-Brown; Sarah E. J. Arnold; Geoffrey C. Kite; Iain W. Farrell; Dudley I. Farman; Dominique W. Collins; Philip C. Stevenson (Planta, 2019)

The Effects of Selenomethionine on the Escape Behaviours of Fathead Minnows - Philip J. Anderson; Matthew D. Mitchell; Katherine J. Fedoroff; Douglas P. Chivers; Maud C. O. Ferrari (Archives of Environmental Contamination and Toxicology, 2019)

Connectivity in coastal systems: Barrier island vegetation influences upland migration in a changing climate - Julie C. Zinnert; Stephen M. Via; Benjamin P. Nettleton; Philip A. Tuley; Laura J. Moore; Jon Anthony Stallins (Global Change Biology, 2019)
Due to their position at the land–sea interface, barrier islands are vulnerable to both oceanic and atmospheric climate change‐related drivers. In response to relative sea‐level rise, barrier islands tend to migrate landward via overwash processes which deposit sediment onto the backbarrier marsh, thus maintaining elevation above sea level. In this paper, we assess the importance of interior upland vegetation and sediment transport (from upland to marsh) on the movement of the marsh–upland boundary in a transgressive barrier system along the mid‐Atlantic Coast. We hypothesize that recent woody expansion is altering the rate of marsh to upland conversion. Using Landsat imagery over a 32 year time period (1984–2016), we quantify transitions between land cover (bare, grassland, woody vegetation, and marsh) and the marsh–upland boundary. We find that the Virginia Barrier Islands have both gains and losses in backbarrier marsh and upland, with 19% net loss from the system during the timeframe of the study and increased variance in marsh to upland conversion. This is consistent with recent work indicating a shift toward increasing rates of landward barrier island migration. Despite a net loss of upland area, macroclimatic winter warming resulted in 41% increase in woody vegetation in protected, low‐elevation areas, introducing new ecological scenarios that increase resistance to sediment movement from upland to marsh. Our analysis demonstrates how the interplay between elevation and interior island vegetative cover influences landward migration of the boundary between upland and marsh (a previously underappreciated indicator that an island is migrating), and thus, the importance of including ecological processes in the island interior into coastal modeling of barrier island migration and sediment movement across the barrier landscape.

High-resolution habitat and bathymetry maps for 65,000 sq. km of Earth’s remotest coral reefs - Sam J. Purkis; Arthur C. R. Gleason; Charlotte R. Purkis; Alexandra C. Dempsey; Philip G. Renaud; Mohamed Faisal; Steven Saul; Jeremy M. Kerr (Coral Reefs, 2019)

Trends in Sandeel Growth and Abundance off the East Coast of Scotland - Alan MacDonald; Douglas C. Speirs; Simon P. R. Greenstreet; Philip Boulcott; Michael R. Heath (Frontiers in Marine Science, 2019)

Global modeling of tropical cyclone storm surges using high-resolution forecasts - Nadia Bloemendaal; Sanne Muis; Reindert J. Haarsma; Martin Verlaan; Maialen Irazoqui Apecechea; Hans de Moel; Philip J. Ward; Jeroen C. J. H. Aerts (Climate Dynamics, 2019)

Secondary metabolites from nectar and pollen: a resource for ecological and evolutionary studies - Evan C. Palmer‐Young; Iain W. Farrell; Lynn S. Adler; Nelson J. Milano; Paul A. Egan; Rebecca E. Irwin; Philip C. Stevenson (Ecology, 2019)
Floral chemistry mediates plant interactions with herbivores, pathogens, and pollinators. The chemistry of floral nectar and pollen, the primary food rewards for pollinators, can affect both plant reproduction and pollinator health. Although the existence and functional significance of nectar and pollen secondary metabolites has long been known, comprehensive quantitative characterizations of secondary chemistry exist for only a few species. Moreover, little is known about intraspecific variation in nectar and pollen chemical profiles. Because the ecological effects of secondary chemicals are dose‐dependent, heterogeneity across genotypes and populations could influence floral trait evolution and pollinator foraging ecology. To better understand within‐ and across‐species heterogeneity in nectar and pollen secondary chemistry, we undertook exhaustive LC ‐ MS and LC ‐ UV ‐based chemical characterizations of nectar and pollen methanol extracts from 31 cultivated and wild plant species. Nectar and pollen were collected from farms and natural areas in Massachusetts, Vermont, and California, USA , in 2013 and 2014. For wild species, we aimed to collect 10 samples from each of three sites. For agricultural and horticultural species, we aimed for 10 samples from each of three cultivars. Our data set (1,535 samples, 102 identified compounds) identifies and quantifies each compound recorded in methanolic extracts, and includes chemical metadata that describe the molecular mass, retention time, and chemical classification of each compound. A reference phylogeny is included for comparative analyses. We found that each species possessed a distinct chemical profile; moreover, within species, few compounds were found in both nectar and pollen. The most common secondary chemical classes were flavonoids, terpenoids, alkaloids and amines, and chlorogenic acids. The most common compounds were quercetin and kaempferol glycosides. Pollens contained high concentrations of hydroxycinnamoyl‐spermidine conjugates, mainly triscoumaroyl and trisferuloyl spermidine, found in 71% of species. When present, pollen alkaloids and spermidines had median nonzero concentrations of 23,000 μmol/L (median 52% of recorded micromolar composition). Although secondary chemistry was qualitatively consistent within each species and sample type, we found significant quantitative heterogeneity across cultivars and sites. These data provide a standard reference for future ecological and evolutionary research on nectar and pollen secondary chemistry, including its role in pollinator health and plant reproduction. Data are published under a Creative Commons Attribution License ( CC BY 3.0 US ) and may be freely used if properly cited.

The evaluation of the repeatability of the 13 C-ketoisocaproate breath test for assessing hepatic mitochondrial function - Paul R. Afolabi; Eleonora Scorletti; Philip C. Calder; Christopher D. Byrne (Isotopes in Environmental and Health Studies, 2019)

Changes in soil microbial biomass C, ATP and microbial ATP concentrations due to increasing soil Cd levels in Chinese paddy soils growing rice (Oryza sativa) - Gaoyang Qiu; Min Zhu; Jun Meng; Yu Luo; Hongjie Di; Jianming Xu; Philip C. Brookes (Plant and Soil, 2019)

Oxidation Resistance 1 Modulates Glycolytic Pathways in the Cerebellum via an Interaction with Glucose-6-Phosphate Isomerase - Mattéa J. Finelli; Teresa Paramo; Elisabete Pires; Brent J. Ryan; Richard Wade-Martins; Philip C. Biggin; James McCullagh; Peter L. Oliver (Molecular Neurobiology, 2019)

Developing a list of invasive alien species likely to threaten biodiversity and ecosystems in the European Union - Helen E. Roy; Sven Bacher; Franz Essl; Tim Adriaens; David C. Aldridge; John D. D. Bishop; Tim M. Blackburn; Etienne Branquart; Juliet Brodie; Carles Carboneras; Elizabeth J. Cottier-Cook; Gordon H. Copp; et al. (Global Change Biology, 2019)
The European Union ( EU ) has recently published its first list of invasive alien species ( IAS ) of EU concern to which current legislation must apply. The list comprises species known to pose great threats to biodiversity and needs to be maintained and updated. Horizon scanning is seen as critical to identify the most threatening potential IAS that do not yet occur in Europe to be subsequently risk assessed for future listing. Accordingly, we present a systematic consensus horizon scanning procedure to derive a ranked list of potential IAS likely to arrive, establish, spread and have an impact on biodiversity in the region over the next decade. The approach is unique in the continental scale examined, the breadth of taxonomic groups and environments considered, and the methods and data sources used. International experts were brought together to address five broad thematic groups of potential IAS . For each thematic group the experts first independently assembled lists of potential IAS not yet established in the EU but potentially threatening biodiversity if introduced. Experts were asked to score the species within their thematic group for their separate likelihoods of i) arrival, ii) establishment, iii) spread, and iv) magnitude of the potential negative impact on biodiversity within the EU . Experts then convened for a 2‐day workshop applying consensus methods to compile a ranked list of potential IAS . From an initial working list of 329 species, a list of 66 species not yet established in the EU that were considered to be very high (8 species), high (40 species) or medium (18 species) risk species was derived. Here, we present these species highlighting the potential negative impacts and the most likely biogeographic regions to be affected by these potential IAS.

Greater stem growth, woody allocation, and aboveground biomass in Paleotropical forests than in Neotropical forests - Philip G. Taylor; Cory C. Cleveland; Fiona Soper; William R. Wieder; Solomon Z. Dobrowski; Christopher E. Doughty; Alan R. Townsend (Ecology, 2019)
Forest dynamics and tree species composition vary substantially between Paleotropical and Neotropical forests, but these broad biogeographic regions are treated uniformly in many land models. To assess whether these regional differences translate into variation in productivity and carbon (C) storage, we compiled a database of climate, tree stem growth, litterfall, aboveground net primary production (ANPP), and aboveground biomass across tropical rainforest sites spanning 33 countries throughout Central and South America, Asia, and Australasia, but excluding Africa due to a paucity of available data. Though the sum of litterfall and stem growth (ANPP) did not differ between regions, both stem growth and the ratio of stem growth to litterfall were higher in Paleotropical forests compared to Neotropical forests across the full observed range of ANPP. Greater C allocation to woody growth likely explains the much larger aboveground biomass estimates in Paleotropical forests (~29%, or ~80 Mg DW/ha, greater than in the Neotropics). Climate was similar in Paleo‐ and Neotropical forests, thus the observed differences in C likely reflect differences in the evolutionary history of species and forest structure and function between regions. Our analysis suggests that Paleotropical forests, which can be dominated by tall‐statured Dipterocarpaceae species, may be disproportionate hotspots for aboveground C storage. Land models typically treat these distinct tropical forests with differential structures as a single functional unit, but our findings suggest that this may overlook critical biogeographic variation in C storage potential among regions.

Phytochemistry and bioactivity of Acacia sensu stricto (Fabaceae: Mimosoideae) - Diana Jæger; Martin C. O’Leary; Philip Weinstein; Birger Lindberg Møller; Susan J. Semple (Phytochemistry Reviews, 2019)

Multi-level emulation of complex climate model responses to boundary forcing data - Giang T. Tran; Kevin I. C. Oliver; Philip B. Holden; Neil R. Edwards; András Sóbester; Peter Challenor (Climate Dynamics, 2019)

Evidence gaps and biodiversity threats facing the marine environment of the United Kingdom’s Overseas Territories - Bethan C. O’Leary; Philip Fieldhouse; Colin J. McClean; Adriana E. S. Ford; Polly Burns; Julie P. Hawkins; Callum M. Roberts (Biodiversity and Conservation, 2019)

A statistical seasonal forecast model of North Indian Ocean tropical cyclones using the quasi‐biennial oscillation - Md Wahiduzzaman; Eric C. J. Oliver; Philip J. Klotzbach; Simon J. Wotherspoon; Neil J. Holbrook (International Journal of Climatology, 2019)
Previous studies have shown that the skill of seasonal forecasts of tropical cyclone (TC) activity over the North Indian Ocean (NIO) tends to be poor. This paper investigates the forecast potential of TC formation, trajectories and points of landfall in the NIO region using an index of the stratospheric quasi‐biennial oscillation (QBO) as the predictor variable in a new statistical seasonal forecast model. Genesis was modelled by kernel density estimation, tracks were fitted using a generalized additive model (GAM) approach with an Euler integration step, and landfall location was estimated using a country mask. The model was trained on 30 years of TC observations (1980–2009) from the Joint Typhoon Warning Center and the QBO index at lags from 0 to 6 months. Over this time period, and within each season and QBO phase, the kernel density estimator modelled the distribution of genesis points, and the cyclone trajectories were then fit by the GAM along the observed cyclone tracks as smooth functions of location. Trajectories were simulated from randomly selected genesis points in the kernel density estimates. Ensembles of cyclone paths were traced, taking account of random innovations every 6‐hr along the GAM‐fitted velocity fields, to determine the points of landfall. Lead–lag analysis was used to assess the best predictor timescales for TC forecast potential. We found that the best model utilized the QBO index with a 3‐month lead. Two hindcast validation methods were applied. First, leave‐one‐out cross‐validation was performed where the country of landfall was decided by the majority vote of the simulated tracks. Second, the distances between the landfall locations in the observations and simulations were calculated. Application of seasonal forecast analysis further indicated that including information on the state of the QBO has the potential to improve the skill of TC seasonal forecasts in the NIO region.

Development of ethosomal vesicular carrier for topical application of griseofulvin: effect of ethanol concentration - Chukwuemeka C. Mbah; Philip F. Builders; Chukwuma O. Agubata; Anthony A. Attama (Journal of Pharmaceutical Investigation, 2019)

Eighty Years of Mycopathologia: A Retrospective Analysis of Progress Made in Understanding Human and Animal Fungal Pathogens - Vishnu Chaturvedi; Jean-Philippe Bouchara; Ferry Hagen; Ana Alastruey-Izquierdo; Hamid Badali; Anamelia Lorenzetti Bocca; Jose F. Cano-Lira; Cunwei Cao; Sudha Chaturvedi; Sanjay H. Chotirmall; Anne D. van Diepeningen; Jean-Pierre Gangneux; et al. (Mycopathologia, 2018)

The origins of global invasions of the German wasp (Vespula germanica) and its infection with four honey bee viruses - Evan C. Brenton-Rule; Jana Dobelmann; James W. Baty; Robert L. Brown; Libor Dvorak; Julien Grangier; Maité Masciocchi; Chris McGrannachan; Chris R. Shortall; Julia Schmack; Carolien van Zyl; Ruan Veldtman; et al. (Biological Invasions, 2018)

Ten‐year assessment of the 100 priority questions for global biodiversity conservation - Tommaso Jucker; Bonnie Wintle; Gorm Shackelford; Pierre Bocquillon; Jan Laurens Geffert; Tim Kasoar; Eszter Kovacs; Hannah S. Mumby; Chloé Orland; Judith Schleicher; Eleanor R. Tew; Aiora Zabala; et al. (Conservation Biology, 2018)
In 2008, a group of conservation scientists compiled a list of 100 priority questions for the conservation of the world's biodiversity. However, now almost a decade later, no one has yet published a study gauging how much progress has been made in addressing these 100 high‐priority questions in the peer‐reviewed literature. We took a first step toward reexamining the 100 questions to identify key knowledge gaps that remain. Through a combination of a questionnaire and a literature review, we evaluated each question on the basis of 2 criteria: relevance and effort. We defined highly relevant questions as those that – if answered – would have the greatest impact on global biodiversity conservation and quantified effort based on the number of review publications addressing a particular question, which we used as a proxy for research effort. Using this approach, we identified a set of questions that, despite being perceived as highly relevant, have been the focus of relatively few review publications over the past 10 years. These questions covered a broad range of topics but predominantly tackled 3 major themes: conservation and management of freshwater ecosystems, role of societal structures in shaping interactions between people and the environment, and impacts of conservation interventions. We believe these questions represent important knowledge gaps that have received insufficient attention and may need to be prioritized in future research.

Genetic modifiers of radon-induced lung cancer risk: a genome-wide interaction study in former uranium miners - Albert Rosenberger; Rayjean J. Hung; David C. Christiani; Neil E. Caporaso; Geoffrey Liu; Stig E. Bojesen; Loic Le Marchand; Ch. A. Haiman; Demetrios Albanes; Melinda C. Aldrich; Adonina Tardon; G. Fernández-Tardón; et al. (International Archives of Occupational and Environmental Health, 2018)

Effects of multiple stressors on cyanobacteria abundance vary with lake type - Jessica Richardson; Claire Miller; Stephen C. Maberly; Philip Taylor; Lidija Globevnik; Peter Hunter; Erik Jeppesen; Ute Mischke; S. Jannicke Moe; Agnieszka Pasztaleniec; Martin Søndergaard; Laurence Carvalho (Global Change Biology, 2018)
Blooms of cyanobacteria are a current threat to global water security that is expected to increase in the future because of increasing nutrient enrichment, increasing temperature and extreme precipitation in combination with prolonged drought. However, the responses to multiple stressors, such as those above, are often complex and there is contradictory evidence as to how they may interact. Here we used broad scale data from 494 lakes in central and northern Europe, to assess how cyanobacteria respond to nutrients (phosphorus), temperature and water retention time in different types of lakes. Eight lake types were examined based on factorial combinations of major factors that determine phytoplankton composition and sensitivity to nutrients: alkalinity (low and medium‐high), colour (clear and humic) and mixing intensity (polymictic and stratified). In line with expectations, cyanobacteria increased with temperature and retention time in five of the eight lake types. Temperature effects were greatest in lake types situated at higher latitudes, suggesting that lakes currently not at risk could be affected by warming in the future. However, the sensitivity of cyanobacteria to temperature, retention time and phosphorus varied among lake types highlighting the complex responses of lakes to multiple stressors. For example, in polymictic, medium‐high alkalinity, humic lakes cyanobacteria biovolume was positively explained by retention time and a synergy between TP and temperature, while in polymictic, medium‐high alkalinity, clear lakes only retention time was identified as an explanatory variable. These results show that, although climate change will need to be accounted for when managing the risk of cyanobacteria in lakes, a “one‐size fits‐all” approach is not appropriate. When forecasting the response of cyanobacteria to future environmental change, including changes caused by climate and local management, it will be important to take this differential sensitivity of lakes into account.

Disease where you dine: plant species and floral traits associated with pathogen transmission in bumble bees - Lynn S. Adler; Kristen M. Michaud; Stephen P. Ellner; Scott H. McArt; Philip C. Stevenson; Rebecca E. Irwin (Ecology, 2018)
Hotspots of disease transmission can strongly influence pathogen spread. Bee pathogens may be transmitted via shared floral use, but the role of plant species and floral trait variation in shaping transmission dynamics is almost entirely unexplored. Given the importance of pathogens for the decline of several bee species, understanding whether and how plant species and floral traits affect transmission could give us important tools for predicting which plant species may be hotspots for disease spread. We assessed variation in transmission via susceptibility (probability of infection) and mean intensity (cell count of infected bees) of the trypanosomatid gut pathogen Crithidia bombi to uninfected Bombus impatiens workers foraging on 14 plant species, and assessed the role of floral traits, bee size and foraging behavior on transmission. We also conducted a manipulative experiment to determine how the number of open flowers affected transmission on three plant species, Penstemon digitalis , Monarda didyma , and Lythrum salicaria . Plant species differed fourfold in the overall mean abundance of Crithidia in foraging bumble bees (mean including infected and uninfected bees). Across plant species, bee susceptibility and mean intensity increased with the number of reproductive structures per inflorescence (buds, flowers and fruits); smaller bees and those that foraged longer were also more susceptible. Trait‐based models were as good or better than species‐based models at predicting susceptibility and mean intensity based on AIC values. Surprisingly, floral size and morphology did not significantly predict transmission across species. In the manipulative experiment, more open flowers increased mean pathogen abundance fourfold in Monarda , but had no effect in the other two plant species. Our results suggest that variation among plant species, through their influence on pathogen transmission, may shape bee disease dynamics. Given widespread investment in pollinator‐friendly plantings to support pollinators, understanding how plant species affect disease transmission is important for recommending plant species that optimize pollinator health.

Contrasting biomass, dynamics and diversity of microbial community following the air-drying and rewetting of an upland and a paddy soil of the same type - Qunli Shen; Kaile Zhang; Jiuwei Song; Jiaxian Shen; Jianming Xu; Kazuyki Inubushi; Philip C. Brookes (Biology and Fertility of Soils, 2018)

Diagnostic Utility of Cord Blood Thyroid Stimulating Hormone in Congenital Hypothyroidism in the Era of Expanded Newborn Screening - C. M. Nasheeda; Prijo Philip; Rathika Damodara Shenoy; Sukanya Shetty (Indian Journal of Clinical Biochemistry, 2018)

3D human liver tissue from pluripotent stem cells displays stable phenotype in vitro and supports compromised liver function in vivo - Hassan Rashidi; Nguyet-Thin Luu; Salamah M. Alwahsh; Maaria Ginai; Sharmin Alhaque; Hua Dong; Rute A. Tomaz; Bertrand Vernay; Vasanthy Vigneswara; John M. Hallett; Anil Chandrashekran; Anil Dhawan; et al. (Archives of Toxicology, 2018)

Exploring drivers of litter decomposition in a greening Arctic: results from a transplant experiment across a treeline - Thomas C. Parker; Jonathan Sanderman; Robert D. Holden; Gesche Blume‐Werry; Sofie Sjögersten; David Large; Miguel Castro‐Díaz; Lorna E. Street; Jens‐Arne Subke; Philip A. Wookey (Ecology, 2018)
Decomposition of plant litter is a key control over carbon (C) storage in the soil. The biochemistry of the litter being produced, the environment in which the decomposition is taking place, and the community composition and metabolism of the decomposer organisms exert a combined influence over decomposition rates. As deciduous shrubs and trees are expanding into tundra ecosystems as a result of regional climate warming, this change in vegetation represents a change in litter input to tundra soils and a change in the environment in which litter decomposes. To test the importance of litter biochemistry and environment in determining litter mass loss, we reciprocally transplanted litter between heath ( Empetrum nigrum ), shrub ( Betula nana ), and forest ( Betula pubescens ) at a sub‐Arctic treeline in Sweden. As expansion of shrubs and trees promotes deeper snow, we also used a snow fence experiment in a tundra heath environment to understand the importance of snow depth, relative to other factors, in the decomposition of litter. Our results show that B. pubescens and B. nana leaf litter decomposed at faster rates than E. nigrum litter across all environments, while all litter species decomposed at faster rates in the forest and shrub environments than in the tundra heath. The effect of increased snow on decomposition was minimal, leading us to conclude that microbial activity over summer in the productive forest and shrub vegetation is driving increased mass loss compared to the heath. Using B. pubescens and E. nigrum litter, we demonstrate that degradation of carbohydrate‐C is a significant driver of mass loss in the forest. This pathway was less prominent in the heath, which is consistent with observations that tundra soils typically have high concentrations of “labile” C. This experiment suggests that further expansion of shrubs and trees may stimulate the loss of undecomposed carbohydrate C in the tundra.

Assessment of a commercial spider venom peptide against spotted-wing Drosophila and interaction with adjuvants - Philip D. Fanning; Anthony VanWoerkom; John C. Wise; Rufus Isaacs (Journal of Pest Science, 2018)

Genetic variants in components of the NALCN–UNC80–UNC79 ion channel complex cause a broad clinical phenotype (NALCN channelopathies) - Nuria C. Bramswig; Aida M. Bertoli-Avella; Beate Albrecht; Aida I. Al Aqeel; Amal Alhashem; Nouriya Al-Sannaa; Maissa Bah; Katharina Bröhl; Christel Depienne; Nathalie Dorison; Diane Doummar; Nadja Ehmke; et al. (Human Genetics, 2018)

Amazon soil charcoal: Pyrogenic carbon stock depends of ignition source distance and forest type in Roraima, Brazil - Lidiany C. da Silva Carvalho; Philip M. Fearnside; Marcelo T. Nascimento; Reinaldo I. Barbosa (Global Change Biology, 2018)
Pyrogenic carbon (PyC) derived from charcoal particles (paleo + modern) deposited in the soil column has been little studied in the Amazon, and our understanding of the factors that control the spatial and vertical distribution of these materials in the region's forest soils is still unclear. The objective of this study was to test the effect of forest type and distance from the ignition source on the PyC stocks contained in macroscopic particles of soil charcoal (≥2 mm; 1 m depth) dispersed in ecotone forests of the northern Brazilian Amazon. Thirty permanent plots were set up near a site that had been occupied by pre‐Columbian and by modern populations until the late 1970s. The sampled plots represent seasonal and ombrophilous forests that occur under different hydro‐edaphic restrictions. Our results indicate that the largest PyC stock was spatially dependent on distance to the ignition source ( 50 cm) in seasonal forests was limited by hydro‐edaphic impediments that restricted the occurrence of charcoal. These results suggest that PyC stocks derived from macroscopic charcoal particles in the soil of this Brazilian Amazon ecotone region are controlled by the distance from the ignition source of the fire, and that forest types with higher hydro‐edaphic restrictions can inhibit formation and accumulation of charcoal. Making use of these distinctions reduces uncertainty and improves our ability to understand the variability of PyC stocks in forests with a history of fire in the Amazon.

Spatial heterogeneity in species composition constrains plant community responses to herbivory and fertilisation - Dorothee Hodapp; Elizabeth T. Borer; W. Stanley Harpole; Eric M. Lind; Eric W. Seabloom; Peter B. Adler; Juan Alberti; Carlos A. Arnillas; Jonathan D. Bakker; Lori Biederman; Marc Cadotte; Elsa E. Cleland; et al. (Ecology Letters, 2018)
Environmental change can result in substantial shifts in community composition. The associated immigration and extinction events are likely constrained by the spatial distribution of species. Still, studies on environmental change typically quantify biotic responses at single spatial (time series within a single plot) or temporal (spatial beta diversity at single time points) scales, ignoring their potential interdependence. Here, we use data from a global network of grassland experiments to determine how turnover responses to two major forms of environmental change – fertilisation and herbivore loss – are affected by species pool size and spatial compositional heterogeneity. Fertilisation led to higher rates of local extinction, whereas turnover in herbivore exclusion plots was driven by species replacement. Overall, sites with more spatially heterogeneous composition showed significantly higher rates of annual turnover, independent of species pool size and treatment. Taking into account spatial biodiversity aspects will therefore improve our understanding of consequences of global and anthropogenic change on community dynamics.

Publisher Correction to: Background invertebrate herbivory on dwarf birch (Betula glandulosa-nana complex) increases with temperature and precipitation across the tundra biome - Isabel C. Barrio; Elin Lindén; Mariska Te Beest; Johan Olofsson; Adrian Rocha; Eeva M. Soininen; Juha M. Alatalo; Tommi Andersson; Ashley Asmus; Julia Boike; Kari Anne Bråthen; John P. Bryant; et al. (Polar Biology, 2018)

Soil carbon and nitrogen accumulation in residential lawns of the Salt Lake Valley, Utah - Rose M. Smith; Jeb C. Williamson; Diane E. Pataki; James Ehleringer; Philip Dennison (Oecologia, 2018)

“Periderm Disorder Syndrome”: a New Name for the Syndrome Formerly Referred to as Pink Eye - Edward C. Lulai; Robert P. Sabba; Philip Nolte; Neil C. Gudmestad; Gary A. Secor (American Journal of Potato Research, 2018)

The decline of the Turtle Dove: Dietary associations with body condition and competition with other columbids analysed using high‐throughput sequencing - Jenny C. Dunn; Jennifer E. Stockdale; Rosemary J. Moorhouse‐Gann; Alexandra McCubbin; Helen Hipperson; Antony J. Morris; Philip V. Grice; William O. C. Symondson (Molecular Ecology, 2018)
Dietary changes linked to the availability of anthropogenic food resources can have complex implications for species and ecosystems, especially when species are in decline. Here, we use recently developed primers targeting the ITS 2 region of plants to characterize diet from faecal samples of four UK columbids, with particular focus on the European turtle dove ( Streptopelia turtur ), a rapidly declining obligate granivore. We examine dietary overlap between species (potential competition), associations with body condition in turtle doves and spatiotemporal variation in diet. We identified 143 taxonomic units, of which we classified 55% to species, another 34% to genus and the remaining 11% to family. We found significant dietary overlap between all columbid species, with the highest between turtle doves and stock doves ( Columba oenas ), then between turtle doves and woodpigeons ( Columba palumbus ). The lowest overlap was between woodpigeons and collared doves ( Streptopelia decaocto ). We show considerable change in columbid diets compared to previous studies, probably reflecting opportunistic foraging behaviour by columbids within a highly anthropogenically modified landscape, although our data for nonturtle doves should be considered preliminary. Nestling turtle doves in better condition had a higher dietary proportion of taxonomic units from natural arable plant species and a lower proportion of taxonomic units from anthropogenic food resources such as garden bird seed mixes and brassicas. This suggests that breeding ground conservation strategies for turtle doves should include provision of anthropogenic seeds for adults early in the breeding season, coupled with habitat rich in accessible seeds from arable plants once chicks have hatched.

Long‐term nitrogen fertilization decreases bacterial diversity and favors the growth of Actinobacteria and Proteobacteria in agro‐ecosystems across the globe - Zhongmin Dai; Weiqin Su; Huaihai Chen; Albert Barberán; Haochun Zhao; Mengjie Yu; Lu Yu; Philip C. Brookes; Christopher W. Schadt; Scott X. Chang; Jianming Xu (Global Change Biology, 2018)
Long‐term elevated nitrogen (N) input from anthropogenic sources may cause soil acidification and decrease crop yield, yet the response of the belowground microbial community to long‐term N input alone or in combination with phosphorus (P) and potassium (K) is poorly understood. We explored the effect of long‐term N and NPK fertilization on soil bacterial diversity and community composition using meta‐analysis of a global dataset. Nitrogen fertilization decreased soil pH , and increased soil organic carbon (C) and available N contents. Bacterial taxonomic diversity was decreased by N fertilization alone, but was increased by NPK fertilization. The effect of N fertilization on bacterial diversity varied with soil texture and water management, but was independent of crop type or N application rate. Changes in bacterial diversity were positively related to both soil pH and organic C content under N fertilization alone, but only to soil organic C under NPK fertilization. Microbial biomass C decreased with decreasing bacterial diversity under long‐term N fertilization. Nitrogen fertilization increased the relative abundance of Proteobacteria and Actinobacteria , but reduced the abundance of Acidobacteria , consistent with the general life history strategy theory for bacteria. The positive correlation between N application rate and the relative abundance of Actinobacteria indicates that increased N availability favored the growth of Actinobacteria . This first global analysis of long‐term N and NPK fertilization that differentially affects bacterial diversity and community composition provides a reference for nutrient management strategies for maintaining belowground microbial diversity in agro‐ecosystems worldwide.

A singular K-space model for fast reconstruction of magnetic resonance images from undersampled data - Jianhua Luo; Zhiying Mou; Binjie Qin; Wanqing Li; Philip Ogunbona; Marc C. Robini; Yuemin Zhu (Medical & Biological Engineering & Computing, 2018)

Correction to: Nest predation and the influence of habitat structure on nest predation of Wood Warbler Phylloscopus sibilatrix, a ground-nesting forest passerine - Paul E. Bellamy; Malcolm D. Burgess; John W. Mallord; Andrew Cristinacce; Christopher J. Orsman; Tony Davis; Philip V. Grice; Elisabeth C. Charman (Journal of Ornithology, 2018)

Intermittent convection-enhanced delivery of GDNF into rhesus monkey putamen: absence of local or cerebellar toxicity - Matthias Luz; Philip C. Allen; John Bringas; Chris Boiko; Diane E. Stockinger; Kristen J. Nikula; Owen Lewis; Max Woolley; H. Christian Fibiger; Krystof Bankiewicz; Erich Mohr (Archives of Toxicology, 2018)

Genome-wide association for testis weight in the diversity outbred mouse population - Joshua T. Yuan; Daniel M. Gatti; Vivek M. Philip; Steven Kasparek; Andrew M. Kreuzman; Benjamin Mansky; Kayvon Sharif; Dominik Taterra; Walter M. Taylor; Mary Thomas; Jeremy O. Ward; Andrew Holmes; et al. (Mammalian Genome, 2018)

Correction to: Energetic trade-offs and feedbacks between behavior and metabolism influence correlations between pace-of-life attributes - Timothy C. Salzman; Allison L. McLaughlin; David F. Westneat; Philip H. Crowley (Behavioral Ecology and Sociobiology, 2018)

Nest predation and the influence of habitat structure on nest predation of Wood Warbler Phylloscopus sibilatrix, a ground-nesting forest passerine - Paul E. Bellamy; Malcolm D. Burgess; John W. Mallord; Andrew Cristinacce; Christopher J. Orsman; Tony Davis; Philip V. Grice; Elisabeth C. Charman (Journal of Ornithology, 2018)

Signature of postglacial colonization on contemporary genetic structure and diversity of Quadrula quadrula (Bivalvia: Unionidae) - Philip T. Mathias; Jordan R. Hoffman; Chris C. Wilson; David T. Zanatta (Hydrobiologia, 2018)

Male origin determines satyrization potential of Aedes aegypti by invasive Aedes albopictus - Nildimar A. Honório; María C. Carrasquilla; Irka E. Bargielowski; Naoya Nishimura; Tom Swan; L. Philip Lounibos (Biological Invasions, 2018)

Energetic trade-offs and feedbacks between behavior and metabolism influence correlations between pace-of-life attributes - Timothy C. Salzman; Allison L. McLaughlin; David F. Westneat; Philip H. Crowley (Behavioral Ecology and Sociobiology, 2018)

Herpetofaunal Communities in Restored and Unrestored Remnant Tallgrass Prairie and Associated Wetlands in Northwest Arkansas, USA - Joseph A. Baecher; Philip N. Vogrinc; Jacquelyn C. Guzy; Chelsea S. Kross; John D. Willson (Wetlands, 2018)

Staying in place during times of change in Arctic Alaska: the implications of attachment, alternatives, and buffering - Henry P. Huntington; Philip A. Loring; Glenna Gannon; Shari Fox Gearheard; S. Craig Gerlach; Lawrence C. Hamilton (Regional Environmental Change, 2018)

Caught in a trap: landscape and climate implications of the insect fauna from a Roman well in Sherwood Forest - Paul C. Buckland; Philip I. Buckland; Eva Panagiotakopulu (Archaeological and Anthropological Sciences, 2018)

Compound-specific amino acid isotopic proxies for distinguishing between terrestrial and aquatic resource consumption - Emily C. Webb; Noah V. Honch; Philip J. H. Dunn; Anna Linderholm; Gunilla Eriksson; Kerstin Lidén; Richard P. Evershed (Archaeological and Anthropological Sciences, 2018)

Evidence for declining forest resilience to wildfires under climate change - Camille S. Stevens‐Rumann; Kerry B. Kemp; Philip E. Higuera; Brian J. Harvey; Monica T. Rother; Daniel C. Donato; Penelope Morgan; Thomas T. Veblen (Ecology Letters, 2018)
Forest resilience to climate change is a global concern given the potential effects of increased disturbance activity, warming temperatures and increased moisture stress on plants. We used a multi‐regional dataset of 1485 sites across 52 wildfires from the US Rocky Mountains to ask if and how changing climate over the last several decades impacted post‐fire tree regeneration, a key indicator of forest resilience. Results highlight significant decreases in tree regeneration in the 21st century. Annual moisture deficits were significantly greater from 2000 to 2015 as compared to 1985–1999, suggesting increasingly unfavourable post‐fire growing conditions, corresponding to significantly lower seedling densities and increased regeneration failure. Dry forests that already occur at the edge of their climatic tolerance are most prone to conversion to non‐forests after wildfires. Major climate‐induced reduction in forest density and extent has important consequences for a myriad of ecosystem services now and in the future.

Infections Up to 76 Days After Stroke Increase Disability and Death - Annastazia E. Learoyd; Lisa Woodhouse; Laurence Shaw; Nikola Sprigg; Daniel Bereczki; Eivind Berge; Valeria Caso; Hanne Christensen; Ronan Collins; Anna Czlonkowska; Anwar El Etribi; Tracy D. Farr; et al. (Translational Stroke Research, 2017)

Climate Change and Consequences for Potato Production: a Review of Tolerance to Emerging Abiotic Stress - Timothy S. George; Mark A. Taylor; Ian C. Dodd; Philip J. White (Potato Research, 2017)

Nutritional composition of honey bee food stores vary with floral composition - Philip Donkersley; Glenn Rhodes; Roger W. Pickup; Kevin C. Jones; Eileen F. Power; Geraldine A. Wright; Kenneth Wilson (Oecologia, 2017)

Phosphorus dynamics and phosphatase activity of soils under corn production with supplemental irrigation in humid coastal plain region, USA - Gilbert C. Sigua; Kenneth C. Stone; Philip J. Bauer; Ariel A. Szogi (Nutrient Cycling in Agroecosystems, 2017)

Long‐term changes in abundances of Sonoran Desert lizards reveal complex responses to climatic variation - Aaron D. Flesch; Philip C. Rosen; Peter Holm (Global Change Biology, 2017)
Understanding how climatic variation affects animal populations and communities is essential for addressing threats posed by climate change, especially in systems where impacts are projected to be high. We evaluated abundance dynamics of five common species of diurnal lizards over 25 years in a Sonoran Desert transition zone where precipitation decreased and temperature increased across time, and assessed hypotheses for the influence of climatic flux on spatiotemporal variation in abundances. We repeatedly surveyed lizards in spring and summer of each year at up to 32 sites, and used hierarchical mixture models to estimate detection probabilities, abundances, and population growth rates. Among terrestrial species, abundances of a short‐lived, winter–spring breeder increased markedly by an estimated 237%–285% across time, while two larger spring–summer breeders with higher thermal preferences declined by up to 64%. Abundances of two arboreal species that occupy shaded and thus sheltered microhabitats fluctuated but did not decline systematically. Abundances of all species increased with precipitation at short lag times (1–1.5 years) likely due to enhanced food availability, but often declined after periods of high precipitation at longer lag times (2–4 years) likely due to predation and other biotic pressures. Although rising maximum daily temperatures ( T max ) are expected to drive global declines of lizards, associations with T max were variable and weak for most species. Instead, abundances of all species declined with rising daily minimum temperatures, suggesting degradation of cool refugia imposed widespread metabolic or other costs. Our results suggest climate warming and drying are having major impacts on lizard communities by driving declines in species with traits that augment exposure to abiotic extremes and by modifying species interactions. The complexity of patterns we report indicates that evaluating and responding to the influence of climate change on biodiversity must consider a broad array of ecological processes.

Background invertebrate herbivory on dwarf birch (Betula glandulosa-nana complex) increases with temperature and precipitation across the tundra biome - Isabel C. Barrio; Elin Lindén; Mariska Te Beest; Johan Olofsson; Adrian Rocha; Eeva M. Soininen; Juha M. Alatalo; Tommi Andersson; Ashley Asmus; Julia Boike; Kari Anne Bråthen; John P. Bryant; et al. (Polar Biology, 2017)

Transcriptome sequencing and annotation of the halophytic microalga Dunaliella salina - Ling Hong; Jun-li Liu; Samira Z. Midoun; Philip C. Miller (Journal of Zhejiang University-SCIENCE B, 2017)

Spontaneous imbibition of water and determination of effective contact angles in the Eagle Ford Shale Formation using neutron imaging - Victoria H. DiStefano; Michael C. Cheshire; Joanna McFarlane; Lindsay M. Kolbus; Richard E. Hale; Edmund Perfect; Hassina Z. Bilheux; Louis J. Santodonato; Daniel S. Hussey; David L. Jacobson; Jacob M. LaManna; Philip R. Bingham; et al. (Journal of Earth Science, 2017)

Informing Marine Protected Area Designation and Management for Nesting Olive Ridley Sea Turtles Using Satellite Tracking - Tiffany M. Dawson; Angela Formia; Pierre D. Agamboué; Georges M. Asseko; François Boussamba; Floriane Cardiec; Emmanuel Chartrain; Philip D. Doherty; J. Michael Fay; Brendan J. Godley; Francis Lambert; Brice D. Koumba Mabert; et al. (Frontiers in Marine Science, 2017)

Climate, Topography, and Canopy Chemistry Exert Hierarchical Control Over Soil N Cycling in a Neotropical Lowland Forest - Brooke B. Osborne; Megan K. Nasto; Gregory P. Asner; Christopher S. Balzotti; Cory C. Cleveland; Benjamin W. Sullivan; Philip G. Taylor; Alan R. Townsend; Stephen Porder (Ecosystems, 2017)

Disease-associated change in an amphibian life-history trait - Benjamin C. Scheele; Lee F. Skerratt; David A. Hunter; Sam C. Banks; Jennifer C. Pierson; Don A. Driscoll; Philip G. Byrne; Lee Berger (Oecologia, 2017)

Uncertainties in vegetated buffer strip function in controlling phosphorus export from agricultural land in the Canadian prairies - Reza Habibiandehkordi; David A. Lobb; Steve C. Sheppard; Don N. Flaten; Philip N. Owens (Environmental Science and Pollution Research, 2017)

Identification of simple sequence repeat markers for sweetpotato weevil resistance - Benard Yada; Agnes Alajo; Gorrettie N. Ssemakula; Gina Brown-Guedira; Milton Anyanga Otema; Philip C. Stevenson; Robert O. M. Mwanga; G. Craig Yencho (Euphytica, 2017)
The development of sweetpotato [ Ipomoea batatas (L.) Lam] germplasm with resistance to sweetpotato weevil (SPW) requires an understanding of the biochemical and genetic mechanisms of resistance to optimize crop resistance. The African sweetpotato landrace, ‘New Kawogo’, was reported to be moderately resistant to two species of SPW, Cylas puncticollis and Cylas brunneus . Resistance has been associated with the presence of hydroxycinnamic acids esters (HCAs), but the underlying genetic basis remains unknown. To determine the genetic basis of this resistance, a bi-parental sweetpotato population from a cross between the moderately resistant, white-fleshed ‘New Kawogo’ and the highly susceptible, orange-fleshed North American variety ‘Beauregard’ was evaluated for SPW resistance and genotyped with simple sequence repeat (SSR) markers to identify weevil resistance loci. SPW resistance was measured on the basis of field storage root SPW damage severity and total HCA ester concentrations. Moderate broad sense heritability (H 2 = 0.49) was observed for weevil resistance in the population. Mean genotype SPW severity scores ranged from 1.0 to 9.0 and 25 progeny exhibited transgressive segregation for SPW resistance. Mean genotype total HCA ester concentrations were significantly different (P < 0.0001). A weak but significant correlation (r = 0.103, P = 0.015) was observed between total HCA ester concentration and SPW severity. A total of five and seven SSR markers were associated with field SPW severity and total HCA ester concentration, respectively. Markers IBS11, IbE5 and IbJ544b showed significant association with both field and HCA-based resistance, representing potential markers for the development of SPW resistant sweetpotato cultivars.

Soil Carbon and Nitrogen Responses to Nitrogen Fertilizer and Harvesting Rates in Switchgrass Cropping Systems - Zachary P. Valdez; William C. Hockaday; Caroline A. Masiello; Morgan E. Gallagher; G. Philip Robertson (BioEnergy Research, 2017)

Temperature and rainfall interact to control carbon cycling in tropical forests - Philip G. Taylor; Cory C. Cleveland; William R. Wieder; Benjamin W. Sullivan; Christopher E. Doughty; Solomon Z. Dobrowski; Alan R. Townsend (Ecology Letters, 2017)
Tropical forests dominate global terrestrial carbon (C) exchange, and recent droughts in the Amazon Basin have contributed to short‐term declines in terrestrial carbon dioxide uptake and storage. However, the effects of longer‐term climate variability on tropical forest carbon dynamics are still not well understood. We synthesised field data from more than 150 tropical forest sites to explore how climate regulates tropical forest aboveground net primary productivity ( ANPP ) and organic matter decomposition, and combined those data with two existing databases to explore climate – C relationships globally. While previous analyses have focused on the effects of either temperature or rainfall on ANPP , our results highlight the importance of interactions between temperature and rainfall on the C cycle. In cool forests ( 20 °C) it consistently enhanced both ANPP and decomposition. At the global scale, our analysis showed an increase in ANPP with rainfall in relatively warm sites, inconsistent with declines in ANPP with rainfall reported previously. Overall, our results alter our understanding of climate – C cycle relationships, with high precipitation accelerating rates of C exchange with the atmosphere in the most productive biome on earth.

Erratum to: Systematic Verification of Bioanalytical Similarity Between a Biosimilar and a Reference Biotherapeutic: Committee Recommendations for the Development and Validation of a Single Ligand-Binding Assay to Support Pharmacokinetic Assessments - Joseph C. Marini; Michael Anderson; Xiao-Yan Cai; John Chappell; Todd Coffey; Dominique Gouty; Aparna Kasinath; Vera Koppenburg; Philip Oldfield; Shannon Rebarchak; Ronald R. Bowsher (The AAPS Journal, 2017)

Novel mutations involving βI-, βIIA-, or βIVB-tubulin isotypes with functional resemblance to βIII-tubulin in breast cancer - Weiwei Wang; Hangxiao Zhang; Xumin Wang; Jordan Patterson; Philip Winter; Kathryn Graham; Sunita Ghosh; John C. Lee; Christos D. Katsetos; John R. Mackey; Jack A. Tuszynski; Gane Ka-Shu Wong; et al. (Protoplasma, 2017)

Attenuating the alcohol allure: attentional broadening reduces rapid motivational response to alcohol pictures - Nicole C. Ryerson; Lauren B. Neal; Philip A. Gable (Psychopharmacology, 2017)

Sorption of surfactants and personal care products in Indian soils - C. Ramprasad; L. Philip (International Journal of Environmental Science and Technology, 2017)

Seasonal spatial patterns of projected anthropogenic warming in complex terrain: a modeling study of the western US - David E. Rupp; Sihan Li; Philip W. Mote; Karen M. Shell; Neil Massey; Sarah N. Sparrow; David C. H. Wallom; Myles R. Allen (Climate Dynamics, 2017)

ICOADS Release 3.0: a major update to the historical marine climate record - Eric Freeman; Scott D. Woodruff; Steven J. Worley; Sandra J. Lubker; Elizabeth C. Kent; William E. Angel; David I. Berry; Philip Brohan; Ryan Eastman; Lydia Gates; Wolfgang Gloeden; Zaihua Ji; et al. (International Journal of Climatology, 2017)
We highlight improvements to the International Comprehensive Ocean‐Atmosphere Data Set ( ICOADS ) in the latest Release 3.0 ( R3 .0; covering 1662–2014). ICOADS is the most widely used freely available collection of surface marine observations, providing data for the construction of gridded analyses of sea surface temperature, estimates of air–sea interaction and other meteorological variables. ICOADS observations are assimilated into all major atmospheric, oceanic and coupled reanalyses, further widening its impact. R3 .0 therefore includes changes designed to enable effective exchange of information describing data quality between ICOADS , reanalysis centres, data set developers, scientists and the public. These user‐driven innovations include the assignment of a unique identifier ( UID ) to each marine report – to enable tracing of observations, linking with reports and improved data sharing. Other revisions and extensions of the ICOADS ' International Maritime Meteorological Archive common data format incorporate new near‐surface oceanographic data elements and cloud parameters. Many new input data sources have been assembled, and updates and improvements to existing data sources, or removal of erroneous data, made. Coupled with enhanced ‘preliminary’ monthly data and product extensions past 2014, R3 .0 provides improved support of climate assessment and monitoring, reanalyses and near‐real‐time applications.

Impacts of invasive plants on carbon pools depend on both species’ traits and local climate - Philip A. Martin; Adrian C. Newton; James M. Bullock (Ecology, 2017)
Invasive plants can alter ecosystem properties, leading to changes in the ecosystem services on which humans depend. However, generalizing about these effects is difficult because invasive plants represent a wide range of life forms, and invaded ecosystems differ in their plant communities and abiotic conditions. We hypothesize that differences in traits between the invader and native species can be used to predict impacts and so aid generalization. We further hypothesize that environmental conditions at invaded sites modify the effect of trait differences and so combine with traits to predict invasion impacts. To test these hypotheses, we used systematic review to compile data on changes in aboveground and soil carbon pools following non‐native plant invasion from studies across the World. Maximum potential height ( H max ) of each species was drawn from trait databases and other sources. We used meta‐regression to assess which of invasive species’ H max , differences in this height trait between native and invasive plants, and climatic water deficit, a measure of water stress, were good predictors of changes in carbon pools following invasion. We found that aboveground biomass in invaded ecosystems relative to uninvaded ones increased as the value of H max of invasive relative to native species increased, but that this effect was reduced in more water stressed ecosystems. Changes in soil carbon pools were also positively correlated with the relative H max of invasive species, but were not altered by water stress. This study is one of the first to show quantitatively that the impact of invasive species on an ecosystem may depend on differences in invasive and native species’ traits, rather than solely the traits of invasive species. Our study is also the first to show that the influence of trait differences can be altered by climate. Further developing our understanding of the impacts of invasive species using this framework could help researchers to identify not only potentially dangerous invasive species, but also the ecosystems where impacts are likely to be greatest.

South Polar Skua breeding populations in the Ross Sea assessed from demonstrated relationship with Adélie Penguin numbers - Deborah J. Wilson; Philip O’B. Lyver; Terry C. Greene; Amy L. Whitehead; Katie M. Dugger; Brian J. Karl; James R. F. Barringer; Roger McGarry; Annie M. Pollard; David G. Ainley (Polar Biology, 2017)

Combined biochar and nitrogen fertilizer reduces soil acidity and promotes nutrient use efficiency by soybean crop - Lu Yu; Xing Lu; Yan He; Philip C. Brookes; Hong Liao; Jianming Xu (Journal of Soils and Sediments, 2017)

Taxon-specific responses of soil microbial communities to different soil priming effects induced by addition of plant residues and their biochars - Peng Su; Jun Lou; Philip C. Brookes; Yu Luo; Yan He; Jianming Xu (Journal of Soils and Sediments, 2017)

Slowed Biogeochemical Cycling in Sub-arctic Birch Forest Linked to Reduced Mycorrhizal Growth and Community Change after a Defoliation Event - Thomas C. Parker; Jesse Sadowsky; Haley Dunleavy; Jens-Arne Subke; Serita D. Frey; Philip A. Wookey (Ecosystems, 2017)

Depth distribution and abundance of a coral-associated reef fish: roles of recruitment and post-recruitment processes - Patrick F. Smallhorn-West; Tom C. L. Bridge; Philip L. Munday; Geoffrey P. Jones (Coral Reefs, 2017)

A multicenter assessment of single-cell models aligned to standard measures of cell health for prediction of acute hepatotoxicity - Rowena L. Sison-Young; Volker M. Lauschke; Esther Johann; Eliane Alexandre; Sébastien Antherieu; Hélène Aerts; Helga H. J. Gerets; Gilles Labbe; Delphine Hoët; Martina Dorau; Christopher A. Schofield; Cerys A. Lovatt; et al. (Archives of Toxicology, 2017)

Anemonefish personalities influence the strength of mutualistic interactions with host sea anemones - Philip F. P. Schmiege; Cassidy C. D’Aloia; Peter M. Buston (Marine Biology, 2017)

The effects of combinations of biochar, lime, and organic fertilizer on nitrification and nitrifiers - Kaile Zhang; Lin Chen; Yong Li; Philip C. Brookes; Jianming Xu; Yu Luo (Biology and Fertility of Soils, 2017)

Estimating the microbiological risks associated with inland flood events: Bridging theory and models of pathogen transport - Philip A. Collender; Olivia C. Cooke; Lee D. Bryant; Thomas R. Kjeldsen; Justin V. Remais (Critical Reviews in Environmental Science and Technology, 2016)

Diatom assemblages reveal regional-scale differences in lake responses to recent climate change at the boreal-tundra ecotone, Manitoba, Canada - Avery L. C. Shinneman; Charles E. Umbanhowar; Mark B. Edlund; William O. Hobbs; Philip Camill; Christoph Geiss (Journal of Paleolimnology, 2016)

Decontamination treatments to eliminate problem biota from macroalgal tank cultures of Osmundea pinnatifida, Palmaria palmata and Ulva lactuca - Philip D. Kerrison; Hau Nhu Le; Gail C. Twigg; Duncan R. Smallman; Rory MacPhee; Fiona A. B. Houston; Adam D. Hughes (Journal of Applied Phycology, 2016)

Microwave drying characteristics of microalgae (Chlorella vulgaris) for biofuel production - Al Rey C. Villagracia; Andres Philip Mayol; Aristotle T. Ubando; Jose Bienvenido Manuel M. Biona; Nelson B. Arboleda; Melanie Y. David; Roy B. Tumlos; Henry Lee; Ong Hui Lin; Rafael A. Espiritu; Alvin B. Culaba; Hideaki Kasai (Clean Technologies and Environmental Policy, 2016)

Amazon aquatic biodiversity imperiled by oil spills - Valter M. Azevedo-Santos; James R. Garcia-Ayala; Philip M. Fearnside; Francisco A. Esteves; Fernando M. Pelicice; William F. Laurance; Ricardo C. Benine (Biodiversity and Conservation, 2016)

Reducing emissions from agriculture to meet the 2 °C target - Eva Wollenberg; Meryl Richards; Pete Smith; Petr Havlík; Michael Obersteiner; Francesco N. Tubiello; Martin Herold; Pierre Gerber; Sarah Carter; Andrew Reisinger; Detlef P. van Vuuren; Amy Dickie; et al. (Global Change Biology, 2016)
More than 100 countries pledged to reduce agricultural greenhouse gas ( GHG ) emissions in the 2015 Paris Agreement of the United Nations Framework Convention on Climate Change. Yet technical information about how much mitigation is needed in the sector vs. how much is feasible remains poor. We identify a preliminary global target for reducing emissions from agriculture of ~1 Gt CO 2 e yr −1 by 2030 to limit warming in 2100 to 2 °C above pre‐industrial levels. Yet plausible agricultural development pathways with mitigation cobenefits deliver only 21–40% of needed mitigation. The target indicates that more transformative technical and policy options will be needed, such as methane inhibitors and finance for new practices. A more comprehensive target for the 2 °C limit should be developed to include soil carbon and agriculture‐related mitigation options. Excluding agricultural emissions from mitigation targets and plans will increase the cost of mitigation in other sectors or reduce the feasibility of meeting the 2 °C limit.

Lack of association between dopaminergic antagonism and negative symptoms in schizophrenia: a positron emission tomography dopamine D2/3 receptor occupancy study - Gagan Fervaha; Fernando Caravaggio; David C. Mamo; Benoit H. Mulsant; Bruce G. Pollock; Shinichiro Nakajima; Philip Gerretsen; Tarek K. Rajji; Wanna Mar; Yusuke Iwata; Eric Plitman; Jun Ku Chung; et al. (Psychopharmacology, 2016)

Quantification of Four Efflux Drug Transporters in Liver and Kidney Across Species Using Targeted Quantitative Proteomics by Isotope Dilution NanoLC-MS/MS - John K. Fallon; Philip C. Smith; Cindy Q. Xia; Mi-Sook Kim (Pharmaceutical Research, 2016)

The properties and functions of biochars in forest ecosystems - Yu Luo; Zhuyun Yu; Kaile Zhang; Jianming Xu; Philip C. Brookes (Journal of Soils and Sediments, 2016)

Development of microbial community structure in vegetable-growing soils from open-field to plastic-greenhouse cultivation based on the PLFA analysis - Zhiyuan Yao; Jiajia Xing; Haiping Gu; Haizhen Wang; Jianjun Wu; Jianming Xu; Philip C. Brookes (Journal of Soils and Sediments, 2016)

Messages from the Other Side: Parasites Receive Damage Cues from their Host Plants - Muvari Connie Tjiurutue; Philip C. Stevenson; Lynn S. Adler (Journal of Chemical Ecology, 2016)

Land cover change and carbon emissions over 100 years in an A frican biodiversity hotspot - Simon Willcock; Oliver L. Phillips; Philip J. Platts; Ruth D. Swetnam; Andrew Balmford; Neil D. Burgess; Antje Ahrends; Julian Bayliss; Nike Doggart; Kathryn Doody; Eibleis Fanning; Jonathan M. H. Green; et al. (Global Change Biology, 2016)
Agricultural expansion has resulted in both land use and land cover change ( LULCC ) across the tropics. However, the spatial and temporal patterns of such change and their resulting impacts are poorly understood, particularly for the presatellite era. Here, we quantify the LULCC history across the 33.9 million ha watershed of Tanzania's Eastern Arc Mountains, using geo‐referenced and digitized historical land cover maps (dated 1908, 1923, 1949 and 2000). Our time series from this biodiversity hotspot shows that forest and savanna area both declined, by 74% (2.8 million ha) and 10% (2.9 million ha), respectively, between 1908 and 2000. This vegetation was replaced by a fivefold increase in cropland, from 1.2 million ha to 6.7 million ha. This LULCC implies a committed release of 0.9 Pg C (95% CI : 0.4–1.5) across the watershed for the same period, equivalent to 0.3 Mg C ha −1 yr −1 . This is at least threefold higher than previous estimates from global models for the same study area. We then used the LULCC data from before and after protected area creation, as well as from areas where no protection was established, to analyse the effectiveness of legal protection on land cover change despite the underlying spatial variation in protected areas. We found that, between 1949 and 2000, forest expanded within legally protected areas, resulting in carbon uptake of 4.8 (3.8–5.7) Mg C ha −1 , compared to a committed loss of 11.9 (7.2–16.6) Mg C ha −1 within areas lacking such protection. Furthermore, for nine protected areas where LULCC data are available prior to and following establishment, we show that protection reduces deforestation rates by 150% relative to unprotected portions of the watershed. Our results highlight that considerable LULCC occurred prior to the satellite era, thus other data sources are required to better understand long‐term land cover trends in the tropics.

Biological responses to environmental heterogeneity under future ocean conditions - Philip W. Boyd; Christopher E. Cornwall; Andrew Davison; Scott C. Doney; Marion Fourquez; Catriona L. Hurd; Ivan D. Lima; Andrew McMinn (Global Change Biology, 2016)
Organisms are projected to face unprecedented rates of change in future ocean conditions due to anthropogenic climate‐change. At present, marine life encounters a wide range of environmental heterogeneity from natural fluctuations to mean climate change. Manipulation studies suggest that biota from more variable marine environments have more phenotypic plasticity to tolerate environmental heterogeneity. Here, we consider current strategies employed by a range of representative organisms across various habitats – from short‐lived phytoplankton to long‐lived corals – in response to environmental heterogeneity. We then discuss how, if and when organismal responses (acclimate/migrate/adapt) may be altered by shifts in the magnitude of the mean climate‐change signal relative to that for natural fluctuations projected for coming decades. The findings from both novel climate‐change modelling simulations and prior biological manipulation studies, in which natural fluctuations are superimposed on those of mean change, provide valuable insights into organismal responses to environmental heterogeneity. Manipulations reveal that different experimental outcomes are evident between climate‐change treatments which include natural fluctuations vs. those which do not. Modelling simulations project that the magnitude of climate variability, along with mean climate change, will increase in coming decades, and hence environmental heterogeneity will increase, illustrating the need for more realistic biological manipulation experiments that include natural fluctuations. However, simulations also strongly suggest that the timescales over which the mean climate‐change signature will become dominant, relative to natural fluctuations, will vary for individual properties, being most rapid for CO 2 (~10 years from present day) to 4 decades for nutrients. We conclude that the strategies used by biota to respond to shifts in environmental heterogeneity may be complex, as they will have to physiologically straddle wide‐ranging timescales in the alteration of ocean conditions, including the need to adapt to rapidly rising CO 2 and also acclimate to environmental heterogeneity in more slowly changing properties such as warming.

Effects of the potential lithium-mimetic, ebselen, on impulsivity and emotional processing - Charles Masaki; Ann L. Sharpley; Charlotte M. Cooper; Beata R. Godlewska; Nisha Singh; Sridhar R. Vasudevan; Catherine J. Harmer; Grant C. Churchill; Trevor Sharp; Robert D. Rogers; Philip J. Cowen (Psychopharmacology, 2016)

Linking agricultural adaptation strategies, food security and vulnerability: evidence from West Africa - Sabine Douxchamps; Mark T. Van Wijk; Silvia Silvestri; Abdoulaye S. Moussa; Carlos Quiros; Ndèye Yacine B. Ndour; Saaka Buah; Léopold Somé; Mario Herrero; Patricia Kristjanson; Mathieu Ouedraogo; Philip K. Thornton; et al. (Regional Environmental Change, 2016)

An evaluation of a microbial inoculum in promoting organic C decomposition in a paddy soil following straw incorporation - Peng Su; Philip C. Brookes; Yan He; Jianjun Wu; Jianming Xu (Journal of Soils and Sediments, 2016)

Groundwater flow, nutrient, and stable isotope dynamics in the parafluvial-hyporheic zone of the regulated Lower Colorado River (Texas, USA) over the course of a small flood - Alyse C. Briody; M. Bayani Cardenas; Pin Shuai; Peter S. K. Knappett; Philip C. Bennett (Hydrogeology Journal, 2016)

Non-cultured faecal and gastrointestinal seed samples fail to detect Trichomonad infection in clinically and sub-clinically infected columbid birds - Jenny C. Dunn; Jennifer E. Stockdale; Alexandra McCubbin; Rebecca C. Thomas; Simon J. Goodman; Philip V. Grice; Antony J. Morris; Keith C. Hamer; William O. C. Symondson (Conservation Genetics Resources, 2016)

Climate change‐related regime shifts have altered spatial synchrony of plankton dynamics in the North Sea - Emma J. Defriez; Lawrence W. Sheppard; Philip C. Reid; Daniel C. Reuman (Global Change Biology, 2016)
During the 1980s, the North Sea plankton community underwent a well‐documented ecosystem regime shift, including both spatial changes (northward species range shifts) and temporal changes (increases in the total abundances of warmer water species). This regime shift has been attributed to climate change. Plankton provide a link between climate and higher trophic‐level organisms, which can forage on large spatial and temporal scales. It is therefore important to understand not only whether climate change affects purely spatial or temporal aspects of plankton dynamics, but also whether it affects spatiotemporal aspects such as metapopulation synchrony. If plankton synchrony is altered, higher trophic‐level feeding patterns may be modified. A second motivation for investigating changes in synchrony is that the possibility of such alterations has been examined for few organisms, in spite of the fact that synchrony is ubiquitous and of major importance in ecology. This study uses correlation coefficients and spectral analysis to investigate whether synchrony changed between the periods 1959–1980 and 1989–2010. Twenty‐three plankton taxa, sea surface temperature ( SST ), and wind speed were examined. Results revealed that synchrony in SST and plankton was altered. Changes were idiosyncratic, and were not explained by changes in abundance. Changes in the synchrony of Calanus helgolandicus and Para‐pseudocalanus spp appeared to be driven by changes in SST synchrony. This study is one of few to document alterations of synchrony and climate‐change impacts on synchrony. We discuss why climate‐change impacts on synchrony may well be more common and consequential than previously recognized.

Importance of lethal control of invasive predators for island conservation - James C. Russell; Holly P. Jones; Doug P. Armstrong; Franck Courchamp; Peter J. Kappes; Philip J. Seddon; Steffen Oppel; Mark J. Rauzon; Phil E. Cowan; Gérard Rocamora; Piero Genovesi; Elsa Bonnaud; et al. (Conservation Biology, 2016)

A cell wall-bound anionic peroxidase, PtrPO21, is involved in lignin polymerization in Populus trichocarpa - Chien-Yuan Lin; Quanzi Li; Sermsawat Tunlaya-Anukit; Rui Shi; Ying-Hsuan Sun; Jack P. Wang; Jie Liu; Philip Loziuk; Charles W. Edmunds; Zachary D. Miller; Ilona Peszlen; David C. Muddiman; et al. (Tree Genetics & Genomes, 2016)

A Framework to Assess Biogeochemical Response to Ecosystem Disturbance Using Nutrient Partitioning Ratios - J. Marty Kranabetter; Kendra K. McLauchlan; Sara K. Enders; Jennifer M. Fraterrigo; Philip E. Higuera; Jesse L. Morris; Edward B. Rastetter; Rebecca Barnes; Brian Buma; Daniel G. Gavin; Laci M. Gerhart; Lindsey Gillson; et al. (Ecosystems, 2016)

The influence of captive breeding management on founder representation and inbreeding in the ‘Alalā, the Hawaiian crow - Philip W. Hedrick; Paquita E. A. Hoeck; Robert C. Fleischer; Susan Farabaugh; Bryce M. Masuda (Conservation Genetics, 2016)

Effects of the potential lithium-mimetic, ebselen, on brain neurochemistry: a magnetic resonance spectroscopy study at 7 tesla - Charles Masaki; Ann L. Sharpley; Beata R. Godlewska; Adam Berrington; Tasuku Hashimoto; Nisha Singh; Sridhar R. Vasudevan; Uzay E. Emir; Grant C. Churchill; Philip J. Cowen (Psychopharmacology, 2016)

Rare copy number variants and congenital heart defects in the 22q11.2 deletion syndrome - Elisabeth E. Mlynarski; Michael Xie; Deanne Taylor; Molly B. Sheridan; Tingwei Guo; Silvia E. Racedo; Donna M. McDonald-McGinn; Eva W. C. Chow; Jacob Vorstman; Ann Swillen; Koen Devriendt; Jeroen Breckpot; et al. (Human Genetics, 2016)

Hydropower and the future of Amazonian biodiversity - Alexander C. Lees; Carlos A. Peres; Philip M. Fearnside; Maurício Schneider; Jansen A. S. Zuanon (Biodiversity and Conservation, 2016)

Shaping species with ephemeral boundaries: the distribution and genetic structure of desert tortoise ( Gopherus morafkai ) in the Sonoran Desert region - Taylor Edwards; Mercy Vaughn; Philip C. Rosen; Cristina Meléndez Torres; Alice E. Karl; Melanie Culver; Robert W. Murphy (Journal of Biogeography, 2016)
Aim We examine the role biogeographical features played in the evolution of Morafka's desert tortoise ( Gopherus morafkai ) and test the hypothesis that G. morafkai maintains genetically distinct lineages associated with different Sonoran Desert biomes. Increased knowledge of the past and present distribution of the Sonoran Desert region's biota provides insight into the forces that drive and maintain its biodiversity. Location Sonoran Desert biogeographical region; Sonora and Sinaloa, Mexico and Arizona, USA. Methods We examined wild tortoises from Mexico ( n = 155) and Arizona ( n = 78), spanning their known distribution. We used mt DNA sequences to reconstruct matrilineal relationships and 25 microsatellite ( STR ) loci for Bayesian analyses of gene flow. We performed clinal analyses on both mt DNA and STR loci to determine the position and amount of introgression where lineages co‐occur. We used GIS to assess the association of genetic structuring with ecological features. We used these data in a hypothesis‐driven approach to assess different models of how genetic diversity is maintained and distributed in G. morafkai . Results Gopherus morafkai was found to comprise genetically and geographically distinct ‘Sonoran’ and ‘Sinaloan’ lineages. Both lineages occurred in a relatively narrow zone of overlap in Sinaloan thornscrub, where it transitions into Sonoran desertscrub. Limited introgression occurred at the contact zone. The best‐fit model suggests that these lineages diverged in parapatry where the distribution of genotypes is environment‐dependent and introgression is inhibited by exogenous selection. Main conclusions The historically shifting ecotone between tropical deciduous forest and Sonoran desertscrub appears to be a boundary that fostered divergence between parapatric lineages of tortoises. The sharp genetic cline between the two lineages suggests that periods of isolation in temporary refugia due to Pleistocene climatic cycling influenced divergence. Despite incomplete reproductive isolation, the Sonoran and Sinaloan lineages of G. morafkai are on separate evolutionary trajectories.

Global impacts of the 1980s regime shift - Philip C. Reid; Renata E. Hari; Grégory Beaugrand; David M. Livingstone; Christoph Marty; Dietmar Straile; Jonathan Barichivich; Eric Goberville; Rita Adrian; Yasuyuki Aono; Ross Brown; James Foster; et al. (Global Change Biology, 2016)
Despite evidence from a number of Earth systems that abrupt temporal changes known as regime shifts are important, their nature, scale and mechanisms remain poorly documented and understood. Applying principal component analysis, change‐point analysis and a sequential t ‐test analysis of regime shifts to 72 time series, we confirm that the 1980s regime shift represented a major change in the Earth's biophysical systems from the upper atmosphere to the depths of the ocean and from the Arctic to the Antarctic, and occurred at slightly different times around the world. Using historical climate model simulations from the Coupled Model Intercomparison Project Phase 5 ( CMIP 5) and statistical modelling of historical temperatures, we then demonstrate that this event was triggered by rapid global warming from anthropogenic plus natural forcing, the latter associated with the recovery from the El Chichón volcanic eruption. The shift in temperature that occurred at this time is hypothesized as the main forcing for a cascade of abrupt environmental changes. Within the context of the last century or more, the 1980s event was unique in terms of its global scope and scale; our observed consequences imply that if unavoidable natural events such as major volcanic eruptions interact with anthropogenic warming unforeseen multiplier effects may occur.

Remnants of Antarctic vegetation on King George Island during the early Miocene Melville Glaciation - Sophie Warny; C. Madison Kymes; Rosemary A. Askin; Krzysztof P. Krajewski; Philip J. Bart (Palynology, 2016)

A major QTL corresponding to the Rk locus for resistance to root-knot nematodes in cowpea (Vigna unguiculata L. Walp.) - Bao-Lam Huynh; William C. Matthews; Jeffrey D. Ehlers; Mitchell R. Lucas; Jansen R. P. Santos; Arsenio Ndeve; Timothy J. Close; Philip A. Roberts (Theoretical and Applied Genetics, 2016)

Contact and fumigant toxicity of five pesticidal plants against Callosobruchus maculatus (Coleoptera: Chrysomelidae) in stored cowpea (Vigna unguiculata) - Prisila A. Mkenda; Philip C. Stevenson; Patrick Ndakidemi; Dudley I. Farman; Steven R. Belmain (International Journal of Tropical Insect Science, 2015)

Climate change, climate justice and the application of probabilistic event attribution to summer heat extremes in the California Central Valley - Roberto Mera; Neil Massey; David E. Rupp; Philip Mote; Myles Allen; Peter C. Frumhoff (Climatic Change, 2015)

Seasonal inhomogeneity of soot particles over the central Indo-Gangetic Plains, India: Influence of meteorology - B. P. Singh; S. Tiwari; Philip K. Hopke; R. S. Singh; D. S. Bisht; A. K. Srivastava; R. K. Singh; U. C. Dumka; A. K. Singh; B. N. Rai; Manoj K. Srivastava (Journal of Meteorological Research, 2015)

A meta‐analysis of functional group responses to forest recovery outside of the tropics - Rebecca Spake; Thomas H. G. Ezard; Philip A. Martin; Adrian C. Newton; C. Patrick Doncaster (Conservation Biology, 2015)
Both active and passive forest restoration schemes are used in degraded landscapes across the world to enhance biodiversity and ecosystem service provision. Restoration is increasingly also being implemented in biodiversity offset schemes as compensation for loss of natural habitat to anthropogenic development. This has raised concerns about the value of replacing old‐growth forest with plantations, motivating research on biodiversity recovery as forest stands age. Functional diversity is now advocated as a key metric for restoration success, yet it has received little analytical attention to date. We conducted a meta‐analysis of 90 studies that measured differences in species richness for functional groups of fungi, lichens, and beetles between old‐growth control and planted or secondary treatment forests in temperate, boreal, and Mediterranean regions. We identified functional‐group–specific relationships in the response of species richness to stand age after forest disturbance. Ectomycorrhizal fungi averaged 90 years for recovery to old‐growth values (between 45 years and unrecoverable at 95% prediction limits), and epiphytic lichens took 180 years to reach 90% of old‐growth values (between 140 years and never for recovery to old‐growth values at 95% prediction limits). Non‐saproxylic beetle richness, in contrast, decreased as stand age of broadleaved forests increased. The slow recovery by some functional groups essential to ecosystem functioning makes old‐growth forest an effectively irreplaceable biodiversity resource that should be exempt from biodiversity offsetting initiatives.

Text analysis tools for identification of emerging topics and research gaps in conservation science - Martin J. Westgate; Philip S. Barton; Jennifer C. Pierson; David B. Lindenmayer (Conservation Biology, 2015)
Keeping track of conceptual and methodological developments is a critical skill for research scientists, but this task is increasingly difficult due to the high rate of academic publication. As a crisis discipline, conservation science is particularly in need of tools that facilitate rapid yet insightful synthesis. We show how a common text‐mining method (latent Dirichlet allocation, or topic modeling) and statistical tests familiar to ecologists (cluster analysis, regression, and network analysis) can be used to investigate trends and identify potential research gaps in the scientific literature. We tested these methods on the literature on ecological surrogates and indicators. Analysis of topic popularity within this corpus showed a strong emphasis on monitoring and management of fragmented ecosystems, while analysis of research gaps suggested a greater role for genetic surrogates and indicators. Our results show that automated text analysis methods need to be used with care, but can provide information that is complementary to that given by systematic reviews and meta‐analyses, increasing scientists’ capacity for research synthesis.

Bismuth(III) α-hydroxy carboxylates: highly selective toxicity of glycolates towards Leishmania major - Allan Loh; Yih Ching Ong; Victoria L. Blair; Lukasz Kedzierski; Philip C. Andrews (JBIC Journal of Biological Inorganic Chemistry, 2015)

Quantifying landscape‐level methane fluxes in subarctic Finland using a multiscale approach - Iain. P. Hartley; Timothy. C. Hill; Thomas. J. Wade; Robert. J. Clement; John. B. Moncrieff; Ana. Prieto‐Blanco; Mathias. I. Disney; Brian. Huntley; Mathew. Williams; Nicholas. J. K. Howden; Philip. A. Wookey; Robert. Baxter (Global Change Biology, 2015)
Quantifying landscape‐scale methane ( CH 4 ) fluxes from boreal and arctic regions, and determining how they are controlled, is critical for predicting the magnitude of any CH 4 emission feedback to climate change. Furthermore, there remains uncertainty regarding the relative importance of small areas of strong methanogenic activity, vs. larger areas with net CH 4 uptake, in controlling landscape‐level fluxes. We measured CH 4 fluxes from multiple microtopographical subunits (sedge‐dominated lawns, interhummocks and hummocks) within an aapa mire in subarctic Finland, as well as in drier ecosystems present in the wider landscape, lichen heath and mountain birch forest. An intercomparison was carried out between fluxes measured using static chambers, up‐scaled using a high‐resolution landcover map derived from aerial photography and eddy covariance. Strong agreement was observed between the two methodologies, with emission rates greatest in lawns. CH 4 fluxes from lawns were strongly related to seasonal fluctuations in temperature, but their floating nature meant that water‐table depth was not a key factor in controlling CH 4 release. In contrast, chamber measurements identified net CH 4 uptake in birch forest soils. An intercomparison between the aerial photography and satellite remote sensing demonstrated that quantifying the distribution of the key CH 4 emitting and consuming plant communities was possible from satellite, allowing fluxes to be scaled up to a 100 km 2 area. For the full growing season (May to October), ~ 1.1–1.4 g CH 4 m −2 was released across the 100 km 2 area. This was based on up‐scaled lawn emissions of 1.2–1.5 g CH 4 m −2 , vs. an up‐scaled uptake of 0.07–0.15 g CH 4 m −2 by the wider landscape. Given the strong temperature sensitivity of the dominant lawn fluxes, and the fact that lawns are unlikely to dry out, climate warming may substantially increase CH 4 emissions in northern Finland, and in aapa mire regions in general.

Common and distinct neural effects of risperidone and olanzapine during procedural learning in schizophrenia: a randomised longitudinal fMRI study - Veena Kumari; Ulrich Ettinger; Seoung Eun Lee; Christine Deuschl; Anantha P. Anilkumar; Anne Schmechtig; Philip J. Corr; Dominic H. ffytche; Steven C. R. Williams (Psychopharmacology, 2015)

Barriers to climate change adaptation: evidence from northeast Ghana in the context of a systematic literature review - Philip Antwi-Agyei; Andrew J. Dougill; Lindsay C. Stringer (Climate and Development, 2015)

GPCR structure, function, drug discovery and crystallography: report from Academia-Industry International Conference (UK Royal Society) Chicheley Hall, 1–2 September 2014 - Alexander Heifetz; Gebhard F. X. Schertler; Roland Seifert; Christopher G. Tate; Patrick M. Sexton; Vsevolod V. Gurevich; Daniel Fourmy; Vadim Cherezov; Fiona H. Marshall; R. Ian Storer; Isabel Moraes; Irina G. Tikhonova; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

Summer dormancy in Elymus scaber and its hybridity with wheat - Matthew T. Newell; Richard C. Hayes; James M. Virgona; Philip J. Larkin (Euphytica, 2015)

The Tosontsengel Mongolia world record sea‐level pressure extreme: spatial analysis of elevation bias in adjustment‐to‐sea‐level pressures - Gomboluudev Purevjav; Robert C. Balling; Randall S. Cerveny; Rob Allan; Gilbert P. Compo; Philip Jones; Thomas C. Peterson; Manola Brunet; Fatima Driouech; José Luis Stella; Bohumil M. Svoma; Daniel Krahenbuhl; et al. (International Journal of Climatology, 2015)
A World Meteorological Organization ( WMO ) committee evaluated the record sea‐level pressure ( SLP ) measurement of 1089.4 hPa on 30 December 2004 in Tosontsengel, Mongolia (1724.6 m). Although instrumentation and data collection procedures were properly followed according to the assessment of the committee, concern was raised regarding the reliability of SLP adjustment from such a high‐elevation station. This paper addresses this concern with a number of analyses that look at relationships between SLP extremes and corresponding station elevation and temperature. First, we selected data from stations extracted from the Integrated Surface Database ( ISD ‐Lite) of NOAA 's National Climate Data Center. A spatial analysis indicates that elevation shows little to no association ( R 2 values essentially zero) to extreme SLP . However, a second analysis between extreme SLP and air temperature indicates that high regionalism exists in spatial correlations (local R 2 ) between those two variables. This relationship to temperature is likely the result of differences in SLP adjustment formulae used around the world. Based on this analysis, on the need to differentiate the SLP values adjusted using extremely cold temperatures (and generally high elevation), and following past WMO SLP guidelines, the WMO Rapporteurs for Climate and Weather Extremes therefore have created two distinct SLP records: (a) highest adjusted SLP (below 750 m), currently 1083.3 hPa recorded on 31 December 1968 at Agata, Evenhiyskiy, Russia; and (b) highest adjusted SLP (above 750 m), currently 1089.4 hPa (by Russian method; 1089.1 hPa by WMO formula) on 30 December 2004 in Tosontsengel, Mongolia. Future WMO guidance regarding SLP adjustment may lead to re‐evaluation of this and other SLP records.

Morphology and water permeability of red blood cells from green sea turtle (Chelonia mydas) - Gheorghe Benga; Bogdan E. Chapman; Tony Romeo; Guy C. Cox; Philip W. Kuchel (Protoplasma, 2015)

Effects of active, passive, and combined smoking on cervical cancer mortality: a nationwide proportional mortality study in Chinese urban women - Jingmei Jiang; Haiyu Pang; Boqi Liu; Philip C. Nasca; Biao Zhang; Yanping Wu; Wei Han; Margaret Gates; Tao Lu; Xiaonong Zou; Fang Xue; Lei Hou; et al. (Cancer Causes & Control, 2015)

Faunal and sedimentological analysis of a latest Silurian stromatoporoid biostrome from the central Appalachian Basin - Selina R. Cole; John T. Haynes; Philip C. Lucas; Richard A. Lambert (Facies, 2015)

Plant community change mediates the response of foliar δ15N to CO2 enrichment in mesic grasslands - H. Wayne Polley; Justin D. Derner; Robert B. Jackson; Richard A. Gill; Andrew C. Procter; Philip A. Fay (Oecologia, 2015)

Acute Methylenedioxypyrovalerone Toxicity - Blake A. Froberg; Michael Levine; Michael C. Beuhler; Bryan S. Judge; Philip W. Moore; Kristin M. Engebretsen; Nathanael J. Mckeown; Christopher D. Rosenbaum; Amy C. Young; Daniel E. Rusyniak (Journal of Medical Toxicology, 2015)

Global low-frequency motions in protein allostery: CAP as a model system - Philip D. Townsend; Thomas L. Rodgers; Ehmke Pohl; Mark R. Wilson; Tom C. B. McLeish; Martin J. Cann (Biophysical Reviews, 2015)

Physical oceanography of the deep seas around New Zealand: a review - Stephen M Chiswell; Helen C Bostock; Philip JH Sutton; Michael JM Williams (New Zealand Journal of Marine and Freshwater Research, 2015)
We review the advances in ‘blue water’ physical oceanography of the seas around New Zealand since the last major review in 1985. By 1985, a basic description had been made of the circulation around New Zealand. Since then, dramatic increases in data from satellites, hydrographic cruises, surface drifters and profiling floats have improved knowledge on the locations, strengths and variability of the currents, water masses and fronts in the region. We have better estimates of the surface and deep circulation, and a better understanding of the dynamical processes driving this circulation and its variability. This review covers the open ocean, including water masses, ocean currents, tides and numerical modelling, and discusses the future of New Zealand oceanography.

Topographic controls on soil nitrogen availability in a lowland tropical forest - Samantha R. Weintraub; Philip G. Taylor; Stephen Porder; Cory C. Cleveland; Gregory P. Asner; Alan R. Townsend (Ecology, 2015)
Geomorphic position often correlates with nutrient cycling across landscapes. In tropical forests, topography is known to influence phosphorus (P) availability, but its effect on nitrogen (N) cycling has received less exploration, especially in lowland forests where widespread N richness is frequently assumed. Here, we report significant effects of topographic slope and landscape position on multiple aspects of the N cycle across a highly dissected lowland tropical forest on the Osa Peninsula, Costa Rica. A suite of N cycle metrics measured along a topographic sequence revealed a distinct gradient in N availability. Values of soil δ 15 N, inorganic N pools, net nitrification rates, and nitrification potentials were all substantially lower on a flanking steep hillslope (~28°) compared to a relatively flat ridge top (~6°), indicating lower N availability and a less open N cycle in steep parts of the landscape. Slope soils also hosted smaller total carbon and nitrogen stocks and notably less weathered soil minerals than did ridge soils. These latter findings suggest that elevated N loss resulting from high rates of soil and particulate organic matter erosion could underpin the spatial variation in N cycling and availability. Expanding our analysis to the larger study landscape, a strong negative linear relationship between soil δ 15 N values and surface slope angles was observed. N isotope mass balance models suggest that this pattern is most plausibly explained by an increase in N loss via erosive, non‐fractioning pathways from steep zones, as most other variables commonly assumed to affect soil δ 15 N values (such as temperature, precipitation, and vegetation type) did not vary across the sampled region. Together, these results reveal notable hillslope‐scale variation in N richness and suggest an important role for non‐fractionating N loss in the maintenance of this pattern. Such findings highlight the importance of geomorphology and the significant capacity of erosion to influence N availability in steepland ecosystems.

Chronic administration of ketamine mimics the perturbed sense of body ownership associated with schizophrenia - Jinsong Tang; Hannah L. Morgan; Yanhui Liao; Philip R. Corlett; Dong Wang; Hong Li; Yanqing Tang; Jindong Chen; Tieqiao Liu; Wei Hao; Paul C. Fletcher; Xiaogang Chen (Psychopharmacology, 2015)

Arabinose and protocatechuate catabolism genes are important for growth of Rhizobium leguminosarum biovar viciae in the pea rhizosphere - Paula Garcia-Fraile; Jonathan C. Seaman; Ramakrishnan Karunakaran; Anne Edwards; Philip S. Poole; J. Allan Downie (Plant and Soil, 2015)

Human ALDH1B1 Polymorphisms may Affect the Metabolism of Acetaldehyde and All-trans retinaldehyde—In Vitro Studies and Computational Modeling - Brian C. Jackson; Philip Reigan; Bettina Miller; David C. Thompson; Vasilis Vasiliou (Pharmaceutical Research, 2015)

Carbon Dynamics on the Louisiana Continental Shelf and Cross-Shelf Feeding of Hypoxia - Brian Fry; Dubravko Justić; Philip Riekenberg; Erick M. Swenson; R. Eugene Turner; Lixia Wang; Lora Pride; Nancy N. Rabalais; Janis C. Kurtz; John C. Lehrter; Michael C. Murrell; Elizabeth H. Shadwick; et al. (Estuaries and Coasts, 2015)

Interactive effects of ocean acidification and rising sea temperatures alter predation rate and predator selectivity in reef fish communities - Maud. C. O. Ferrari; Philip L. Munday; Jodie L. Rummer; Mark I. McCormick; Katherine Corkill; Sue‐Ann Watson; Bridie J. M. Allan; Mark G. Meekan; Douglas P. Chivers (Global Change Biology, 2015)
Ocean warming and acidification are serious threats to marine life. While each stressor alone has been studied in detail, their combined effects on the outcome of ecological interactions are poorly understood. We measured predation rates and predator selectivity of two closely related species of damselfish exposed to a predatory dottyback. We found temperature and CO 2 interacted synergistically on overall predation rate, but antagonistically on predator selectivity. Notably, elevated CO 2 or temperature alone reversed predator selectivity, but the interaction between the two stressors cancelled selectivity. Routine metabolic rates of the two prey showed strong species differences in tolerance to CO 2 and not temperature, but these differences did not correlate with recorded mortality. This highlights the difficulty of linking species‐level physiological tolerance to resulting ecological outcomes. This study is the first to document both synergistic and antagonistic effects of elevated CO 2 and temperature on a crucial ecological process like predator–prey dynamics.

Rapid carbon turnover beneath shrub and tree vegetation is associated with low soil carbon stocks at a subarctic treeline - Thomas C. Parker; Jens‐Arne Subke; Philip A. Wookey (Global Change Biology, 2015)
Climate warming at high northern latitudes has caused substantial increases in plant productivity of tundra vegetation and an expansion of the range of deciduous shrub species. However significant the increase in carbon (C) contained within above‐ground shrub biomass, it is modest in comparison with the amount of C stored in the soil in tundra ecosystems. Here, we use a ‘space‐for‐time’ approach to test the hypothesis that a shift from lower‐productivity tundra heath to higher‐productivity deciduous shrub vegetation in the sub‐Arctic may lead to a loss of soil C that out‐weighs the increase in above‐ground shrub biomass. We further hypothesize that a shift from ericoid to ectomycorrhizal systems coincident with this vegetation change provides a mechanism for the loss of soil C. We sampled soil C stocks, soil surface CO 2 flux rates and fungal growth rates along replicated natural transitions from birch forest ( Betula pubescens ), through deciduous shrub tundra ( Betula nana ) to tundra heaths ( Empetrum nigrum ) near Abisko, Swedish Lapland. We demonstrate that organic horizon soil organic C ( SOC org ) is significantly lower at shrub (2.98 ± 0.48 kg m −2 ) and forest (2.04 ± 0.25 kg m −2 ) plots than at heath plots (7.03 ± 0.79 kg m −2 ). Shrub vegetation had the highest respiration rates, suggesting that despite higher rates of C assimilation, C turnover was also very high and less C is sequestered in the ecosystem. Growth rates of fungal hyphae increased across the transition from heath to shrub, suggesting that the action of ectomycorrhizal symbionts in the scavenging of organically bound nutrients is an important pathway by which soil C is made available to microbial degradation. The expansion of deciduous shrubs onto potentially vulnerable arctic soils with large stores of C could therefore represent a significant positive feedback to the climate system.

Organic forms dominate hydrologic nitrogen export from a lowland tropical watershed - Philip G. Taylor; William R. Wieder; Samantha Weintraub; Sagy Cohen; Cory C. Cleveland; Alan R. Townsend (Ecology, 2015)
Observations of high dissolved inorganic nitrogen (DIN) concentrations in stream water have reinforced the notion that primary tropical rain forests cycle nitrogen (N) in relative excess compared to phosphorus. Here we test this notion by evaluating hydrologic N export from a small watershed on the Osa Peninsula, Costa Rica, where prior research has shown multiple indicators of conservative N cycling throughout the ecosystem. We repeatedly measured a host of factors known to influence N export for one year, including stream water chemistry and upslope litterfall, soil N availability and net N processing rates, and soil solution chemistry at the surface, 15‐ and 50‐cm depths. Contrary to prevailing assumptions about the lowland N cycle, we find that dissolved organic nitrogen (DON) averaged 85% of dissolved N export for 48 of 52 consecutive weeks. For most of the year stream water nitrate (NO 3 − ) export was very low, which reflected minimal net N processing and DIN leaching from upslope soils. Yet, for one month in the dry season, NO 3 − was the major component of N export due to a combination of low flows and upslope nitrification that concentrated NO 3 − in stream water. Particulate organic N (PON) export was much larger than dissolved forms at 14.6 kg N·ha −1 ·yr −1 , driven by soil erosion during storms. At this rate, PON export was slightly greater than estimated inputs from free‐living N fixation and atmospheric N deposition, which suggests that erosion‐driven PON export could constrain ecosystem level N stocks over longer timescales. This phenomenon is complimentary to the “DON leak” hypothesis, which postulates that the long‐term accumulation of ecosystem N in unpolluted ecosystems is constrained by the export of organic N independently of biological N demand. Using an established global sediment generation model, we illustrate that PON erosion may be an important vector for N loss in tropical landscapes that are geomorphically active. This study supports an emerging view that landscape geomorphology influences nutrient biogeochemistry and limitation, though more research is needed to understand the mechanisms and spatial significance of erosional N loss from terrestrial ecosystems.

Intramuscular determinants of the ability to recover work capacity above critical power - Philip Friere Skiba; Jonathan Fulford; David C. Clarke; Anni Vanhatalo; Andrew M. Jones (European Journal of Applied Physiology, 2015)

Electrochemically mediated enantioselective reduction of chiral sulfoxides - Kuan-I. Chen; Victoria L. Challinor; Linda Kielmann; Philip C. Sharpe; James J. De Voss; Ulrike Kappler; Alastair G. McEwan; Paul V. Bernhardt (JBIC Journal of Biological Inorganic Chemistry, 2015)

Disturbed subsurface microbial communities follow equivalent trajectories despite different structural starting points - Kim M. Handley; Kelly C. Wrighton; Christopher S. Miller; Michael J. Wilkins; Rose S. Kantor; Brian C. Thomas; Kenneth H. Williams; Jack A. Gilbert; Philip E. Long; Jillian F. Banfield (Environmental Microbiology, 2015)
Summary Microbial community structure, and niche and neutral processes can all influence response to disturbance. Here, we provide experimental evidence for niche versus neutral and founding community effects during a bioremediation‐related organic carbon disturbance. Subsurface sediment, partitioned into 22 flow‐through columns, was stimulated in situ by the addition of acetate as a carbon and electron donor source. This drove the system into a new transient biogeochemical state characterized by iron reduction and enriched D esulfuromonadales , C omamonadaceae and B acteroidetes lineages. After approximately 1 month conditions favoured sulfate reduction, and were accompanied by a substantial increase in the relative abundance of D esulfobulbus , D esulfosporosinus , D esulfitobacterium and D esulfotomaculum . Two subsets of four to five columns each were switched from acetate to lactate amendment during either iron (earlier) or sulfate (later) reduction. Hence, subsets had significantly different founding communities. All lactate treatments exhibited lower relative abundances of D esulfotomaculum and B acteroidetes , enrichments of C lostridiales and P sychrosinus species, and a temporal succession from highly abundant C lostridium sensu stricto to P sychrosinus . Regardless of starting point, lactate‐switch communities followed comparable structural trajectories, whereby convergence was evident 9 to 16 days after each switch, and significant after 29 to 34 days of lactate addition. Results imply that neither the founding community nor neutral processes influenced succession following perturbation.

Remote Ischemic Postconditioning: Harnessing Endogenous Protection in a Murine Model of Vascular Cognitive Impairment - Mohammad Badruzzaman Khan; Md Nasrul Hoda; Kumar Vaibhav; Shailendra Giri; Philip Wang; Jennifer L. Waller; Adviye Ergul; Krishnan M. Dhandapani; Susan C. Fagan; David C. Hess (Translational Stroke Research, 2015)

Gene amplification of 5-enol-pyruvylshikimate-3-phosphate synthase in glyphosate-resistant Kochia scoparia - Andrew T. Wiersma; Todd A. Gaines; Christopher Preston; John P. Hamilton; Darci Giacomini; C. Robin Buell; Jan E. Leach; Philip Westra (Planta, 2015)

Quantifying aquatic insect deposition from lake to land - Jamin Dreyer; Philip A. Townsend; James C. Hook III; David Hoekman; M. Jake Vander Zanden; Claudio Gratton (Ecology, 2015)
Adjacent ecosystems are influenced by organisms that move across boundaries, such as insects with aquatic larval stages and terrestrial adult stages, which transport energy and nutrients from water to land. However, the ecosystem‐level effect of aquatic insects on land has generally been ignored, perhaps because the organisms themselves are individually small. At the naturally productive Lake Mývatn, Iceland, we used two readily measured quantities: total insect emergence from water and relative insect density on land, to demonstrate an approach for estimating aquatic insect deposition (e.g., kg N·m −2 ·yr −1 ) to shore. Estimates from emergence traps between 2008 and 2011 indicated a range of 0.15–3.7 g·m −2 ·yr −1 , or a whole‐lake emergence of 3.1–76 Mg/yr; all masses are given as dry mass. Using aerial infall trap measurements of midge relative abundance over land, we developed a local‐maximum decay function model to predict proportional midge deposition with distance from the lake. The dispersal model predicted midge abundance with R 2 = 0.89, a pattern consistent among years, with peak midge deposition occurring 20–25 m inland and 70% of midges deposited within 100 m of shore. During a high‐midge year (2008), we estimate midge deposition within the first 50 m of shoreline to be 100 kg·ha −1 ·yr −1 , corresponding to inputs of 10 kg N·ha −1 ·yr −1 and 1 kg P·ha −1 ·yr −1 , or about three to five times above background terrestrial N deposition rates. Consistent with elevated N input where midges are most dense, we observed that soil available nitrate in resin bags decreases with increasing distance from the lake. Our approach, generalizable to other systems, shows that aquatic insects can be a major source of nutrients to terrestrial ecosystems and have the capacity to significantly affect ecosystem processes.

The pH dependence of Escherichia coli O157:H7 adsorption on kaolinite and goethite surfaces - Taoxiang Zhang; Wenhao Yang; Xinyu Zhu; Haizhen Wang; Philip C. Brookes; Jianming Xu (Journal of Soils and Sediments, 2015)

Long-term applications of untreated and alum-treated poultry litter drive soil nitrogen concentrations and associated microbial community dynamics - Peter J. Tomlinson; Mary C. Savin; Philip A. Moore (Biology and Fertility of Soils, 2015)

Trends in the daily and extreme temperatures in the Qiantang River basin, China - Fang Xia; Xingmei Liu; Jianming Xu; Zhonggen Wang; Jingfeng Huang; Philip C. Brookes (International Journal of Climatology, 2015)
Temporal and spatial changes in the annual and seasonal temperatures in a typical basin of the Qiantang River were analysed based on the time series databases of daily temperatures from 14 meteorological stations. Both the Mann–Kendall ( MK ) trend test and simple linear regression analyses were employed to detect trends in the mean and extreme temperatures. The temperature changes during the three periods of 1960–1990, 1960–2000 and 1960–2006 were investigated at each meteorological station and over the entire basin as an average. The spatial and temporal changes were characterized by significant warming throughout the region, with the minimum temperature (Tn) increasing the most, particularly after 1990. Various percentiles of extreme temperatures, as well as their corresponding frequencies, were chosen to explore the trends of extreme climate change in this region. Linear regression analyses showed a significant warming trend in cold events both on an annual and seasonal basis, especially in the winter. Conversely, the hot events were dominated by an insignificant warming trend ( p > 0.05). When comparing the time series before and after 1990, trend shifts were apparent in both the mean and extreme temperatures, particularly in the spring and winter. In addition to the large‐scale circulation, regional factors may have influenced the observed climate change in the studied region. Climate change has already influenced human society by, for example, increasing the frequency of haze in the study region. We conclude that the warming here is mainly attributed to changes in the minimum temperature.

Joule–Thomson Effects on the Flow of Liquid Water - Philip H. Stauffer; K. C. Lewis; Joshua S. Stein; Bryan J. Travis; Peter Lichtner; George Zyvoloski (Transport in Porous Media, 2014)

Systematic Verification of Bioanalytical Similarity Between a Biosimilar and a Reference Biotherapeutic: Committee Recommendations for the Development and Validation of a Single Ligand-Binding Assay to Support Pharmacokinetic Assessments - Joseph C. Marini; Michael Anderson; Xiao-Yan Cai; John Chappell; Todd Coffey; Dominique Gouty; Aparna Kasinath; Vera Koppenburg; Philip Oldfield; Shannon Rebarchak; Ronald R. Bowsher (The AAPS Journal, 2014)

Bacterial degradation of Aroclor 1242 in the mycorrhizosphere soils of zucchini (Cucurbita pepo L.) inoculated with arbuscular mycorrhizal fungi - Hua Qin; Philip C. Brookes; Jianming Xu; Youzhi Feng (Environmental Science and Pollution Research, 2014)

Autophagy of Mitochondria: A Promising Therapeutic Target for Neurodegenerative Disease - Pradip K. Kamat; Anuradha Kalani; Philip Kyles; Suresh C. Tyagi; Neetu Tyagi (Cell Biochemistry and Biophysics, 2014)

Apparent environmental synergism drives the dynamics of Amazonian forest fragments - William F. Laurance; Ana S. Andrade; Ainhoa Magrach; José L. C. Camargo; Mason Campbell; Philip M. Fearnside; Will Edwards; Jefferson J. Valsko; Thomas E. Lovejoy; Susan G. Laurance (Ecology, 2014)
Many contemporary ecosystems are likely to be affected by multiple environmental drivers, complicating efforts to predict future changes in those ecosystems. We studied long‐term changes (1980–2012) in forest dynamics and liana (woody vine) abundance and biomass in fragmented and intact forests of the central Amazon. We did so by contrasting trends in 33 permanent 1‐ha plots near forest edges (plot center 2 or regional climate drivers that influence forest dynamics. Hence, the dynamics of Amazonian forest fragments cannot be understood simply as a consequence of forest fragmentation. Rather, the changes we observed appear to arise from an interaction of fragmentation with one or more global‐ or regional‐scale drivers affecting forest dynamics. Both sets of phenomena are evidently increasing forest dynamics and liana abundances in fragmented forests, changes that could reduce carbon storage and alter many aspects of forest ecology.

Habitat degradation modifies the strength of interspecific competition in coral dwelling damselfishes - Lisa Boström-Einarsson; Mary C. Bonin; Philip L. Munday; Geoffrey P. Jones (Ecology, 2014)
Habitat degradation is predicted to exacerbate competition for critical resources; however, the relationship between habitat quality and competition is poorly understood. In this study, we used a manipulative experiment to test the effects of habitat degradation on competition between two planktivorous, coral‐dwelling damselfishes, Chrysiptera parasema and Dascyllus melanurus . Experimental reefs were constructed with either healthy (100% live) or degraded (10% live) Acropora longicyathus coral, stocked with varying densities of these two fish species, and monitored for two months. On healthy habitat, the mortality of C. parasema was density dependent, and increased substantially in the presence of the dominant interspecific competitor D. melanurus . In contrast, on reefs where habitat was degraded, C. parasema mortality was highly variable, density independent, and was no longer influenced by the presence of dominant competitor D. melanurus . Behavioral observations revealed that agonistic interactions for both species increased with density on degraded habitat, but not on healthy habitat. In addition, on degraded reefs, both species displayed a reduced association with reef habitat and ventured further away from shelter with increasing densities of the dominant competitor D. melanurus . These results suggest that reduced habitat quality can have such a profound effect on reef fishes, that it eliminates density‐dependent mortality and competitive dominance hierarchies, thereby substantially altering the mechanisms that structure reef fish communities.

Toxins induce ‘malaise’ behaviour in the honeybee (Apis mellifera) - Victoria Hurst; Philip C. Stevenson; Geraldine A. Wright (Journal of Comparative Physiology A, 2014)

Climate change and Southern Ocean ecosystems I: how changes in physical habitats directly affect marine biota - Andrew J. Constable; Jessica Melbourne‐Thomas; Stuart P. Corney; Kevin R. Arrigo; Christophe Barbraud; David K. A. Barnes; Nathaniel L. Bindoff; Philip W. Boyd; Angelika Brandt; Daniel P. Costa; Andrew T. Davidson; Hugh W. Ducklow; et al. (Global Change Biology, 2014)
Antarctic and Southern Ocean ( ASO ) marine ecosystems have been changing for at least the last 30 years, including in response to increasing ocean temperatures and changes in the extent and seasonality of sea ice; the magnitude and direction of these changes differ between regions around Antarctica that could see populations of the same species changing differently in different regions. This article reviews current and expected changes in ASO physical habitats in response to climate change. It then reviews how these changes may impact the autecology of marine biota of this polar region: microbes, zooplankton, salps, Antarctic krill, fish, cephalopods, marine mammals, seabirds, and benthos. The general prognosis for ASO marine habitats is for an overall warming and freshening, strengthening of westerly winds, with a potential pole‐ward movement of those winds and the frontal systems, and an increase in ocean eddy activity. Many habitat parameters will have regionally specific changes, particularly relating to sea ice characteristics and seasonal dynamics. Lower trophic levels are expected to move south as the ocean conditions in which they are currently found move pole‐ward. For Antarctic krill and finfish, the latitudinal breadth of their range will depend on their tolerance of warming oceans and changes to productivity. Ocean acidification is a concern not only for calcifying organisms but also for crustaceans such as Antarctic krill; it is also likely to be the most important change in benthic habitats over the coming century. For marine mammals and birds, the expected changes primarily relate to their flexibility in moving to alternative locations for food and the energetic cost of longer or more complex foraging trips for those that are bound to breeding colonies. Few species are sufficiently well studied to make comprehensive species‐specific vulnerability assessments possible. Priorities for future work are discussed.

Improved allometric models to estimate the aboveground biomass of tropical trees - Jérôme Chave; Maxime Réjou‐Méchain; Alberto Búrquez; Emmanuel Chidumayo; Matthew S. Colgan; Welington B.C. Delitti; Alvaro Duque; Tron Eid; Philip M. Fearnside; Rosa C. Goodman; Matieu Henry; Angelina Martínez‐Yrízar; et al. (Global Change Biology, 2014)
Terrestrial carbon stock mapping is important for the successful implementation of climate change mitigation policies. Its accuracy depends on the availability of reliable allometric models to infer oven‐dry aboveground biomass of trees from census data. The degree of uncertainty associated with previously published pantropical aboveground biomass allometries is large. We analyzed a global database of directly harvested trees at 58 sites, spanning a wide range of climatic conditions and vegetation types (4004 trees ≥ 5 cm trunk diameter). When trunk diameter, total tree height, and wood specific gravity were included in the aboveground biomass model as covariates, a single model was found to hold across tropical vegetation types, with no detectable effect of region or environmental factors. The mean percent bias and variance of this model was only slightly higher than that of locally fitted models. Wood specific gravity was an important predictor of aboveground biomass, especially when including a much broader range of vegetation types than previous studies. The generic tree diameter–height relationship depended linearly on a bioclimatic stress variable E , which compounds indices of temperature variability, precipitation variability, and drought intensity. For cases in which total tree height is unavailable for aboveground biomass estimation, a pantropical model incorporating wood density, trunk diameter, and the variable E outperformed previously published models without height. However, to minimize bias, the development of locally derived diameter–height relationships is advised whenever possible. Both new allometric models should contribute to improve the accuracy of biomass assessment protocols in tropical vegetation types, and to advancing our understanding of architectural and evolutionary constraints on woody plant development.

pH, nitrogen mineralization, and KCl-extractable aluminum as affected by initial soil pH and rate of vetch residue application: results from a laboratory study - Kongcao Xiao; Lu Yu; Jianming Xu; Philip C. Brookes (Journal of Soils and Sediments, 2014)

Is obesity associated with colorectal cancer screening for African American and Latino individuals in the context of patient navigation? - Errol J. Philip; Rachel C. Shelton; Hayley S. Thompson; Elizaveta Efuni; Steven Itzkowitz; Lina Jandorf (Cancer Causes & Control, 2014)

Ultrasensitive immuno-detection using viral nanoparticles with modular assembly using genetically-directed biotinylation - Julia Litvinov; Anna E. V. Hagström; Yubitza Lopez; Meenu Adhikari; Katerina Kourentzi; Ulrich Strych; Federico A. Monzon; William Foster; Philip T. Cagle; Richard C. Willson (Biotechnology Letters, 2014)

Livelihood adaptations to climate variability: insights from farming households in Ghana - Philip Antwi-Agyei; Lindsay C. Stringer; Andrew J. Dougill (Regional Environmental Change, 2014)

Adverse effects from antidepressant treatment: randomised controlled trial of 601 depressed individuals - Andrew A. Crawford; Sarah Lewis; David Nutt; Tim J. Peters; Philip Cowen; Michael C. O’Donovan; Nicola Wiles; Glyn Lewis (Psychopharmacology, 2014)

Recurring patterns in stationary intervals of abdominal uterine electromyograms during gestation - Luigi Yuri Di Marco; Costanzo Di Maria; Wing-Chiu Tong; Michael J. Taggart; Stephen C. Robson; Philip Langley (Medical & Biological Engineering & Computing, 2014)

Herbivore Defence Compounds Occur in Pollen and Reduce Bumblebee Colony Fitness - Sarah E. J. Arnold; M. Eduardo Peralta Idrovo; Luis J. Lomas Arias; Steven R. Belmain; Philip C. Stevenson (Journal of Chemical Ecology, 2014)

Solid Lipid Particles for Oral Delivery of Peptide and Protein Drugs III — the Effect of Fed State Conditions on the In Vitro Release and Degradation of Desmopressin - Philip C. Christophersen; Dimple Vaghela; Anette Müllertz; Mingshi Yang; Hanne M. Nielsen; Huiling Mu (The AAPS Journal, 2014)

A new chasmosaurine from northern Laramidia expands frill disparity in ceratopsid dinosaurs - Michael J. Ryan; David C. Evans; Philip J. Currie; Mark A. Loewen (The Science of Nature, 2014)

Gestational hypertension and the developmental origins of cardiac hypertrophy and diastolic dysfunction - David W. J. Armstrong; M. Yat Tse; Philip G. Wong; Nicole M. Ventura; Jalna A. Meens; Amer M. Johri; Murray F. Matangi; Stephen C. Pang (Molecular and Cellular Biochemistry, 2014)

Modelling microalgal activity as a function of inorganic carbon concentration: accounting for the impact of pH on the bicarbonate system - Philip C. Keymer; Paul A. Lant; Steven Pratt (Journal of Applied Phycology, 2014)

Prospective evaluation of designs for analysis of variance without knowledge of effect sizes - C. Patrick Doncaster; Andrew J. H. Davey; Philip M. Dixon (Environmental and Ecological Statistics, 2014)

Mito‐nuclear discord in six congeneric lineages of H olarctic ducks (genus A nas ) - Jeffrey L. Peters; Kevin Winker; Kendra C. Millam; Philip Lavretsky; Irina Kulikova; Robert E. Wilson; Yuri N. Zhuravlev; Kevin G. McCracken (Molecular Ecology, 2014)
Many species have Holarctic distributions that extend across Europe, Asia and North America. Most genetics research on these species has examined only mitochondrial (mt) DNA , which has revealed wide variance in divergence between Old World ( OW ) and New World ( NW ) populations, ranging from shallow, unstructured genealogies to deeply divergent lineages. In this study, we sequenced 20 nuclear introns to test for concordant patterns of OW – NW differentiation between mt DNA and nuclear (nu) DNA for six lineages of Holarctic ducks (genus Anas ). Genetic differentiation for both marker types varied widely among these lineages (idiosyncratic population histories), but mt DNA and nu DNA divergence within lineages was not significantly correlated. Moreover, compared with the association between mt DNA and nu DNA divergence observed among different species, OW – NW nu DNA differentiation was generally lower than mt DNA divergence, at least for lineages with deeply divergent mt DNA . Furthermore, coalescent estimates indicated significantly higher rates of gene flow for nu DNA than mt DNA for four of the six lineages. Thus, Holarctic ducks show prominent mito‐nuclear discord between OW and NW populations, and we reject differences in sorting rates as the sole cause of the within‐species discord. Male‐mediated intercontinental gene flow is likely a leading contributor to this discord, although selection could also cause increased mt DNA divergence relative to weak nu DNA differentiation. The population genetics of these ducks contribute to growing evidence that mt DNA can be an unreliable indicator of stage of speciation and that more holistic approaches are needed for species delimitation.

H alomonas sulfidaeris ‐dominated microbial community inhabits a 1.8 km‐deep subsurface C ambrian S andstone reservoir - Yiran Dong; Charu Gupta Kumar; Nicholas Chia; Pan‐Jun Kim; Philip A. Miller; Nathan D. Price; Isaac K. O. Cann; Theodore M. Flynn; Robert A. Sanford; Ivan G. Krapac; Randall A. Locke; Pei‐Ying Hong; et al. (Environmental Microbiology, 2014)
Summary A low‐diversity microbial community, dominated by the γ ‐proteobacterium H alomonas sulfidaeris , was detected in samples of warm saline formation porewater collected from the C ambrian Mt. S imon S andstone in the I llinois B asin of the N orth A merican M idcontinent (1.8 km/5872 ft burial depth, 50° C , pH 8, 181 bars pressure). These highly porous and permeable quartz arenite sandstones are directly analogous to reservoirs around the world targeted for large‐scale hydrocarbon extraction, as well as subsurface gas and carbon storage. A new downhole low‐contamination subsurface sampling probe was used to collect in situ formation water samples for microbial environmental metagenomic analyses. Multiple lines of evidence suggest that this H . sulfidaeris ‐dominated subsurface microbial community is indigenous and not derived from drilling mud microbial contamination. Data to support this includes V 1‐ V 3 pyrosequencing of formation water and drilling mud, as well as comparison with previously published microbial analyses of drilling muds in other sites. Metabolic pathway reconstruction, constrained by the geology, geochemistry and present‐day environmental conditions of the Mt . S imon S andstone, implies that H . sulfidaeris ‐dominated subsurface microbial community may utilize iron and nitrogen metabolisms and extensively recycle indigenous nutrients and substrates. The presence of aromatic compound metabolic pathways suggests this microbial community can readily adapt to and survive subsurface hydrocarbon migration.

Long‐term changes in liana abundance and forest dynamics in undisturbed Amazonian forests - William F. Laurance; Ana S. Andrade; Ainhoa Magrach; José L. C. Camargo; Jefferson J. Valsko; Mason Campbell; Philip M. Fearnside; Will Edwards; Thomas E. Lovejoy; Susan G. Laurance (Ecology, 2014)
Lianas (climbing woody vines) are important structural parasites of tropical trees and may be increasing in abundance in response to global‐change drivers. We assessed long‐term (∼14‐year) changes in liana abundance and forest dynamics within 36 1‐ha permanent plots spanning ∼600 km 2 of undisturbed rainforest in central Amazonia. Within each plot, we counted each liana stem (≥2 cm diameter) and measured its diameter at 1.3 m height, and then used these data to estimate liana aboveground biomass. An initial liana survey was completed in 1997–1999 and then repeated in 2012, using identical methods. Liana abundance in the plots increased by an average of 1.00% ± 0.88% per year, leading to a highly significant ( t = 6.58, df = 35, P t = 1.46, df = 35, P = 0.15; paired t tests). Liana size distributions shifted significantly (χ 2 = 191, df = 8, P We used long‐term data on rainfall and forest dynamics from our study site to test hypotheses about potential drivers of change in liana communities. Lianas generally increase with rainfall seasonality, but we found no significant trends over time (1997–2012) in five rainfall parameters (total annual rainfall, dry‐season rainfall, wet‐season rainfall, number of very dry months, CV of monthly rainfall). However, rates of tree mortality and recruitment have increased significantly over time in our plots, and general linear mixed‐effect models suggested that lianas were more abundant at sites with higher tree mortality and flatter topography. Rising concentrations of atmospheric CO 2 , which may stimulate liana growth, might also have promoted liana increases. Our findings clearly support the view that lianas are increasing in abundance in old‐growth tropical forests, possibly in response to accelerating forest dynamics and rising CO 2 concentrations. The aboveground biomass of trees was lowest in plots with abundant lianas, suggesting that lianas could reduce forest carbon storage and potentially alter forest dynamics if they continue to proliferate.

Virtual screening based on pharmacophoric features of known calpain inhibitors to identify potent inhibitors of calpain - Arumugam Ramachandran Muralidharan; Chandrabose Selvaraj; Sanjeev Kumar Singh; C. A. Nelson Jesudasan; Pitchairaj Geraldine; Philip A. Thomas (Medicinal Chemistry Research, 2014)

The combined effects of urea application and simulated acid rain on soil acidification and microbial community structure - Xingmei Liu; Jian Zhou; Wanlu Li; Jianming Xu; Philip C. Brookes (Environmental Science and Pollution Research, 2014)

Classification of HHV-6A and HHV-6B as distinct viruses - Dharam Ablashi; Henri Agut; Roberto Alvarez-Lafuente; Duncan A. Clark; Stephen Dewhurst; Dario DiLuca; Louis Flamand; Niza Frenkel; Robert Gallo; Ursula A. Gompels; Per Höllsberg; Steven Jacobson; et al. (Archives of Virology, 2014)

Advancing climate compatible development: lessons from southern Africa - Lindsay C. Stringer; Andrew J. Dougill; Jen C. Dyer; Katharine Vincent; Florian Fritzsche; Julia Leventon; Mario Paulo Falcão; Pascal Manyakaidze; Stephen Syampungani; Philip Powell; Gabriel Kalaba (Regional Environmental Change, 2014)

Arsenic Species Uptake and Subcellular Distribution in Vallisneria natans (Lour.) Hara as Influenced by Aquatic pH - Guoliang Chen; Xingmei Liu; Jianming Xu; Philip C. Brookes; Jianjun Wu (Bulletin of Environmental Contamination and Toxicology, 2014)

Capital and income breeding: the role of food supply - Philip A. Stephens; Alasdair I. Houston; Karin C. Harding; Ian L. Boyd; John M. McNamara (Ecology, 2014)
An aspect of life history that has seen increasing attention in recent years is that of strategies for financing the costs of offspring production. These strategies are often described by a continuum ranging from capital breeding, in which costs are met purely from endogenous reserves, to income breeding, in which costs are met purely from concurrent intake. A variety of factors that might drive strategies toward a given point on the capital–income continuum has been reviewed, and assessed using analytical models. However, aspects of food supply, including seasonality and unpredictability, have often been cited as important drivers of capital and income breeding, but are difficult to assess using analytical models. Consequently, we used dynamic programming to assess the role of the food supply in shaping offspring provisioning strategies. Our model is parameterized for a pinniped (one taxon remarkable for the range of offspring‐provisioning strategies that it illustrates). We show that increased food availability, increased seasonality, and, to a lesser extent, increased unpredictability can all favor the emergence of capital breeding. In terms of the conversion of energy into offspring growth, the shorter periods of care associated with capital breeding are considerably more energetically efficient than income breeding, because shorter periods of care are associated with a higher ratio of energy put into offspring growth to energy spent on parent and offspring maintenance metabolism. Moreover, no clear costs are currently associated with capital accumulation in pinnipeds. This contrasts with general assumptions about endotherms, which suggest that income breeding will usually be preferred. Our model emphasizes the role of seasonally high abundances of food in enabling mothers to pursue an energetically efficient capital‐breeding strategy. We discuss the importance of offspring development for dictating strategies for financing offspring production.

New Frontiers—Accelerator Mass Spectrometry (AMS): Recommendation for Best Practices and Harmonization from Global Bioanalysis Consortium Harmonization Team - Graeme C. Young; Mark Seymour; Stephen R. Dueker; Philip Timmerman; Ali Arjomand; Kohei Nozawa (The AAPS Journal, 2014)

Pharmacological treatments prescribed to people with autism spectrum disorder (ASD) in primary health care - Macey L. Murray; Yingfen Hsia; Karen Glaser; Emily Simonoff; Declan G. M. Murphy; Philip J. Asherson; Hanna Eklund; Ian C. K. Wong (Psychopharmacology, 2014)
Rationale Autism spectrum disorders (ASDs) affect 1 % of children, having significant impact on health and social outcomes. Psychotropic medication use by individuals with ASD in the USA increased over time, and polypharmacy occurred in >50 % of those prescribed. In the UK, no psychotropic drugs are approved in ASDs, and little is known about patterns of pharmacological treatment in the ASD population and associated co-morbidities. Methods We used The Health Improvement Network, a nationally representative primary care database, to assess the prevalence of ASD diagnoses, psychotropic drug prescribing and neuropsychiatric co-morbidities of 0–24 year olds between 1992 and 2008. Results ASD prevalence increased 65-fold from 0.01 % (1992) to 0.50 % (2008). Psychotropic drugs were prescribed to 29 % (1,619/5,651) of the ASD cohort; the most prescribed drugs were sleep medication (9.7 % of prescribed patients), psychostimulants (7.9 %) and antipsychotics (7.3 %). More patients were given psychostimulants and sleep medications over time from 1.5–6.3 % and 2.2–5.9 % respectively. Thirty-seven per cent of the cohort had ≥1 record of a neuropsychiatric co-morbidity, the most common being developmental difficulties and learning disabilities (12.6 %), behavioural, conduct and personality disorders (11.1 %) and attention deficit hyperactivity disorder (7.5 %). Conclusions British physicians are more conservative in prescribing practice than American colleagues. However, use of psychostimulants and antipsychotics is much higher in those with ASD than in the general population. Polypharmacy was seen in 34 % of prescribed patients in 2008. Additional studies examining use, efficacy, and long-term safety of antipsychotics and psychostimulants in autistic individuals are warranted.

Dominant Drivers of Seedling Establishment in a Fire-Dependent Obligate Seeder: Climate or Fire Regimes? - Annabel L. Smith; David Blair; Lachlan McBurney; Sam C. Banks; Philip S. Barton; Wade Blanchard; Don A. Driscoll; A. Malcolm Gill; David B. Lindenmayer (Ecosystems, 2014)

Effects of nitrogen fertilizer on the acidification of two typical acid soils in South China - Jian Zhou; Fang Xia; Xingmei Liu; Yan He; Jianming Xu; Philip C. Brookes (Journal of Soils and Sediments, 2014)

Waves of intermediate length through an array of vertical cylinders - Chiang C. Mei; I. -Chi Chan; Philip L. -F. Liu (Environmental Fluid Mechanics, 2014)

Temperature explains variable spread rates of the invasive woodwasp Sirex noctilio in the Southern Hemisphere - M. Victoria Lantschner; José M. Villacide; Jeffrey R. Garnas; Philip Croft; Angus J. Carnegie; Andrew M. Liebhold; Juan C. Corley (Biological Invasions, 2014)

Impaired learning of predators and lower prey survival under elevated CO 2 : a consequence of neurotransmitter interference - Douglas P. Chivers; Mark I. McCormick; Göran E. Nilsson; Philip L. Munday; Sue‐Ann Watson; Mark G. Meekan; Matthew D. Mitchell; Katherine C. Corkill; Maud C. O. Ferrari (Global Change Biology, 2014)
Ocean acidification is one of the most pressing environmental concerns of our time, and not surprisingly, we have seen a recent explosion of research into the physiological impacts and ecological consequences of changes in ocean chemistry. We are gaining considerable insights from this work, but further advances require greater integration across disciplines. Here, we showed that projected near‐future CO 2 levels impaired the ability of damselfish to learn the identity of predators. These effects stem from impaired neurotransmitter function; impaired learning under elevated CO 2 was reversed when fish were treated with gabazine, an antagonist of the GABA ‐A receptor – a major inhibitory neurotransmitter receptor in the brain of vertebrates. The effects of CO 2 on learning and the link to neurotransmitter interference were manifested as major differences in survival for fish released into the wild. Lower survival under elevated CO 2 , as a result of impaired learning, could have a major influence on population recruitment.

An empirical assessment of the consistency of taxonomic identifications - Philip F. Culverhouse; Norman Macleod; Robert Williams; Mark C. Benfield; Rubens M. Lopes; Marc Picheral (Marine Biology Research, 2014)

Organic carbon mineralization responses to temperature increases in subtropical paddy soils - Ping Zhou; Yong Li; Xiu’e Ren; He’ai Xiao; Chengli Tong; Tida Ge; Philip C. Brookes; Jianlin Shen; Jinshui Wu (Journal of Soils and Sediments, 2014)

Relation between plant nutrition, hormones, insecticide applications, bacterial endophytes, and Candidatus Liberibacter Ct values in citrus trees infected with Huanglongbing - Weishou Shen; Juan M. Cevallos-Cevallos; Ulisses Nunes da Rocha; Hector A. Arevalo; Philip A. Stansly; Pamela D. Roberts; Ariena H. C. van Bruggen (European Journal of Plant Pathology, 2013)

Predicting invasion in grassland ecosystems: is exotic dominance the real embarrassment of richness? - Eric W. Seabloom; Elizabeth T. Borer; Yvonne Buckley; Elsa E. Cleland; Kendi Davies; Jennifer Firn; W. Stanley Harpole; Yann Hautier; Eric Lind; Andrew MacDougall; John L. Orrock; Suzanne M. Prober; et al. (Global Change Biology, 2013)
Invasions have increased the size of regional species pools, but are typically assumed to reduce native diversity. However, global‐scale tests of this assumption have been elusive because of the focus on exotic species richness, rather than relative abundance. This is problematic because low invader richness can indicate invasion resistance by the native community or, alternatively, dominance by a single exotic species. Here, we used a globally replicated study to quantify relationships between exotic richness and abundance in grass‐dominated ecosystems in 13 countries on six continents, ranging from salt marshes to alpine tundra. We tested effects of human land use, native community diversity, herbivore pressure, and nutrient limitation on exotic plant dominance. Despite its widespread use, exotic richness was a poor proxy for exotic dominance at low exotic richness, because sites that contained few exotic species ranged from relatively pristine (low exotic richness and cover) to almost completely exotic‐dominated ones (low exotic richness but high exotic cover). Both exotic cover and richness were predicted by native plant diversity (native grass richness) and land use (distance to cultivation). Although climate was important for predicting both exotic cover and richness, climatic factors predicting cover (precipitation variability) differed from those predicting richness (maximum temperature and mean temperature in the wettest quarter). Herbivory and nutrient limitation did not predict exotic richness or cover. Exotic dominance was greatest in areas with low native grass richness at the site‐ or regional‐scale. Although this could reflect native grass displacement, a lack of biotic resistance is a more likely explanation, given that grasses comprise the most aggressive invaders. These findings underscore the need to move beyond richness as a surrogate for the extent of invasion, because this metric confounds monodominance with invasion resistance. Monitoring species' relative abundance will more rapidly advance our understanding of invasions.

A new dromaeosaurid (Dinosauria: Theropoda) with Asian affinities from the latest Cretaceous of North America - David C. Evans; Derek W. Larson; Philip J. Currie (The Science of Nature, 2013)

The floral transition is not the developmental switch that confers competence for the Arabidopsis age-related resistance response to Pseudomonas syringae pv. tomato - Daniel C. Wilson; Philip Carella; Marisa Isaacs; Robin K. Cameron (Plant Molecular Biology, 2013)

Novel bacterial endophytes from Hevea brasiliensis as biocontrol agent against Phytophthora leaf fall disease - Amith Abraham; Shaji Philip; C. Kuruvilla Jacob; K. Jayachandran (BioControl, 2013)

Evolutionary implications of the distribution and variation of the skeletal muscles of the anuran lymphatic system - Robert C. Drewes; Stanley S. Hillman; Michael S. Hedrick; Philip C. Withers (Zoomorphology, 2013)
Lymphatic return to the circulation in anurans is dependent upon the interaction of a number of skeletal muscles and lung deflation. We define character states and describe variation of these putative lymphatic skeletal muscles: the M. cutaneus pectoris (CP), M. cutaneus dorsi (CD), M. piriformis (P), M. sphincter ani cloacalis (SAC), and the complex of the M. gracilis minor/M. abdominal crenator (GM/AC). We include examination of over 400 specimens of 377 species belonging to 40 of the 42 currently recognized anuran families. Some muscles show limited variation (P) or are clearly linked to phylogeny (CP; CD) and thus have limited value in the determination of form and function. However, the GM/AC and SAC show a high degree of structural variation that appears in taxa across the phylogenetic spectrum. This allows us to make phylogenetically independent determinations of form and function. We define an ancestral state of the GM and conclude that evolution of the GM/AC and SAC has progressed in two directions from this ancestral state: toward either elaboration or reduction. Where present, the character states of both of these muscle groups were observed in all species examined and the number of states correlated within each family as well. The degree of development of the GM/AC and SAC compliance pump system is strongly correlated with previously determined lymph flux rates in a three species test. Our data suggest there may be a relationship between greater elaboration of the GM/AC and SAC system and terrestriality among the Anura.

PM10 source apportionment in a Swiss Alpine valley impacted by highway traffic - Regina E. Ducret-Stich; Ming-Yi Tsai; Devraj Thimmaiah; Nino Künzli; Philip K. Hopke; Harish C. Phuleria (Environmental Science and Pollution Research, 2013)

In silico drug metabolism and pharmacokinetic profiles of natural products from medicinal plants in the Congo basin - Fidele Ntie-Kang; Lydia L Lifongo; James A Mbah; Luc C Owono Owono; Eugene Megnassan; Luc Meva’a Mbaze; Philip N Judson; Wolfgang Sippl; Simon M N Efange (In Silico Pharmacology, 2013)
Purpose Drug metabolism and pharmacokinetics (DMPK) assessment has come to occupy a place of interest during the early stages of drug discovery today. The use of computer modelling to predict the DMPK and toxicity properties of a natural product library derived from medicinal plants from Central Africa (named ConMedNP). Material from some of the plant sources are currently employed in African Traditional Medicine. Methods Computer-based methods are slowly gaining ground in this area and are often used as preliminary criteria for the elimination of compounds likely to present uninteresting pharmacokinetic profiles and unacceptable levels of toxicity from the list of potential drug candidates, hence cutting down the cost of discovery of a drug. In the present study, we present an in silico assessment of the DMPK and toxicity profile of a natural product library containing ~3,200 compounds, derived from 379 species of medicinal plants from 10 countries in the Congo Basin forests and savannas, which have been published in the literature. In this analysis, we have used 46 computed physico-chemical properties or molecular descriptors to predict the absorption, distribution, metabolism and elimination and toxicity (ADMET) of the compounds. Results This survey demonstrated that about 45% of the compounds within the ConMedNP compound library are compliant, having properties which fall within the range of ADME properties of 95% of currently known drugs, while about 69% of the compounds have ≤ 2 violations. Moreover, about 73% of the compounds within the corresponding “drug-like” subset showed compliance. Conclusions In addition to the verified levels of “drug-likeness”, diversity and the wide range of measured biological activities, the compounds from medicinal plants in Central Africa show interesting DMPK profiles and hence could represent an important starting point for hit/lead discovery.

Efficacy of Strychnos spinosa (Lam.) and Solanum incanum L. aqueous fruit extracts against cattle ticks - James Madzimure; Emmanuel T. Nyahangare; Humphrey Hamudikuwanda; Thokozani Hove; Steve R. Belmain; Philip C. Stevenson; Brighton M. Mvumi (Tropical Animal Health and Production, 2013)

Characterising the nature of household vulnerability to climate variability: empirical evidence from two regions of Ghana - Philip Antwi-Agyei; Andrew J. Dougill; Evan D. G. Fraser; Lindsay C. Stringer (Environment, Development and Sustainability, 2013)

Topographic regulation of neuronal intermediate filaments by phosphorylation, role of peptidyl-prolyl isomerase 1: significance in neurodegeneration - B. K. Binukumar; Varsha Shukla; Niranjana D. Amin; Preethi Reddy; Suzanne Skuntz; Philip Grant; Harish C. Pant (Histochemistry and Cell Biology, 2013)

The potential feasibility for soil improvement, based on the properties of biochars pyrolyzed from different feedstocks - Zhongmin Dai; Jun Meng; Niaz Muhammad; Xingmei Liu; Haizhen Wang; Yan He; Philip C. Brookes; Jianming Xu (Journal of Soils and Sediments, 2013)

US EPA particulate matter research centers: summary of research results for 2005–2011 - Patrick N. Breysse; Ralph J. Delfino; Francesca Dominici; Alison C. P. Elder; Mark W. Frampton; John R. Froines; Alison S. Geyh; John J. Godleski; Diane R. Gold; Philip K. Hopke; Petros Koutrakis; Ning Li; et al. (Air Quality, Atmosphere & Health, 2013)

New Direct Compression Excipient from Tigernut Starch: Physicochemical and Functional Properties - Philip F. Builders; Patricia A. Anwunobi; Chukwuemeka C. Mbah; Michael U. Adikwu (AAPS PharmSciTech, 2013)

Fishing groupers towards extinction: a global assessment of threats and extinction risks in a billion dollar fishery - Yvonne Sadovy de Mitcheson; Matthew T Craig; Athila A Bertoncini; Kent E Carpenter; William W L Cheung; John H Choat; Andrew S Cornish; Sean T Fennessy; Beatrice P Ferreira; Philip C Heemstra; Min Liu; Robert F Myers; et al. (Fish and Fisheries, 2013)
Groupers are a valuable fishery resource of reef ecosystems and are among those species most vulnerable to fishing pressure because of life history characteristics including longevity, late sexual maturation and aggregation spawning. Despite their economic importance, few grouper fisheries are regularly monitored or managed at the species level, and many are reported to be undergoing declines. To identify major threats to groupers, the International Union for Conservation of Nature (IUCN) Red List criteria were applied to all 163 species. Red List assessments show that 20 species (12%) risk extinction if current trends continue, and an additional 22 species (13%) are considered to be Near Threatened. The Caribbean Sea, coastal Brazil and Southeast Asia contain a disproportionate number of Threatened species, while numerous poorly documented and Near Threatened species occur in many regions. In all, 30% of all species are considered to be Data Deficient. Given that the major threat is overfishing, accompanied by a general absence and/or poor application of fishery management, the prognosis for restoration and successful conservation of Threatened species is poor. We believe that few refuges remain for recovery and that key biological processes (e.g. spawning aggregations) continue to be compromised by uncontrolled fishing. Mariculture, through hatchery‐rearing, increases production of a few species and contributes to satisfying high market demand, but many such operations depend heavily on wild‐caught juveniles with resultant growth and recruitment overfishing. Better management of fishing and other conservation efforts are urgently needed, and we provide examples of possible actions and constraints.

Remote climate forcing of decadal‐scale regime shifts in Northwest Atlantic shelf ecosystems - Charles H. Greene; Erin Meyer-Gutbrod; Bruce C. Monger; Louise P. McGarry; Andrew J. Pershing; Igor M. Belkin; Paula S. Fratantoni; David G. Mountain; Robert S. Pickart; Andrey Proshutinsky; Rubao Ji; James J. Bisagni; et al. (Limnology and Oceanography, 2013)
Decadal‐scale regime shifts in Northwest Atlantic shelf ecosystems can be remotely forced by climate‐associated atmosphere‐ocean interactions in the North Atlantic and Arctic Ocean Basins. This remote climate forcing is mediated primarily by basin‐ and hemispheric‐scale changes in ocean circulation. We review and synthesize results from process‐oriented field studies and retrospective analyses of time‐series data to document the linkages between climate, ocean circulation, and ecosystem dynamics. Bottom‐up forcing associated with climate plays a prominent role in the dynamics of these ecosystems, comparable in importance to that of top‐down forcing associated with commercial fishing. A broad perspective, one encompassing the effects of basin‐ and hemispheric‐scale climate processes on marine ecosystems, will be critical to the sustainable management of marine living resources in the Northwest Atlantic.

Amazonian forest loss and the long reach of China’s influence - Philip M. Fearnside; Adriano M. R. Figueiredo; Sandra C. M. Bonjour (Environment, Development and Sustainability, 2013)

A Strategy for Prioritizing Threats and Recovery Actions for At-Risk Species - Catherine R. Darst; Philip J. Murphy; Nathan W. Strout; Steven P. Campbell; Kimberleigh J. Field; Linda Allison; Roy C. Averill-Murray (Environmental Management, 2013)

Japanese barberry seed predation by Rhagoletis meigenii fruit flies harboring Wolbachia endosymbionts - Vanessa C. Coats; Philip A. Stack; Mary E. Rumpho (Symbiosis, 2013)

Marked host specificity and lack of phylogeographic population structure of Campylobacter jejuni in wild birds - Petra Griekspoor; Frances M. Colles; Noel D. McCarthy; Philip M. Hansbro; Chris Ashhurst‐Smith; Björn Olsen; Dennis Hasselquist; Martin C. J. Maiden; Jonas Waldenström (Molecular Ecology, 2013)
Zoonotic pathogens often infect several animal species, and gene flow among populations infecting different host species may affect the biological traits of the pathogen including host specificity, transmissibility and virulence. The bacterium Campylobacter jejuni is a widespread zoonotic multihost pathogen, which frequently causes gastroenteritis in humans. Poultry products are important transmission vehicles to humans, but the bacterium is common in other domestic and wild animals, particularly birds, which are a potential infection source. Population genetic studies of C. jejuni have mainly investigated isolates from humans and domestic animals, so to assess C. jejuni population structure more broadly and investigate host adaptation, 928 wild bird isolates from Europe and Australia were genotyped by multilocus sequencing and compared to the genotypes recovered from 1366 domestic animal and human isolates. Campylobacter jejuni populations from different wild bird species were distinct from each other and from those from domestic animals and humans, and the host species of wild bird was the major determinant of C. jejuni genotype, while geographic origin was of little importance. By comparison, C. jejuni differentiation was restricted between more phylogenetically diverse farm animals, indicating that domesticated animals may represent a novel niche for C. jejuni and thereby driving the evolution of those bacteria as they exploit this niche. Human disease is dominated by isolates from this novel domesticated animal niche.

Agonist high- and low-affinity states of dopamine D2 receptors: methods of detection and clinical implications - Jan-Peter van Wieringen; Jan Booij; Vladimir Shalgunov; Philip Elsinga; Martin C. Michel (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Sex-specific differences in natriuretic peptide and nitric oxide synthase expression in ANP gene-disrupted mice - Philip G. Wong; David W. J. Armstrong; M. Yat Tse; Emily P. A. Brander; Stephen C. Pang (Molecular and Cellular Biochemistry, 2013)

Progressive genome‐wide introgression in agricultural Campylobacter coli - Samuel K. Sheppard; Xavier Didelot; Keith A. Jolley; Aaron E. Darling; Ben Pascoe; Guillaume Meric; David J. Kelly; Alison Cody; Frances M. Colles; Norval J. C. Strachan; Iain D. Ogden; Ken Forbes; et al. (Molecular Ecology, 2013)
Hybridization between distantly related organisms can facilitate rapid adaptation to novel environments, but is potentially constrained by epistatic fitness interactions among cell components. The zoonotic pathogens C ampylobacter coli and C . jejuni differ from each other by around 15% at the nucleotide level, corresponding to an average of nearly 40 amino acids per protein‐coding gene. Using whole genome sequencing, we show that a single C. coli lineage, which has successfully colonized an agricultural niche, has been progressively accumulating C. jejuni DNA . Members of this lineage belong to two groups, the ST ‐828 and ST ‐1150 clonal complexes. The ST ‐1150 complex is less frequently isolated and has undergone a substantially greater amount of introgression leading to replacement of up to 23% of the C. coli core genome as well as import of novel DNA . By contrast, the more commonly isolated ST ‐828 complex bacteria have 10–11% introgressed DNA , and C. jejuni and nonagricultural C. coli lineages each have C. coli that colonize agriculture, and consequently cause most human disease, have hybrid origin, but this cross‐species exchange has so far not had a substantial impact on the gene pools of either C. jejuni or nonagricultural C. coli . These findings also indicate remarkable interchangeability of basic cellular machinery after a prolonged period of independent evolution.

Cardiac magnetic resonance imaging of rapid VCAM-1 up-regulation in myocardial ischemia–reperfusion injury - Stuart M. Grieve; Jacob Lønborg; Jawad Mazhar; Timothy C. Tan; Edwin Ho; Chia-Chi Liu; William Lay; Anthony J. Gill; Philip Kuchel; Ravinay Bhindi; Gemma A. Figtree (European Biophysics Journal, 2013)

Using variance components to estimate power in a hierarchically nested sampling design - Maria C. Dzul; Philip M. Dixon; Michael C. Quist; Stephen J. Dinsmore; Michael R. Bower; Kevin P. Wilson; D. Bailey Gaines (Environmental Monitoring and Assessment, 2013)

Recent Shrub Proliferation in the Mackenzie Delta Uplands and Microclimatic Implications - Trevor C. Lantz; Philip Marsh; Steven V. Kokelj (Ecosystems, 2013)

Analysis of the subcomponents and cortical terminations of the perisylvian superior longitudinal fasciculus: a fiber dissection and DTI tractography study - Juan Martino; Philip C. De Witt Hamer; Mitchel S. Berger; Michael T. Lawton; Christine M. Arnold; Enrique Marco de Lucas; Hugues Duffau (Brain Structure and Function, 2013)

How do enzymes catalysing soil nitrogen transformations respond to changing temperatures? - Fiona C. Fraser; Paul D. Hallett; Philip A. Wookey; Iain P. Hartley; David W. Hopkins (Biology and Fertility of Soils, 2013)

Thermal and hygric physiology of Australian burrowing mygalomorph spiders (Aganippe spp.) - Leanda D. Mason; Sean Tomlinson; Philip C. Withers; Barbara Y. Main (Journal of Comparative Physiology B, 2013)

Estimates of the North Atlantic Oscillation back to 1692 using a Paris–London westerly index - Richard C. Cornes; Philip D. Jones; Keith R. Briffa; Timothy J. Osborn (International Journal of Climatology, 2013)
A westerly index for Europe is developed back to 1692 using newly recovered and corrected Mean Sea‐level Pressure (MSLP) data from London and Paris. The index is compared against various instrumental and proxy indices of the North Atlantic Oscillation (NAO). In the winter, the Paris‐London index depicts a spatial pattern of atmospheric circulation that is bi‐modal, with centres of action that are shifted eastwards compared to the NAO. Owing to asymmetry in the NAO the Paris‐London index provides a good depiction of positive NAO conditions as well as extreme negative phases of the NAO that arise from reversals of the pressure centres, but less extreme negative NAO conditions are associated with westerly index values approaching zero. The merit in using the Paris‐London index lies with its consistency over time as a measure of westerly wind flow, which may not be the case with other proxy‐based indices. In the summer, the Paris‐London index bears a close relationship to the reconstructed high‐summer NAO series of Folland et al. ( 2009 ) as well as the summer Luterbacher et al. ( 1999 ) NAO reconstruction. An important finding is that the summer NAO was highly variable during the early nineteenth century but was predominately positive on the decadal time scale during that period. Since circa 1970 the summer index has mostly been negative, indicating reduced westerlies and increased blocking conditions that are exceptional in the context of the last 250 years. Copyright © 2012 Royal Meteorological Society

An interlaboratory comparison of sediment elutriate preparation and toxicity test methods - Herman J. Haring; Mark E. Smith; James M. Lazorchak; Philip A. Crocker; Abel Euresti; Karen Blocksom; Melissa C. Wratschko; Michael C. Schaub (Environmental Monitoring and Assessment, 2012)

Maspin: molecular mechanisms and therapeutic implications - Thomas M. Bodenstine; Richard E. B. Seftor; Zhila Khalkhali-Ellis; Elisabeth A. Seftor; Philip A. Pemberton; Mary J. C. Hendrix (Cancer and Metastasis Reviews, 2012)

A composite score for executive functioning, validated in Alzheimer’s Disease Neuroimaging Initiative (ADNI) participants with baseline mild cognitive impairment - Laura E. Gibbons; Adam C. Carle; R. Scott Mackin; Danielle Harvey; Shubhabrata Mukherjee; Philip Insel; S. McKay Curtis; Dan Mungas; Paul K. Crane (Brain Imaging and Behavior, 2012)

Comparing Fisher Interviews, Logbooks, and Catch Landings Estimates of Extraction Rates in a Small-Scale Fishery - Kerrie P. O’Donnell; Philip P. Molloy; Amanda C. J. Vincent (Coastal Management, 2012)

7-Nitro-4-(phenylthio)benzofurazan is a potent generator of superoxide and hydrogen peroxide - Eric V. Patridge; Emma S. E. Eriksson; Philip G. Penketh; Raymond P. Baumann; Rui Zhu; Krishnamurthy Shyam; Leif A. Eriksson; Alan C. Sartorelli (Archives of Toxicology, 2012)

Ocean acidification weakens the structural integrity of coralline algae - Federica Ragazzola; Laura C. Foster; Armin Form; Philip S.L. Anderson; Thor H. Hansteen; Jan Fietzke (Global Change Biology, 2012)
The uptake of anthropogenic emission of carbon dioxide is resulting in a lowering of the carbonate saturation state and a drop in ocean pH. Understanding how marine calcifying organisms such as coralline algae may acclimatize to ocean acidification is important to understand their survival over the coming century. We present the first long‐term perturbation experiment on the cold‐water coralline algae, which are important marine calcifiers in the benthic ecosystems particularly at the higher latitudes. Lithothamnion glaciale, after three months incubation, continued to calcify even in undersaturated conditions with a significant trend towards lower growth rates with increasing p CO 2 . However, the major changes in the ultra‐structure occur by 589 μatm (i.e. in saturated waters). Finite element models of the algae grown at these heightened levels show an increase in the total strain energy of nearly an order of magnitude and an uneven distribution of the stress inside the skeleton when subjected to similar loads as algae grown at ambient levels. This weakening of the structure is likely to reduce the ability of the alga to resist boring by predators and wave energy with severe consequences to the benthic community structure in the immediate future (50 years).

Experimental litterfall manipulation drives large and rapid changes in soil carbon cycling in a wet tropical forest - Jonathan W. Leff; William R. Wieder; Philip G. Taylor; Alan R. Townsend; Diana R. Nemergut; A. Stuart Grandy; Cory C. Cleveland (Global Change Biology, 2012)
Global changes such as variations in plant net primary production are likely to drive shifts in leaf litterfall inputs to forest soils, but the effects of such changes on soil carbon ( C ) cycling and storage remain largely unknown, especially in C ‐rich tropical forest ecosystems. We initiated a leaf litterfall manipulation experiment in a tropical rain forest in C osta R ica to test the sensitivity of surface soil C pools and fluxes to different litter inputs. After only 2 years of treatment, doubling litterfall inputs increased surface soil C concentrations by 31%, removing litter from the forest floor drove a 26% reduction over the same time period, and these changes in soil C concentrations were associated with variations in dissolved organic matter fluxes, fine root biomass, microbial biomass, soil moisture, and nutrient fluxes. However, the litter manipulations had only small effects on soil organic C ( SOC ) chemistry, suggesting that changes in C cycling, nutrient cycling, and microbial processes in response to litter manipulation reflect shifts in the quantity rather than quality of SOC . The manipulation also affected soil CO 2 fluxes; the relative decline in CO 2 production was greater in the litter removal plots (−22%) than the increase in the litter addition plots (+15%). Our analysis showed that variations in CO 2 fluxes were strongly correlated with microbial biomass pools, soil C and nitrogen ( N ) pools, soil inorganic P fluxes, dissolved organic C fluxes, and fine root biomass. Together, our data suggest that shifts in leaf litter inputs in response to localized human disturbances and global environmental change could have rapid and important consequences for belowground C storage and fluxes in tropical rain forests, and highlight differences between tropical and temperate ecosystems, where belowground C cycling responses to changes in litterfall are generally slower and more subtle.

A Review of the Ecology, Genomics, and Stress Response of Listeria innocua and Listeria monocytogenes - Sara R. Milillo; Erik C. Friedly; Joshua C. Saldivar; Arunachalam Muthaiyan; Corliss O'bryan; Philip G. Crandall; Michael G. Johnson; Steven C. Ricke (Critical Reviews in Food Science and Nutrition, 2012)

Effect of nutritional interventions and resistance exercise on aging muscle mass and strength - Darren G. Candow; Scott C. Forbes; Jonathan P. Little; Stephen M. Cornish; Craig Pinkoski; Philip D. Chilibeck (Biogerontology, 2012)

Social competition masculinizes the communication signals of female electric fish - Sat Gavasa; Ana C. Silva; Emmanuel Gonzalez; Juan Molina; Philip K. Stoddard (Behavioral Ecology and Sociobiology, 2012)

Discrete phosphorylated retinoblastoma protein isoform expression in mouse tooth development - Weibo Zhang; Betsy Vazquez; Viktoria Andreeva; Daisy Spear; Elizabeth Kong; Philip W. Hinds; Pamela C. Yelick (Journal of Molecular Histology, 2012)

Microbial biodiversity in a Malaysian oil field and a systematic comparison with oil reservoirs worldwide - Dongmei Li; David J. Midgley; Jason P. Ross; Yalchin Oytam; Guy C. J. Abell; Herbert Volk; Wan Ata Wan Daud; Philip Hendry (Archives of Microbiology, 2012)

Ecosystem Impacts of Geoengineering: A Review for Developing a Science Plan - Lynn M. Russell; Philip J. Rasch; Georgina M. Mace; Robert B. Jackson; John Shepherd; Peter Liss; Margaret Leinen; David Schimel; Naomi E. Vaughan; Anthony C. Janetos; Philip W. Boyd; Richard J. Norby; et al. (Ambio, 2012)

Cost-benefit analysis for intentional plant introductions under uncertainty - Hiroyuki Yokomizo; Hugh P. Possingham; Philip E. Hulme; Anthony C. Grice; Yvonne M. Buckley (Biological Invasions, 2012)

Soil-mediated local adaptation alters seedling survival and performance - David Solance Smith; Jennifer A. Schweitzer; Philip Turk; Joseph K. Bailey; Stephen C. Hart; Stephen M. Shuster; Thomas G. Whitham (Plant and Soil, 2012)

Carbon dynamics in a 60 year fallowed loamy-sand soil compared to that in a 60 year permanent arable or permanent grassland UK soil - Yuping Wu; Sarah Kemmitt; Rodger P. White; Jianming Xu; Philip C. Brookes (Plant and Soil, 2012)

Empirical Methods for Detecting Regional Trends and Other Spatial Expressions in Antrim Shale Gas Productivity, with Implications for Improving Resource Projections Using Local Nonparametric Estimation Techniques - Timothy C. Coburn; Philip A. Freeman; Emil D. Attanasi (Natural Resources Research, 2012)

DNA damage in cichlids from an oil production facility in Guatemala - Christopher W. Theodorakis; John W. Bickham; Kirby C. Donnelly; Thomas J. McDonald; Philip W. Willink (Ecotoxicology, 2012)

Global assessment of experimental climate warming on tundra vegetation: heterogeneity over space and time - Sarah C. Elmendorf; Gregory H. R. Henry; Robert D. Hollister; Robert G. Björk; Anne D. Bjorkman; Terry V. Callaghan; Laura Siegwart Collier; Elisabeth J. Cooper; Johannes H. C. Cornelissen; Thomas A. Day; Anna Maria Fosaa; William A. Gould; et al. (Ecology Letters, 2012)
Ecology Letters (2011) Abstract Understanding the sensitivity of tundra vegetation to climate warming is critical to forecasting future biodiversity and vegetation feedbacks to climate. In situ warming experiments accelerate climate change on a small scale to forecast responses of local plant communities. Limitations of this approach include the apparent site‐specificity of results and uncertainty about the power of short‐term studies to anticipate longer term change. We address these issues with a synthesis of 61 experimental warming studies, of up to 20 years duration, in tundra sites worldwide. The response of plant groups to warming often differed with ambient summer temperature, soil moisture and experimental duration. Shrubs increased with warming only where ambient temperature was high, whereas graminoids increased primarily in the coldest study sites. Linear increases in effect size over time were frequently observed. There was little indication of saturating or accelerating effects, as would be predicted if negative or positive vegetation feedbacks were common. These results indicate that tundra vegetation exhibits strong regional variation in response to warming, and that in vulnerable regions, cumulative effects of long‐term warming on tundra vegetation – and associated ecosystem consequences – have the potential to be much greater than we have observed to date.

Ketamine perturbs perception of the flow of time in healthy volunteers - Jennifer T Coull; Hannah Morgan; Victoria C Cambridge; James W Moore; Francesco Giorlando; Ram Adapa; Philip R. Corlett; Paul C Fletcher (Psychopharmacology, 2011)

An Open Source Multivariate Framework for n-Tissue Segmentation with Evaluation on Public Data - Brian B. Avants; Nicholas J. Tustison; Jue Wu; Philip A. Cook; James C. Gee (Neuroinformatics, 2011)

Aspirin and NSAID use and lung cancer risk: a pooled analysis in the International Lung Cancer Consortium (ILCCO) - Valerie A. McCormack; Rayjean J. Hung; Darren R. Brenner; Heike Bickeböller; Albert Rosenberger; Joshua E. Muscat; Philip Lazarus; Anne Tjønneland; Søren Friis; David C. Christiani; Eun-mi Chun; Loic Le Marchand; et al. (Cancer Causes & Control, 2011)

Update on the Relationship of Fish Intake with Prostate, Breast, and Colorectal Cancers - Aleix Sala-Vila; Philip C. Calder (Critical Reviews in Food Science and Nutrition, 2011)

No evidence for widespread bird declines in protected South American forests - Philip C Stouffer; Kristina L. Cockle; Alexandre Aleixo; Juan I. Areta; Juan Mazar Barnett; Alejandro Bodrati; Carlos Daniel Cadena; Adrián S. Di Giacomo; Sebastian K. Herzog; Peter Hosner; Erik I. Johnson; Luciano N. Naka; et al. (Climatic Change, 2011)

Cardenolides from Gomphocarpus sinaicus and Pergularia tomentosa (Apocynaceae: Asclepiadoideae) deter the feeding of Spodoptera littoralis - Paul W. C. Green; Nigel C. Veitch; Philip C. Stevenson; Monique S. J. Simmonds (Arthropod-Plant Interactions, 2011)

Intrageneric variation in antipredator responses of coral reef fishes affected by ocean acidification: implications for climate change projections on marine communities - MAUD C. O. FERRARI; DANIELLE L. DIXSON; PHILIP L. MUNDAY; MARK I. McCORMICK; MARK G. MEEKAN; ANDREW SIH; DOUGLAS P. CHIVERS (Global Change Biology, 2011)
Our planet is experiencing an increase in the concentration of atmospheric carbon dioxide (CO 2 ) unprecedented in the past 800 000 years. About 30% of excess atmospheric CO 2 is absorbed by the oceans, thus increasing the concentration of carbonic acid and reducing the ocean's pH. Species able to survive the physiological stress imposed by ocean acidification may still suffer strong indirect negative consequences. Comparing the tolerance of different species to dissolved CO 2 is a necessary first step towards predicting the ecological impacts of rising CO 2 levels on marine communities. While it is intuitive that not all aquatic species will be affected the same way by CO 2 , one could predict that closely related species, sharing similar life histories and ecology, may show similar tolerance levels to CO 2 . Our ability to create functional groups of species according to their CO 2 tolerance may be crucial in our ability to predict community change in the future. Here, we tested the effects of CO 2 exposure on the antipredator responses of four damselfish species ( Pomacentrus chrysurus, Pomacentrus moluccensis, Pomacentrus amboinensis and Pomacentrus nagasakiensis ). Although being sympatric and sharing the same ecology and life history, the four congeneric species showed striking and unexpected variation in CO 2 tolerance, with CO 2 ‐induced loss of response to predation risk ranging from 30% to 95%. Using P. chrysurus as a model species, we further tested if these behavioural differences translated into differential ability to survive predators under natural conditions. Our results indicate that P. chrysurus larvae raised under CO 2 levels predicted by 2070 and 2100 showed decreased antipredator responses to risk, leading to a five‐ to sevenfold increase in predation‐related mortality in the first few hours of settlement. Examining ocean acidification, along with other environmental variables, will be a critical step in further evaluating ecological responses to predicted climatic change.

Relationships among net primary productivity, nutrients and climate in tropical rain forest: a pan‐tropical analysis - Cory C. Cleveland; Alan R. Townsend; Philip Taylor; Silvia Alvarez‐Clare; Mercedes M. C. Bustamante; George Chuyong; Solomon Z. Dobrowski; Pauline Grierson; Kyle E. Harms; Benjamin Z. Houlton; Alison Marklein; William Parton; et al. (Ecology Letters, 2011)
Ecology Letters (2011) 14 : 939–947 Abstract Tropical rain forests play a dominant role in global biosphere‐atmosphere CO 2 exchange. Although climate and nutrient availability regulate net primary production (NPP) and decomposition in all terrestrial ecosystems, the nature and extent of such controls in tropical forests remain poorly resolved. We conducted a meta‐analysis of carbon‐nutrient‐climate relationships in 113 sites across the tropical forest biome. Our analyses showed that mean annual temperature was the strongest predictor of aboveground NPP (ANPP) across all tropical forests, but this relationship was driven by distinct temperature differences between upland and lowland forests. Within lowland forests ( k ), soil N and soil respiration were all directly related with total surface (0–10 cm) soil P concentrations. Our analysis provides some evidence that P availability regulates NPP and other ecosystem processes in lowland tropical forests, but more importantly, underscores the need for a series of large‐scale nutrient manipulations – especially in lowland forests – to elucidate the most important nutrient interactions and controls.

Tree population dynamics of three altitudinal vegetation communities on Mount Cameroon (1989–2004) - Philip F. Forboseh; Terry C. H. Sunderland; James A. Comiskey; Michael Balinga (Journal of Mountain Science, 2011)

Applications of phytochemical and in vitro techniques for reducing over-harvesting of medicinal and pesticidal plants and generating income for the rural poor - Viswambharan Sarasan; Geoffrey C. Kite; Gudeta W. Sileshi; Philip C. Stevenson (Plant Cell Reports, 2011)

Copper, Zinc-Superoxide Dismutase from Clinically Isolated Escherichia coli: Cloning, Analysis of sodC and Its Possible Role in Pathogenicity - M. K. Sanjay; S. M. Srideshikan; V. L. Vanishree; M. S. Usha; A. Philip Raj; S. M. Gaddad; C. T. Shivannavar (Indian Journal of Microbiology, 2011)

Effects of experiment start time and duration on measurement of standard physiological variables - Amanda J. Page; Christine E. Cooper; Philip C. Withers (Journal of Comparative Physiology B, 2011)

ICOADS Release 2.5: extensions and enhancements to the surface marine meteorological archive - Scott D. Woodruff; Steven J. Worley; Sandra J. Lubker; Zaihua Ji; J. Eric Freeman; David I. Berry; Philip Brohan; Elizabeth C. Kent; Richard W. Reynolds; Shawn R. Smith; Clive Wilkinson (International Journal of Climatology, 2011)
Release 2.5 of the International Comprehensive Ocean‐Atmosphere Data Set (ICOADS) is a major update (covering 1662–2007) of the world's most extensive surface marine meteorological data collection. Building on extensive national and international partnerships, many new and improved contributing datasets have been processed into a uniform format and combined with the previous Release 2.4. The new data range from early non‐instrumental ship observations to measurements initiated in the twentieth century from buoys and other automated platform types. Improvements to existing data include replacing preliminary Global Telecommunication System (GTS) receipts with more reliable, delayed mode reports for post‐1997 data, and in the processing and quality control (QC) of humidity observations. Over the entire period of record, spatial and temporal coverage has been enriched and data and metadata quality has been improved. Along with the observations, now updated monthly in near real time, Release 2.5 includes quality‐controlled monthly summary products for 2° latitude × 2° longitude (since 1800) and 1° × 1° boxes (since 1960), together with multiple options for access to the data and products. The measured and estimated data in Release 2.5 are subject to many technical changes, multiple archive sources, and historical events throughout the more than three‐century record. Some of these data characteristics are highlighted, including known unresolved errors and inhomogeneities, which may impact climate and other research applications. Anticipated future directions for ICOADS aim to continue adding scientific value to the observations, products, and metadata, as well as strengthen the cooperative enterprise through expanded linkages to international initiatives and organisations. Copyright © 2010 Royal Meteorological Society

Sensitivity of discharge and flood frequency to twenty-first century and late Holocene changes in climate and land use (River Meuse, northwest Europe) - Philip J. Ward; Hans Renssen; Jeroen C. J. H. Aerts; Peter H. Verburg (Climatic Change, 2011)

Influence of indomethacin on the ventilatory and cerebrovascular responsiveness to hypoxia - Jui-Lin Fan; Keith R. Burgess; Kate N. Thomas; Karen C. Peebles; Samuel J. E. Lucas; Rebekah A. I. Lucas; James D. Cotter; Philip N. Ainslie (European Journal of Applied Physiology, 2011)

Macroscale factors affecting diatom abundance: a synergistic use of Continuous Plankton Recorder and satellite remote sensing data - Dionysios E. Raitsos; Samantha J. Lavender; Christos D. Maravelias; John Haralabous; Abigail McQuatters-Gollop; Martin Edwards; Philip C. Reid (International Journal of Remote Sensing, 2011)

The logistics and mechanics of conducting tracer injection experiments in urban streams - Robert J. Ryan; Philip C. Larson; Claire Welty (Urban Ecosystems, 2011)

The impact of childhood abuse and recent stress on serum brain-derived neurotrophic factor and the moderating role of BDNF Val66Met - Bernet M. Elzinga; Marc L. Molendijk; Richard C. Oude Voshaar; Boudewijn A. A. Bus; Jos Prickaerts; Philip Spinhoven; Brenda J. W. H. Penninx (Psychopharmacology, 2011)

Acaricidal efficacy against cattle ticks and acute oral toxicity of Lippia javanica (Burm F.) Spreng - James Madzimure; Emmanuel T. Nyahangare; Humphrey Hamudikuwanda; Thokozani Hove; Philip C. Stevenson; Steve R. Belmain; Brighton M. Mvumi (Tropical Animal Health and Production, 2011)

Impact of soil tillage on the robustness of the genetic component of variation in phosphorus (P) use efficiency in barley (Hordeum vulgare L.) - Timothy S. George; Lawrie K. Brown; Adrian C. Newton; Paul D. Hallett; Ben Hua Sun; William T. B. Thomas; Philip J. White (Plant and Soil, 2011)

Farming for pests? Local and landscape-scale effects of grassland management on rabbit densities - Silviu O. Petrovan; Isabel C. Barrio; Alastair I. Ward; Philip M. Wheeler (European Journal of Wildlife Research, 2011)

High efficiency plastid transformation in potato and regulation of transgene expression in leaves and tubers by alternative 5′ and 3′ regulatory sequences - Vladimir T. Valkov; Daniela Gargano; Carmela Manna; Gelsomina Formisano; Philip J. Dix; John C. Gray; Nunzia Scotti; Teodoro Cardi (Transgenic Research, 2011)

Arginine in Membranes: The Connection Between Molecular Dynamics Simulations and Translocon-Mediated Insertion Experiments - Eric V. Schow; J. Alfredo Freites; Philip C. Myint; Andreas Bernsel; Gunnar von Heijne; Stephen H. White; Douglas J. Tobias (The Journal of Membrane Biology, 2011)

The evolutionary consequences of oxygenic photosynthesis: a body size perspective - Jonathan L. Payne; Craig R. McClain; Alison G. Boyer; James H. Brown; Seth Finnegan; Michał Kowalewski; Richard A. Krause; S. Kathleen Lyons; Daniel W. McShea; Philip M. Novack-Gottshall; Felisa A. Smith; Paula Spaeth; et al. (Photosynthesis Research, 2011)

Modulation of the response to a somatosensory stimulation of the hand during the observation of manual actions - Julien I. A. Voisin; Erika C. Rodrigues; Sébastien Hétu; Philip L. Jackson; Claudia D. Vargas; Francine Malouin; C. Elaine Chapman; Catherine Mercier (Experimental Brain Research, 2011)

Functional alpha-1B adrenergic receptors on human epicardial coronary artery endothelial cells - Brian C. Jensen; Philip M. Swigart; Megan D. Montgomery; Paul C. Simpson (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Understanding Recreational Boater Attitudes to Zoning in a Proposed Marine Protected Area - Darcy L. Gray; Rosaline R. Canessa; Rick B. Rollins; Philip Dearden; C. Peter Keller (Coastal Management, 2010)

Plant genotypic diversity does not beget root-fungal species diversity - David Johnson; Ian C. Anderson; Alison Williams; Raj Whitlock; J. Philip Grime (Plant and Soil, 2010)

Effects of uridine diphosphate glucuronosyltransferase 2B7 and 1A7 pharmacogenomics and patient clinical parameters on steady-state mycophenolic acid pharmacokinetics in glomerulonephritis - Melanie S. Joy; Tammy Boyette; Yichun Hu; Jinzhao Wang; Mary La; Susan L. Hogan; Paul W. Stewart; Ronald J. Falk; Mary Anne Dooley; Philip C. Smith (European Journal of Clinical Pharmacology, 2010)

Public Internet‐connected cameras used as a cross‐continental ground‐based plant phenology monitoring system - ERIC A. GRAHAM; ERIN C. RIORDAN; ERIC M. YUEN; DEBORAH ESTRIN; PHILIP W. RUNDEL (Global Change Biology, 2010)
Plant phenology is highly sensitive to changes in environmental conditions and can vary widely across landscapes. Current observation methods are either manual for small‐scale, high precision measurements or by satellite remote sensing for large‐scale, low spatial resolution measurement. The development of inexpensive approaches is necessary to advance large scale, high precision phenology monitoring. The use of publicly available, Internet‐connected cameras, often associated with airports, national parks, and roadway conditions, for detecting and monitoring plant phenology at a continental scale can augment existing ground and satellite‐based methodologies. We collected twice‐daily images from over 1100 georeferenced public cameras across North America from February 2008 to 2009. Using a test subset of these cameras, we compared modeled spring ‘green‐up’ with that from co‐occurring remote sensing products. Although varying image exposure and color correction introduced noise to camera measurements, we were able to correlate spring green‐up across North America with visual validation from images and detect a latitudinal trend. Public cameras had an equivalent or higher ability to detect spring compared with satellite‐based data for corresponding locations, with fewer numbers of poor quality days, shorter continuous bad data days, and significantly lower errors of spring estimates. Manual image segmentation into deciduous, evergreen, and understory vegetation allowed detection of spring and fall onset for multiple vegetation types. Additional advantages of a public camera‐based monitoring system include frequent image capture (subdaily) and the potential to detect quantitative responses to environmental changes in organisms, species, and communities. Public cameras represent a relatively untapped and freely available resource for supporting large‐scale ecological and environmental monitoring.

Leaf habit and woodiness regulate different leaf economy traits at a given nutrient supply - Jenny C. Ordoñez; Peter M. van Bodegom; Jan-Philip M. Witte; Ruud P. Bartholomeus; Han F. van Dobben; Rien Aerts (Ecology, 2010)
The large variation in the relationships between environmental factors and plant traits observed in natural communities exemplifies the alternative solutions that plants have developed in response to the same environmental limitations. Qualitative attributes, such as growth form, woodiness, and leaf habit can be used to approximate these alternative solutions. Here, we quantified the extent to which these attributes affect leaf trait values at a given resource supply level, using measured plant traits from 105 different species (254 observations) distributed across 50 sites in mesic to wet plant communities in The Netherlands. For each site, soil total N, soil total P, and water supply estimates were obtained by field measurements and modeling. Effects of growth forms, woodiness, and leaf habit on relations between leaf traits (SLA, specific leaf area; LNC, leaf nitrogen concentration; and LPC, leaf phosphorus concentration) vs. nutrient and water supply were quantified using maximum‐likelihood methods and Bonferroni post hoc tests. The qualitative attributes explained 8–23% of the variance within sites in leaf traits vs. soil fertility relationships, and therefore they can potentially be used to make better predictions of global patterns of leaf traits in relation to nutrient supply. However, at a given soil fertility, the strength of the effect of each qualitative attribute was not the same for all leaf traits. These differences may imply a differential regulation of the leaf economy traits at a given nutrient supply, in which SLA and LPC seem to be regulated in accordance to changes in plant size and architecture while LNC seems to be primarily regulated at the leaf level by factors related to leaf longevity.

Habitat preference and mobility of Polia bombycina: are non-tailored agri-environment schemes any good for a rare and localised species? - Thomas Merckx; Ruth E. Feber; Mark S. Parsons; Nigel A. D. Bourn; Martin C. Townsend; Philip Riordan; David W. Macdonald (Journal of Insect Conservation, 2010)

Variations in long term wind speed during different decades in Arabian Sea and Bay of Bengal - V. Sanil Kumar; C. Sajiv Philip (Journal of Earth System Science, 2010)

A probabilistic calibration of climate sensitivity and terrestrial carbon change in GENIE-1 - Philip B. Holden; N. R. Edwards; K. I. C. Oliver; T. M. Lenton; R. D. Wilkinson (Climate Dynamics, 2010)

Evergreen Agriculture: a robust approach to sustainable food security in Africa - Dennis Philip Garrity; Festus K. Akinnifesi; Oluyede C. Ajayi; Sileshi G. Weldesemayat; Jeremias G. Mowo; Antoine Kalinganire; Mahamane Larwanou; Jules Bayala (Food Security, 2010)

Inhibition of type 1 diabetes by upregulation of the circadian rhythm-related aryl hydrocarbon receptor nuclear translocator-like 2 - Chen-Xia He; Nicolas Prevot; Christian Boitard; Philip Avner; Ute C. Rogner (Immunogenetics, 2010)

The live-attenuated yellow fever vaccine 17D induces broad and potent T cell responses against several viral proteins in Indian rhesus macaques—implications for recombinant vaccine design - Philip A. Mudd; Shari M. Piaskowski; Patricia C. Costa Neves; Richard Rudersdorf; Holly L. Kolar; Christopher M. Eernisse; Kim L. Weisgrau; Marlon G. Veloso de Santana; Nancy A. Wilson; Myrna C. Bonaldo; Ricardo Galler; Eva G. Rakasz; et al. (Immunogenetics, 2010)

Incorporating Recreational Users into Marine Protected Area Planning: A Study of Recreational Boating in British Columbia, Canada - Darcy L. Gray; Rosaline Canessa; Rick Rollins; C. Peter Keller; Philip Dearden (Environmental Management, 2010)

Comparative physiology of Australian quolls (Dasyurus; Marsupialia) - Christine E. Cooper; Philip C. Withers (Journal of Comparative Physiology B, 2010)

Wildfire promotes dominance of invasive giant reed (Arundo donax) in riparian ecosystems - Gretchen C. Coffman; Richard F. Ambrose; Philip W. Rundel (Biological Invasions, 2010)

Ecological Relationships of Verticillium Wilt Suppression of Potato by Green Manures - James R. Davis; Oen C. Huisman; Dale O. Everson; Philip Nolte; Leland H. Sorensen; Ann T. Schneider (American Journal of Potato Research, 2010)

Selenium biofortification of high-yielding winter wheat (Triticum aestivum L.) by liquid or granular Se fertilisation - Martin R. Broadley; John Alcock; James Alford; Paul Cartwright; Ian Foot; Susan J. Fairweather-Tait; David J. Hart; Rachel Hurst; Peter Knott; Steve P. McGrath; Mark C. Meacham; Keith Norman; et al. (Plant and Soil, 2010)

Genetic structure and regulation of isoprene synthase in Poplar (Populus spp.) - Claudia E. Vickers; Malcolm Possell; C. Nicholas Hewitt; Philip M. Mullineaux (Plant Molecular Biology, 2010)

A call for standardized classification of metagenome projects - Natalia Ivanova; Susannah G. Tringe; Konstantinos Liolios; Wen‐Tso Liu; Norman Morrison; Philip Hugenholtz; Nikos C. Kyrpides (Environmental Microbiology, 2010)

Modeling shifts in the rate and pattern of subthalamopallidal network activity during deep brain stimulation - Philip J. Hahn; Cameron C. McIntyre (Journal of Computational Neuroscience, 2010)

Strategies for Enhancing the Effectiveness of Metagenomic-based Enzyme Discovery in Lignocellulolytic Microbial Communities - Kristen M. DeAngelis; John M. Gladden; Martin Allgaier; Patrik D’haeseleer; Julian L. Fortney; Amitha Reddy; Philip Hugenholtz; Steven W. Singer; Jean S. Vander Gheynst; Whendee L. Silver; Blake A. Simmons; Terry C. Hazen (BioEnergy Research, 2010)

Does tree harvesting in streamside management zones adversely affect stream turbidity?—preliminary observations from an Australian case study - Daniel G. Neary; Philip J. Smethurst; Brenda R. Baillie; Kevin C. Petrone; William E. Cotching; Craig C. Baillie (Journal of Soils and Sediments, 2010)

Identification of 28 novel mutations in the Bardet–Biedl syndrome genes: the burden of private mutations in an extensively heterogeneous disease - Jean Muller; C. Stoetzel; M. C. Vincent; C. C. Leitch; V. Laurier; J. M. Danse; S. Hellé; V. Marion; V. Bennouna-Greene; S. Vicaire; A. Megarbane; J. Kaplan; et al. (Human Genetics, 2010)

Skin cooling aids cerebrovascular function more effectively under severe than moderate heat stress - Rebekah A. I. Lucas; Philip N. Ainslie; Jui-Lin Fan; Luke C. Wilson; Kate N. Thomas; James D. Cotter (European Journal of Applied Physiology, 2010)

Effects of fosmidomycin on plant photosynthesis as measured by gas exchange and chlorophyll fluorescence - Malcolm Possell; Annette Ryan; Claudia E. Vickers; Philip M. Mullineaux; C. Nicholas Hewitt (Photosynthesis Research, 2010)

Comparison of Bulk Sediment and Sediment Elutriate Toxicity Testing Methods - Herman J. Haring; Mark E. Smith; James M. Lazorchak; Philip A. Crocker; Abel Euresti; Melissa C. Wratschko; Michael C. Schaub (Archives of Environmental Contamination and Toxicology, 2010)

The Suppression of Verticillium Wilt of Potato Using Corn as a Green Manure Crop - James R. Davis; O. C. Huisman; Dale O. Everson; Philip Nolte; L. H. Sorenson; A. T. Schneider (American Journal of Potato Research, 2010)

Something Old and Something New: An Update on the Amazing Repertoire of Bacteriocins Produced by Streptococcus salivarius - Philip A. Wescombe; Nicholas C. K. Heng; Jeremy P. Burton; John R. Tagg (Probiotics and Antimicrobial Proteins, 2010)

An Overview of APP Processing Enzymes and Products - Vivian W. Chow; Mark P. Mattson; Philip C. Wong; Marc Gleichmann (NeuroMolecular Medicine, 2010)

Inactivation of Baculovirus by Isoflavonoids on Chickpea (Cicer arietinum) Leaf Surfaces Reduces the Efficacy of Nucleopolyhedrovirus Against Helicoverpa armigera - Philip C. Stevenson; Reju F. D’Cunha; David Grzywacz (Journal of Chemical Ecology, 2010)

Formal ratification of the Quaternary System/Period and the Pleistocene Series/Epoch with a base at 2.58 Ma - Philip L. Gibbard; Martin J. Head; Michael J. C. Walker (Journal of Quaternary Science, 2010)
In June 2009, the Executive Committee of the International Union of Geological Sciences (IUGS) formally ratified a proposal by the International Commission on Stratigraphy to lower the base of the Quaternary System/Period to the Global Stratotype Section and Point (GSSP) of the Gelasian Stage/Age at Monte San Nicola, Sicily, Italy. The Gelasian until then had been the uppermost stage of the Pliocene Series/Epoch. The base of the Gelasian corresponds to Marine Isotope Stage 103, and has an astronomically tuned age of 2.58 Ma. A proposal that the base of the Pleistocene Series/Epoch be lowered to coincide with that of the Quaternary (the Gelasian GSSP) was also accepted by the IUGS Executive Committee. The GSSP at Vrica, Calabria, Italy, which had hitherto defined the basal boundary of both the Quaternary and the Pleistocene, remains available as the base of the Calabrian Stage/Age (now the second stage of the revised Pleistocene). In ratifying these proposals, the IUGS has acknowledged the distinctive qualities of the Quaternary by reaffirming it as a full system/period, correctly complied with the hierarchical requirements of the geological timescale by lowering the base of the Pleistocene to that of the Quaternary, and fully respected the historical and widespread current usage of both the terms ‘Quaternary’ and ‘Pleistocene’. Copyright © 2009 John Wiley & Sons, Ltd.

Phylogeography of the ground squirrel subgenus Xerospermophilus and assembly of the Mojave Desert biota - Kayce C. Bell; David J. Hafner; Philip Leitner; Marjorie D. Matocq (Journal of Biogeography, 2010)
Aim The Mohave ground squirrel ( Xerospermophilus mohavensis ) is one of a few endemic species of the Mojave Desert of south‐western North America. We describe phylogeographic patterns within this species and its sister taxon ( Xerospermophilus tereticaudus ) and test hypotheses concerning their biogeographical history using genetic signatures of stable versus expanding populations. We compare these patterns with those of other Mojave species to evaluate the role of vicariance in producing phylogeographic structure during the assembly of the Mojave Desert biota. Location The Mojave Desert and adjacent desert regions of south‐western North America. Methods Complete cytochrome b gene sequences of X. mohavensis (46 individuals representing 11 localities) and X. tereticaudus (38 individuals representing 14 localities) were analysed using Bayesian methods to infer phylogenetic relationships. Genetic signals of stable or expanding populations were examined based on the distribution of recent mutations and pairwise differences, as well as with a coalescent‐based approach. Results The two species are reciprocally monophyletic and may have diverged in response to the late Pliocene–early Pleistocene uplift of the Transverse Ranges and Mojave block. Little phylogeographic structure is evident within X. mohavensis , but there is a signature of northern expansion from a presumably full‐pluvial refugium in the Mojave River basin. Four geographic subgroups are evident within X. tereticaudus , and there is a signature of northern expansion from a presumably full‐pluvial refugium in the Sonoran coastal plains. Roughly congruent phylogeographic patterns are found within five arid‐adapted taxa, indicating a strong element of vicariance during the assembly of the generally transitional Mojave Desert biota. Main conclusions We present a preliminary model for the historical assembly of the Mojave Desert biota that indicates a strong vicariant element producing autochthonous lineages (including X. mohavensis ) that diverged during the major geological and climatic events of the last 5 Myr. Phylogeographic partitioning within the Mojave Desert underscores the necessity of immediate conservation measures for this unique and fragile arid ecosystem that is locked between two large metropolitan population centres and is the target of continued adverse environmental impact.

Molecular dissection of bacterial acrylate catabolism – unexpected links with dimethylsulfoniopropionate catabolism and dimethyl sulfide production - Jonathan D. Todd; Andrew R. J. Curson; Nefeli Nikolaidou‐Katsaraidou; Charles A. Brearley; Nicholas J. Watmough; Yohan Chan; Philip C. B. Page; Lei Sun; Andrew W. B. Johnston (Environmental Microbiology, 2010)
Summary A bacterium in the genus Halomonas that grew on dimethylsulfoniopropionate (DMSP) or acrylate as sole carbon sources and that liberated the climate‐changing gas dimethyl sulfide in media containing DMSP was obtained from the phylloplane of the macroalga Ulva. We identified a cluster that contains genes specifically involved in DMSP catabolism ( dddD, dddT ) or in degrading acrylate ( acuN , acuK ) or that are required to break down both substrates ( dddC , dddA ). Using NMR and HPLC analyses to trace 13 C‐ or 14 C‐labelled acrylate and DMSP in strains of Escherichia coli with various combinations of cloned ddd and/or acu genes, we deduced that DMSP is imported by the BCCT‐type transporter DddT, then converted by DddD to 3‐OH‐propionate (3HP), liberating dimethyl sulfide in the process. As DddD is a predicted acyl CoA transferase, there may be an earlier, unidentified catabolite of DMSP. Acrylate is also converted to 3HP, via a CoA transferase (AcuN) and a hydratase (AcuK). The 3HP is predicted to be catabolized by an alcohol dehydrogenase, DddA, to malonate semialdehyde, thence by an aldehyde dehydrogenase, DddC, to acyl CoA plus CO 2 . The regulation of the ddd and acu genes is unusual, as a catabolite, 3HP, was a co‐inducer of their transcription. This first description of genes involved in acrylate catabolism in any organism shows that the relationship between the catabolic pathways of acrylate and DMSP differs from that which had been suggested in other bacteria.

Modeling and measuring the visual detection of ecologically relevant motion by an Anolis lizard - Adam C. Pallus; Leo J. Fleishman; Philip M. Castonguay (Journal of Comparative Physiology A, 2010)

Effectors of the frequency of calcium oscillations in HEK-293 cells: wavelet analysis and a computer model - David Szekely; Sarah C. Brennan; Hee-Chang Mun; Arthur D. Conigrave; Philip W. Kuchel (European Biophysics Journal, 2009)

The effect of calcium and pH on Florida apple snail, Pomacea paludosa (Gastropoda: Ampullariidae), shell growth and crush weight - Nancy H. Glass; Philip C. Darby (Aquatic Ecology, 2009)

Modelling the distribution of a threatened habitat: the California sage scrub - Erin C. Riordan; Philip W. Rundel (Journal of Biogeography, 2009)
Aim Using predictive species distribution and ecological niche modelling our objectives are: (1) to identify important climatic drivers of distribution at regional scales of a locally complex and dynamic system – California sage scrub; (2) to map suitable sage scrub habitat in California; and (3) to distinguish between bioclimatic niches of floristic groups within sage scrub to assess the conservation significance of analysing such species groups. Location Coastal mediterranean‐type shrublands of southern and central California. Methods Using point localities from georeferenced herbarium records, we modelled the potential distribution and bioclimatic envelopes of 14 characteristic sage scrub species and three floristic groups (south‐coastal, coastal–interior disjunct and broadly distributed species) based upon current climate conditions. M axent was used to map climatically suitable habitat, while principal components analysis followed by canonical discriminant analysis were used to distinguish between floristic groups and visualize species and group distributions in multivariate ecological space. Results Geographical distribution patterns of individual species were mirrored in the habitat suitability maps of floristic groups, notably the disjunct distribution of the coastal–interior species. Overlap in the distributions of floristic groups was evident in both geographical and multivariate niche space; however, discriminant analysis confirmed the separability of floristic groups based on bioclimatic variables. Higher performance of floristic group models compared with sage scrub as a whole suggests that groups have differing climate requirements for habitat suitability at regional scales and that breaking sage scrub into floristic groups improves the discrimination between climatically suitable and unsuitable habitat. Main conclusions The finding that presence‐only data and climatic variables can produce useful information on habitat suitability of California sage scrub species and floristic groups at a regional scale has important implications for ongoing efforts of habitat restoration for sage scrub. In addition, modelling at a group level provides important information about the differences in climatic niches within California sage scrub. Finally, the high performance of our floristic group models highlights the potential a community‐level modelling approach holds for investigating plant distribution patterns.

GeoChip‐based analysis of functional microbial communities during the reoxidation of a bioreduced uranium‐contaminated aquifer - Joy D. Van Nostrand; Wei‐Min Wu; Liyou Wu; Ye Deng; Jack Carley; Sue Carroll; Zhili He; Baohua Gu; Jian Luo; Craig S. Criddle; David B. Watson; Philip M. Jardine; et al. (Environmental Microbiology, 2009)
Summary A pilot‐scale system was established for in situ biostimulation of U(VI) reduction by ethanol addition at the US Department of Energy's (DOE's) Field Research Center (Oak Ridge, TN). After achieving U(VI) reduction, stability of the bioreduced U(IV) was evaluated under conditions of (i) resting (no ethanol injection), (ii) reoxidation by introducing dissolved oxygen (DO), and (iii) reinjection of ethanol. GeoChip, a functional gene array with probes for N, S and C cycling, metal resistance and contaminant degradation genes, was used for monitoring groundwater microbial communities. High diversity of all major functional groups was observed during all experimental phases. The microbial community was extremely responsive to ethanol, showing a substantial change in community structure with increased gene number and diversity after ethanol injections resumed. While gene numbers showed considerable variations, the relative abundance (i.e. percentage of each gene category) of most gene groups changed little. During the reoxidation period, U(VI) increased, suggesting reoxidation of reduced U(IV). However, when introduction of DO was stopped, U(VI) reduction resumed and returned to pre‐reoxidation levels. These findings suggest that the community in this system can be stimulated and that the ability to reduce U(VI) can be maintained by the addition of electron donors. This biostimulation approach may potentially offer an effective means for the bioremediation of U(VI)‐contaminated sites.

Primary Productivity and Water Balance of Grassland Vegetation on Three Soils in a Continuous CO2 Gradient: Initial Results from the Lysimeter CO2 Gradient Experiment - Philip A. Fay; Alexia M. Kelley; Andrew C. Procter; Dafeng Hui; Virginia L. Jin; Robert B. Jackson; Hyrum B. Johnson; H. Wayne Polley (Ecosystems, 2009)

A Literal Use of “Forest Health” Safeguards against Misuse and Misapplication - Kenneth F. Raffa; Brian Aukema; Barbara J. Bentz; Allan Carroll; Nadir Erbilgin; Daniel A. Herms; Jeffrey A. Hicke; Richard W. Hofstetter; Steven Katovich; B. Staffan Lindgren; Jesse Logan; William Mattson; et al. (Journal of Forestry, 2009)

Focus: Synergistetes - Philip Hugenholtz; Sean D. Hooper; Nikos C. Kyrpides (Environmental Microbiology, 2009)

A Lumped Parameter Model for Thermal Conductivity of Paper Coatings - Philip Gerstner; Jouni Paltakari; Patrick A. C. Gane (Transport in Porous Media, 2009)

Bridge health monitoring system based on vibration measurements - Evaggelos Ntotsios; Costas Papadimitriou; Panagiotis Panetsos; Grigorios Karaiskos; Kyriakos Perros; Philip C. Perdikaris (Bulletin of Earthquake Engineering, 2009)

Ecosystem feedbacks and cascade processes: understanding their role in the responses of Arctic and alpine ecosystems to environmental change - PHILIP A. WOOKEY; RIEN AERTS; RICHARD D. BARDGETT; FLORENCE BAPTIST; KARI ANNE BRÅTHEN; JOHANNES H. C. CORNELISSEN; LAURA GOUGH; IAIN P. HARTLEY; DAVID W. HOPKINS; SANDRA LAVOREL; GAIUS R. SHAVER (Global Change Biology, 2009)
Global environmental change, related to climate change and the deposition of airborne N‐containing contaminants, has already resulted in shifts in plant community composition among plant functional types in Arctic and temperate alpine regions. In this paper, we review how key ecosystem processes will be altered by these transformations, the complex biological cascades and feedbacks that might result, and some of the potential broader consequences for the earth system. Firstly, we consider how patterns of growth and allocation, and nutrient uptake, will be altered by the shifts in plant dominance. The ways in which these changes may disproportionately affect the consumer communities, and rates of decomposition, are then discussed. We show that the occurrence of a broad spectrum of plant growth forms in these regions (from cryptogams to deciduous and evergreen dwarf shrubs, graminoids and forbs), together with hypothesized low functional redundancy, will mean that shifts in plant dominance result in a complex series of biotic cascades, couplings and feedbacks which are supplemental to the direct responses of ecosystem components to the primary global change drivers. The nature of these complex interactions is highlighted using the example of the climate‐driven increase in shrub cover in low‐Arctic tundra, and the contrasting transformations in plant functional composition in mid‐latitude alpine systems. Finally, the potential effects of the transformations on ecosystem properties and processes that link with the earth system are reviewed. We conclude that the effects of global change on these ecosystems, and potential climate‐change feedbacks, cannot be predicted from simple empirical relationships between processes and driving variables. Rather, the effects of changes in species distributions and dominances on key ecosystem processes and properties must also be considered, based upon best estimates of the trajectories of key transformations, their magnitude and rates of change.

Targeted transgene integration in plant cells using designed zinc finger nucleases - Charles Q. Cai; Yannick Doyon; W. Michael Ainley; Jeffrey C. Miller; Russell C. DeKelver; Erica A. Moehle; Jeremy M. Rock; Ya-Li Lee; Robbi Garrison; Lisa Schulenberg; Ryan Blue; Andrew Worden; et al. (Plant Molecular Biology, 2009)

Ten commercial antibodies for alpha-1-adrenergic receptor subtypes are nonspecific - Brian C. Jensen; Philip M. Swigart; Paul C. Simpson (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Concentration dependent effect of GsMTx4 on mechanosensitive channels of small conductance in E. coli spheroplasts - Annette C. Hurst; Philip A. Gottlieb; Boris Martinac (European Biophysics Journal, 2009)

Perinatal risk factors for neuroblastoma - Colleen C. McLaughlin; Mark S. Baptiste; Maria J. Schymura; Michael S. Zdeb; Philip C. Nasca (Cancer Causes & Control, 2009)

A global study of relationships between leaf traits, climate and soil measures of nutrient fertility - Jenny C. Ordoñez; Peter M. Van Bodegom; Jan‐Philip M. Witte; Ian J. Wright; Peter B. Reich; Rien Aerts (Global Ecology and Biogeography, 2009)
Aim This first global quantification of the relationship between leaf traits and soil nutrient fertility reflects the trade‐off between growth and nutrient conservation. The power of soils versus climate in predicting leaf trait values is assessed in bivariate and multivariate analyses and is compared with the distribution of growth forms (as a discrete classification of vegetation) across gradients of soil fertility and climate. Location All continents except for Antarctica. Methods Data on specific leaf area (SLA), leaf N concentration (LNC), leaf P concentration (LPC) and leaf N:P were collected for 474 species distributed across 99 sites (809 records), together with abiotic information from each study site. Individual and combined effects of soils and climate on leaf traits were quantified using maximum likelihood methods. Differences in occurrence of growth form across soil fertility and climate were determined by one‐way ANOVA. Results There was a consistent increase in SLA, LNC and LPC with increasing soil fertility. SLA was related to proxies of N supply, LNC to both soil total N and P and LPC was only related to proxies of P supply. Soil nutrient measures explained more variance in leaf traits among sites than climate in bivariate analysis. Multivariate analysis showed that climate interacted with soil nutrients for SLA and area‐based LNC. Mass‐based LNC and LPC were determined mostly by soil fertility, but soil P was highly correlated to precipitation. Relationships of leaf traits to soil nutrients were stronger than those of growth form versus soil nutrients. In contrast, climate determined distribution of growth form more strongly than it did leaf traits. Main conclusions We provide the first global quantification of the trade‐off between traits associated with growth and resource conservation ‘strategies’ in relation to soil fertility. Precipitation but not temperature affected this trade‐off. Continuous leaf traits might be better predictors of plant responses to nutrient supply than growth form, but growth forms reflect important aspects of plant species distribution with climate.

A changing of the guard - Philip Hugenholtz; Nikos C. Kyrpides (Environmental Microbiology, 2009)

The order Herpesvirales - Andrew J. Davison; Richard Eberle; Bernhard Ehlers; Gary S. Hayward; Duncan J. McGeoch; Anthony C. Minson; Philip E. Pellett; Bernard Roizman; Michael J. Studdert; Etienne Thiry (Archives of Virology, 2009)

Solid Phase Synthesis and Circular Dichroism Analysis of (i → i + 4) Cyclic Lactam Analogues of Kisspeptin - Michelle A. Camerino; David C. M. Kong; David K. Chalmers; Philip E. Thompson (International Journal of Peptide Research and Therapeutics, 2008)

Use of space as an indicator of social behavior and breeding systems in the gymnotiform electric fish Brachyhypopomus pinnicaudatus - Manuela Miranda; Ana C. Silva; Philip K. Stoddard (Environmental Biology of Fishes, 2008)

Effects of intermittent hypoxia on SaO2, cerebral and muscle oxygenation during maximal exercise in athletes with exercise-induced hypoxemia - Helen C. Marshall; Michael J. Hamlin; John Hellemans; Carissa Murrell; Nik Beattie; Ien Hellemans; Tracy Perry; Aimee Burns; Philip N. Ainslie (European Journal of Applied Physiology, 2008)

Timing of glaciation in the Mediterranean mountains during the last cold stage - Philip D. Hughes; Jamie C. Woodward (Journal of Quaternary Science, 2008)
Recent research in the mountains of the Mediterranean has attempted to establish the timing of the maximum extent of glaciers during the last cold stage. Several dating methods have been utilised and new dating frameworks have emerged in key areas. In several places, multiple dating techniques (radiocarbon, optically stimulated luminescence, U‐series) applied to glacial and associated sediments suggest that local glacier maxima preceded the global Last Glacial Maximum (LGM, ca. 18 14 C ka BP/ 21 cal. ka BP) by at least several thousand years. Studies in Spain, the Pyrenees, the Maritime Alps and Turkey utilising cosmogenic isotope analyses ( 10 Be and 36 Cl), have yielded glacial geochronologies with maxima that correlate closely with the marine isotope record of ice volume and the global LGM. In some cases, the use of different geochronological techniques has led to conflicting evidence for the timing of the local last glacier maxima in the same area. From a palaeoclimate perspective, glacier–climate reconstructions for the local last glacier maxima in the mountains of central Italy, northern Greece and western Turkey indicate that climate was wet and cold. In Italy and Greece the local glacier maxima preceded the driest part of the last cold stage – as indicated by palaeoecological records – by several thousand years. For western Turkey, however, recent cosmogenic exposure ages combined with glacier modelling suggest a local last glacier maximum characterised by cold and wet conditions coinciding with the global LGM. The available evidence indicates that a dichotomy is emerging, not only in our understanding of the timing of glaciation across the Mediterranean, but also in the palaeoclimatic interpretations derived from glacial and palaeoecological records. Copyright © 2008 John Wiley & Sons, Ltd.

Phylogenetic analysis of Porphyromonas species isolated from the oral cavity of Australian marsupials - Deirdre Mikkelsen; Gabriel J. Milinovich; Paul C. Burrell; Sharnan C. Huynh; Lyndall M. Pettett; Linda L. Blackall; Darren J. Trott; Philip S. Bird (Environmental Microbiology, 2008)
Summary Porphyromonas species are frequently isolated from the oral cavity and are associated with periodontal disease in both animals and humans. Black, pigmented Porphyromonas spp. isolated from the gingival margins of selected wild and captive Australian marsupials with varying degrees of periodontal disease (brushtail possums, koalas and macropods) were compared phylogenetically to Porphyromonas strains from non‐marsupials (bear, wolf, coyote, cats and dogs) and Porphyromonas gingivalis strains from humans using 16S rRNA gene sequence analysis. The results of the phylogenetic analysis identified three distinct groups of strains. A monophyletic P. gingivalis group (Group 1) contained only strains isolated from humans and a Porphyromonas gulae group (Group 2) was divided into three distinct subclades, each containing both marsupial and non‐marsupial strains. Group 3, which contained only marsupial strains, including all six strains isolated from captive koalas, was genetically distinct from P. gulae and may constitute a new Porphyromonas species.

Apical and basolateral localisation of GLUT2 transporters in human lung epithelial cells - Kameljit K. Kalsi; Emma H. Baker; Rodolfo A. Medina; Suman Rice; David M. Wood; Jonathan C. Ratoff; Barbara J. Philips; Deborah L. Baines (Pflügers Archiv - European Journal of Physiology, 2008)

Population PK–PD model for Fc-osteoprotegerin in healthy postmenopausal women - Matthew L. Zierhut; Marc R. Gastonguay; Steven W. Martin; Paolo Vicini; Pirow J. Bekker; Donna Holloway; Philip T. Leese; Mark C. Peterson (Journal of Pharmacokinetics and Pharmacodynamics, 2008)

Perchlorate Distribution, Excretion, and Depuration in Prairie Voles and Deer Mice - Qiuqiong Cheng; Fujun Liu; Philip N. Smith; W. Andrew Jackson; Scott T. McMurry; Michael J. Hooper; Ernest E. Smith; Benjamin C. Blount; Liza Valentin-Blasini; Todd A. Anderson (Water, Air, & Soil Pollution, 2008)

Suitability of mycorrhiza-defective mutant/wildtype plant pairs (Solanum lycopersicum L. cv Micro-Tom) to address questions in mycorrhizal soil ecology - Matthias C. Rillig; Philip W. Ramsey; James E. Gannon; Daniel L. Mummey; Vijay Gadkar; Yoram Kapulnik (Plant and Soil, 2008)

Fine-mapping the genetic basis of CRP regulation in African Americans: a Bayesian approach - Benjamin Rhodes; David L. Morris; Lakshman Subrahmanyan; Cristin Aubin; Carlos F. Mendes de Leon; Jeremiah F. Kelly; Dennis A. Evans; John C. Whittaker; Jorge R. Oksenberg; Philip L. De Jager; Tim J. Vyse (Human Genetics, 2008)

Temporal changes in kin structure through a population cycle in a territorial bird, the red grouse Lagopus lagopus scoticus - STUART B. PIERTNEY; XAVIER LAMBIN; ANDREW D. C. MACCOLL; KERRY LOCK; PHILIP J. BACON; JOHN F. DALLAS; FIONA LECKIE; FRANCOIS MOUGEOT; PAUL A. RACEY; STEVE REDPATH; ROBERT MOSS (Molecular Ecology, 2008)
Populations of red grouse ( Lagopus lagopus scoticus ) undergo regular multiannual cycles in abundance. The ‘kinship hypothesis’ posits that such cycles are caused by changes in kin structure among territorial males producing delayed density‐dependent changes in aggressiveness, which in turn influence recruitment and regulate density. The kinship hypothesis makes several specific predictions about the levels of kinship, aggressiveness and recruitment through a population cycle: (i) kin structure will build up during the increase phase of a cycle, but break down prior to peak density; (ii) kin structure influences aggressiveness, such that there will be a negative relationship between kinship and aggressiveness over the years; (iii) as aggressiveness regulates recruitment and density, there will be a negative relationship between aggressiveness in one year and both recruitment and density in the next; (iv) as kin structure influences recruitment via an affect on aggressiveness, there will be a positive relationship between kinship in one year and recruitment the next. Here we test these predictions through the course of an 8‐year cycle in a natural population of red grouse in northeast Scotland, using microsatellite DNA markers to resolve changing patterns of kin structure, and supra‐orbital comb height of grouse as an index of aggressiveness. Both kin structure and aggressiveness were dynamic through the course of the cycle, and changing patterns were entirely consistent with the expectations of the kinship hypothesis. Results are discussed in relation to potential drivers of population regulation and implications of dynamic kin structure for population genetics.

Dry down impacts on apple snail (Pomacea paludosa) demography: Implications for wetland water management - Philip C. Darby; Robert E. Bennetts; H. Franklin Percival (Wetlands, 2008)

Osteopontin: regulation in tumor metastasis - Philip Y. Wai; Paul C. Kuo (Cancer and Metastasis Reviews, 2008)

Spatially explicit decision support for selecting translocation areas for Mojave desert tortoises - Jill S. Heaton; Kenneth E. Nussear; Todd C. Esque; Richard D. Inman; Frank M. Davenport; Thomas E. Leuteritz; Philip A. Medica; Nathan W. Strout; Paul A. Burgess; Lisa Benvenuti (Biodiversity and Conservation, 2008)

Identifying four phytoplankton functional types from space: An ecological approach - Dionysios E. Raitsos; Samantha J. Lavender; Christos D. Maravelias; John Haralabous; Anthony J. Richardson; Philip C. Reid (Limnology and Oceanography, 2008)
Deriving maps of phytoplankton taxa based on remote sensing data using bio‐optical properties of phytoplankton alone is challenging. A more holistic approach was developed using artificial neural networks, incorporating ecological and geographical knowledge together with ocean color, bio‐optical characteristics, and remotely sensed physical parameters. Results show that the combined remote sensing approach could discriminate four major phytoplankton functional types (diatoms, dinoflagellates, coccolithophores, and silicoflagellates) with an accuracy of more than 70%. Models indicate that the most important information for phytoplankton functional type discrimination is spatio‐temporal information and sea surface temperature. This approach can supply data for large‐scale maps of predicted phytoplankton functional types, and an example is shown.

The Gulf Stream - Philip C. Reid (Fish and Fisheries, 2008)

Short-term carbon dioxide emissions and denitrification losses from soils amended with low-P manure from genetically modified pigs - X. M. Yang; C. F. Drury; T. Q. Zhang; A. Ajakaiye; C. W. Forsberg; M. Z. Fan; J. P. Philip (Nutrient Cycling in Agroecosystems, 2008)

A comparison of the effect of urchin size and diet on gonad yield and quality in the sea urchin Evechinus chloroticus Valenciennes - Chris M. C. Woods; Philip J. James; Graeme A. Moss; Johnny Wright; Sten Siikavuopio (Aquaculture International, 2008)

Habitat Use and Life History as Predictors of Bird Responses to Habitat Change - NICOLA C. OKES; PHILIP A. R. HOCKEY; GRAEME S. CUMMING (Conservation Biology, 2008)
In theory the consideration of life‐history characteristics should provide a way of making predictive generalizations about the responses of different species to environmental modification. Nevertheless, few studies have tested the validity of this assumption or attempted to apply it across large numbers of related species. We explored both quantitative and qualitative contrasts between species of waterbirds that have either expanded or contracted their ranges in southern Africa over the past 40 years to test the hypothesis that expansionists and contractionists, respectively, should share life‐history characteristics and/or ecological attributes. Similarities and differences in life history and ecology were explored through multivariate statistics. Overall, life‐history traits provided an inadequate explanation of whether species would be range expansionists or contractionists. By contrast, ecological attributes of species that related to habitat use correlated well with range changes. In particular, waterbird species that inhabit pans seemed to be preadapted to using human‐made dams and impoundments. The ability of many species to use artificial wetlands has aided their westward range expansions into arid regions of southern Africa. By contrast, species that rely on vegetated wetlands and that require reeds for nesting were predisposed to range contraction because their habitats have been severely affected by agricultural development and urbanization. In direct contrast to range expansions, most range contractions were west to east, the eastward contraction reflected the high level of wetland loss and degradation in the eastern lowlands of South Africa. Based on analysis of ecological attributes of regional contractionists, several additional species were identified as of potential conservation concern, although such concern may not as yet have been expressed.

Bioenergetic models for acetate and phosphate transport in bacteria important in enhanced biological phosphorus removal - Luke C. Burow; Amanda N. Mabbett; Alastair G. McEwan; Philip L. Bond; Linda L. Blackall (Environmental Microbiology, 2008)
Summary Most of our understanding of the physiology of microorganisms is the result of investigations in pure culture. However, in order to understand complex environmental processes, there is a need to investigate mixed microbial communities. This is true for enhanced biological phosphorus removal (EBPR), an environmental process that results in the enrichment of the polyphosphate‐accumulating organism Accumulibacter spp. and the glycogen non‐polyphosphate accumulating organism Defluviicoccus spp. We investigated acetate and inorganic phosphate (P i ) uptake in enrichments of Accumulibacter spp. and acetate uptake in enrichments of Defluviicoccus spp. For both enrichments, anaerobic acetate uptake assays in the presence of the protonophore, carbonyl cyanide m ‐chlorophenylhydrazone (CCCP) or the membrane potential ( Δψ ) uncoupler valinomycin, indicated that acetate is likely to be taken up by a permease‐mediated process driven by the Δψ . Further investigation with the sodium ionophore monensin suggested that anaerobic acetate uptake by Defluviicoccus spp. may in part be dependent on a sodium potential. Results of this study also suggest that Accumulibacter spp. generate a proton motive force (pmf or Δp ) for anaerobic acetate uptake by efflux of protons in symport with P i through an inorganic phosphate transport (Pit) system. In contrast, we suggest that the anaerobic Δp in Defluviicoccus spp. is generated by an efflux of protons across the cell membrane by the fumarate respiratory system, or by extrusion of sodium ions via decarboxylation of methylmalonyl‐CoA. Aerobic P i uptake by the Accumulibacter spp. enrichment was strongly inhibited in the presence of an ATPase inhibitor, suggesting that the phosphate‐specific transport (Pst) system is important even under relatively high concentrations of P i . Acetate permease activity in these microorganisms may play an important role in the competition for acetate in the often acetate‐limited EBPR process. Activity of a high‐velocity Pst system in Accumulibacter spp. may further explain its ability to compete strongly in EBPR.

How do elevated [CO2], warming, and reduced precipitation interact to affect soil moisture and LAI in an old field ecosystem? - Orla Dermody; Jake F. Weltzin; Elizabeth C. Engel; Philip Allen; Richard J. Norby (Plant and Soil, 2007)

Simulation of networks of spiking neurons: A review of tools and strategies - Romain Brette; Michelle Rudolph; Ted Carnevale; Michael Hines; David Beeman; James M. Bower; Markus Diesmann; Abigail Morrison; Philip H. Goodman; Frederick C. Harris; Milind Zirpe; Thomas Natschläger; et al. (Journal of Computational Neuroscience, 2007)

Tuning the antiproliferative activity of biologically active iron chelators: characterization of the coordination chemistry and biological efficacy of 2-acetylpyridine and 2-benzoylpyridine hydrazone ligands - Paul V. Bernhardt; Gregory J. Wilson; Philip C. Sharpe; Danuta S. Kalinowski; Des R. Richardson (JBIC Journal of Biological Inorganic Chemistry, 2007)

A biological consequence of reducing Arctic ice cover: arrival of the Pacific diatom Neodenticula seminae in the North Atlantic for the first time in 800 000 years - PHILIP C. REID; DAVID G. JOHNS; MARTIN EDWARDS; MICHEL STARR; MICHEL POULIN; PAULI SNOEIJS (Global Change Biology, 2007)
The Continuous Plankton Recorder survey has monitored plankton in the Northwest Atlantic at monthly intervals since 1962, with an interegnum between 1978 and 1990. In May 1999, large numbers of the Pacific diatom Neodenticula seminae were found in Continuous Plankton Recorder (CPR) samples in the Labrador Sea as the first record in the North Atlantic for more than 800 000 years. The event coincided with modifications in Arctic hydrography and circulation, increased flows of Pacific water into the Northwest Atlantic and in the previous year the exceptional occurrence of extensive ice‐free water to the North of Canada. These observations indicate that N. seminae was carried in a pulse of Pacific water in 1998/early 1999 via the Canadian Arctic Archipelago and/or Fram Strait. The species occurred previously in the North Atlantic during the Pleistocene from∼1.2 to∼0.8 Ma as recorded in deep sea sediment cores. The reappearance of N. seminae in the North Atlantic is an indicator of the scale and speed of changes that are taking place in the Arctic and North Atlantic oceans as a consequence of regional climate warming. Because of the unusual nature of the event it appears that a threshold has been passed, marking a change in the circulation between the North Pacific and North Atlantic Oceans via the Arctic. Trans‐Arctic migrations from the Pacific into the Atlantic are likely to occur increasingly over the next 100 years as Arctic ice continues to melt affecting Atlantic biodiversity and the biological pump with consequent feedbacks to the carbon cycle.

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Effects of Cd, Zn, or both on soil microbial biomass and activity in a clay loam soil - Giancarlo Renella; Amar M. Chaudri; Céline M. Falloon; Loretta Landi; Paolo Nannipieri; Philip C. Brookes (Biology and Fertility of Soils, 2007)

Hypertonicity induced apoptosis in HL-60 cells in the presence of intracellular potassium - Arko Ghosh; Peter C. Keng; Philip A. Knauf (Apoptosis, 2007)

Documenting hurricane impacts on coral reefs using two‐dimensional video‐mosaic technology - Arthur C. R. Gleason; Diego Lirman; Dana Williams; Nuno R. Gracias; Brooke E. Gintert; Hossein Madjidi; R. Pamela Reid; G. Chris Boynton; Shahriar Negahdaripour; Margaret Miller; Philip Kramer (Marine Ecology, 2007)
Four hurricanes impacted the reefs of Florida in 2005. In this study, we evaluate the combined impacts of hurricanes Dennis, Katrina, Rita, and Wilma on a population of Acropora palmata using a newly developed video‐mosaic methodology that provides a high‐resolution, spatially accurate landscape view of the reef benthos. Storm damage to A. palmata was surprisingly limited; only 2 out of 19 colonies were removed from the study plot at Molasses Reef. The net tissue losses for those colonies that remained were only 10% and mean diameter of colonies decreased slightly from 88.4 to 79.6 cm. In contrast, the damage to the reef framework was more severe, and a large section (6 m in diameter) was dislodged, overturned, and transported to the bottom of the reef spur. The data presented here show that two‐dimensional video‐mosaic technology is well‐suited to assess the impacts of physical disturbance on coral reefs and can be used to complement existing survey methodologies.

In situ detection of novel Acidobacteria in microbial mats from a chemolithoautotrophically based cave ecosystem (Lower Kane Cave, WY, USA) - Daniela B. Meisinger; Johannes Zimmermann; Wolfgang Ludwig; Karl‐Heinz Schleifer; Gerhard Wanner; Michael Schmid; Philip C. Bennett; Annette S. Engel; Natuschka M. Lee (Environmental Microbiology, 2007)
Summary Lower Kane Cave, Wyoming (USA), has hydrogen sulfide‐bearing springs that discharge into the cave passage. The springs and cave stream harbour white filamentous microbial mats dominated by Epsilonproteobacteria . Recently, novel 16S rRNA gene sequences from the phylum Acidobacteria , subgroup 7, were found in these cave mats. Although Acidobacteria are ubiquitously distributed in many terrestrial and marine habitats, little is known about their ecophysiology. To investigate this group in Lower Kane Cave in more detail, a full‐cycle rRNA approach was applied based on 16S and 23S rRNA gene clone libraries and the application of novel probes for fluorescence in situ hybridization . The 16S and 23S rRNA gene clone libraries yielded seven and six novel acidobacterial operational taxonomic units (OTUs) respectively. The majority of the OTUs were affiliated with subgroups 7 and 8. One OTU was affiliated with subgroup 6, and one OTU could not be assigned to any of the present acidobacterial subgroups. Fluorescence in situ hybridization distinguished two morphologically distinct, rod‐shaped cells of the acidobacterial subgroups 7 and 8. Although the ecophysiology of Acidobacteria from Lower Kane Cave will not be fully resolved until cultures are obtained, acidobacterial cells were always associated with the potentially chemolithoautotrophic epsilon‐ or gammaproteobacterial filaments, suggesting perhaps a lifestyle based on heterotrophy or chemoorganotrophy.

Relation between phylogenetic position, lipid metabolism and butyrate production by different Butyrivibrio-like bacteria from the rumen - Delphine Paillard; Nest McKain; Lal C. Chaudhary; Nicola D. Walker; Florian Pizette; Ingrid Koppova; Neil R. McEwan; Jan Kopečný; Philip E. Vercoe; Petra Louis; R. John Wallace (Antonie van Leeuwenhoek, 2007)

Prediction of Resource Volumes at Untested Locations Using Simple Local Prediction Models - Emil D. Attanasi; Timothy C. Coburn; Philip A. Freeman (Natural Resources Research, 2007)

Effects of long-term captivity on thermoregulation, metabolism and ventilation of the southern brown bandicoot (Marsupialia: Peramelidae) - Alexander N. Larcombe; Philip C. Withers (Journal of Comparative Physiology B, 2007)

Focusing of phytodetritus deposition beneath a deep‐ocean front, Chatham Rise, New Zealand - Scott D. Nodder; Gerard C. A. Duineveld; Conrad A. Pilditch; Philip J. Sutton; P. Keith Probert; Marc S. S. Lavaleye; Rob Witbaard; F. Hoe Chang; Julie A. Hall; Ken M. Richardson (Limnology and Oceanography, 2007)
In October 2001, we observed a deep‐ocean phytodetritus deposition event on Chatham Rise beneath the Subtropical Front (STF). The origin of this phytodetritus was probably an extensive phytoplankton bloom that occurred in the STF in the preceding weeks. We assessed the spatial distribution of the deposition event using video images from benthic lander and epibenthic trawl deployments and sediment pigment analyses at six sites on a north—south transect across Chatham Rise. High surficial sediment chlorophyll a concentrations were restricted spatially to the southern flank of Chatham Rise (350–1,200‐m depth) with the highest values centered at ~750‐m water depth (750 S). This southern 750 S site was also the only site where macroscopic phytodetritus was observed, coincident with elevated benthic biomass and sediment community respiration rates. At 750 S, phytodetritus resuspension was observed on video and corroborated by current meter, sediment trap, and optical backscatter measurements, suggesting a threshold erosion current speed for phytodetritus of ~10 cm s −1 , equivalent to a shear velocity of 0.5 cm s −1 and similar to other deep‐ocean studies elsewhere. The restriction of macroscopic phytodetritus deposition to 750 S was related to a zone of current convergence within the STF and lower near‐bed current speeds observed across ~1‐day that promoted deposition. Observations of high benthic biomass and respiration on the southern flank of Chatham Rise suggest that this focusing process is important in fueling the energy demands of benthic communities, in association with the general west‐east advection of organic matter within the STF itself. Such physical focusing of labile organic matter deposition may be an important process in other highly productive frontal systems.

The effects of wetland habitat structure on Florida apple snail density - Laksiri B. Karunaratne; Philip C. Darby; Robert E. Bennetts (Wetlands, 2006)

Transition metal complexes as mediator-titrants in protein redox potentiometry - Paul V. Bernhardt; Kuan-I. Chen; Philip C. Sharpe (JBIC Journal of Biological Inorganic Chemistry, 2006)

Megaplasmids encode differing combinations of lantibiotics in Streptococcus salivarius - Philip A. Wescombe; Jeremy P. Burton; Peter A. Cadieux; Nikolai A. Klesse; Otto Hyink; Nicholas C. K. Heng; Chris N. Chilcott; Gregor Reid; John R. Tagg (Antonie van Leeuwenhoek, 2006)

Nitrate impacts on the Florida apple snail, Pomacea paludosa - Norah Myers Corrao; Philip C. Darby; Christopher M. Pomory (Hydrobiologia, 2006)

Inorganic N Dynamics from Soils Amended with Low-P Manure from Genetically Modified Pigs (EnviropigTM) - X. M. Yang; C. F. Drury; T. Q. Zhang; A. Ajakaiye; C. W. Forsberg; M. Z. Fan; J. P. Philip (Nutrient Cycling in Agroecosystems, 2006)

Long‐Term Landscape Change and Bird Abundance in Amazonian Rainforest Fragments - PHILIP C. STOUFFER; RICHARD O. BIERREGAARD; CHERYL STRONG; THOMAS E. LOVEJOY (Conservation Biology, 2006)
The rainforests of the Amazon basin are being cut by humans at a rate >20,000 km 2 /year, leading to smaller and more isolated patches of forest, with remaining fragments often in the range of 1–100 ha. We analyzed samples of understory birds collected over 20 years from a standardized mist‐netting program in 1– to 100‐ha rainforest fragments in a dynamic Amazonian landscape near Manaus, Brazil. Across bird guilds, the condition of second growth immediately surrounding fragments was often as important as fragment size or local forest cover in explaining variation in abundance. Some fragments surrounded by 100 m of open pasture showed reductions in insectivorous bird abundance of over 95%, even in landscapes dominated by continuous forest and old second growth. These extreme reductions may be typical throughout Amazonia in small (≤10 ha), isolated fragments of rainforest. Abundance for some guilds returned to preisolation levels in 10‐ and 100‐ha fragments connected to continuous forest by 20‐year‐old second growth. Our results show that the consequences of Amazonian forest loss cannot be accurately described without explicit consideration of vegetation dynamics in matrix habitat. Any dichotomous classification of the landscape into “forest” and “nonforest” misses essential information about the matrix.

Larval bullfrog skin expresses ENaC despite having no amiloride-blockable transepithelial Na+ transport - Makoto Takada; Tomoko Shimomura; Shigeru Hokari; Philip J. Jensik; Thomas C. Cox (Journal of Comparative Physiology B, 2006)

Atmospheric nitrogen deposition in world biodiversity hotspots: the need for a greater global perspective in assessing N deposition impacts - GARETH K. PHOENIX; W. KEVIN HICKS; STEVE CINDERBY; JOHAN C. I. KUYLENSTIERNA; WILLIAM D. STOCK; FRANK J. DENTENER; KEN E. GILLER; AMY T. AUSTIN; ROD D. B. LEFROY; BEN S. GIMENO; MIKE R. ASHMORE; PHILIP INESON (Global Change Biology, 2006)
Increased atmospheric nitrogen (N) deposition is known to reduce plant diversity in natural and semi‐natural ecosystems, yet our understanding of these impacts comes almost entirely from studies in northern Europe and North America. Currently, we lack an understanding of the threat of N deposition to biodiversity at the global scale. In particular, rates of N deposition within the newly defined 34 world biodiversity hotspots, to which 50% of the world's floristic diversity is restricted, has not been quantified previously. Using output from global chemistry transport models, here we provide the first estimates of recent (mid‐1990s) and future (2050) rates and distributions of N deposition within biodiversity hotspots. Our analysis shows that the average deposition rate across these areas was 50% greater than the global terrestrial average in the mid‐1990s and could more than double by 2050, with 33 of 34 hotspots receiving greater N deposition in 2050 compared with 1990. By this time, 17 hotspots could have between 10% and 100% of their area receiving greater than 15 kg N ha −1 yr −1 , a rate exceeding critical loads set for many sensitive European ecosystems. Average deposition in four hotspots is predicted to be greater than 20 kg N ha −1 yr −1 . This elevated N deposition within areas of high plant diversity and endemism may exacerbate significantly the global threat of N deposition to world floristic diversity. Overall, we highlight the need for a greater global approach to assessing the impacts of N deposition.

Polymorphisms in Inflammation-related Genes and Risk of Gastric Cancer (Finland) - Farin Kamangar; Christian C. Abnet; Amy A. Hutchinson; Craig J. Newschaffer; Kathy Helzlsouer; Yin Yao Shugart; Pirjo Pietinen; Sanford M. Dawsey; Demetrius Albanes; Jarmo Virtamo; Philip R. Taylor (Cancer Causes & Control, 2006)

Establishment of primary cultures of rat olfactory bulb under serum-free conditions for studies of cellular injury - Mark C. Farso; Fiona Y. Carroll; Philip M. Beart (Cell and Tissue Research, 2006)

Intracellular colonization of roots of Arabidopsis and crop plants by Gluconacetobacter diazotrophicus - Edward C. Cocking; Philip J. Stone; Michael R. Davey (In Vitro Cellular & Developmental Biology - Plant, 2006)

Postnatal developmental expression of the PDZ scaffolds Na+-H+ exchanger regulatory factors 1 and 2 in the rat cochlea - Refik Kanjhan; Deanne H. Hryciw; C. Chris Yun; Mark C. Bellingham; Philip Poronnik (Cell and Tissue Research, 2006)

Effects of ketamine on prefrontal and striatal regions in an overt verbal fluency task: a functional magnetic resonance imaging study - Cynthia H. Y. Fu; Kathryn M. Abel; Matthew P. G. Allin; David Gasston; Sergi G. Costafreda; John Suckling; Steve C. R. Williams; Philip K. McGuire (Psychopharmacology, 2005)

Novel diaroylhydrazine ligands as iron chelators: coordination chemistry and biological activity - Paul V. Bernhardt; Piao Chin; Philip C. Sharpe; Jing-Yan C. Wang; Des R. Richardson (JBIC Journal of Biological Inorganic Chemistry, 2005)

Relationship between communities and processes; new insights from a field study of a contaminated ecosystem - Philip W. Ramsey; Matthias C. Rillig; Kevin P. Feris; Nathan S. Gordon; Johnnie N. Moore; William E. Holben; James E. Gannon (Ecology Letters, 2005)
We used a 93‐year‐old mine waste contamination gradient in alluvial soil to explore the relationship between ecosystem level functioning and community structure in a chronically stressed ecosystem. The sensitivity of broad functional parameters ( in situ soil respiration, microbial biomass, above and below ground plant biomass) and microbial diversity [phospholipid fatty acid (PLFA) abundance and richness] were compared. Functional responses were linear with respect to contaminants while thresholds were detected in the community structural response to contamination along the gradient. For example, in situ soil respiration was negatively and linearly correlated to contamination concentration ( R = −0.783, P

New techniques and findings in the study of a candidate allelochemical implicated in invasion success - Amy C. Blair; Bradley D. Hanson; Galen R. Brunk; Robin A. Marrs; Philip Westra; Scott J. Nissen; Ruth A. Hufbauer (Ecology Letters, 2005)
Allelopathy has been hypothesized to promote the success of invasive plants. Support for the role of allelopathy in invasions has emerged from research on the candidate allelochemical (−)‐catechin, which is secreted by spotted knapweed. Here we describe new methods to quantify catechin in liquid and soil. With a new technique, we assayed catechin production by individual plants in liquid media and found levels up to two orders of magnitude less than previously reported. An acetone/water solution provided consistent recovery of catechin from soil, with percent recovery depending upon soil type. We evaluated soils from two spotted knapweed sites in Montana, USA, but found no measurable catechin. Idaho fescue, a native species reportedly sensitive to catechin, only exhibited slightly reduced growth at concentrations 10 times higher than previously reported to cause 100% mortality. Our results emphasize that more research is required to clarify the role of catechin in the invasion of spotted knapweed.

5-HT6 receptor antagonists improve performance in an attentional set shifting task in rats - Paula D. Hatcher; Verity J. Brown; David S. Tait; Simon Bate; Philip Overend; Jim J. Hagan; Declan N. C. Jones (Psychopharmacology, 2005)

Economic valuation of policies for managing acidity in remote mountain lakes: Examining validity through scope sensitivity testing - Ian J. Bateman; Philip Cooper; Stavros Georgiou; Ståle Navrud; Gregory L. Poe; Richard C. Ready; Pere Riera; Mandy Ryan; Christian A. Vossler (Aquatic Sciences, 2005)

Modulation of leaf economic traits and trait relationships by climate - Ian J. Wright; Peter B. Reich; Johannes H. C. Cornelissen; Daniel S. Falster; Philip K. Groom; Kouki Hikosaka; William Lee; Christopher H. Lusk; Ülo Niinemets; Jacek Oleksyn; Noriyuki Osada; Hendrik Poorter; et al. (Global Ecology and Biogeography, 2005)
Aim Our aim was to quantify climatic influences on key leaf traits and relationships at the global scale. This knowledge provides insight into how plants have adapted to different environmental pressures, and will lead to better calibration of future vegetation–climate models. Location The data set represents vegetation from 175 sites around the world. Methods For more than 2500 vascular plant species, we compiled data on leaf mass per area (LMA), leaf life span (LL), nitrogen concentration (N mass ) and photosynthetic capacity (A mass ). Site climate was described with several standard indices. Correlation and regression analyses were used for quantifying relationships between single leaf traits and climate. Standardized major axis (SMA) analyses were used for assessing the effect of climate on bivariate relationships between leaf traits. Principal components analysis (PCA) was used to summarize multidimensional trait variation. Results At hotter, drier and higher irradiance sites, (1) mean LMA and leaf N per area were higher; (2) average LL was shorter at a given LMA, or the increase in LL was less for a given increase in LMA (LL–LMA relationships became less positive); and (3) A mass was lower at a given N mass , or the increase in A mass was less for a given increase in N mass . Considering all traits simultaneously, 18% of variation along the principal multivariate trait axis was explained by climate. Main conclusions Trait‐shifts with climate were of sufficient magnitude to have major implications for plant dry mass and nutrient economics, and represent substantial selective pressures associated with adaptation to different climatic regimes.

Unusual segregation products in sperm from a pericentric inversion 17 heterozygote - Monica M. Mikhaail-Philips; Barbara C. McGillivray; Sara J. Hamilton; Evelyn Ko; Judy Chernos; Alfred Rademaker; Renée H. Martin (Human Genetics, 2005)

Edge and Area Effects on the Occurrence of Migrant Forest Songbirds - TIMOTHY H. PARKER; BROOKE M. STANSBERRY; C. DUSTIN BECKER; PHILIP S. GIPSON (Conservation Biology, 2005)
Concerns about forest fragmentation and its conservation implications have motivated numerous studies that investigate the influence of forest patch area and forest edge on songbird distribution patterns. The generalized effects of forest patch size and forest edge on animal distributions is still debatable because forest patch size and forest edge are often confounded and because of an incomplete synthesis of available data. To fill a portion of this gap, we incorporated all available published data (33 papers) in meta‐analyses of forest edge and area effects on site occupancy patterns for 26 Neotropical migrant forest‐nesting songbirds in eastern North America. All reported area effects are confounded or potentially confounded by edge effects, and we refer to these as “confounded” studies. The converse, however, is not true and most reported edge effects are independent of patch area. When considering only nonconfounded studies of edge effects, only 1 of 17 species showed significant edge avoidance and 3 had significant affinity for edges. In confounded studies, 12 of 22 species showed significant avoidance of small patches and edges, and 1 had an affinity for small patches and edges. Furthermore, average effect sizes averaged across studies or species tended to be higher for confounded studies than for edge studies. We discuss three possible reasons for differences in results between these two groups of studies. First, studies of edge effects tended to be carried out in landscapes with greater forest cover than studies of confounded effects; among confounded effects studies, as forest cover increased, we observed a nonsignificant trend towards decreasing strength of small patch or edge avoidance effects. Thus, the weaker effects in edge studies may be due to the fact that these studies were conducted in forest‐dominated landscapes. Second, we may have detected strong effects only in confounded studies because area effects are much stronger than edge effects on bird occurrence, and area effects drive the results in confounded studies. Third, edge and area effects may interact in such a way that edge effects become more important as forest patch size decreases; thus, both edge and area effects are responsible for results in confounded studies. These three explanations cannot be adequately separated with existing data. Regardless, it is clear that fragmentation of forests into small patches is detrimental to many migrant songbird species.

Decreased transcription of the human FCGR2B gene mediated by the -343 G/C promoter polymorphism and association with systemic lupus erythematosus - Marissa C. Blank; Radu N. Stefanescu; Emi Masuda; Francesc Marti; Philip D. King; Patricia B. Redecha; Robert J. Wurzburger; Margaret G.E. Peterson; Shizuko Tanaka; Luminita Pricop (Human Genetics, 2005)

Improving Map Accuracy of Soil Variables Using Soil Electrical Conductivity as a Covariate - Alison B. Tarr; Kenneth J. Moore; Donald G. Bullock; Philip M. Dixon; C. Lee Burras (Precision Agriculture, 2005)

Antioxidants and basal cell carcinoma of the skin: A nested case–control study - Sarah A. McNaughton; Geoffrey C. Marks; Philip Gaffney; Gail Williams; Adele C. Green (Cancer Causes & Control, 2005)

Duelling timescales of host movement and disease recovery determine invasion of disease in structured populations - Paul C. Cross; James O. Lloyd‐Smith; Philip L. F. Johnson; Wayne M. Getz (Ecology Letters, 2005)
The epidemic potential of a disease is traditionally assessed using the basic reproductive number, R 0 . However, in populations with social or spatial structure a chronic disease is more likely to invade than an acute disease with the same R 0 , because it persists longer within each group and allows for more host movement between groups. Acute diseases ‘perceive’ a more structured host population, and it is more important to consider host population structure in analyses of these diseases. The probability of a pandemic does not arise independently from characteristics of either the host or disease, but rather from the interaction of host movement and disease recovery timescales. The R * statistic, a group‐level equivalent of R 0 , is a better indicator of disease invasion in structured populations than the individual‐level R 0 .

Edge Influence on Forest Structure and Composition in Fragmented Landscapes - KAREN A. HARPER; S. ELLEN MACDONALD; PHILIP J. BURTON; JIQUAN CHEN; KIMBERLEY D. BROSOFSKE; SARI C. SAUNDERS; EUGÉNIE S. EUSKIRCHEN; DAR ROBERTS; MALANDING S. JAITEH; PER‐ANDERS ESSEEN (Conservation Biology, 2005)
Although forest edges have been studied extensively as an important consequence of fragmentation, a unifying theory of edge influence has yet to be developed. Our objective was to take steps toward the development of such a theory by (1) synthesizing the current knowledge of patterns of forest structure and composition at anthropogenically created forest edges, (2) developing hypotheses about the magnitude and distance of edge influence that consider the ecological processes influencing these patterns, and (3) identifying needs for future research. We compiled data from 44 published studies on edge influence on forest structure and composition in boreal, temperate, and tropical forests. Abiotic and biotic gradients near created forest edges generate a set of primary responses to edge creation. Indirect effects from these primary responses and the original edge gradient perpetuate edge influence, leading to secondary responses. Further changes in vegetation affect the edge environment, resulting in ongoing edge dynamics. We suggest that the magnitude and distance of edge influence are a direct function of the contrast in structure and composition between adjacent communities on either side of the edge. Local factors such as climate, edge characteristics, stand attributes, and biotic factors affect patch contrast. Regional factors define the context within which to assess the ecological significance of edge influence (the degree to which the edge habitat differs from interior forest habitat). Our hypotheses will help predict edge influence on structure and composition in forested ecosystems, an important consideration for conservation. For future research on forest edges in fragmented landscapes, we encourage the testing of our hypotheses, the use of standardized methodology, complete descriptions of study sites, studies on other types of edges, synthesis of edge influence on different components of the ecosystem, and investigations of edges in a landscape context.

Gene regulation in planta by plant-derived engineered zinc finger protein transcription factors - Rachel Holmes-Davis; Guofu Li; Andrew C. Jamieson; Edward J. Rebar; Qiang Liu; Yanhong Kong; Casey C. Case; Philip D. Gregory (Plant Molecular Biology, 2005)

Effect of Volatile Constituents from Securidaca Longepedunculata on Insect pests Of Stored Grain - Thamara K. Jayasekara; Philip C. Stevenson; David R. Hall; Steven R. Belmain (Journal of Chemical Ecology, 2005)

A general model of local competition for space - Philip H. Crowley; Heather M. Davis; Amanda L. Ensminger; Linda C. Fuselier; J. Kasi Jackson; D. Nicholas McLetchie (Ecology Letters, 2005)
Local competition for space across a wide array of taxa typically involves three mechanisms that we denote here as expansion (spreading into unoccupied habitat), lottery (replacing dead competitors), and overgrowth (encroaching on competitors along zones of contact). By formulating and analysing a simple, general model incorporating these features, we identify ecological conditions and life‐history features that lead to stable coexistence or competitive exclusion (with or without initial‐condition dependence) and gain insight by linking these to case studies in the literature. We demonstrate the importance of contact inhibition, a little‐studied feature of overgrowth, and we show how life‐history tradeoffs may influence and be influenced by local competition for space. The general model we present can help indicate whether local interactions are sufficient to explain patterns of coexistence or exclusion and can serve as the foundation for more specific, realistic models of spatial competition.

Localisation of NMU1R and NMU2R in human and rat central nervous system and effects of neuromedin-U following central administration in rats - Jane Gartlon; Philip Szekeres; Mark Pullen; Henry M. Sarau; Nambi Aiyar; Usman Shabon; David Michalovich; Klaudia Steplewski; Cathy Ellis; Nabil Elshourbagy; Mark Duxon; Tracey E. Ashmeade; et al. (Psychopharmacology, 2004)

Occurrence of the parasitic sea lampreyPetromyzon marinus on western North Atlantic right whales Eubalaena glacialis - Owen C. Nichols; Philip K. Hamilton (Environmental Biology of Fishes, 2004)

Polymorphic variation of CYP1A1 is associated with the risk of gastric cardia cancer: a prospective case?cohort study of cytochrome P-450 1A1 and GST enzymes - Mark J. Roth; Christian C. Abnet; Laura Lee Johnson; Steven D. Mark; Zhi Wei Dong; Philip R. Taylor; Sanford M. Dawsey; You-Lin Qiao (Cancer Causes & Control, 2004)

40Ar/39Ar dating of the eruptive history of Mount Erebus, Antarctica: volcano evolution - Richard P. Esser; Philip R. Kyle; William C. McIntosh (Bulletin of Volcanology, 2004)

40Ar/39Ar dating of the eruptive history of Mount Erebus, Antarctica: summit flows, tephra, and caldera collapse - Christopher J. Harpel; Philip R. Kyle; Richard P. Esser; William C. McIntosh; David A. Caldwell (Bulletin of Volcanology, 2004)

Differential effects of arginine, glutamate and phosphoarginine on Ca2+-activation properties of muscle fibres from crayfish and rat - David W. Jame; Jan M. West; Philip C. Dooley; D. George Stephenson (Journal of Muscle Research and Cell Motility, 2004)

Protein accumulation and distribution in floodplain soils and river foam - Mary J. Harner; Philip W. Ramsey; Matthias C. Rillig (Ecology Letters, 2004)
Many processes contribute to nutrient transfer from terrestrial to aquatic systems, but in most cases the contribution of particular organisms is unknown. In this study, we explore how a Bradford‐reactive soil protein (BRSP) produced by arbuscular mycorrhizal fungi may provide nutrients to river ecosystems. Along a floodplain in Montana, we extracted BRSP from soils and related the protein concentrations to the age of soil surfaces. We identified BRSP in surface soils, as well as to a depth of 1.4 m, and found that the protein accumulates through time. We also detected BRSP in foam from five rivers in the western United States. Experiments were conducted that demonstrate that the protein may be leached or washed from soils and become a constituent of foam when mixed into turbulent water. We propose that terrestrially derived soil protein may enter rivers via erosion and leaching and serve as a nutrient source for aquatic organisms.

Matrix metalloproteinase-2: Mechanism and regulation of NF-?B-mediated activation and its role in cell motility and ECM-invasion - Subha Philip; Anuradha Bulbule; Gopal C. Kundu (Glycoconjugate Journal, 2004)

Effects of Road Clearings on Movement Patterns of Understory Rainforest Birds in Central Amazonia - SUSAN G. W. LAURANCE; PHILIP C. STOUFFER; WILLIAM F. LAURANCE (Conservation Biology, 2004)
The impacts of potential linear barriers such as roads, highways, and power lines on rainforest fauna are poorly understood. In the central Brazilian Amazon, we compared the frequency of local movements (≤300 m long) of understory birds within intact forest and across a 30‐ to 40‐m‐wide road over a 2‐year period. Rainforest had regenerated along some road verges, to the extent that a nearly complete canopy was formed in some areas, so we also assessed whether this facilitated bird movement. Movement data were determined from 1212 recaptures of 3681 netted birds at six study sites. The road significantly inhibited total bird movement across roads at five of the six sites. Bird foraging guilds varied in their responses to the road and different ages of regrowth. Movements of frugivorous and edge and gap species were not inhibited at any site, whereas most forest‐dependent insectivores (mixed‐species flocks, terrestrial species, and army‐ant followers) had markedly inhibited road‐crossing movements, except at sites with extensive regrowth. Solitary understory species were especially vulnerable, rarely crossing even roads overgrown by tall regrowth. For sensitive species, road‐crossing movements were inhibited because individuals tended to avoid both edge‐affected habitat near the road and the road clearing itself. Our results suggest that even narrow roads with low traffic volumes can reduce local movements of many insectivorous birds in Amazonia.

Fluvial system response to Late Devensian (Weichselian) aridity, Baston, Lincolnshire, England - Rebecca M. Briant; G. Russell Coope; Richard C. Preece; David H. Keen; Steve Boreham; Huw I. Griffiths; Mary B. Seddon; Philip L. Gibbard (Journal of Quaternary Science, 2004)
Little is known about the impact of Late Devensian (Weichselian) aridity on lowland British landscapes, largely because they lack the widespread coversand deposits of the adjacent continent. The concentration of large interformational ice‐wedge casts in the upper part of many Devensian fluvial sequences suggests that fluvial activity may have decreased considerably during this time. The development of optically stimulated luminescence (OSL) dating enables this period of ice‐wedge cast formation to be constrained for the first time in eastern England, where a marked horizon of ice‐wedge casts is found between two distinctive dateable facies associations. Contrasts between this horizon and adjacent sediments show clear changes in environment and fluvial system behaviour in response to changing water supply, in line with palaeontological evidence. In addition to providing chronological control on the period of ice‐wedge formation, the study shows good agreement of the radiocarbon and OSL dating techniques during the Middle and Late Devensian, with direct comparison of these techniques beyond 15 000 yr for the first time in Britain. It is suggested that aridity during the Late Devensian forced a significant decrease in fluvial activity compared with preceding and following periods, initiating a system with low peak flows and widespread permafrost development. Copyright © 2004 John Wiley & Sons, Ltd.

An Atomic Force Microscopy Study of the Effect of Nanoscale Contact Geometry and Surface Chemistry on the Adhesion of Pharmaceutical Particles - Jennifer C. Hooton; Caroline S. German; Stephanie Allen; Martyn C. Davies; Clive J. Roberts; Saul J. B. Tendler; Philip M. Williams (Pharmaceutical Research, 2004)

GROWTH, IMMORTALIZATION, AND DIFFERENTIATION POTENTIAL OF NORMAL ADULT HUMAN PROXIMAL TUBULE CELLS - DAVID E. OROSZ; PHILIP G. WOOST; ROBERT J. KOLB; MARGARET B. FINESILVER; WENWU JIN; PHYLLIS S. FRISA; CHEE-KEONG CHOO; CHUNG-FAI YAU; KWOK-WAH CHAN; MARTIN I. RESNICK; JANICE G. DOUGLAS; JOHN C. EDWARDS; et al. (In Vitro Cellular & Developmental Biology - Animal, 2004)

Serotonin receptors in platelets of bipolar and schizoaffective patients: effect of lithium treatment - Ghanshyam N. Pandey; Subhash C. Pandey; Xinguo Ren; Yogesh Dwivedi; Philip G. Janicak (Psychopharmacology, 2003)

Field Survey and Numerical Simulations: A Review of the 1998 Papua New Guinea Tsunami - Patrick J. Lynett; Jose C. Borrero; Philip L.-F. Liu; Costas E. Synolakis (Pure and Applied Geophysics, 2003)

Prospective study of serum retinol, β-carotene, β-cryptoxanthin, and lutein/zeaxanthin and esophageal and gastric cancers in China - Christian C. Abnet; You-Lin Qiao; Sanford M. Dawsey; Dennis W. Buckman; Chung S. Yang; William J. Blot; Zhi-Wei Dong; Philip R. Taylor; Steven D. Mark (Cancer Causes & Control, 2003)

Periodic changes in the zooplankton of the North Sea during the twentieth century linked to oceanic inflow - Philip C. Reid; Martin Edwards; Gregory Beaugrand; Morten Skogen; Darren Stevens (Fisheries Oceanography, 2003)
Oceanic inflow is estimated to contribute more than 90% of the nutrient input into the North Sea. Variability in the volume, chemical properties, biological content and source of the inflowing water is thus likely to have a considerable effect on North Sea ecosystems. Changes seen in the plankton, and in particular Calanus finmarchicus and Calanus helgolandicus , over the last 40 years as measured by the Continuous Plankton Recorder survey, allow clear periods to be identified that appear to be associated with variability in inflow. Monthly estimates of inflow and outflow across a section between Orkney and Utsira in Norway as well as netflow (sum of Baltic outflow, runoff and Channel inflow), have been derived from runs of the NORWECOM model for two integrated depth intervals: surface to 150 m and >150 m. A comparison is made between the physical model output and plankton results for the period 1958–99. Distinct plankton periods that appear to reflect changing inflow events are discussed in relation to hydrometeorological and earlier plankton studies over approximately the last 100 years.

Hierarchical genetic structure in fragmented populations of the Little Pocket Mouse (Perognathus longimembris) in Southern California - Andrea Swei; Philip V. Brylski; Wayne D. Spencer; Shana C. Dodd; James L. Patton (Conservation Genetics, 2003)

Viability of invertebrate diapausing eggs collected from residual ballast sediment - Sarah A. Bailey; Ian C. Duggan; Colin D. A. van Overdijk; Philip T. Jenkins; Hugh J. MacIsaac (Limnology and Oceanography, 2003)
Natural or anthropogenic movement of sediments may be an important vector for the dispersal of invertebrate resting stages between water bodies. Here we record the presence of invertebrate diapausing eggs in residual sediments from transoceanic vessels and explore whether these may pose an invasion risk. Viability of diapausing eggs was explored under light and dark conditions using sediment collected from eleven tanks on nine vessels operating on the Great Lakes. Seventeen cladoceran, copepod, and rotifer taxa were identified. Four of the species hatched have not yet been reported as established in the Great Lakes. Egg viability for individual species varied from 0% to 92%. Exposure to saline water may impact egg viability of some freshwater species. Generally, the proportion of eggs hatched in light and dark treatments did not differ significantly, indicating that light was not required to terminate diapause. As a result, eggs could potentially hatch in dark ballast tanks when immersed in freshwater loaded as ballast during operation on the Great Lakes. Viability of diapausing eggs differed among ballast tanks on a single vessel, indicating that tanks with independent ballast histories have different invasion risks. While additional work is needed to quantify risk, results from this study indicate that vessels entering the Great Lakes with only residual ballast are a potential vector for the introduction of new nonindigenous species during multiport operations.

Glomalin, an arbuscular-mycorrhizal fungal soil protein, responds to land-use change - Matthias C. Rillig; Philip W. Ramsey; Sherri Morris; Eldor A. Paul (Plant and Soil, 2003)

Long‐term changes in phytoplankton, zooplankton and salmon related to climate - GRÉGORY BEAUGRAND; PHILIP C. REID (Global Change Biology, 2003)
Recently, large‐scale changes in the biogeography of calanoid copepod crustaceans have been detected in the northeastern North Atlantic Ocean and adjacent seas. Strong biogeographical shifts in all copepod assemblages were found with a northward extension of more than ° in latitude of warm‐water species associated with a decrease in the number of colder‐water species. These changes were attributed to regional increase in sea surface temperature. Here, we have extended these studies to examine long‐term changes in phytoplankton, zooplankton and salmon in relation to hydro‐meteorological forcing in the northeast Atlantic Ocean and adjacent seas. We found highly significant relationships between (1) long‐term changes in all three trophic levels, (2) sea surface temperature in the northeastern Atlantic, (3) Northern Hemisphere temperature and (4) the North Atlantic Oscillation. The similarities detected between plankton, salmon, temperature and hydro‐climatic parameters are also seen in their cyclical variability and in a stepwise shift that started after a pronounced increase in Northern Hemisphere Temperature anomalies at the end of the 1970s. All biological variables show a pronounced change which started after circa 1982 for euphausiids (decline), 1984 for the total abundance of small copepods (increase), 1986 for phytoplankton biomass (increase) and Calanus finmarchicus (decrease) and 1988 for salmon (decrease). This cascade of biological events led to an exceptional period, which is identified after 1986 to present and followed another shift in large‐scale hydro‐climatic variables and sea surface temperature. This regional temperature increase therefore appears to be an important parameter that is at present governing the dynamic equilibrium of northeast Atlantic pelagic ecosystems with possible consequences for biogeochemical processes and fisheries.

Phenolic Compounds on the Pod-Surface of Pigeonpea, Cajanus cajan, Mediate Feeding Behavior of Helicoverpa armigera Larvae - Paul W. C. Green; Philip C. Stevenson; Monique S. J. Simmonds; Hari C. Sharma (Journal of Chemical Ecology, 2003)

Arsenic resistance in the archaeon "Ferroplasma acidarmanus": new insights into the structure and evolution of the ars genes - Thomas M. Gihring; Philip L. Bond; Stephen C. Peters; Jillian F. Banfield (Extremophiles, 2003)

Characterization of Particle-Interactions by Atomic Force Microscopy: Effect of Contact Area - Jennifer C. Hooton; Caroline S. German; Stephanie Allen; Martyn C. Davies; Clive J. Roberts; Saul J. B. Tendler; Philip M. Williams (Pharmaceutical Research, 2003)

Selecting plants to minimise radiocaesium in the food chain - Philip J. White; Kamal Swarup; Abraham J. Escobar-Gutiérrez; Helen C. Bowen; Neil J. Willey; Martin R. Broadley (Plant and Soil, 2003)

Sex Pheromone of the Scarab Beetle Phyllophaga elenans and Some Intriguing Minor Components - Walter S. Leal; Allan C. Oehlschlager; Paulo H. G. Zarbin; Eduardo Hidalgo; Philip J. Shannon; Yasuhiro Murata; Lilliana Gonzalez; Romano Andrade; Mikio Ono (Journal of Chemical Ecology, 2003)

Kappa opioid antagonist effects of the novel kappa antagonist 5?-guanidinonaltrindole (GNTI) in an assay of schedule-controlled behavior in rhesus monkeys - Stevens S. Negus; Nancy K. Mello; David C. Linsenmayer; R. Jones; Philip S. Portoghese (Psychopharmacology, 2002)

Movements of Florida apple snails in relation to water levels and drying events - Philip C. Darby; Robert E. Bennetts; Steven J. Miller; H. Franklin Percival (Wetlands, 2002)

The potential use of PIT telemetry for identifying and tracking crayfish in their natural environment - Damian H. Bubb; Martyn C. Lucas; Timothy J. Thom; Philip Rycroft (Hydrobiologia, 2002)

A Phylogeny of the Neotropical Nectar-Feeding Bats (Chiroptera: Phyllostomidae) Based on Morphological and Molecular Data - Bryan C. Carstens; Barbara L. Lundrigan; Philip Myers (Journal of Mammalian Evolution, 2002)

Ecosystem Decay of Amazonian Forest Fragments: a 22‐Year Investigation - William F. Laurance; Thomas E. Lovejoy; Heraldo L. Vasconcelos; Emilio M. Bruna; Raphael K. Didham; Philip C. Stouffer; Claude Gascon; Richard O. Bierregaard; Susan G. Laurance; Erica Sampaio (Conservation Biology, 2002)
We synthesized key findings from the Biological Dynamics of Forest Fragments Project, the world's largest and longest‐running experimental study of habitat fragmentation. Although initially designed to assess the influence of fragment area on Amazonian biotas, the project has yielded insights that go far beyond the original scope of the study. Results suggest that edge effects play a key role in fragment dynamics, that the matrix has a major influence on fragment connectivity and functioning, and that many Amazonian species avoid even small (

Induction of persistent changes in the organisation of the human motor cortex - Darrin R. McKay; Michael C. Ridding; Philip D. Thompson; Timothy S. Miles (Experimental Brain Research, 2002)

Intelligent Multichannel Stimulator for the Study of Cardiac Arrhythmias - Philip L. Johnson; Jonathan C. Newton; Dennis L. Rollins; Stephen B. Knisley; Raymond E. Ideker; William M. Smith (Annals of Biomedical Engineering, 2002)

Congruent trends in long‐term zooplankton decline in the north‐east Atlantic and basking shark ( Cetorhinus maximus ) fishery catches off west Ireland - David W. Sims; Philip C. Reid (Fisheries Oceanography, 2002)
Trends in basking shark ( Cetorhinus maximus ) fishery catches off Achill Island, west Ireland between 1949 and 1975 were examined in relation to zooplankton (total copepod) abundance in four adjacent sea areas over a 27‐year period. The numbers of basking sharks caught and copepod abundance showed downward trends and were positively correlated ( r ‐value range, 0.44–0.74). A possible explanation for the downward trend in shark catches was that progressively fewer basking sharks occurred there between 1956 and 1975 because fewer copepods, their food resource, occurred near the surface off west Ireland over the same period. We suggest that the decline in basking sharks may have been due to a distributional shift of sharks to more productive areas, rather than a highly philopatric, localized stock that was over‐exploited.

Intertidal communities in Doubtful Sound, New Zealand: Changes over time - Michelle C. Boyle; John B. Jillett; Philip V. Mladenov (New Zealand Journal of Marine and Freshwater Research, 2001)
Intertidal communities of Doubtful Sound, New Zealand, were surveyed in 1995 to establish the extent of changes since they were first surveyed 30 years earlier, before the Manapouri power scheme was completed in 1969. This scheme resulted in more than a 3‐fold increase of freshwater inflow to Doubtful Sound, through a tailrace to Deep Cove. Thickness of the low salinity surface layer exceeded the tidal range and was greater at high than low contemporary volumes of tailrace inflow. Intertidal habitats were mostly steep shores of solid rock, little more than 2 m in vertical extent. Freshwater run‐off, groundwater seepage, and aspect to sun were all major factors affecting the intertidal communities. Algae and lichens dominated shore communities. Normally common invertebrates were scarce, especially molluscan grazers. Major changes since the early 1960s included almost total disappearance of Hormosira banksii and exclusion of many other species notably Apophloea lyallii and Elminius modestus to outer reaches of the Sound.

Primary productivity of planet earth: biological determinants and physical constraints in terrestrial and aquatic habitats - Richard J. Geider; Evan H. Delucia; Paul G. Falkowski; Adrien C. Finzi; J. Philip Grime; John Grace; Todd M. Kana; Julie La Roche; Stephen P. Long; Bruce A. Osborne; Trevor Platt; I. Colin Prentice; et al. (Global Change Biology, 2001)

Prospective study of tooth loss and incident esophageal and gastric cancers in China - Christian C. Abnet; You-Lin Qiao; Steven D. Mark; Zhi-Wei Dong; Philip R. Taylor; Sanford M. Dawsey (Cancer Causes & Control, 2001)

Sphingolipids as biomarkers of fumonisin exposure and risk of esophageal squamous cell carcinoma in China - Christian C. Abnet; Craig B. Borkowf; You-Lin Qiao; Paul S. Albert; Elaine Wang; Alfred H. Merrill; Steven D. Mark; Zhi-Wei Dong; Philip R. Taylor; Sanford M. Dawsey (Cancer Causes & Control, 2001)

Effects of Roads on Movements by Understory Birds in Mixed-Species Flocks in Central Amazonian Brazil - Pedro F. Develey; Philip C. Stouffer (Conservation Biology, 2001)

Effects of Roads on Movements by Understory Birds in Mixed‐Species Flocks in Central Amazonian Brazil - Pedro F. Develey; Philip C. Stouffer (Conservation Biology, 2001)
Roads through tropical forest create linear disturbances that have unknown consequences for forest birds. We studied how a narrow, rarely used road through otherwise undisturbed Amazonian forest affected the movements and area requirements of understory birds that form mixed‐species flocks. Differences in road maintenance led to two distinct treatments along the same road. Trees along the “closed” road formed a partial canopy connecting the two sides of the road, although the roadway itself was kept open. The “open” road was regularly maintained, making a complete opening 10–30 m wide.We followed 15 flocks, 5 each in interior forest, along the open road, and along the closed road. These flocks were led by Thamnomanes antshrikes, and each flock had a discreet, permanent territory. Flock territory size (mean = 8.5 ha) did not differ among the three locations. The open road formed the territorial boundary for all five flocks, although birds moved within a few meters of the edge of the road. The closed road was less of a barrier: 2 of 5 flocks used both sides of the closed road. Playback experiments showed that flocks readily crossed the closed road to approach agonistic vocalizations. Along the open road, even though birds responded to playback by becoming agitated and moving to the extreme edge of the roadside vegetation, they were less likely to cross the road and did so only after a longer duration of playback. Our results suggest that flocks respond to a road as they would to a long linear gap. They use the vegetation along the edges of the road, but because they are unwilling to cross the open area, it becomes a flock territory boundary. Similarly, as in forest gaps, successional change along the closed road produced suitable habitat for flocks. Although this suggests that roads are a trivial problem, we caution that this result applies only to narrow roads that are not accompanied by deforestation or other disturbance.

The role of soil microorganisms in soil organic matter conservation in the tropics - David S. Powlson; Penny R. Hirsch; Philip C. Brookes (Nutrient Cycling in Agroecosystems, 2001)

Does the Small White Butterfly (Pieris rapae L.) Aggregate Eggs on Plants with Greater Gas Exchange Activity? - A. Mark Langan; C. Philip Wheater; Peter J. Dunleavy (Journal of Insect Behavior, 2001)

Reduced Feather Growth Rates of Two Common Birds Inhabiting Central Amazonian Forest Fragments - Jeffrey A. Stratford; Philip C. Stouffer (Conservation Biology, 2001)
Forest fragmentation may negatively affect populations typically found within continuous forest tracts. Some effects, such as absence from small fragments, are obvious, but other effects may be subtle and easily overlooked. We evaluated the hypothesis that forest birds dwelling in fragments, where microclimatic conditions have been shown to be hotter and drier than in continuous forest, may be in poorer physiological condition than those in the forest interior. We studied two bird species, the Wedge‐billed Woodcreeper ( Glyphorynchus spirurus ) and the White‐crowned Manakin ( Pipra pipra ), common to the fragmented landscape north of Manaus, Brazil. We analyzed feather growth rates in Pipra and Glyphorynchus captured in 1‐, 10‐, and 100‐ha forest fragments and continuous forest. Mean daily feather growth rates of the outer right rectrix of birds captured in fragments were significantly slower than feather growth rates of birds captured in continuous forest. Based on recapture data, Wedge‐billed Woodcreepers probably grew their feathers in sites where they were first captured. White‐crowned Manakins, however, were highly mobile and were recaptured rarely. Although we cannot conclusively show that fragmentation caused birds to be in poorer physiological condition, the data indicate that birds in poorer physiological condition were more likely to be captured in fragments than in continuous forest. Thus, our data suggest that forest fragmentation may have subtle but important effects on species that are relatively common after landscape alteration.

Collecting Florida applesnails (Pomacea paludosa) from wetland habitats using funnel traps - Philip C. Darby; Patricia L. Valentine-Darby; H. Franklin Percival; Wiley M. Kitchens (Wetlands, 2001)

Ecological effects of the North Atlantic Oscillation - Geir Ottersen; Benjamin Planque; Andrea Belgrano; Eric Post; Philip C. Reid; Nils C. Stenseth (Oecologia, 2001)

The use of photolytic rhodamines WT and sulpho G as conservative tracers of dispersion in surface waters - Robert C. Upstill-Goddard; Jo M. Suijlen; Gillian Malin; Philip D. Nightingale (Limnology and Oceanography, 2001)
We describe the use of sulpho rhodamine G (SG) and rhodamine WT (WT) as oceanographic tracers in tidally active waters of the southeastern North Sea. Ten kilograms of SG and 5 kg of WT dissolved in 1,000 liters of sea water were released to produce an initial tracer patch ~10 X ~0.5 km. Tracer dispersal was monitored for 11 d by high‐performance liquid chromatography analysis of samples collected close to the patch center. The patch center was initially identified during surveys for sulfur hexafluoride released simultaneously, and its position was subsequently confirmed by use of a two‐dimensional tracer dispersion model. Temporal changes in the SG/WT ratio were undetectable, so photolytic tracer losses were not directly quantified. A simple photolysis model was used to correct to conservative behavior for WT. Results are compared with the dispersal of spores of Bacillus globigii var. niger released simultaneously. Photolytic tracer pairs are ideally suited to tracer experiments in unconstrained water

Effects of Isoflavonoids from Cicer on Larvae of Heliocoverpa armigera - Monique S. J. Simmonds; Philip C. Stevenson (Journal of Chemical Ecology, 2001)

Force-induced melting of a short DNA double helix - Lisa H. Pope; Martyn C. Davies; Charles A. Laughton; Clive J. Roberts; Saul J.B. Tendler; Philip M. Williams (European Biophysics Journal, 2001)

Elevational distribution of restricted range forest tree taxa in eastern Tanzania - Jon C. Lovett; G. Philip Clarke; Robin Moore; Gilbert H. Morrey (Biodiversity and Conservation, 2001)

Terrestrial organic carbon storage in a British moorland - MarK. H. Garnett; Philip Ineson; Anthony C. Stevenson; David C. Howard (Global Change Biology, 2001)
Summary Accurate estimates for the size of terrestrial organic carbon (C) stores are needed to determine their importance in regulating atmospheric CO 2 concentrations. The C stored in vegetation and soil components of a British moorland was evaluated in order to: (i) investigate the importance of these ecosystems for C storage and (ii) test the accuracy of the United Kingdom's terrestrial C inventory. The area of vegetation and soil types was determined using existing digitized maps and a Geographical Information System (GIS). The importance of evaluating C storage using 2D area projections, as opposed to true surface areas, was investigated and found to be largely insignificant. Vegetation C storage was estimated from published results of productivity studies at the site supplemented by field sampling to evaluate soil C storage. Vegetation was found to be much less important for C storage than soil, with peat soils, particularly Blanket bog, containing the greatest amounts of C. Whilst the total amount of C in vegetation was similar to the UK national C inventory's estimate for the same area, the national inventory estimate for soil C was over three times higher than the value derived in the current study. Because the UK's C inventory can be considered relatively accurate compared to many others, the results imply that current estimates for soil C storage, at national and global scales, should be treated with caution.

Determination of Permeability Distributions Using NMR Velocity Imaging - Kenji Seto; Jeromy T. Hollenshead; A. Ted Watson; C. T. Philip Chang; John C. Slattery (Transport in Porous Media, 2001)

Tumor necrosis factor-α promoter polymorphism TNF2 is associated with a stronger delayed-type hypersensivity reaction in the skin of borderline tuberculoid leprosy patients - Milton O. Moraes; Nádia C. Duppre; Philip N. Suffys; Adalberto R. Santos; Alexandre S. Almeida; José A. C. Nery; Elizabeth P. Sampaio; Euzenir N. Sarno (Immunogenetics, 2001)

Pharmacokinetics and Safety of an Anti-Vascular Endothelial Growth Factor Aptamer (NX1838) Following Injection into the Vitreous Humor of Rhesus Monkeys - Daniel W. Drolet; Joyce Nelson; Christopher E. Tucker; Philip M. Zack; Kerry Nixon; Richard Bolin; Mark B. Judkins; James A. Farmer; Julie L. Wolf; Stanley C. Gill; Raymond A. Bendele (Pharmaceutical Research, 2000)

Cold-induced photoinhibition affects establishment of Eucalyptus nitens (Deane and Maiden) Maiden and Eucalyptus globulus Labill - Dugald C. Close; Chris L. Beadle; Philip H. Brown; Greg K. Holz (Trees, 2000)

Structural and functional characterization of the mouse Hlx homeobox gene - Michael D. Bates; Lynn C. Schatzman; Thierry Lints; Philip E. Hamlin; Richard P. Harvey; S. Steven Potter (Mammalian Genome, 2000)

PAHs in the Soils of a Mature, Mixed-Deciduous (Quercus-Fraxinus) Woodland and the Surrounding Pasture - Mike Howsam; Kevin C. Jones; Philip Ineson (Water, Air, & Soil Pollution, 2000)

Tumor specific activation of the VEGF/KDR angiogenic pathway in a subset of locally advanced squamous cell head and neck carcinomas - Alexandra Giatromanolaki; Michael I. Koukourakis; Efthimios Sivridis; Philip E. Thorpe; Rolf A. Brekken; Simopoulos Konstantinos; George Fountzilas; Kevin C. Gatter; Adrian L. Harris (Clinical & Experimental Metastasis, 2000)

Parental occupational exposures and risk of neuroblastoma: a case–control study (United States) - Mia A. Kerr; Philip C. Nasca; Kenneth A. Mundt; Arthur M. Michalek; Mark S. Baptiste; Martin C. Mahoney (Cancer Causes & Control, 2000)

Physical microhabitat requirements of freshwater pearl mussels, Margaritifera margaritifera (L.) - Lee C. Hastie; Philip J. Boon; Mark R. Young (Hydrobiologia, 2000)

The relationship between ions, vigour and salinity tolerance of Acacia seeds - Shafiq Rehman; Philip J C Harris; William F Bourne; John Wilkin (Plant and Soil, 2000)

Site of Interaction of Copper on Bacillus Polymyxa - Ligy Philip; Leela Iyengar; C. Venkobachar (Water, Air, & Soil Pollution, 2000)

Pharmacokinetics of a Hematoregulatory Peptide (SK&F 107647) in Healthy Male Volunteers and in Patients with Colorectal or Pancreatic Adenocarcinoma Not Amenable to Standard Therapy - Parnian Zia-Amirhosseini; Robert Z. Harris; Hugh C. Cowley; Juan W. Valle; David R. Citerone; Venkata K. Boppana; Howard Scarffe; Philip Watson; Charles B. Davis (Pharmaceutical Research, 2000)

Microbial control of mineral-groundwater equilibria:Macroscale to microscale - Philip C. Bennett; Franz K. Hiebert; Jennifer Roberts Rogers (Hydrogeology Journal, 2000)

Gastroesophageal reflux disease, use of H2 receptor antagonists, and risk of esophageal and gastric cancer - Diana C. Farrow; Thomas L. Vaughan; Carol Sweeney; Marilie D. Gammon; Wong-Ho Chow; Harvey A. Risch; Janet L. Stanford; Philip D. Hansten; Susan T. Mayne; Janet B. Schoenberg; Heidi Rotterdam; Habibul Ahsan; et al. (Cancer Causes & Control, 2000)

Late Middle Pleistocene deposits at Norton Farm on the West Sussex coastal plain, southern England - Martin R. Bates; C. Richard Bates; Philip L. Gibbard; Richard I. Macphail; Frederick J. Owen; Simon A. Parfitt; Richard C. Preece; Mark B. Roberts; J. Eric Robinson; John E. Whittaker; Keith N. Wilkinson (Journal of Quaternary Science, 2000)

Local Extinctions of Terrestrial Insectivorous Birds in a Fragmented Landscape near Manaus, Brazil - Jeffrey A. Stratford; Philip C. Stouffer (Conservation Biology, 1999)
We examined the distributions of nine species of terrestrial insectivorous birds in 4‐ to 14‐year‐old rainforest fragments north of Manaus, Brazil. We surveyed 11 fragments of 1, 10, and 100 ha, 95 ha of secondary vegetation, and nine continuous forest plots (controls) of 1–100 ha. We augmented standard spot‐mapping with extensive playback surveys. The fragments had been sampled with mist nets before isolation, so our results could be compared with the pre‐isolation distribution. For the nine species, there were 55 cases of local extinction in the 11 fragments between about 1 year after isolation and the time of our surveys. This corresponds to 74% extinction of the local populations in fragments. These extinctions occurred despite the second‐growth connection of some fragments to continuous forest as little as 70 m away. Three apparent colonization events by species not detected before isolation also occurred, but these may also reflect inadequate sampling before isolation. Our comparison of fragments and similar‐sized control plots in continuous forest showed an area effect on species richness in both fragments and control plots, but fragments had fewer species than control plots of equal size. In a fragmented Amazonian landscape, the full suite of terrestrial insectivores would persist in the short term only in large fragments ( > 100 ha), although much larger areas are probably necessary for the long‐term persistence of their populations.

The δ 2 -opioid receptor antagonist naltriben reduces motivated responding for ethanol - Harry L. June; Shannan R. McCane; Richard W. Zink; Philip S. Portoghese; Ting-Kai Li; Janice C. Froehlich (Psychopharmacology, 1999)

Heat Shielding: A Novel Method of Colonial Thermoregulation in Honey Bees - Philip T. Starks; David C. Gilley (The Science of Nature, 1999)

Ways out of the sewage sludge dilemma: Connecting administrative and participatory decision making - Philip C. R. Gray; Peter M. Wiedemann (Urban Ecosystems, 1999)

Errors Caused by Combination of Di-4 ANEPPS and Fluo3/4 for Simultaneous Measurements of Transmembrane Potentials and Intracellular Calcium - Philip L. Johnson; William Smith; Tamara C. Baynham; Stephen B. Knisley (Annals of Biomedical Engineering, 1999)

Increased mRNAs for procollagens and key regulating enzymes in rat skeletal muscle following downhill running - Xiao-Yan Han; W. Wang; Satu O. A. Koskinen; Vuokko Kovanen; T. E. S. Takala; Jyrki Komulainen; Veikko Vihko; Philip C. Trackman (Pflügers Archiv - European Journal of Physiology, 1999)

Effects of a short-term strength training programme on lymphocyte subsets at rest in elderly humans - S. Bermon; P. Philip; P. Ferrari; M. Candito; C. Dolisi (European Journal of Applied Physiology, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Life history interactions with environmental conditions in a host–parasite relationship and the parasite's mode of transmission - Philip Agnew; Jacob C. Koella (Evolutionary Ecology, 1999)

In vitro percutaneous absorption of boron as boric acid, borax, and disodium octaborate tetrahydrate in human skin - Ronald C. Wester; Tracy Hartway; Howard I. Maibach; Michael J. Schell; D. Jack Northington; B. Dwight Culver; Philip L. Strong (Biological Trace Element Research, 1998)

In vivo percutaneous absorption of boron as boric acid, borax, and disodium octaborate tetrahydrate in humans - Ronald C. Wester; Xiaoying Hui; Howard I. Maibach; Kathleen Bell; Michael J. Schell; D. Jack Northington; Philip Strong; B. Dwight Culver (Biological Trace Element Research, 1998)

Local genetic structure in red grouse ( Lagopus lagopus scoticus ): evidence from microsatellite DNA markers - STUART B. PIERTNEY; ANDREW D. C. MACCOLL; PHILIP J. BACON; JOHN F. DALLAS (Molecular Ecology, 1998)
Allelic variation at seven hypervariable tri‐ and tetranucleotide microsatellite loci was used to determine levels of population differentiation between 14 populations of red grouse ( Lagopus lagopus scoticus ) in northeast Scotland, UK. Despite the potential for long‐distance dispersal in grouse, and a semicontinuous habitat, significant population divergence was observed (mean R ST = 0.153; P P

Is observed variability in the long‐term results of the Continuous Plankton Recorder survey a response to climate change? - PHILIP C. REID; BENJAMIN PLANQUE; MARTIN EDWARDS (Fisheries Oceanography, 1998)
In the more than 50 years that the Continuous Plankton Recorder (CPR) survey has operated on a regular monthly basis in the north‐east Atlantic and North Sea, large changes have been witnessed in the planktonic ecosystem. These changes have taken the form of long‐term trends in abundance for certain species or stepwise changes for others, and in many cases are correlated with a mode of climatic variability in the North Atlantic, either: (1) the North Atlantic Oscillation (NAO), a basin‐scale atmospheric alteration of the pressure field between the Azores high pressure cell and the Icelandic Low; or (2) the Gulf Stream Index (GSI), which measures the latitudinal position of the north wall of the Gulf Stream. Recent work has shown that the changes in the GSI are coupled with the NAO and Pacific Southern Oscillation with a 2 year lag. The plankton variability is also possibly linked to changes observed in the distribution and flux of water masses in the surface, intermediate and deep waters of the North Atlantic. For example, in the last two decades, the extent and location of the formation of North Atlantic Deep Water, Labrador Sea Intermediate Water and Norwegian Sea intermediate and upper‐layer water has altered considerably. This paper discusses the extent to which observed changes in plankton abundance and distribution may be linked to this basin‐scale variability in hydrodynamics. The results are also placed within the context of global climate warming and the possible effects of the observed melting of Arctic permafrost and sea ice on the subpolar North Atlantic.

Homogeneity adjustments ofin situ atmospheric climate data: a review - Thomas C. Peterson; David R. Easterling; Thomas R. Karl; Pavel Groisman; Neville Nicholls; Neil Plummer; Simon Torok; Ingeborg Auer; Reinhard Boehm; Donald Gullett; Lucie Vincent; Raino Heino; et al. (International Journal of Climatology, 1998)

In Vivo Bioavailability and Metabolism of Topical Diclofenac Lotion in Human Volunteers - Xiaoying Hui; Philip G. Hewitt; Nicholas Poblete; Howard I. Maibach; J. Zev Shainhouse; Ronald C. Wester (Pharmaceutical Research, 1998)

In Vitro Cutaneous Disposition of a Topical Diclofenac Lotion in Human Skin: Effect of a Multi-Dose Regimen - Philip G. Hewitt; Nicholas Poblete; Ronald C. Wester; Howard I. Maibach; J. Zev Shainhouse (Pharmaceutical Research, 1998)

Establishment of monk seal cell lines - Yuanan Lu; Alonso Aguirre; Robert C. Braun; Philip C. Loh (In Vitro Cellular & Developmental Biology - Animal, 1998)

Changes in Upland Wildlife Habitat on Farmland in Illinois 19201987 - Christine A. Ribic; Richard E. Warner; Philip C. Mankin (Environmental Management, 1998)

Purification and chacterization of acid-type phosphatases from a heavy-metal-accumulating Citrobacter sp. - Byeong C. Jeong; Philip S. Poole; Anthony C. Willis; L. E. Macaskie (Archives of Microbiology, 1998)

Observations of Solitary Waves in the Stable Atmospheric Boundary Layer - Julia M. Rees; Philip S. Anderson; John C. King (Boundary-Layer Meteorology, 1998)

A Field-Compatible Method for Interpolating Biopotentials - John E. Burnes; David C. Kaelber; Bruno Taccardi; Robert L. Lux; Philip R. Ershler; Yoram Rudy (Annals of Biomedical Engineering, 1998)

Synthesis and characterization of cyclic pseudopeptide libraries containing thiomethylene and thiomethylene-sulfoxide amide bond surrogates - Yvon Crozet; James J. Wen; Rachel O. Loo; Philip C. Andrews; Arno F. Spatola (Molecular Diversity, 1997)

Analysis of responses to human synthetic adrenomedullin and calcitonin gene-related peptides in the hindlimb vascular bed of the cat - Hunter C. Champion; Donald L. Akers; José A. Santiago; David G. Lambert; Dennis B. McNamara; Philip J. Kadowitz (Molecular and Cellular Biochemistry, 1997)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Characterization of Poly(glycolide-co-D,L-lactide)/Poly(D,L-lactide) Microspheres for Controlled Release of GM-CSF - Dean K. Pettit; J. Ronald Lawter; W. James Huang; Susan C. Pankey; Nancy S. Nightlinger; David H. Lynch; Jo Ann C. L. Schuh; Philip J. Morrissey; Wayne R. Gombotz (Pharmaceutical Research, 1997)

Planted conifer seedling growth under two soil thermal regimes in high-elevation forest openings in interior British Columbia - Allen C. Balisky; Philip Burton (New Forests, 1997)

Modulation of mitogen-independent hepatocyte proliferation during the perinatal period in the rat - Philip A. Gruppuso; Michael Awad; Theresa C. Bienieki; Joan M. Boylan; Shaneli Fernando; Ronald A. Faris (In Vitro Cellular & Developmental Biology - Animal, 1997)

Increased cerebral free radical production during thiamine deficiency - Philip J. Langlais; Gary Anderson; S. X. Guo; Stephen C. Bondy (Metabolic Brain Disease, 1997)

Spectroscopic characterization of quinone-site mutants of the bacterial photosynthetic reaction center - Philip D. Laible; Yuenian Zhang; Andrea L. Morris; Seth W. Snyder; Clint Ainsworth; Scott R. Greenfield; Michael R. Wasielewski; Pierre Parot; Barbara Schoepp; Marianne Schiffer; Deborah K. Hanson; Marion C. Thurnauer (Photosynthesis Research, 1997)

High D-glucose does not affect binding of α-tocopherol to human erythrocytes - Mary C. Bellizzi; Asim K. Dutta-Roy; W. Philip T. James (Molecular and Cellular Biochemistry, 1997)

Baroreceptor responses derived from a fundamental concept - Mona F. Taher; Albert B. P. Cecchini; Mark A. Allen; Sherif R. Gobran; Robert C. Gorman; Brian L. Guthrie; Kyle A. Lingenfelter; Sina Y. Rabbany; Philip M. Rolchigo; Julius Melbin; Abraham Noordergraaf (Annals of Biomedical Engineering, 1988)

Reovirus cytotoxicity: Some properties of the UV-irradiated reovirus and its capsid proteins - Henry A. Subasinghe; Philip C. Loh (Archives of Virology, 1972)

The effect of metabolic inhibitors on the loss of isocitrate lyase activity from Chlorella - Christopher F. Thurston; Peter C. L. John; Philip J. Syrett (Archives of Microbiology, 1972)

Role of lysine in the replication of reovirus - Philip C. Loh; Herbert K. Oie; K. P. Camyre (Archives of Virology, 1971)

Growth characteristics and immunocytochemical studies of reovirus type 2 in a line of human amnion cells - Herbert Oie; Philip C. Loh; Marge Soergel (Archives of Virology, 1966)

Nyando virus: A hitherto undescribed virus isolated fromAnopheles funestus giles collected in Kenya - M. C. Williams; J. P. Woodall; Philip S. Corbet (Archives of Virology, 1965)

“Errata” in vol. IV, No. 4, April, 1927 - B. E. Brown; Freeman Weiss; Philip Brierley; R. C. Wright; W. M. Peacock (American Journal of Potato Research, 1927)

Effect of fertilizer on potato tubers - B. E. Brown; Freeman Weiss; Philip Brierley; R. C. Wright; W. M. Peacock (American Journal of Potato Research, 1927)